(23)Na MRI reveals persistent sodium accumulation in tumefactive MS lesions - Huhn, Konstantin; Mennecke, Angelika; Linz, Peter; Tschunko, Franz; Kästle, Nicola; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Linker, Ralf; Engelhorn, Tobias (Journal of the Neurological Sciences, 2017)
Chronic inflammatory demyelinating diseases of the CNS typically show a limited lesion size. However, extended lesions may appear with an atypical configuration. Large lesions with a diameter>2cm accompanied by tumor-like edema are entitled "tumefactive" and may occur in multiple sclerosis (MS) and other demyelinating diseases. Historically, differential diagnosis often requires histological analysis. Therefore, advanced imaging techniques are warranted to allow for a precise non-invasive diagnosis. Cerebral sodium ((23)Na) MRI was recently described as a new method to investigate in vivo sodium accumulation. Indicating extended sodium levels in MS lesions, (23)Na MRI is a promising differential diagnostic tool further elucidating the role of sodium in demyelinating lesions.Repetitive (23)Na MRI measurements in a MS patient with a tumefactive demyelinating lesion providing insight into the medium-term course of cerebral sodium levels.(23)Na MRI depicts persistent lesional sodium accumulation after anti-inflammatory treatment and provides the opportunity of a non-invasive, in vivo analysis of sodium levels in inflammatory CNS lesions without need for contrast enhancing media. As a result of the extended dimension, tumefactive lesions may have an appropriate size for the analysis of inflammatory demyelination by (23)Na MRI with sufficient resolution.
EVALuna2:14686

2D Vessel Segmentation Using Local Adaptive Contrast Enhancement - Schuldhaus, Dominik; Spiegel, Martin; Redel, Thomas; Polyanskaya, Maria; Struffert, Tobias; Hornegger, Joachim; Dörfler, Arnd (Bildverarbeitung für die Medizin, 2011)

3D-Visualization of Neurovascular Compression at the Ventrolateral Medulla in Patients with Arterial Hypertension - Manava, Panagiota; Naraghi, Ramin; Schmieder, Roland; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael M.; Buchfelder, Michael; Hastreiter, Peter (Clinical Neuroradiology, 2020)
Purpose: Controversy exists on the association of arterial hypertension (HTN) and neurovascular compression (NVC) at the ventrolateral medulla (VLM). No standardized and reproducible technique has been introduced yet for detection of NVC in HTN. This study aimed to generate, analyze and compare different results of exact reproducible anatomical 3D-representations of the VLM in patients with HTN, based on magnetic resonance imaging (MRI). Methods: A 3T scanner provided MRI (T2-constructive interference in steady state (CISS) high resolution imaging and three-dimensional Time-of-flight (3D-TOF) angiography) from the posterior fossa of 44 patients with clinical treatment-resistant HTN. Image processing consists of segmentation of the CISS data, registration and fusion of the CISS and TOF data and visualization. For each patient two 3D-visualizations (before and after fusion) were obtained. The reproduction quality of the vessels, flow-related signal variability and pulsation artifacts were analyzed and compared, using a ranking score. Results: Integrating vascular information from TOF into CISS data reduced artifacts in 3D-visualizations of exclusively processed CISS data. The quality of 3D-visualization of the vessels near the brain stem was significantly improved (p = 0.004). The results were reproducible and reliable. The quality of the 3D-presentations of neurovascular relationships at the VLM improved significantly (p < 0.001). Conclusion: The 3D-visualization of fused image data provides an excellent overview of the relationship between cranial nerves and vessels at the VLM and simplifies the detection of NVC in HTN. It provides a powerful tool for future clinical and scientific research. Although microvascular decompression (MVD) in treatment resistant HTN is not a standard procedure, it can be discussed in selected patients with intractable severe HTN.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cranial nerves; Image fusion; Image processing; MRI; Posterior fossa; Vascular compression disorders

3T-MRI in patients with pharmacoresistant epilepsy and a vagus nerve stimulator: a pilot study - Roesch, Julie; Hamer, Hajo; Mennecke, Angelika; Kasper, Burkhard; Engelhorn, Tobias; Dörfler, Arnd; Graf, Wolfgang (Epilepsy Research, 2015)
For safe 3T-MRI of patients with VNS (vagus nerve stimulator), specific conditions are mandatory. However, application of these conditions can lead to a loss of image quality. In this work, we evaluated the diagnostic value of 3T-MRI in VNS patients with pharmacoresistant epilepsy.Using a transmit-and-receive head coil and adapting our sequences to allow for low SAR (specific absorption rate), we examined 15 patients with pharmacoresistant epilepsy. Diagnostic quality was assessed by comparison of the SNR (signal to noise ratio) and CNR (contrast to noise ratio) of the hippocampus, the grey-white matter contrast and epileptogenic lesions to images of patients without VNS acquired with our routine 3T-MRI protocol and the 32-channel head coil.3T-MRI is feasible in VNS-patients. Image quality is adequate for detection and follow-up of epileptogenic lesions such as ganglioglioma or PNH (periventricular nodular heterotopia). Due to a significant reduction of SNR and CNR, the diagnostic value for subtle lesions may be decreased. Overall, the feasibility of 3T-MRI is beneficial in the diagnostic workup and follow-up of epilepsy-patients with VNS.
EVALuna2:22359

3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Objective: Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task. Methods: 18 healthy volunteers underwent two resting state and a stimulus driven measurement using a finger tapping motor task at 3 and 7 T, respectively. The SNR for each field strength was adjusted by targeted voxel size variation to minimize the effect of SNR on the field strength specific outcome. Spatial and temporal characteristics of resting state ICA, network graphs, and motor task related activated areas were compared. Finally, a graph theoretical approach was used to detect resting state modulation subsequent to a simple motor task. Results: Spatial extensions of resting state ICA and motor task related activated areas were consistent between field strengths, but temporal characteristics varied, indicating that 7 T achieved a higher functional specificity of the BOLD response than 3 T-fMRI. Following the motor task, only 7 T-fMRI enabled the detection of highly specific connectivity modulations representing an “offline replay” of previous motor activation. Modulated connections of the motor cortex were directly linked to brain regions associated with memory consolidation. Conclusion: These findings reveal how memory processing is initiated even after simple motor tasks, and that it begins earlier than previously shown. Thus, the superior capability of 7 T-fMRI to detect subtle functional dynamics promises to improve diagnostics and therapeutic assessment of neurological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 7T fMRI; graph theory; memory; motor task; offline replay; resting state

4D co-registration of X-ray and MR-mammograms: initial clinical results and potential incremental diagnostic value - Dietzel, Matthias; Hopp, Torsten; Ruiter, Nicole V.; Kaiser, Clemens G.; Kaiser, Werner A.; Baltzer, Pascal A. (Clinical Imaging, 2015)
4D co-registration of X-ray- and MR-mammograms (XM and MM) is a new method of image fusion. The present study aims to evaluate its clinical feasibility, radiological accuracy, and potential clinical value.XM and MM of 25 patients were co-registered. Results were evaluated by a blinded reader.Precision of the 4D co-registration was "very good" (mean-score [ms]=7), and lesions were "easier to delineate" (ms=5). In 88.8%, "relevant additional diagnostic information" was present, accounting for a more "confident diagnosis" in 76% (ms=5).4D co-registration is feasible, accurate, and of potential clinical value.
EVALuna2:23007

4D DSA for Dynamic Visualization of Cerebral Vasculature: A Single-Center Experience in 26 Cases - Lang, Stefan; Gölitz, Philipp; Struffert, Tobias; Roesch, J.; Roessler, Karl; Kowarschik, M.; Strother, C.; Dörfler, Arnd (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: 4D DSA allows acquisition of time-resolved 3D reconstructions of cerebral vessels by using C-arm conebeam CT systems. The aim of our study was to evaluate this new method by qualitative and quantitative means. MATERIALS AND METHODS: 2D and 4D DSA datasets were acquired in patients presenting with AVMs, dural arteriovenous fistulas, and cerebral aneurysms. 4D DSA was compared with 2D DSA in a consensus reading of qualitative and quantitative parameters of AVMs (eg, location, feeder, associated aneurysms, nidus size, drainage, Martin-Spetzler Score), dural arteriovenous fistulas (eg, fistulous point, main feeder, diameter of the main feeder, drainage), and cerebral aneurysms (location, neck configuration, aneurysmal size). Identifiability of perforators and diameters of the injection vessel (ICA, vertebral artery) were analyzed in 2D and 4D DSA. Correlation coefficients and a pairedttest were calculated for quantitative parameters. The effective patient dose of the 4D DSA protocol was evaluated with an anthropomorphic phantom. RESULTS: In 26 patients, datasets were acquired successfully (AVM = 10, cerebral aneurysm = 10, dural arteriovenous fistula = 6). Qualitative and quantitative evaluations of 4D DSA in AVMs (nidus size:r= 0.99,P= .001), dural arteriovenous fistulas (diameter of the main feeder:r= 0.954,P= .03), and cerebral aneurysms (aneurysmal size:r= 1,P= .001) revealed nearly complete accordance with 2D DSA. Perforators were comparably visualized with 4D DSA. Measurement of the diameter of the injection vessel in 4D DSA was equivalent to that in 2D DSA (P= .039). The effective patient dose of 4D DSA was 1.2 mSv. CONCLUSIONS: 4D DSA is feasible for imaging of AVMs, dural arteriovenous fistulas, and cerebral aneurysms. 4D DSA offers reliable visualization of the cerebral vasculature and may improve the understanding and treatment of AVMs and dural arteriovenous fistulas. The number of 2D DSA acquisitions required for an examination may be reduced through 4D DSA.
EVALuna2:33141

7 Tesla Hippocampal Subfield Analyses In Patients With Medically Refractory Epilepsy And Hippocampal Sclerosis - Roessler, K.; Roesch, Johannes; Coras, R.; Blümcke, Ingmar; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan; Mennecke, Angelika (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

7 tricks for 7 T CEST: Improving the reproducibility of multipool evaluation provides insights into the effects of age and the early stages of Parkinson's disease - Mennecke, Angelika; Khakzar, Katrin M.; German, Alexander; Herz, Kai; Fabian, Moritz; Liebert, Andrzej; Blümcke, Ingmar; Kasper, Burkhard; Nagel, Armin Michael; Laun, Frederik Bernd; Schmidt, Manuel; Winkler, Jürgen; et al. (NMR in Biomedicine, 2022)
The objective of the current study was to optimize the postprocessing pipeline of 7 T chemical exchange saturation transfer (CEST) imaging for reproducibility and to prove this optimization for the detection of age differences and differences between patients with Parkinson's disease versus normal subjects. The following 7 T CEST MRI experiments were analyzed: repeated measurements of a healthy subject, subjects of two age cohorts (14 older, seven younger subjects), and measurements of 12 patients with Parkinson's disease. A slab-selective, (Formula presented.) -homogeneous parallel transmit protocol was used. The postprocessing, consisting of motion correction, smoothing, (Formula presented.) -correction, normalization, denoising, (Formula presented.) -correction and Lorentzian fitting, was optimized regarding the intrasubject and intersubject coefficient of variation (CoV) of the amplitudes of the amide pool and the aliphatic relayed nuclear Overhauser effect (rNOE) pool within the brain. Seven “tricks” for postprocessing accomplished an improvement of the mean voxel CoV of the amide pool and the aliphatic rNOE pool amplitudes of less than 5% and 3%, respectively. These postprocessing steps are: motion correction with interpolation of the motion of low-signal offsets (1) using the amide pool frequency offset image as reference (2), normalization of the Z-spectrum using the outermost saturated measurements (3), (Formula presented.) correction of the Z-spectrum with moderate spline smoothing (4), denoising using principal component analysis preserving the 11 highest intensity components (5), (Formula presented.) correction using a linear fit (6) and Lorentzian fitting using the five-pool fit model (7). With the optimized postprocessing pipeline, a significant age effect in the amide pool can be detected. Additionally, for the first time, an aliphatic rNOE contrast between subjects with Parkinson's disease and age-matched healthy controls in the substantia nigra is detected. We propose an optimized postprocessing pipeline for CEST multipool evaluation. It is shown that by the use of these seven “tricks”, the reproducibility and, thus, the statistical power of a CEST measurement, can be greatly improved and subtle changes can be detected.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 7 T; age; amide; CEST; Lorentzian fitting; Parkinson; rNOE; standardization

A 2D driven 3D vessel segmentation algorithm for 3D digital subtraction angiography data - Spiegel, Martin; Redel, T.; Struffert, Tobias; Hornegger, Joachim; Dörfler, Arnd (Physics in Medicine and Biology, 2011)
Cerebrovascular disease is among the leading causes of death in western industrial nations. 3D rotational angiography delivers indispensable information on vessel morphology and pathology. Physicians make use of this to analyze vessel geometry in detail, i.e. vessel diameters, location and size of aneurysms, to come up with a clinical decision. 3D segmentation is a crucial step in this pipeline. Although a lot of different methods are available nowadays, all of them lack a method to validate the results for the individual patient. Therefore, we propose a novel 2D digital subtraction angiography (DSA)-driven 3D vessel segmentation and validation framework. 2D DSA projections are clinically considered as gold standard when it comes to measurements of vessel diameter or the neck size of aneurysms. An ellipsoid vessel model is applied to deliver the initial 3D segmentation. To assess the accuracy of the 3D vessel segmentation, its forward projections are iteratively overlaid with the corresponding 2D DSA projections. Local vessel discrepancies are modeled by a global 2D/3D optimization function to adjust the 3D vessel segmentation toward the 2D vessel contours. Our framework has been evaluated on phantom data as well as on ten patient datasets. Three 2D DSA projections from varying viewing angles have been used for each dataset. The novel 2D driven 3D vessel segmentation approach shows superior results against state-of-the-art segmentations like region growing, i.e. an improvement of 7.2% points in precision and 5.8% points for the Dice coefficient. This method opens up future clinical applications requiring the greatest vessel accuracy, e.g. computational fluid dynamic modeling. © 2011 Institute of Physics and Engineering in Medicine.

Accuracy of Dose-Saving Artificial-Intelligence-Based 3D Angiography (3DA) for Grading of Intracranial Artery Stenoses: Preliminary Findings - Lang, Stefan; Hölter, Philip; Schmidt, Manuel; Mrochen, Anne; Kuramatsu, Joji; Kaethner, Christian; Roser, Philipp; Kowarschik, Markus; Dörfler, Arnd (Diagnostics, 2023)
Background and purpose: Based on artificial intelligence (AI), 3D angiography (3DA) is a novel postprocessing algorithm for “DSA-like” 3D imaging of cerebral vasculature. Because 3DA requires neither mask runs nor digital subtraction as the current standard 3D-DSA does, it has the potential to cut the patient dose by 50%. The object was to evaluate 3DA’s diagnostic value for visualization of intracranial artery stenoses (IAS) compared to 3D-DSA. Materials and methods: 3D-DSA datasets of IAS (nIAS = 10) were postprocessed using conventional and prototype software (Siemens Healthineers AG, Erlangen, Germany). Matching reconstructions were assessed by two experienced neuroradiologists in consensus reading, considering image quality (IQ), vessel diameters (VD1/2), vessel-geometry index (VGI = VD1/VD2), and specific qualitative/quantitative parameters of IAS (e.g., location, visual IAS grading [low-/medium-/high-grade] and intra-/poststenotic diameters [dintra-/poststenotic in mm]). Using the NASCET criteria, the percentual degree of luminal restriction was calculated. Results: In total, 20 angiographic 3D volumes (n3DA = 10; n3D-DSA = 10) were successfully reconstructed with equivalent IQ. Assessment of the vessel geometry in 3DA datasets did not differ significantly from 3D-DSA (VD1: r = 0.994, p = 0.0001; VD2:r = 0.994, p = 0.0001; VGI: r = 0.899, p = 0.0001). Qualitative analysis of IAS location (3DA/3D-DSA:nICA/C4 = 1, nICA/C7 = 1, nMCA/M1 = 4, nVA/V4 = 2, nBA = 2) and the visual IAS grading (3DA/3D-DSA:nlow-grade = 3, nmedium-grade = 5, nhigh-grade = 2) revealed identical results for 3DA and 3D-DSA, respectively. Quantitative IAS assessment showed a strong correlation regarding intra-/poststenotic diameters (rdintrastenotic = 0.995, pdintrastenotic = 0.0001; rdpoststenotic = 0.995, pdpoststenotic = 0.0001) and the percentual degree of luminal restriction (rNASCET 3DA = 0.981; pNASCET 3DA = 0.0001). Conclusions: The AI-based 3DA is a resilient algorithm for the visualization of IAS and shows comparable results to 3D-DSA. Hence, 3DA is a promising new method that allows a considerable patient-dose reduction, and its clinical implementation would be highly desirable.
CRIS-Team Scopus Importer:2023-03-10
Keywords: 3D angiography; artificial intelligence; deep learning; dose reduction; flat-detector computed tomography (FD-CT); innovative postprocessing; intracranial artery stenosis

A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

A complex fracture of the hyoid bone and the larynx after a bicycle accident – Case report and review of literature - Sievert, Matti; Eisenhut, Felix; Iro, Heinrich; Traxdorf, Maximilian; Müller, Susanna; Taha, Lava (International Journal of Surgery Case Reports, 2021)
Introduction and importance: Reports about laryngeal trauma and fractures of the hyoid bone are rare in the literature. Most cases are forensic cases and the results of postmortem analysis. Traumatic larynx and hyoid bone fractures represent a rare but important differential diagnosis of the common symptom hoarseness. Case presentation: A 60-year-old female patient presented with unclear dysphonia and globus sensation following intubation for a surgical treatment for a lower leg fracture after a bicycle accident two months ago. Endoscopy and the computed tomography (CT) of the neck revealed a fixed and immobile fractured piece of the larynx, a hyoid bone fracture and a pseudarthrosis between the greater horn of the hyoid bone and the upper edge of the thyroid cartilage. The hyoid bone fracture led to a distortion of the supraglottis. After surgical removal of the fractured part of the hyoid bone and the pseudarthrosis separation, the supraglottis appeared symmetrical again. Four weeks after surgery the patient was symptom-free. Clinical discussion: Though combined hyoid bone and larynx fractures after traumatic injuries are rare, they represent an important differential diagnosis in trauma patients with dysphagia or dysphonia. The clinical symptoms can vary and occur immediately or within a latent period taking weeks or months until the proper diagnosis. Depending on the symptoms, surgical management can be effective. Conclusion: An isolated partial resection of the hyoid bone with separation of the pseudarthrosis is a reasonable therapeutic option and can lead to completely resolving symptom. Preoperatively, a CT provides further valuable information.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Case report; Computed tomography; Dysphagia; Dysphonia; Hyoid bone fracture; Laryngeal trauma

Acoustic-noise-optimized diffusion-weighted imaging - Ott, Martin; Blaimer, Martin; Grodzki, David M.; Breuer, Felix A.; Roesch, Julie; Dörfler, Arnd; Heismann, Bjoern; Jakob, Peter M. (Magnetic Resonance Materials in Physics Biology and Medicine, 2015)
This work was aimed at reducing acoustic noise in diffusion-weighted MR imaging (DWI) that might reach acoustic noise levels of over 100 dB(A) in clinical practice.A diffusion-weighted readout-segmented echo-planar imaging (EPI) sequence was optimized for acoustic noise by utilizing small readout segment widths to obtain low gradient slew rates and amplitudes instead of faster k-space coverage. In addition, all other gradients were optimized for low slew rates. Volunteer and patient imaging experiments were conducted to demonstrate the feasibility of the method. Acoustic noise measurements were performed and analyzed for four different DWI measurement protocols at 1.5T and 3T.An acoustic noise reduction of up to 20 dB(A) was achieved, which corresponds to a fourfold reduction in acoustic perception. The image quality was preserved at the level of a standard single-shot (ss)-EPI sequence, with a 27-54 % increase in scan time.The diffusion-weighted imaging technique proposed in this study allowed a substantial reduction in the level of acoustic noise compared to standard single-shot diffusion-weighted EPI. This is expected to afford considerably more patient comfort, but a larger study would be necessary to fully characterize the subjective changes in patient experience.
EVALuna2:22999

Acute-onset migrainous aura mimicking acute stroke: MR perfusion imaging features - Floery, D.; Vosko, M. R.; Fellner, F. A.; Fellner, C.; Ginthoer, C.; Gruber, F.; Ransmayr, G.; Dörfler, Arnd; Uder, Michael; Bradley, W. G. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: In a very limited number of cases, acute migrainous aura may mimic acute brain infarction. The aim of this study was to recognize patterns of MR perfusion abnormalities in this presentation. MATERIALS AND METHODS: One thousand eight hundred fifty MR imaging studies performed for the suspicion of acute brain infarction were analyzed retrospectively to detect patients with acute migrainous aura not from stroke. All patients were examined clinically by 2 neurologists and underwent a standard stroke MR imaging protocol, including PWI. Two radiologists reviewed the perfusion maps visually and quantitatively for the presence, distribution, and grade of perfusion abnormalities. RESULTS: Among 1850 MR imaging studies, 20 (1.08%) patients were found to have acute migrainous aura. Hypoperfusion was found in 14/20 patients (70%) with delayed rMTT and TTP, decreased rCBF, and minimal decrease in rCBV. In contrast to the typical pattern in stroke, perfusion abnormalities were not limited to a single vascular territory but extended to >1. Bilateral hypoperfusion was seen in 3/14 cases. In 11/14 cases, hypoperfusion with a posterior predominance was found. TTP and rMTT were the best maps to depict perfusion changes at visual assessment, but also rCBF maps demonstrated significant hypoperfusion in quantitative analysis. In all patients, clinical and imaging follow-up findings were negative for stroke. CONCLUSIONS: Acute migrainous aura is rare but important in the differential diagnosis among patients with the suspicion of acute brain infarction. Atypical stroke perfusion abnormalities can be seen in these patients.
CRIS-Team Scopus Importer:2022-08-05

Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission [National Institutes of Health Stroke Scale (NIHSS) <= 4] remains to be elucidated. The aim of the present study was to investigate the prognostic factors and therapeutic management of those patients.
CRIS-Team WoS Importer:2021-11-19

Additive sex-specific influence of common non-synonymous DISC1 variants on amygdala, basal ganglia, and white cortical surface area in healthy young adults - Mühle, Christiane; Kreczi, Jakob; Rhein, Cosima; Richter-Schmidinger, Tanja; Alexopoulos, Panagiotis; Dörfler, Arnd; Lenz, Bernd; Kornhuber, Johannes (Brain Structure & Function, 2017)
The disrupted-in-schizophrenia-1 (DISC1) gene is known for its role in the development of mental disorders. It is also involved in neurodevelopment, cognition, and memory. To investigate the association between DISC1 variants and brain morphology, we analyzed the influence of the three common non-synonymous polymorphisms in DISC1 on specific brain structures in healthy young adults. The volumes of brain regions were determined in 145 subjects by magnetic resonance imaging and automated analysis using FreeSurfer. Genotyping was performed by high resolution melting of amplified products. In an additive genetic model, rs6675281 (Leu607Phe), rs3738401 (Arg264Gln), and rs821616 (Ser704Cys) significantly explained the volume variance of the amygdala (p = 0.007) and the pallidum (p = 0.004). A higher cumulative portion of minor alleles was associated with larger volumes of the amygdala (p = 0.005), the pallidum (p = 0.001), the caudate (p = 0.024), and the putamen (p = 0.007). Sex-stratified analysis revealed a strong genetic effect of rs6675281 on putamen and pallidum in females but not in males and an opposite influence of rs3738401 on the white cortical surface in females compared to males. The strongest single association was found for rs821616 and the amygdala volume in male subjects (p < 0.001). No effect was detected for the nucleus accumbens. We report-to our knowledge-for the first time a significant and sex-specific influence of common DISC1 variants on volumes of the basal ganglia, the amygdala and on the cortical surface area. Our results demonstrate that the additive model of all three polymorphisms outperforms their single analysis.
EVALuna2:33147

Advanced MRI in neuro-oncology: Can we proceed without inclusion of energy metabolism? - Stadlbauer, Andreas; Buchfelder, Michael; Dörfler, Arnd; Oberndorfer, Stefan (Oncotarget, 2019)
CRIS-Team Scopus Importer:2019-07-09
Keywords: Glioblastoma; Intratumoral heterogeneity; Magnetic resonance imaging; Tumor microenvironment; Warburg effect

A framework for voxel-based morphometric analysis of the optic radiation using diffusion tensor imaging in glaucoma - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Magnetic Resonance Imaging, 2011)
EVALuna2:21060

A fully-automatic locally adaptive thresholding algorithm for blood vessel segmentation in 3D digital subtraction angiography - Bögel, Marco; Hölter, Philip; Redel, Thomas; Maier, Andreas; Hornegger, Joachim; Dörfler, Arnd (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2015)
Subarachnoid hemorrhage due to a ruptured cerebral aneurysm is still a devastating disease. Planning of endovascular aneurysm therapy is increasingly based on hemodynamic simulations necessitating reliable vessel segmentation and accurate assessment of vessel diameters. In this work, we propose a fully-automatic, locally adaptive, gradient-based thresholding algorithm. Our approach consists of two steps. First, we estimate the parameters of a global thresholding algorithm using an iterative process. Then, a locally adaptive version of the approach is applied using the estimated parameters. We evaluated both methods on 8 clinical 3D DSA cases. Additionally, we propose a way to select a reference segmentation based on 2D DSA measurements. For large vessels such as the internal carotid artery, our results show very high sensitivity (97.4%), precision (98.7%) and Dice-coefficient (98.0%) with our reference segmentation. Similar results (sensitivity: 95.7%, precision: 88.9% and Dice-coefficient: 90.7%) are achieved for smaller vessels of approximately 1mm diameter.
CRIS-Team Scopus Importer:2022-08-05

Age-dependent clinical outcomes in primary versus oral anticoagulation-related intracerebral hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan T.; Sembill, Jochen; Madzar, Dominik; Reindl, Caroline; Bobinger, Tobias; Müller, Tamara; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Huttner, Hagen (International Journal of Stroke, 2019)
Aims This study determined the influence of age on bleeding characteristics and clinical outcomes in primary spontaneous (non-OAC), vitamin K antagonist-related (VKA-) and non-vitamin K antagonist oral anticoagulant-related (NOAC-) ICH. Methods Pooled individual patient data of multicenter cohort studies were analyzed by logistic regression modelling and propensity-score-matching (PSM) to explore the influence of advanced age on clinical outcomes among non-OAC-, VKA-, and NOAC-ICH. Primary outcome measure was functional outcome at three months assessed by the modified Rankin Scale, dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6) functional outcome. Secondary outcome measures included mortality, hematoma characteristics, and frequency of invasive interventions. Results In VKA-ICH 33.5% (670/2001), in NOAC-ICH 44.2% (69/156) and in non-OAC-ICH 25.2% (254/1009) of the patients were >= 80 years. After adjustment for treatment interventions and relevant parameters, elderly ICH patients comprised worse functional outcome at three months (adjusted odds ratio (aOR) in VKA-ICH: 1.49 (1.21-1.84); p < 0.001; NOAC-ICH: 2.01 (0.95-4.26); p = 0.069; non-OAC-ICH: 3.54 (2.50-5.03); p < 0.001). Anticoagulation was significantly associated with worse functional outcome below the age of 70 years, (aOR: 2.38 (1.78-3.16); p < 0.001), but not in patients of >= 70 years (aOR: 1.21 (0.89-1.65); p = 0.217). The differences in initial ICH volume and extent of ICH enlargement between OAC-ICH and non-OAC-ICH gradually decreased with increasing patient age. Conclusions As compared to elderly ICH-patients, in patients <70 years OAC-ICH showed worse clinical outcomes compared to non-OAC-ICH because of larger baseline ICH-volumes and extent of hematoma enlargement. Treatment strategies aiming at neutralizing altered coagulation should be aware of these findings.
CRIS-Team WoS Importer:2020-01-28

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Alpha power decrease in quantitative EEG detects development of cerebral infarction after subarachnoid hemorrhage early - Müller, Tamara; Gollwitzer, Stephanie; Hopfengartner, Ruediger; Rampp, Stefan; Lang, Johannes; Stritzelberger, Jenny; Madzar, Dominik; Reindl, Caroline; Sprügel, Maximilian; Onugoren, Muejgan Dogan; Mühlen, Iris; Kuramatsu, Joji; et al. (Clinical Neurophysiology, 2021)
Objective: In subarachnoid hemorrhage (SAH), transcranial Doppler/color-coded-duplex sonography (TCD/TCCS) is used to detect delayed cerebral ischemia (DCI). In previous studies, quantitative electroencephalography (qEEG) also predicted imminent DCI. This study aimed to compare and analyse the ability of qEEG and TCD/TCCS to early identify patients who will develop later manifest cerebral infarction. Methods: We analysed cohorts of two previous qEEG studies. Continuous six-channel-EEG with artefact rejection and a detrending procedure was applied. Alpha power decline of ≥ 40% for ≥ 5 hours compared to a 6-hour-baseline was defined as significant EEG event. Median reduction and duration of alpha power decrease in each channel was determined. Vasospasm was diagnosed by TCD/TCCS, identifying the maximum frequency and days of vasospasm in each territory. Results: 34 patients were included (17 male, mean age 56 ± 11 years, Hunt and Hess grade: I–V, cerebral infarction: 9). Maximum frequencies in TCD/TCCS and alpha power reduction in qEEG were correlated (r = 0.43; p = 0.015). Patients with and without infarction significantly differed in qEEG parameters (maximum alpha power decrease: 78% vs 64%, p = 0.019; summed hours of alpha power decline: 236 hours vs 39 hours, p = 0.006) but showed no significant differences in TCD/TCCS parameters. Conclusions: There was a moderate correlation of TCD/TCCS frequencies and qEEG alpha power reduction but only qEEG differentiated between patients with and without cerebral infarction. Significance: qEEG represents a non-invasive, continuous tool to identify patients at risk of cerebral infarction.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Delayed cerebral ischemia; Quantitative EEG; Subarachnoid hemorrhage; Vasospasm

Analysis of the expression pattern of the schizophrenia-risk and intellectual disability gene TCF4 in the developing and adult brain suggests a role in development and plasticity of cortical and hippocampal neurons - Jung, Matthias; Häberle, Benjamin; Tschaikowsky, Tristan; Wittmann, Marie-Theres; Balta, Elli-Anna; Stadler, Vivien-Charlott; Zweier, Christiane; Dörfler, Arnd; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Molecular Autism, 2018)
Background: Haploinsufficiency of the class I bHLH transcription factor TCF4 causes Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder, while common variants in the TCF4 gene have been identified as susceptibility factors for schizophrenia. It remains largely unknown, which brain regions are dependent on TCF4 for their development and function. Methods: We systematically analyzed the expression pattern of TCF4 in the developing and adult mouse brain. We used immunofluorescent staining to identify candidate regions whose development and function depend on TCF4. In addition, we determined TCF4 expression in the developing rhesus monkey brain and in the developing and adult human brain through analysis of transcriptomic datasets and compared the expression pattern between species. Finally, we morphometrically and histologically analyzed selected brain structures in Tcf4-haploinsufficient mice and compared our morphometric findings to neuroanatomical findings in PTHS patients. Results: TCF4 is broadly expressed in cortical and subcortical structures in the developing and adult mouse brain. The TCF4 expression pattern was highly similar between humans, rhesus monkeys, and mice. Moreover, Tcf4 haploinsufficiency in mice replicated structural brain anomalies observed in PTHS patients. Conclusion: Our data suggests that TCF4 is involved in the development and function of multiple brain regions and indicates that its regulation is evolutionary conserved. Moreover, our data validate Tcf4-haploinsufficient mice as a model to study the neurodevelopmental basis of PTHS.
EVALuna:34022

Anatomy and malformations of the posterior cranial fossa - Struffert, Tobias (Radiologe, 2016)
Many important structures are located in the confined space within the posterior cranial fossa. This article describes the main aspects of the anatomy. As a uniform classification of malformations of the posterior cranial fossa does not exist the main syndromes, such as Chiari malformations, zerebellar hypoplasia and dysplasia are discussed separately.
EVALuna2:33223

A Nested Eight-Channel Transmit Array With Open-Face Concept for Human Brain Imaging at 7 Tesla - Williams, Sydney N.; Allwood-Spiers, Sarah; Mcelhinney, Paul; Paterson, Gavin; Herrler, Jürgen; Liebig, Patrick; Nagel, Armin M.; Foster, John E.; Porter, David A.; Gunamony, Shajan (Frontiers in Physics, 2021)
Purpose: Parallel transmit technology for MRI at 7 tesla will significantly benefit from high performance transmit arrays that offer high transmit efficiency and low mutual coupling between the individual array elements. A novel dual-mode transmit array with nested array elements has been developed to support imaging the human brain in both the single-channel (sTx) and parallel-transmit (pTx) excitation modes of a 7 tesla MRI scanner. In this work, the design, implementation, validation, specific absorption rate (SAR) management, and performance of the head coil is presented. Methods: The transmit array consisted of a nested arrangement to improve decoupling between the second-neighboring elements. Two large cut-outs were introduced in the RF shield for an open-face design to reduce claustrophobia and to allow patient monitoring. A hardware interface allows the coil to be used in both the sTx and pTx modes. SAR monitoring is done with virtual observation points (VOP) derived from human body models. The transmit efficiency and coverage is compared with the commercial single-channel and parallel-transmit head coils. Results: Decoupling inductors between the second-neighboring coil elements reduced the coupling to less than −20 dB. Local SAR estimates from the electromagnetic (EM) simulations were always less than the EM-based VOPs, which in turn were always less than scanner predictions and measurements for static and dynamic pTx waveforms. In sTx mode, we demonstrate improved coverage of the brain compared to the commercial sTx coil. The transmit efficiency is within 10% of the commercial pTx coil despite the two large cut-outs in the RF shield. In pTx mode, improved signal homogeneity was shown when the Universal Pulse was used for acquisition in vivo. Conclusion: A novel head coil which includes a nested eight-channel transmit array has been presented. The large cut-outs improve patient monitoring and reduce claustrophobia. For pTx mode, the EM simulation and VOP-based SAR management provided greater flexibility to apply pTx methods without the limitations of SAR constraints. For scanning in vivo, the coil was shown to provide an improved coverage in sTx mode compared to a standard commercial head coil.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 7 Tesla; B1 homogeneity; parallel-transmit (pTx); RF coil; specific absorption rate (SAR); transmit array; ultra-high field; virtual observation points (VOPs)

Angioedema in Stroke Patients With Thrombolysis - Fröhlich, Katharina; Macha, Kosmas; Gerner, Stefan; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank; Kallmünzer, Bernd; Winder, Klemens (Stroke, 2019)
Background and Purpose- Oral angioedema (OA) is a rare but life-threatening complication in patients with ischemic stroke receiving intravenous thrombolysis with r-tPA (recombinant tissue-type plasminogen activator). This study intended to determine associations between thrombolysis-related OA and ischemic stroke lesion sites using a voxel-wise lesion analysis. Methods- Prospective registry data were used to identify ischemic stroke patients with thrombolysis-related OA between 2002 and 2018. For the study registry, ethics approval was obtained by the Ethics Committee of the Friedrich-Alexander Universität (FAU) Erlangen-Nürnberg (clinical registry registration: 377_17Bc). Ischemic stroke patients with thrombolysis treatment but without OA admitted in the years 2011 and 2012 comprised the control group. Ischemic lesions were manually outlined on magnetic resonance imaging (1.5T or 3T) or computed tomographic scans and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of OA voxel-wise between patients with and without lesions in a given voxel using the Liebermeister test. Stroke severity was rated using the National Institutes of Health Stroke Scale score, and blood pressure, heart rate, blood glucose levels, and body temperature were determined on admission. Results- Fifteen ischemic stroke patients with thrombolysis-related OA were identified. The voxel-wise analysis yielded associations between OA and ischemic lesions in the insulo-opercular region with a right hemispheric dominance. Mean blood pressure was significantly lower in patients with OA than in controls. Age, National Institutes of Health Stroke Scale scores, infarct volumes, heart rate, and blood glucose levels did not differ between patients with and without OA. Conclusions- The voxel-wise analysis linked thrombolysis-related OA to right insulo-opercular lesions. The lower blood pressure in patients with thrombolysis-related OA may reflect bradykinin effects causing vasodilatation and increasing vascular permeability.
CRIS-Team Scopus Importer:2019-07-19
Keywords: angioedema; autonomic nervous system; brain ischemia; neuroimaging; stroke; tissue-type plasminogen activator

Angiographic assessment of the efficacy of flow diverter treatment for cerebral aneurysms - Sadasivan, Chander; Dholakia, Ronak; Peeling, Lissa; Gölitz, Philipp; Dörfler, Arnd; Lieber, Baruch B.; Fiorella, David J.; Woo, Henry H. (Interventional Neuroradiology, 2019)
Background: The recent growth of neuro-endovascular treatment has rekindled interest in the use of angiographic techniques for flow assessment. Aneurysm treatment with flow diverters is particularly amenable to such analysis. We analyze contrast time–density curves — recorded within aneurysms before (pre) and immediately after (post) flow diverter implantation to estimate six-month treatment outcomes. Methods: Fifty-six patients with 65 aneurysms were treated with flow diverters at two institutions. A region of interest was drawn around the aneurysm perimeter in image sequences taken both pre and post angiography, and the temporal variation in grayscale intensity within the aneurysm (time–density curve) was recorded. Eleven parameters were quantified from each time–density curve. Aneurysm occlusion status was recorded six months post treatment. The change in parameters from pre to post treatment was statistically evaluated between aneurysm occluded and non-occluded groups. Results: Of the 11 parameters, eight were significantly different before and immediately after flow diversion. Considering the entire data set, none of the parameters was statistically different between the occluded and non-occluded groups. However, subgroup analyses showed that four variables were significantly different between the aneurysm occluded and non-occluded groups. The sensitivity of these variables to predict aneurysm occlusion at six months ranged from 60% to 89%, while the specificity ranged from 55% to 70%. Conclusions: Device-induced intra-aneurysmal flow alterations quantified by simple aneurysmal time–density curves can potentially be used to predict long-term outcomes of flow diversion. Large multi-center studies will be required to confirm these findings. Patient-to-patient variability in coagulation may need to be incorporated for clinically relevant predictive values.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Concentration–time curve; contrast washout; time–density curve

Angiographic C-arm CT visualization of the Woven EndoBridge cerebral aneurysm embolization device (WEB): first experience in an animal aneurysm model - Struffert, Tobias; Lang, Sabine; Adamek, Edyta; Engelhorn, Tobias; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2014)
Improvements in the imaging capabilities of angiographic C-arm computed tomography (CT) using flat detector angiographic (FD-CT) systems now provide a means for the in vivo visualization of devices used for the treatment of intracranial aneurysms. One such device, the WEB embolization device, is made of a braided mesh of nitinol wires, the size of which are near to the limits of visualization using conventional x-ray fluoroscopy. Our hypothesis was that the imaging of these implants C-arm CT would provide useful information regarding their positioning and deployment.In five New Zealand white rabbits elastase induced aneurysms were created and subsequently treated using a WEB. Imaging was performed using digital subtraction angiography (DSA), X-ray imaging and two different Angiographic C-arm CT protocols. The images were evaluated by two neuroradiologists using an evaluation scale.The mesh of the WEB was barely visible on the DSA or x-ray fluoroscopy images. Volume rendering technique (VRT) reconstruction and multiplanar reconstruction (MPR) of images done using the C-arm CT protocols clearly delineated the shape and structure of the device. Contrast-enhanced MPR and VRT reconstructions allowed assessment of the status of blood flow in the aneurysms. Beam hardening artifacts caused by platinum markers on the WEB were present.In vivo C-arm CT imaging of the WEB is feasible and allows precise determination of the position and deployment status of the device. On contrast-enhanced images the occlusion status of aneurysms and the positioning of the WEB in relationship to the parent artery can be evaluated. C-arm-CT may serve as a minimal-invasive follow-up imaging modality.
EVALuna2:22996

Angiographic CT for intraprocedural monitoring of complex neuroendovascular procedures - Pfaff, Johannes Alex Rolf; Struffert, Tobias; Gölitz, Philipp; Dörfler, Arnd (American Journal of Neuroradiology, 2013)
Evolving techniques in interventional neuroradiology have widened therapeutic options, allowing treatment even in complex cases. Complex neuroendovascular procedures (eg, stent-assisted coiling, stent placement in X- or Y-techniques) require precise delineation of cerebral vasculature and devices. However, because of the complex anatomy or if an ideal projection is not possible, visualization of the parent artery might be difficult. We present 2 complex cases of basilar tip aneurysm in which ACT proved to be beneficial in the intraprocedural monitoring of stent-assisted coil embolization.
CRIS-Team Scopus Importer:2022-08-05

Angiographic CT with intravenous contrast agent application for monitoring of intracranial flow diverting stents - Saake, Marc; Struffert, Tobias; Gölitz, Philipp; Ott, Sabine; Seifert, Frank; Ganslandt, Oliver; Dörfler, Arnd (Neuroradiology, 2012)
Introduction: Intracranial flow diverting devices are increasingly used to treat cerebral aneurysms. A reliable, noninvasive follow-up modality would be desirable. Our aim was to compare intra-arterial digital subtraction angiography (ia DSA) to angiographic computed tomography with intravenous contrast agent application (iv ACT) in the visualisation of flow diverting devices and aneurysm lumina. Methods: Follow-up monitoring by iv ACT (n=36) and ia DSA (n=25) in 14 patients treated with flow diverting devices for intracranial aneurysms was evaluated retrospectively. Images were evaluated by two neuroradiologists in anonymous consensus reading regarding the device deployment, wall apposition, neck coverage of the aneurysm, opacification of the vessel and device lumen, as well as the degree of aneurysm occlusion. Results: Corresponding ia DSA and iv ACT images were scored identically in all patients regarding the stent deployment, wall apposition and neck coverage, as well as the degree of aneurysm occlusion and patency status of the device and parent artery. Opacification of the parent vessel lumen and perfused parts of the aneurysm was considered slightly inferior for iv ACT in comparison with ia DSA (seven of 36 cases), without impact on diagnosis. Conclusions: We demonstrated the feasibility and diagnostic value of iv ACT in follow-up imaging of intracranial flow diverting devices. Due to its high spatial resolution and non-invasive character, this novel technique might become a valuable imaging modality in these patients. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Computed tomography; Flat detector; Flow diverting stent; Follow-up; Intravenous

Angiographic CT with intravenous contrast injection compared with conventional rotational angiography in the diagnostic work-up of cerebral aneurysms - Gölitz, Philipp; Struffert, Tobias; Knossalla, F.; Saake, Marc; Ott, Sabine; Ganslandt, Oliver; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Noninvasive imaging of cerebral aneurysms is still considered inferior to conventional angiography. The purpose of this study was to evaluate the diagnostic accuracy of ivACT in the assessment of intracranial aneurysms compared with 3D-DSA. MATERIALS AND METHODS: We included 13 patients with 15 incidental unruptured saccular aneurysms scheduled for diagnostic angiographic work-up in our study. In each patient, we performed an ivACT and a conventional angiography including a 3D rotational run. During postprocessing, MPR images were generated for each technique. Maximal aneurysm diameter, neck diameter, aneurysm height, maximum width, bulge height, parent artery diameter, and angle between the parent artery and aneurysm apex were measured for each aneurysm. RESULTS: 3D-DSA and ivACT both provided images of high quality without artificial disturbances (ie, motion artifacts). Measurements of all parameters resulted in comparable values for both modalities with a strong correlation (P ≤ .001). CONCLUSIONS: ivACT is feasible for the noninvasive visualization of saccular cerebral aneurysms and may provide reliable diagnostic information for the assessment of aneurysm size and geometry comparable with conventional intra-arterial 3D rotational angiography. These preliminary results might be a first promising step to replacing conventional angiography in preinterventional aneurysm imaging.
CRIS-Team Scopus Importer:2022-08-05

A novel splice variant expands the LAMC3-associated cortical phenotype to frontal only polymicrogyria and adult-onset epilepsy - Kasper, Burkhard; Kraus, Cornelia; Schwarz, Michael; Rösch, Julie; Thiel, Christian; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Bi-allelic loss-of-function variants in LAMC3, encoding extracellular matrix protein laminin gamma 3, represent a rare cause of occipital polymicrogyria with epilepsy, developmental delay and cognitive impairment. So far, only five families have been reported. We now identified a novel, homozygous splice variant in LAMC3 in an individual with an unusual manifestation of cortical malformation. She presented with polymicrogyria in the frontal but not the occipital lobes, with adult-onset seizures and normal psychomotor development and cognition. Additionally, ictal asystole, requiring implantation of a pacemaker, and nonepileptic seizures occurred. This case expands the spectrum of LAMC3-associated cortical malformation phenotypes to frontal only polymicrogyria and adult-onset of epilepsy.
CRIS-Team Scopus Importer:2020-09-18
Keywords: cortical malformation; epilepsy; LAMC3; polymicrogyria; seizures

A novel use of time separation technique to improve flat detector CT perfusion imaging in stroke patients - Kulvait, Vojtech; Hölter, Philip; Frysch, Robert; Haseljic, Hana; Dörfler, Arnd; Rose, Georg (Medical Physics, 2022)
Background: CT perfusion imaging (CTP) is used in the diagnostic workup of acute ischemic stroke (AIS). CTP may be performed within the angio suite using flat detector CT (FDCT) to help reduce patient management time. Purpose: In order to significantly improve FDCT perfusion (FDCTP) imaging, data-processing algorithms need to be able to compensate for the higher levels of noise, slow rotation speed, and a lower frame rate of current FDCT devices. Methods: We performed a realistic simulation of FDCTP acquisition based on CTP data from seven subjects. We used the time separation technique (TST) as a model-based approach for FDCTP data processing. We propose a novel dimension reduction in which we approximate the time attenuation curves by a linear combination of trigonometric functions. Our goal was to show that the TST can be used even without prior assumptions on the shape of the attenuation profiles. Results: We first demonstrated that a trigonometric basis is suitable for dimension reduction of perfusion data. Using simulated FDCTP data, we have shown that a trigonometric basis in the TST provided better results than the classical straightforward processing even with additional noise. Average correlation coefficients of perfusion maps were improved for cerebral blood flow (CBF), cerebral blood volume, mean transit time (MTT) maps. In a moderate noise scenario, the average Pearson's coefficient for the CBF map was improved using the TST from 0.76 to 0.81. For the MTT map, it was improved from 0.37 to 0.45. Furthermore, we achieved a total processing time from the reconstruction of FDCTP data to the generation of perfusion maps of under 5 min. Conclusions: In our study cohort, perfusion maps created from FDCTP data using the TST with a trigonometric basis showed equivalent perfusion deficits to classic CT perfusion maps. It follows, that this novel FDCTP technique has potential to provide fast and accurate FDCTP imaging for AIS patients.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Brain Stroke; Computed Tomography; CT Perfusion; Model-based Approaches; Perfusion Imaging; Reconstruction Algorithms; Stroke Imaging; Visualization Algorithms

Anticoagulant reversal, blood pressure levels, and anticoagulant resumption in patients with anticoagulation-related intracerebral hemorrhage - Kuramatsu, Joji; Gerner, Stefan; Schellinger, Peter D.; Glahn, Joerg; Endres, Matthias; Sobesky, Jan; Flechsenhar, Julia; Neugebauer, Hermann; Juettler, Eric; Grau, Armin; Palm, Frederick; Roether, Joachim; et al. (Journal of the American Medical Association, 2015)
Although use of oral anticoagulants (OACs) is increasing, there is a substantial lack of data on how to treat OAC-associated intracerebral hemorrhage (ICH).To assess the association of anticoagulation reversal and blood pressure (BP) with hematoma enlargement and the effects of OAC resumption.Retrospective cohort study at 19 German tertiary care centers (2006-2012) including 1176 individuals for analysis of long-term functional outcome, 853 for analysis of hematoma enlargement, and 719 for analysis of OAC resumption.Reversal of anticoagulation during acute phase, systolic BP at 4 hours, and reinitiation of OAC for long-term treatment.Frequency of hematoma enlargement in relation to international normalized ratio (INR) and BP. Incidence analysis of ischemic and hemorrhagic events with or without OAC resumption. Factors associated with favorable (modified Rankin Scale score, 0-3) vs unfavorable functional outcome.Hemorrhage enlargement occurred in 307 of 853 patients (36.0%). Reduced rates of hematoma enlargement were associated with reversal of INR levels <1.3 within 4 hours after admission (43/217 [19.8%]) vs INR of >=1.3 (264/636 [41.5%]; P < .001) and systolic BP <160 mm Hg at 4 hours (167/504 [33.1%]) vs >=160 mm Hg (98/187 [52.4%]; P < .001). The combination of INR reversal <1.3 within 4 hours and systolic BP of <160 mm Hg at 4 hours was associated with lower rates of hematoma enlargement (35/193 [18.1%] vs 220/498 [44.2%] not achieving these values; OR, 0.28; 95% CI, 0.19-0.42; P < .001) and lower rates of in-hospital mortality (26/193 [13.5%] vs 103/498 [20.7%]; OR, 0.60; 95% CI, 0.37-0.95; P = .03). OAC was resumed in 172 of 719 survivors (23.9%). OAC resumption showed fewer ischemic complications (OAC: 9/172 [5.2%] vs no OAC: 82/547 [15.0%]; P < .001) and not significantly different hemorrhagic complications (OAC: 14/172 [8.1%] vs no OAC: 36/547 [6.6%]; P = .48). Propensity-matched survival analysis in patients with atrial fibrillation who restarted OAC showed a decreased HR of 0.258 (95% CI, 0.125-0.534; P < .001) for long-term mortality. Functional long-term outcome was unfavorable in 786 of 1083 patients (72.6%).Among patients with OAC-associated ICH, reversal of INR <1.3 within 4 hours and systolic BP <160 mm Hg at 4 hours were associated with lower rates of hematoma enlargement, and resumption of OAC therapy was associated with lower risk of ischemic events. These findings require replication and assessment in prospective studies.clinicaltrials.gov Identifier: NCT01829581.
EVALuna2:22354

Antiplatelet Therapy in Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Antiplatelet Therapy in Primary Spontaneous and Oral Anticoagulation-Associated Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Stroke, 2018)
Background and Purpose- This study determined the influence of concomitant antiplatelet therapy (APT) on hematoma characteristics and outcome in primary spontaneous intracerebral hemorrhage (ICH), vitamin K antagonist (VKA)- and non-VKA oral anticoagulant-associated ICH. Methods- Data of retrospective cohort studies and a prospective single-center study were pooled. Functional outcome, mortality, and radiological characteristics were defined as primary and secondary outcomes. Propensity score matching and logistic regression analyses were performed to determine the association between single or dual APT and hematoma volume. Results- A total of 3580 patients with ICH were screened, of whom 3545 with information on APT were analyzed. Three hundred forty-six (32.4%) patients in primary spontaneous ICH, 260 (11.4%) in VKA-ICH, and 30 (16.0%) in non-VKA oral anticoagulant-associated ICH were on APT, and these patients had more severe comorbidities. After propensity score matching VKA-ICH patients on APT presented with less favorable functional outcome (modified Rankin Scale score, 0-3; APT, 48/202 [23.8%] versus no APT, 187/587 [31.9%]; P=0.030) and higher mortality (APT, 103/202 [51.0%] versus no APT, 237/587 [40.4%]; P=0.009), whereas no significant differences were present in primary spontaneous ICH and non-VKA oral anticoagulant-associated ICH. In VKA-ICH, hematoma volume was significantly larger in patients with APT (21.9 [7.4-61.4] versus 15.7 [5.7-44.5] mL; P=0.005). Multivariable regression analysis revealed an association of APT and larger ICH volumes (odds ratio, 1.80 [1.20-2.70]; P=0.005), which was more pronounced in dual APT and supratherapeutically anticoagulated patients. Conclusions- APT does not affect ICH characteristics and outcome in primary spontaneous ICH patients; however, it is associated with larger ICH volume and worse functional outcome in VKA-ICH, presumably by additive antihemostatic effects. Combination of anticoagulation and APT should, therefore, be diligently evaluated and restricted to the shortest possible time frame.
EVALuna2:34909

A Realistic Digital Phantom for Perfusion C-Arm CT Based on MRI Data - Aichert, André; Manhart, Michael; Navalpakkam, Bharath; Grimm, Robert; Hutter, Jana; Maier, Andreas; Hornegger, Joachim; Dörfler, Arnd (2013 IEEE Nuclear Science Symposium and Medical Imaging Conference Record (NSS/MIC), 2013)
CTP is an important imaging modality for diagnosis of ischemic stroke, which is computed from of a series of consecutive CT-scans during the injection of contrast agent. Contrast flow at any point in space can be tracked as minor changes in intensity over a period of about 40 seconds to one minute, represented as a time-attenuation curve (TAC) for every voxel. This work presents an isotropic, dense, physiologically realistic and dynamic brain phantom for CT perfusion. The phantom is based on MRI scans of a volunteer and is freely available for download. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD5.areali_2

Are Flow Diverting Stents a Treatment Option in Acutely Ruptured Complex A1-A2 Junction Aneurysms? - Roesch, J.; Gölitz, Philipp; Struffert, Tobias; Köhrmann, Martin; Dörfler, Arnd (Clinical Neuroradiology, 2016)
EVALuna2:22379

Artificial intelligence-based 3D angiography for visualization of complex cerebrovascular pathologies - Lang, Sabine; Hölter, Philip; Schmidt, Manuel; Strother, C.; Kaethner, C.; Kowarschik, M.; Dörfler, Arnd (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: By means of artificial intelligence, 3D angiography is a novel postprocessing method for 3D imaging of cerebral vessels. Because 3D angiography does not require a mask run like the current standard 3D-DSA, it potentially offers a considerable reduction of the patient radiation dose. Our aim was an assessment of the diagnostic value of 3D angiography for visualization of cerebrovascular pathologies. MATERIALS AND METHODS: 3D-DSA data sets of cerebral aneurysms (nCA ¼ 10), AVMs (nAVM ¼ 10), and dural arteriovenous fistulas (dAVFs) (ndAVF ¼ 10) were reconstructed using both conventional and prototype software. Corresponding reconstructions have been analyzed by 2 neuroradiologists in a consensus reading in terms of image quality, injection vessel diameters (vessel diameter [VD] 1/2), vessel geometry index (VGI ¼ VD1/VD2), and specific qualitative/quantitative parameters of AVMs (eg, location, nidus size, feeder, associated aneurysms, drainage, Spetzler-Martin score), dAVFs (eg, fistulous point, main feeder, diameter of the main feeder, drainage), and cerebral aneurysms (location, neck, size). RESULTS: In total, 60 volumes have been successfully reconstructed with equivalent image quality. The specific qualitative/quantitative assessment of 3D angiography revealed nearly complete accordance with 3D-DSA in AVMs (eg, mean nidus size3D angiography/3D-DSA¼ 19.9 [SD, 10.9]/20.2 [SD, 11.2] mm; r ¼ 0.9, P ¼.001), dAVFs (eg, mean diameter of the main feeder3D angiography/3D-DSA¼ 2.04 [SD, 0.65]/2.05 [SD, 0.63] mm; r ¼ 0.9, P ¼.001), and cerebral aneurysms (eg, mean size3D angiography/3D-DSA¼ 5.17 [SD, 3.4]/5.12 [SD, 3.3] mm; r ¼ 0.9, P ¼.001). Assessment of the geometry of the injection vessel in 3D angiography data sets did not differ significantly from that of 3D-DSA (vessel geometry indexAVM: r ¼ 0.84, P ¼.003; vessel geometry indexdAVF: r ¼ 0.82, P ¼.003; vessel geometry indexCA: r ¼ 0.84, P,.001). CONCLUSIONS: In this study, the artificial intelligence-based 3D angiography was a reliable method for visualization of complex cerebrovascular pathologies and showed results comparable with those of 3D-DSA. Thus, 3D angiography is a promising postprocessing method that provides a significant reduction of the patient radiation dose.
CRIS-Team Scopus Importer:2021-11-05

Ascending axonal degeneration of the corticospinal tract in pure hereditary spastic paraplegia: A cross-sectional DTI study - List, Julia; Kohl, Zacharias; Winkler, Jürgen; Marxreiter, Franz; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2019)
Objective: To identify structural white matter alterations in patients with pure hereditary spastic paraplegia (HSP) using high angular resolution diffusion tensor imaging (DTI). Methods: We examined 37 individuals with high resolution DTI, 20 patients with pure forms of hereditary spastic paraplegia and 17 age and gender matched healthy controls. DTI was performed using a 3 T clinical scanner with whole brain tract-based spatial statistical (TBSS) analysis of the obtained fractional anisotropy (FA) data as well as a region-of-interest (ROI)-based analysis of affected tracts including the cervical spinal cord. We further conducted correlation analyses between DTI data and clinical characteristics. Results: TBSS analysis in HSP patients showed significantly decreased fractional anisotropy of the corpus callosum and the corticospinal tract compared to healthy controls. ROI-based analysis confirmed significantly lower FA in HSP compared to controls in the internal capsule (0.77 vs. 0.80, p = 0.048), the corpus callosum (0.84 vs. 0.87, p = 0.048) and the cervical spinal cord (0.72 vs. 0.79, p = 0.003). FA values of the cervical spinal cord significantly correlated with disease duration. Conclusion: DTI metrics of the corticospinal tract from the internal capsule to the cervical spine suggest microstructural damage and axonal degeneration of motor neurons. The CST at the level of the cervical spinal cord is thereby more severely affected than the intracranial part of the CST, suggesting an ascending axonal degeneration of the CST. Since there is a significant correlation with disease duration, FA may serve as a future progression marker for assessment of the disease course in HSP.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Corticospinal tract; Diffusion tensor imaging; Fractional anisotropy; Hereditary spastic paraplegia; Tract-based spatial statistics (TBSS)

Association between tissue hypoxia, perfusion restrictions, and microvascular architecture alterations with lesion-induced impairment of neurovascular coupling - Stadlbauer, Andreas; Kinfe, Thomas Mehari; Zimmermann, Max; Eyüpoglu, Ilker Yasin; Brandner, Nadja; Buchfelder, Michael; Zaiß, Moritz; Dörfler, Arnd; Brandner, Sebastian (Journal of Cerebral Blood Flow and Metabolism, 2020)
Functional magnetic resonance imaging (fMRI) has been mainly utilized for the preoperative localization of eloquent cortical areas. However, lesion-induced impairment of neurovascular coupling (NVC) in the lesion border zone may lead to false-negative fMRI results. The purpose of this study was to determine physiological factors impacting the NVC. Twenty patients suffering from brain lesions were preoperatively examined using multimodal neuroimaging including fMRI, magnetoencephalography (MEG) during language or sensorimotor tasks (depending on lesion location), and a novel physiologic MRI approach for the combined quantification of oxygen metabolism, perfusion state, and microvascular architecture. Congruence of brain activity patterns between fMRI and MEG were found in 13 patients. In contrast, we observed missing fMRI activity in perilesional cortex that demonstrated MEG activity in seven patients, which was interpreted as lesion-induced impairment of NVC. In these brain regions with impaired NVC, physiologic MRI revealed significant brain tissue hypoxia, as well as significantly decreased macro- and microvascular perfusion and microvascular architecture. We demonstrated that perilesional hypoxia with reduced vascular perfusion and architecture is associated with lesion-induced impairment of NVC. Our physiologic MRI approach is a clinically applicable method for preoperative risk assessment for the presence of false-negative fMRI results and may prevent severe postoperative functional deficits.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Blood-oxygen-level-dependent contrast; functional magnetic resonance imaging; hypoxia; magnetoencephalography; neurovascular coupling

Association of a CAMK2A genetic variant with logical memory performance and hippocampal volume in the elderly - Rhein, Cosima; Mühle, Christiane; Lenz, Bernd; Richter-Schmidinger, Tanja; Kogias, Georgios; Boix, Fernando; Lourdusamy, Anbarasu; Dörfler, Arnd; Peters, Oliver; Ramirez, Alfredo; Jessen, Frank; Maier, Wolfgang; et al. (Brain Research Bulletin, 2020)
Calcium/Calmodulin-dependent kinase alpha (αCaMKII) has been shown to play an essential role in synaptic plasticity and in learning and memory in animal models. However, there is little evidence for an involvement in specific memories in humans. Here we tested the potential involvement of the αCaMKII coding gene CAMK2A in verbal logical memory in two Caucasian populations from Germany, in a sample of 209 elderly people with cognitive impairments and a sample of 142 healthy adults. The association of single nucleotide polymorphisms (SNPs) located within the genomic region of CAMK2A with verbal logical memory learning and retrieval from the Wechsler Memory Scale was measured and hippocampal volume was assessed by structural MRI. In the elderly people, we found the minor allele of CAMK2A intronic SNP rs919741 to predict a higher hippocampal volume and better logical memory retrieval. This association was not found in healthy adults. The present study may provide evidence for an association of a genetic variant of the CAMK2A gene specifically with retrieval of logical memory in elderly humans. This effect is possibly mediated by a higher hippocampal volume.
CRIS-Team Scopus Importer:2020-05-22
Keywords: adults; CAMK2A; elderly; hippocampus; logical memory; αCaMKII

Association of brain functional magnetic resonance activity with response to tumor necrosis factor inhibition in rheumatoid arthritis - Rech, Jürgen; Heß, Andreas; Finzel, Stephanie; Kreitz, Silke; Sergeeva, Marina; Englbrecht, Matthias; Dörfler, Arnd; Saake, Marc; Schett, Georg (Arthritis and Rheumatism, 2013)
Objective To test whether brain activity predicts the response to tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA). Since clinical and laboratory parameters have proven unsuccessful in predicting response, we followed a radically different concept, hypothesizing that response to TNFi depends on central nervous system activity rather than the clinical signs of disease. Methods Sequential testing by functional magnetic resonance imaging (MRI) of the brain, anatomic MRI of the hand, and clinical assessment of arthritis were carried out in 10 patients with active RA before and 3, 7, and 28 days after the start of TNFi treatment. Results Baseline demographic and disease-specific parameters were identical in TNFi responders and nonresponders. The mean ± SEM decrease in the Disease Activity Score in 28 joints after 28 days was -1.8 ± 0.3 in TNFi responders (n = 5) and -0.2 ± 0.1 in nonresponders (n = 5). Responders showed significantly higher baseline activation in thalamic, limbic, and associative areas of the brain than nonresponders. Moreover, brain activity decreased within 3 days after TNFi exposure in the responders, preceding clinical responses (day 7) and responses observed on the anatomic hand MRI (day 28). Conclusion These data suggest that response to TNFi depends on brain activity in RA patients, reflecting the subjective perception of disease. Copyright © 2013 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2021-02-03

Association of Intraventricular Fibrinolysis With Clinical Outcomes in Intracerebral Hemorrhage: An Individual Participant Data Meta-Analysis. - Kuramatsu, Joji; Gerner, Stefan; Ziai, Wendy; Bardutzky, Juergen; Sembill, Jochen; Sprügel, Maximilian; Mrochen, Anne; Kölbl, Kathrin; Ram, Malathi; Avadhani, Radhika; Falcone, Guido J.; Selim, Magdy H.; et al. (Stroke, 2022)
BACKGROUND: In patients with intracerebral hemorrhage (ICH), the presence of intraventricular hemorrhage constitutes a promising therapeutic target. Intraventricular fibrinolysis (IVF) reduces mortality, yet impact on functional disability remains unclear. Thus, we aimed to determine the influence of IVF on functional outcomes. METHODS: This individual participant data meta-analysis pooled 1501 patients from 2 randomized trials and 7 observational studies enrolled during 2004 to 2015. We compared IVF versus standard of care (including placebo) in patients treated with external ventricular drainage due to acute hydrocephalus caused by ICH with intraventricular hemorrhage. The primary outcome was functional disability evaluated by the modified Rankin Scale (mRS; range: 0-6, lower scores indicating less disability) at 6 months, dichotomized into mRS score: 0 to 3 versus mRS: 4 to 6. Secondary outcomes included ordinal-shift analysis, all-cause mortality, and intracranial adverse events. Confounding and bias were adjusted by random effects and doubly robust models to calculate odds ratios and absolute treatment effects (ATE). RESULTS: Comparing treatment of 596 with IVF to 905 with standard of care resulted in an ATE to achieve the primary outcome of 9.3% (95% CI, 4.4-14.1). IVF treatment showed a significant shift towards improved outcome across the entire range of mRS estimates, common odds ratio, 1.75 (95% CI, 1.39-2.17), reduced mortality, odds ratio, 0.47 (95% CI, 0.35-0.64), without increased adverse events, absolute difference, 1.0% (95% CI, -2.7 to 4.8). Exploratory analyses provided that early IVF treatment (≤48 hours) after symptom onset was associated with an ATE, 15.2% (95% CI, 8.6-21.8) to achieve the primary outcome. CONCLUSIONS: As compared to standard of care, the administration of IVF in patients with acute hydrocephalus caused by intracerebral and intraventricular hemorrhage was significantly associated with improved functional outcome at 6 months. The treatment effect was linked to an early time window <48 hours, specifying a target population for future trials.
EVALuna2:505459

Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage. - Kölbl, Kathrin; Hock, Stefan; Xu, Mingming; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias Martin; Kallmünzer, Bernd; Kuramatsu, Joji (Frontiers in Neurology, 2024)
OBJECTIVE: Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia and thalamus) ICH who represent an important subgroup of patients at the highest risk for functional deterioration with HE due to the eloquence of the affected brain region. METHODS: From our prospective institutional database, all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 h. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modeling. RESULTS: In 322 patients with deep ICH, NCCT markers were distributed as follows: irregular shape: 69.6%, heterogenous density: 55.9%, hypodensities: 52.5%, island sign: 19.3%, black hole sign: 11.5%, and blend sign: 4.7%. Upon multivariable regression analyses, independent associations were documented with the functional outcome for irregular shape (aOR: 2.73, 95%CI: 1.42-5.22, p = 0.002), heterogenous density (aOR: 2.62, 95%CI: 1.40-4.90, p = 0.003) and island sign (aOR: 2.54, 95%CI: 1.05-6.14, p = 0.038), and with HE for heterogenous density (aOR: 5.01, 95%CI: 1.93-13.05, p = 0.001) and hypodensities (aOR: 3.75, 95%CI: 1.63-8.62, p = 0.002). CONCLUSION: NCCT markers are frequent in deep ICH patients and provide important clinical implications. Specifically, markers defined by diverging intra-hematomal densities provided associations with a 5-times higher risk for HE and a 2.5-times higher likelihood for unfavorable functional long-term outcome. Hence, these markers allow the identification of patients with deep ICH at high risk for clinical deterioration due to HE.
EVALuna2:552372

Association of prothrombin complex concentrate administration and hematoma enlargement in non-vitamin K antagonist oral anticoagulant-related intracerebral hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Endres, Matthias; Haeusler, Karl Georg; Vajkoczy, Peter; Ringleb, Peter A.; Purrucker, Jan; Rizos, Timolaos; Erbguth, Frank; Schellinger, Peter D.; et al. (Annals of Neurology, 2018)
To investigate parameters associated with hematoma enlargement in non-vitamin K antagonist oral anticoagulant (NOAC)-related intracerebral hemorrhage (ICH).This retrospective cohort study includes individual patient data for 190 patients with NOAC-associated ICH over a 5-year period (2011-2015) at 19 departments of neurology across Germany. Primary outcome was the association of prothrombin complex concentrate (PCC) administration with hematoma enlargement. Subanalyses were calculated for blood pressure management and its association with the primary outcome. Secondary outcomes include associations with in-hospital mortality and functional outcome at 3 months assessed using the modified Rankin Scale.The study population for analysis of primary and secondary outcomes consisted of 146 NOAC-ICH patients with available follow-up imaging. Hematoma enlargement occurred in 49/146 (33.6%) patients with NOAC-related ICH. Parameters associated with hematoma enlargement were blood pressure >= 160mmHg within 4 hours and-in the case of factor Xa inhibitor ICH-anti-Xa levels on admission. PCC administration prior to follow-up imaging was not significantly associated with a reduced rate of hematoma enlargement either in overall NOAC-related ICH or in patients with factor Xa inhibitor intake (NOAC: risk ratio [RR] = 1.150, 95% confidence interval [CI] = 0.632-2.090; factor Xa inhibitor: RR = 1.057, 95% CI = 0.565-1.977), regardless of PCC dosage given or time interval until imaging or treatment. Systolic blood pressure levels < 160mmHg within 4 hours after admission were significantly associated with a reduction in the proportion of patients with hematoma enlargement (RR = 0.598, 95% CI = 0.365-0.978). PCC administration had no effect on mortality and functional outcome either at discharge or at 3 months.In contrast to blood pressure control, PCC administration was not associated with a reduced rate of hematoma enlargement in NOAC-related ICH. Our findings support the need of further investigations exploring new hemostatic reversal strategies for patients with factor Xa inhibitor-related ICH. Ann Neurol 2018;83:186-196.
EVALuna2:22552

Association of Surgical Hematoma Evacuation vs Conservative Treatment With Functional Outcome in Patients With Cerebellar Intracerebral Hemorrhage - Kuramatsu, Joji; Biffi, Alessandro; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Leasure, Audrey; Sansing, Lauren; Matouk, Charles; Falcone, Guido J.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; et al. (Journal of the American Medical Association, 2019)
Importance: The association of surgical hematoma evacuation with clinical outcomes in patients with cerebellar intracerebral hemorrhage (ICH) has not been established. Objective: To determine the association of surgical hematoma evacuation with clinical outcomes in cerebellar ICH. Design, Setting, and Participants: Individual participant data (IPD) meta-analysis of 4 observational ICH studies incorporating 6580 patients treated at 64 hospitals across the United States and Germany (2006-2015). Exposure: Surgical hematoma evacuation vs conservative treatment. Main Outcomes and Measures: The primary outcome was functional disability evaluated by the modified Rankin Scale ([mRS] score range: 0, no functional deficit to 6, death) at 3 months; favorable (mRS, 0-3) vs unfavorable (mRS, 4-6). Secondary outcomes included survival at 3 months and at 12 months. Analyses included propensity score matching and covariate adjustment, and predicted probabilities were used to identify treatment-related cutoff values for cerebellar ICH. Results: Among 578 patients with cerebellar ICH, propensity score-matched groups included 152 patients with surgical hematoma evacuation vs 152 patients with conservative treatment (age, 68.9 vs 69.2 years; men, 55.9% vs 51.3%; prior anticoagulation, 60.5% vs 63.8%; and median ICH volume, 20.5 cm3 vs 18.8 cm3). After adjustment, surgical hematoma evacuation vs conservative treatment was not significantly associated with likelihood of better functional disability at 3 months (30.9% vs 35.5%; adjusted odds ratio [AOR], 0.94 [95% CI, 0.81 to 1.09], P = .43; adjusted risk difference [ARD], -3.7% [95% CI, -8.7% to 1.2%]) but was significantly associated with greater probability of survival at 3 months (78.3% vs 61.2%; AOR, 1.25 [95% CI, 1.07 to 1.45], P = .005; ARD, 18.5% [95% CI, 13.8% to 23.2%]) and at 12 months (71.7% vs 57.2%; AOR, 1.21 [95% CI, 1.03 to 1.42], P = .02; ARD, 17.0% [95% CI, 11.5% to 22.6%]). A volume range of 12 to 15 cm3 was identified; below this level, surgical hematoma evacuation was associated with lower likelihood of favorable functional outcome (volume ≤12 cm3, 30.6% vs 62.3% [P = .003]; ARD, -34.7% [-38.8% to -30.6%]; P value for interaction, .01), and above, it was associated with greater likelihood of survival (volume ≥15 cm3, 74.5% vs 45.1% [P < .001]; ARD, 28.2% [95% CI, 24.6% to 31.8%]; P value for interaction, .02). Conclusions and Relevance: Among patients with cerebellar ICH, surgical hematoma evacuation, compared with conservative treatment, was not associated with improved functional outcome. Given the null primary outcome, investigation is necessary to establish whether there are differing associations based on hematoma volume.
CRIS-Team Scopus Importer:2019-10-15

Associations of neutrophil-to-lymphocyte ratio with mortality in spontaneous intracerebral hemorrhage - Giede-Jeppe, A.; Bobinger, Tobias; Gerner, Stefan; Sembill, Jochen; Lücking, Hannes; Kuramatsu, J. B.; Huttner, Hagen; Hölter, Philip (2017)
EVALuna2:22568

Automated ASPECT scoring in acute ischemic stroke: comparison of three software tools - Hölter, Philip; Mühlen, Iris; Gölitz, Philipp; Beuscher, Vanessa; Schwab, Stefan; Dörfler, Arnd (Neuroradiology, 2020)
Purpose: Various software applications offer support in the diagnosis of acute ischemic stroke (AIS), yet it remains unclear whether the performance of these tools is comparable to each other. Our study aimed to evaluate three fully automated software applications for Alberta Stroke Program Early CT (ASPECT) scoring (Syngo.via Frontier ASPECT Score Prototype V2, Brainomix e-ASPECTS® and RAPID ASPECTS) in AIS patients. Methods: Retrospectively, 131 patients with large vessel occlusion (LVO) of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy (EVT), were included. Pre-interventional non-enhanced CT (NECT) datasets were assessed in random order using the automated ASPECT software and by three experienced neuroradiologists in consensus. Interclass correlation coefficient (ICC), Bland-Altman, and receiver operating characteristics (ROC) were applied for statistical analysis. Results: Median ASPECTS of the expert consensus reading was 8 (7–10). Highest correlation was between the expert read and Brainomix (r = 0.871 (0.818, 0.909), p < 0.001). Correlation between expert read and Frontier V2 (r = 0.801 (0.719, 0.859), p < 0.001) and between expert read and RAPID (r = 0.777 (0.568, 0.871), p < 0.001) was high, respectively. There was a high correlation among the software tools (Frontier V2 and Brainomix: r = 0.830 (0.760, 0.880), p < 0.001; Frontier V2 and RAPID: r = 0.847 (0.693, 0.913), p < 0.001; Brainomix and RAPID: r = 0.835 (0.512, 0.923), p < 0.001). An ROC curve analysis revealed comparable accuracy between the applications and expert consensus reading (Brainomix: AUC = 0.759 (0.670–0.848), p < 0.001; Frontier V2: AUC = 0.752 (0.660–0.843), p < 0.001; RAPID: AUC = 0.734 (0.634–0.831), p < 0.001). Conclusion: Overall, there is a convincing yet developable grade of agreement between current ASPECT software evaluation tools and expert evaluation with regard to ASPECT assessment in AIS.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Acute ischemic stroke; Aspects; Diagnostics; Software anylsis

Automated Pupillometry Identifies Absence of Intracranial Pressure Elevation in Intracerebral Hemorrhage Patients - Giede-Jeppe, Antje; Sprügel, Maximilian; Huttner, Hagen; Borutta, Matthias; Kuramatsu, Joji; Hölter, Philip; Engelhorn, Tobias; Schwab, Stefan; Koehn, Julia (Neurocritical Care, 2020)
Introduction Although automated pupillometry is increasingly used in critical care settings, predictive value of automatically assessed pupillary parameters during different intracranial pressure (ICP) levels and possible clinical implications are unestablished. Methods This retrospective cohort study at the neurocritical care unit of the University of Erlangen-Nuremberg (2016-2018) included 23 nontraumatic supratentorial (intracerebral hemorrhage) ICH patients without signs of abnormal pupillary function by manual assessment, i.e., absent light reflex. We assessed ICP levels by an external ventricular drain simultaneously with parameters of pupillary reactivity [i.e., maximum and minimum apertures, light reflex latency (Lat), constriction and redilation velocities (CV, DV), and percentage change of apertures (per-change)] using a portable pupillometer (NeurOptics (R)). Computed tomography (CT) scans were analyzed to determine lesion location, size, intraventricular hemorrhage, hydrocephalus, midline shift, and compression or absence of the basal cisterns. We performed receiver operating characteristics analysis to investigate associations of ICP levels with pupillary parameters and to determine best cutoff values for prediction of ICP elevation. After dichotomization of assessments according to ICP values (normal: < 20 mmHg, elevated: >= 20 mmHg), prognostic performance of the determined cutoff parameters of pupillary function versus of CT-imaging findings was analyzed by calculating sensitivity, specificity, positive and negative predictive values (logistic regression, corresponding ORs with 95% CIs). Results In 23 patients (11 women, median age 59.0 (51.0-69.0) years), 1,934 assessments were available for analysis. A total of 74 ICP elevations >= 20 mmHg occurred in seven patients. Best discriminative thresholds for ICP elevation were: CV < 0.8 mm/s (AUC 0.740), per-change < 10% (AUC 0.743), DV < 0.2 mm/s (AUC 0.703), and Lat > 0.3 s (AUC 0.616). Positive predictive value of all four parameters to indicate ICP elevation ranged between 7.2 and 8.3% only and was similarly low for CT abnormalities (9.1%). We found high negative predictive values of pupillary parameters [CV: 99.2% (95% CI 98.3-99.6), per-change: 98.7% (95% CI 97.8-99.2), DV: 98.0% (95% CI 97.0-98.7), Lat: 97.0% (95% CI 96.0-97.7)], and CT abnormalities [99.7% (95% CI 99.2-99.9)], providing evidence that both techniques adequately identified ICH patients without ICP elevation. Conclusions Our data suggest an association between noninvasively detected changes in pupillary reactivity and ICP levels in sedated ICH patients. Although automated pupillometry and neuroimaging seem not sufficient to noninvasively indicate ICP elevation, both techniques, however, adequately identified ICH patients without ICP elevation. This finding may facilitate routine management by saving invasive ICP monitoring or repeated CT controls in patients with specific automated pupillometry readings.
CRIS-Team WoS Importer:2021-01-08

Automatic Segmentation of the Optic Radiation using DTI in Glaucoma Patients - El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Engelhorn, Tobias; Dörfler, Arnd; Wärntges, Simone; Michelson, Georg (Computational Vision and Medical Image Processing - VipIMAGE 2009, 2009)

Automatic Segmentation of the Optic Radiation Using DTI in Healthy Subjects and Patients with Glaucoma - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Computational Vision and Medical Image Processing, 2011)

A workflow for patient-individualized virtual angiogram generation based on CFD simulation - Endres, Jürgen; Kowarschik, Markus; Redel, Thomas; Sharma, Puneet; Mihalef, Viorel; Hornegger, Joachim; Dörfler, Arnd (Computational and Mathematical Methods in Medicine, 2012)

Baseline magnetic resonance imaging of the optic nerve provides limited predictive information on short-term recovery after acute optic neuritis - Berg, Sebastian; Kaschka, Iris; Utz, Kathrin S.; Huhn, Konstantin; Laemmer, Alexandra; Lämmer, Robert; Waschbisch, Anne; Kloska, Stephan; Lee, De-Hyung; Dörfler, Arnd; Linker, Ralf (PLoS ONE, 2015)
In acute optic neuritis, magnetic resonance imaging (MRI) may help to confirm the diagnosis as well as to exclude alternative diagnoses. Yet, little is known on the value of optic nerve imaging for predicting clinical symptoms or therapeutic outcome.To evaluate the benefit of optic nerve MRI for predicting response to appropriate therapy and recovery of visual acuity.Clinical data as well as visual evoked potentials (VEP) and MRI results of 104 patients, who were treated at the Department of Neurology with clinically definite optic neuritis between December 2010 and September 2012 were retrospectively reviewed including a follow up within 14 days.Both length of the Gd enhancing lesion (r = -0.38; p = 0.001) and the T2 lesion (r = -0.25; p = 0.03) of the optic nerve in acute optic neuritis showed a medium correlation with visual acuity after treatment. Although visual acuity pre-treatment was little but nonsignificantly lower if Gd enhancement of the optic nerve was detected via orbital MRI, improvement of visual acuity after adequate therapy was significantly better (0.40 vs. 0.24; p = 0.04). Intraorbitally located Gd enhancing lesions were associated with worse visual improvement compared to canalicular, intracranial and chiasmal lesions (0.35 vs. 0.54; p = 0.02).Orbital MRI is a broadly available, valuable tool for predicting the improvement of visual function. While the accurate individual prediction of long-term outcomes after appropriate therapy still remains difficult, lesion length of Gd enhancement and T2 lesion contribute to its prediction and a better short-term visual outcome may be associated with detection and localization of Gd enhancement along the optic nerve.
EVALuna2:21236

Bedside Catheter Hematoma Evacuation in Vitamin K Antagonist-Related Intracerebral Hemorrhage: A Safe and Feasible Approach - Volbers, Bastian; Niesen, Wolf Dirk; Amiri-Soltani, Samuel; Staykov, Dimitre; Shah, Mukesch Johannes; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Schwab, Stefan; Bardutzky, Jürgen (Frontiers in Neurology, 2020)
Background and Purpose: Although outcome in intracerebral hemorrhage (ICH) patients is generally not improved by surgical intervention, the use of minimally invasive surgery (MIS) has shown promising results. However, vitamin K antagonist (VKA)-related ICH patients are underrepresented in surgical treatment trials. We therefore assessed the safety and efficacy of a bedside MIS approach including local application of urokinase in VKA-related ICH. Methods: Patients with a VKA-related ICH > 20 ml who received bedside hematoma evacuation treatment (n = 21) at the University Medical Center Freiburg were retrospectively included for analysis and compared to a historical control group (n = 35) selected from an institutional database (University Medical Center Erlangen) according to identical inclusion criteria. Propensity score matching was performed to obtain comparable cohorts. The evolution of hematoma and peri-hemorrhagic edema (PHE) volumes, midline shift, and the occurrence of adverse events were analyzed. Furthermore, we assessed the modified Rankin Scale and NIHSS scores recorded at discharge. Results: Propensity score matching resulted in 16 patients per group with well-balanced characteristics. Median ICH volume at admission was 45.7 (IQR: 24.2–56.7) ml in the control group and 48.4 (IQR: 28.7–59.6) ml in the treatment group (p = 0.327). ICH volume at day 7 was less pronounced in the treatment group [MIS: 23.2 ml (IQR: 15.8–32.3) vs. control: 43.2 ml (IQR: 27.5–52.4); p = 0.013], as was the increase in midline shift up to day 7 [MIS: −3.75 mM (IQR: −4.25 to −2) vs. control: 1 mM (IQR: 0–2); p < 0.001]. No group differences were observed in PHE volume on day 7 [MIS: 42.4 ml (IQR: 25.0–72.3) vs. control: 31.0 ml (IQR: 18.8–53.8); p = 0.274] or mRS at discharge [MIS: 5 (IQR: 4–5) and 5 (IQR: 4–5); p = 0.949]. No hematoma expansion was observed. The catheter had to be replaced in 1 patient (6%). Conclusions: Bedside catheter-based hematoma evacuation followed by local thrombolysis with urokinase appears to be feasible and safe in cases of large VKA-related ICH. Further studies that assess the functional outcome associated with this technique are warranted. Clinical Trial Registration: DRKS00007908 (German Clinical Trial Register; www.drks.de).
CRIS-Team Scopus Importer:2020-09-11
Keywords: intracerebral hemorrhage; midline shift; minimally invasive surgery; peri-hemorrhagic edema; vitamin K antagonist

Beyond Functional Impairment: Redefining Favorable Outcome in Patients with Subarachnoid Hemorrhage - Custal, Christina; Koehn, Julia; Borutta, Matthias; Mrochen, Anne; Brandner, Sebastian; Eyupoglu, Ilker Y.; Lücking, Hannes; Hölter, Philip; Kuramatsu, Joji; Kornhuber, Johannes; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2021)
Background: For outcome assessment in patients surviving subarachnoid hemorrhage (SAH), the modified Rankin scale (mRS) represents the mostly established outcome tool, whereas other dimensions of outcome such as mood disorders and impairments in social life remain unattended so far. Objective: The aim of our study was to correlate 12-month functional and subjective health outcomes in SAH survivors. Methods: All SAH patients treated over a 5-year period received outcome assessment at 12 months, including functional scores (mRS and Barthel Index [BI]), subjective health measurement (EQ-5D), and whether they returned to work. Analyses - including utility-weighted mRS - were conducted to detect associations and correlations among different outcome measures, especially in patients achieving good functional outcome (i.e., mRS 0-2) at 12 months. Results: Of 351 SAH survivors, 287 (81.2%) achieved favorable functional outcome at 12 months. Contrary to the BI, the EQ-5D visual analog scale (VAS) showed a strong association with different mRS grades, accentuated in patients with favorable functional outcome. Despite favorable functional outcome, patients reported a high rate of impairments in activities (24.0%), pain (33.4%), and anxiety/depression (42.5%). Further, multivariable analysis revealed (i) impairments in activities (odds ratio [OR] [95% confidence interval CI]: 0.872 [0.817-0.930]), (ii) presence of depression or anxiety (OR [95% CI]: 0.836 [0.760-0.920]), and (iii) return to work (OR [95% CI]: 1.102 [0.1.013-1.198]) to be independently associated with self-reported subjective health. Conclusion: Established stroke scores mainly focusing on functional outcomes do poorly reflect the high rate of subjective impairments reported in SAH survivors, specifically in those achieving good functional outcome. Further studies are needed to investigate whether psychoeducational approaches aiming at improving coping mechanisms and perceived self-efficacy may result in higher subjective health in these patients.
CRIS-Team WoS Importer:2021-08-06

Biochemical markers of neurodegeneration in hereditary diffuse leucoencephalopathy with spheroids - Spitzer, Philipp; Kohl, Zacharias; Gölitz, Philipp; Coras, Roland; Blümcke, Ingmar; Brueck, Wolfgang; Dörfler, Arnd; Maihöfner, Christian (BMJ Case Reports, 2014)
Hereditary diffuse leucoencephalopathy with spheroids (HDLS) is a rare autosomal dominantly inherited disease with unknown pathophysiology. Diagnosis of neurodegenerative diseases is increasingly based on biomarkers. Although lumbar puncture is routinely performed during the diagnostic workup of HDLS, reports on alterations of neurodegeneration-specific biochemical markers have not been documented so far. We report a 35-year-old woman with clinical, radiological and neuropathological signs of HDLS. She suffered from a rapidly progressive frontal lobe syndrome. Brain MRI revealed diffuse leucoencephalopathy with predominant involvement of the periventricular white matter and corpus callosum. Although she was severely impaired and leucoencephalopathy was prominent, only cerebrospinal fluid total-? was moderately elevated. Other markers of neuronal (NSE) and astrocytic (S100B) damage were within normal range. Therefore, biochemical markers of central nervous system damage are not helpful in the diagnosis of HDL
EVALuna2:7264

Blockade of TNF-α rapidly inhibits pain responses in the central nervous system - Heß, Andreas; Axmann, Roland; Rech, Jürgen; Finzel, Stephanie; Heindl-Erdmann, Cornelia; Kreitz, Silke; Sergeeva, Marina; Saake, Marc; Garcia, Meritxell; Kollias, George; Straub, Rainer H.; Sporns, Olaf; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
There has been a consistent gap in understanding how TNF-α neutralization affects the disease state of arthritis patients so rapidly, considering that joint inflammation in rheumatoid arthritis is a chronic condition with structural changes. We thus hypothesized that neutralization of TNF-α acts through the CNS before directly affecting joint inflammation. Through use of functional MRI (fMRI), we demonstrate that within 24 h after neutralization of TNF-α, nociceptive CNS activity in the thalamus and somatosensoric cortex, but also the activation of the limbic system, is blocked. Brain areas showing blood-oxygen level-dependent signals, a validated method to assess neuronal activity elicited by pain, were significantly reduced as early as 24 h after an infusion of a monoclonal antibody to TNF-α. In contrast, clinical and laboratory markers of inflammation, such as joint swelling and acute phase reactants, were not affected by anti-TNF-α at these early time points. Moreover, arthritic mice overexpressing human TNF-α showed an altered pain behavior and amore intensive, widespread, and prolonged brain activity upon nociceptive stimuli compared with wild-type mice. Similar to humans, these changes, as well as the rewiring of CNS activity resulting in tight clustering in the thalamus, were rapidly reversed after neutralization of TNF-α. These results suggest that neutralization of TNF-α affects nociceptive brain activity in the context of arthritis, long before it achieves antiinflammatory effects in the joints.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Antiinflammatory therapy; Cytokines

Blood Pressure and Anticoagulation Reversal Management during Off-Hours in Oral Anticoagulation-Associated Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Cerebrovascular Diseases, 2020)
Background: Prevention of hematoma enlargement in oral anticoagulation-associated intracerebral hemorrhage (OAC-ICH) focuses on blood pressure (BP) reduction and OAC reversal. We investigated whether treatment efficiency and clinical outcomes differ between OAC-ICH patients admitted outside versus during regular working hours. Methods: Based on pooled data of multicenter cohort studies, we grouped OAC-ICH patients (vitamin K antagonist [VKA], non-vitamin K oral anticoagulant [NOAC]) according to on-vs. off-hour admission. Primary outcome was the functional outcome using the modified Rankin scale (mRS) dichotomized into favorable (mRS 0-3) and unfavorable (mRS 4-6) and mortality at 3 months. Secondary outcome measures included the occurrence of hematoma enlargement, the proportions of patients with systolic BP <140 mm Hg and with anticoagulation treatment achieving international normalized ratio (INR) levels <1.3 at 4 h. Propensity score matching (PSM) was performed to account for imbalances in baseline characteristics. Results: The study population consisted of 76/126 NOAC-ICH patients and 1,005/1,470 VKA patients presenting during off-hours. Functional outcome and mortality rates were not significantly different among PSM patients with VKA-ICH and NOAC-ICH during on-vs. off-hours (mRS 4-6 VKA-ICH: On-hour: 239/357 [66.9%] vs. 253/363 [69.7%] off-hour; p = 0.43; NOAC-ICH: On-hour 26/42 [61.9%] vs. off-hour: 37/57 [64.9%]; p = 0.76; mRS 6 VKA-ICH: On-hour: 127/357 [35.6%] vs. off-hour: 148/363 [40.8%]; p = 0.15;-NOAC-ICH: On-hour 17/42 [40.5%] vs. off-hour: 16/57 [28.1%]; p = 0.20). There were no differences detectable regarding the secondary outcome measures (i.e., hematoma enlargement, the proportion of patients who achieved systolic BP levels <140 mm Hg at 4 h as well as anticoagulation treatment achieving INR levels <1.3 at 4 h) in OAC patients. Conclusion: Our study implies that BP reduction and anticoagulation reversal management are well established and associated with similar rates of hematoma enlargement and clinical outcomes in on-vs. off-hour admitted OAC-ICH patients.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Clinical outcome; Intracerebral hemorrhage; Non-vitamin K oral anticoagulant; Off-hour; Oral anticoagulation; Vitamin K antagonist

Brain correlates of short-term habituation to repetitive electrical noxious stimulation - Nickel, Franziska; Ott, Sabine; Möhringer, Susanne; Saake, Marc; Dörfler, Arnd; Seifert, Frank; Maihöfner, Christian (European Journal of Pain, 2014)
Habituation to repetitive noxious stimuli is a well-known phenomenon. We investigated brain correlates of habituation to pain in a transdermal electrical pain model using functional magnetic resonance imaging (fMRI).Electrical painful stimulation with 1 Hz was applied to the volar forearm of 48 healthy subjects for 45 min. Before and after conditioning stimulation, psychophysical testing and fMRI were performed. During fMRI sessions, the subjects underwent blockwise painful electrical stimulation with a fixed percept-adapted current intensity. After fMRI 1 and fMRI 2 subjects rated the individual pain intensity of the electrical stimulus.Substantial habituation occurred during conditioning electrical stimulation. Accordingly, areas typically involved in pain processing showed decreased activity after conditioning stimulation. The blood oxygen level-dependent signal of the subgenual anterior cingulate gyrus, the superior parietal lobule and the supplemental motor area correlated positively with habituation. In contrast, activity in the periaqueductal grey, thalamus and insula correlated negatively. The results of the correlation analyses did not survive correction for multiple comparisons.With this study, we identified central components associated with habituation to repetitive painful stimuli. The results suggest that an increase in tonic inhibitory activity in cortical pain processing areas is a major mechanism contributing to habituation to phasic noxious stimuli. Moreover, areas involved in descending pain modulation were differentially modulated. This may hint at a simultaneous activation of facilitating and inhibiting nociceptive systems that are both altered in the transdermal electrical pain model.
EVALuna2:14468

Brain fMRI Predicts Responses to Certolizumab Pegol in RA. an International, Multi-center, Randomized, Double-blind, Placebocontrolled Trial (PreCePRA) - Rech, Jürgen; Schenker, Hannah; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Simon, David; Mendez, Larissa Valor; Schoenau, Verena; Prade, Jutta; Sergeeva, Marina; Sulvakumar, Mageshvar; Strobelt, Sandra; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Brain Mechanisms of Abnormal Temperature Perception in Cold Allodynia induced by Ciguatoxin - Eisenblätter, Anneka; Lewis, Richard; Dörfler, Arnd; Forster, Clemens; Zimmermann, Katharina (Annals of Neurology, 2016)
Cold allodynia occurs as a major symptom of neuropathic pain states. It remains poorly treated with current analgesics. Ciguatoxins (CTXs), ichthyosarcotoxins that cause ciguatera, produce a large peripheral sensitization to dynamic cold stimuli in A?-fibers by activating sodium channels without producing heat or mechanical allodynia. We used CTXs as surrogate model of cold allodynia to dissect the framework of cold allodynia activated central pain pathways.Reversible cold allodynia was induced in healthy male volunteers by shallow intracutaneous injection of low nM concentrations of CTX into the dorsal skin of the forefoot. Cold and warm stimuli were delivered to the treated and the control site using a peltier driven thermotest device. Functional Magnetic Resonance Imaging (fMRI) scans were acquired with a 3 Tesla MRI scanner using a blood-oxygen-level-dependent (BOLD) protocol.The CTX-induced substantial peripheral sensitization to cooling stimuli in A?-fibers is particularly retrieved in BOLD changes due to dynamic temperature changes and less during constant cooling. Brain areas which responded during cold allodynia were always located bilateral and appeared in the medial insula, the medial cingulate cortex, the secondary somatosensory cortex, in frontal areas and the cerebellum. While these areas produced also changes in BOLD-signal during the dynamic warming stimulus on the control site they remained silent during the warming stimuli on the injected site.We describe the defining feature of the cold allodynia pain percept in the human brain and illustrate why ciguatera sufferers often report a perceptual temperature reversal. This article is protected by copyright. All rights reserved.
EVALuna2:16742

Brain MRI Lesions are Related to Bowel Incontinence in Multiple Sclerosis - Fröhlich, Katharina; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Huhn, Konstantin; Schwab, Stefan; Hilz, Max-Josef; Seifert, Frank; Winder, Klemens (Journal of Neuroimaging, 2018)
BACKGROUND AND PURPOSE: Bowel incontinence in multiple sclerosis might be associated with specific lesion sites. This study intended to determine associations between bowel incontinence and cerebral multiple sclerosis lesions using a voxel-wise lesion symptom mapping analysis. METHODS: We conducted a retrospective study of multiple sclerosis patients with self-reported bowel incontinence and matched controls. Lesions were manually outlined on T2-weighted MRI scans and transformed into stereotaxic space. We performed a voxel-wise subtraction analysis subtracting the lesion overlap of patients without from patients with bowel incontinence. Finally, we compared the absence or presence of bowel incontinence between patients with and without lesions in a given voxel using the Liebermeister test. RESULTS: A total of 51 patients were included in the study. The analysis yielded associations between bowel incontinence and lesions in the supramarginal gyrus of the left secondary somatosensory cortex and another lesion cluster in the right parahippocampal gyrus and amygdala. CONCLUSIONS: Our analysis indicates associations between bowel incontinence and lesions in the left supramarginal gyral area contributing to integrating anorectal-visceral sensation and in the right parahippocampal gyrus and amygdala contributing to generating visceral autonomic arousal states. Moreover, our results suggest left hemispheric dominance of sensory visceral integration, while limbic areas of the right hemisphere seem to contribute to the autonomic component of the defecation process. A limitation of our study is the retrospective evaluation of the bowel incontinence status based on medical records. Further research should evaluate the bowel incontinence status in multiple sclerosis patients prospectively to overcome the limitations of the current study.
EVALuna2:36318

Brain Structure in Acutely Underweight and Partially Weight-Restored Individuals With Anorexia Nervosa: A Coordinated Analysis by the ENIGMA Eating Disorders Working Group - Walton, Esther; Bernardoni, Fabio; Batury, Victoria Luise; Bahnsen, Klaas; Larivière, Sara; Abbate-Daga, Giovanni; Andres-Perpiña, Susana; Bang, Lasse; Bischoff-Grethe, Amanda; Brooks, Samantha J.; Campbell, Iain C.; Cascino, Giammarco; et al. (Biological Psychiatry, 2022)
Background: The pattern of structural brain abnormalities in anorexia nervosa (AN) is still not well understood. While several studies report substantial deficits in gray matter volume and cortical thickness in acutely underweight patients, others find no differences, or even increases in patients compared with healthy control subjects. Recent weight regain before scanning may explain some of this heterogeneity. To clarify the extent, magnitude, and dependencies of gray matter changes in AN, we conducted a prospective, coordinated meta-analysis of multicenter neuroimaging data. Methods: We analyzed T1-weighted structural magnetic resonance imaging scans assessed with standardized methods from 685 female patients with AN and 963 female healthy control subjects across 22 sites worldwide. In addition to a case-control comparison, we conducted a 3-group analysis comparing healthy control subjects with acutely underweight AN patients (n = 466) and partially weight-restored patients in treatment (n = 251). Results: In AN, reductions in cortical thickness, subcortical volumes, and, to a lesser extent, cortical surface area were sizable (Cohen's d up to 0.95), widespread, and colocalized with hub regions. Highlighting the effects of undernutrition, these deficits were associated with lower body mass index in the AN sample and were less pronounced in partially weight-restored patients. Conclusions: The effect sizes observed for cortical thickness deficits in acute AN are the largest of any psychiatric disorder investigated in the ENIGMA (Enhancing Neuro Imaging Genetics through Meta Analysis) Consortium to date. These results confirm the importance of considering weight loss and renutrition in biomedical research on AN and underscore the importance of treatment engagement to prevent potentially long-lasting structural brain changes in this population.
CRIS-Team Scopus Importer:2022-09-09
Keywords: BMI; Cortical thickness; MRI; Subcortical volume; Surface area

Brain tissues have single-voxel signatures in multi-spectral MRI - German, Alexander; Mennecke, Angelika; Martin, Jan; Hanspach, Jannis; Liebert, Andrzej; Herrler, Jürgen; Kuder, Tristan Anselm; Schmidt, Manuel; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Winkler, Jürgen; et al. (NeuroImage, 2021)
Since the seminal works by Brodmann and contemporaries, it is well-known that different brain regions exhibit unique cytoarchitectonic and myeloarchitectonic features. Transferring the approach of classifying brain tissues – and other tissues – based on their intrinsic features to the realm of magnetic resonance (MR) is a longstanding endeavor. In the 1990s, atlas-based segmentation replaced earlier multi-spectral classification approaches because of the large overlap between the class distributions. Here, we explored the feasibility of performing global brain classification based on intrinsic MR features, and used several technological advances: ultra-high field MRI, q-space trajectory diffusion imaging revealing voxel-intrinsic diffusion properties, chemical exchange saturation transfer and semi-solid magnetization transfer imaging as a marker of myelination and neurochemistry, and current neural network architectures to analyze the data. In particular, we used the raw image data as well to increase the number of input features. We found that a global brain classification of roughly 97 brain regions was feasible with gross classification accuracy of 60%; and that mapping from voxel-intrinsic MR data to the brain region to which the data belongs is possible. This indicates the presence of unique MR signals of different brain regions, similar to their cytoarchitectonic and myeloarchitectonic fingerprints.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Brain; Data Analysis; High-Field Imaging; Machine Learning; MRI; Segmentation

Brain volume reduction after whole-brain radiotherapy: quantification and prognostic relevance - Hoffmann, Christian; Distel, Luitpold; Knippen, Stefan; Gryc, Thomas; Schmidt, Manuel; Fietkau, Rainer; Putz, Florian (Neuro-Oncology, 2018)
Background: Recent studies have questioned the value of adding whole-brain radiotherapy (WBRT) to stereotactic radiosurgery (SRS) for brain metastasis treatment. Neurotoxicity, including radiation-induced brain volume reduction, could be one reason why not all patients benefit from the addition of WBRT. In this study, we quantified brain volume reduction after WBRT and assessed its prognostic significance. Methods: Brain volumes of 91 patients with cerebral metastases were measured during a 150-day period after commencing WBRT and were compared with their pretreatment volumes. The average daily relative change in brain volume of each patient, referred to as the "brain volume reduction rate," was calculated. Univariate and multivariate Cox regression analyses were performed to assess the prognostic significance of the brain volume reduction rate, as well as of 3 treatment-related and 9 pretreatment factors. A one-way analysis of variance was used to compare the brain volume reduction rate across recursive partitioning analysis (RPA) classes. Results: On multivariate Cox regression analysis, the brain volume reduction rate was a significant predictor of overall survival after WBRT (P < 0.001), as well as the number of brain metastases (P = 0.002) and age (P = 0.008). Patients with a relatively favorable prognosis (RPA classes 1 and 2) experienced significantly less brain volume decrease after WBRT than patients with a poor prognosis (RPA class 3) (P = 0.001). There was no significant correlation between delivered radiation dose and brain volume reduction rate (P = 0.147). Conclusion: In this retrospective study, a smaller decrease in brain volume after WBRT was an independent predictor of longer overall survival.
EVALuna2:36468

Can flat-detector CT after successful endovascular treatment predict long-term outcome in patients with large vessel occlusion? An Alberta Stroke Programme Early CT Score–based study - Knott, Michael; Hölter, Philip; Hock, Stefan; Mühlen, Iris; Gerner, Stefan; Sprügel, Maximilian; Huttner, Hagen; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Neurological Sciences, 2022)
Purpose: Recent studies postulate a high prognostic value of the Alberta Stroke Programme Early CT Score (ASPECTS) applied on non-contrast whole-brain flat-detector CT (FDCT) after successful endovascular treatment (EVT). The aim of this study was the evaluation of long-term patient outcome after endovascular treatment using postinterventional FDCT. Methods: Using a local database (Stroke Research Consortium in Northern Bavaria, STAMINA), 517 patients with successful endovascular treatment (modified Thrombolysis in Cerebral Infarction (mTICI) ≥ 2B) due to acute ischaemic stroke (AIS) and large vessel occlusion (LVO) of the anterior circulation were recruited retrospectively. In all cases, non-contrast FDCT after EVT was analysed with special focus at ASPECTS. These results were correlated with the functional outcome in long-term (modified Rankin Scale (mRS) shift from pre-stroke to 90 days after discharge). Results: A significant difference in FDCT-ASPECTS compared to the subgroup of favourable vs. unfavourable outcome (Δ mRS) (median ASPECTS 10 (10–9) vs. median ASPECTS 9 (10–7); p = 0,001) could be demonstrated. Multivariable regression analysis revealed FDCT-ASPECTS (OR 0.234, 95% CI − 0.102–0.008, p = 0.022) along with the NHISS at admission (OR 0.169, 95% CI 0.003–0.018, p = 0.008) as independent factors for a favourable outcome. Cut-off point for a favourable outcome (Δ mRS) was identified at an ASPECTS ≥ 8 (sensitivity 90.6%, specificity 35%). Conclusion: For patients with LVO and successful EVT, FDCT-ASPECTS was found to be highly reliable in predicting long-term outcome.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ASPECTS; Endovascular treatment; Flat-detector CT; Stroke

Can intracranial time-of-flight-MR angiography predict extracranial carotid artery stenosis? - Osmanodja, Filiz; Scheitz, Jan F.; Fiebach, Jochen B.; Ganeshan, Ramanan; Villringer, Kersten (Journal of Neurology, 2021)
Objectives Extracranial stenosis of the internal carotid artery (ICA) is an important cause of ischemic stroke and transient ischemic attack (TIA). It can be diagnosed using contrast-enhanced CT or MR angiography (MRA) as well as Doppler ultrasound. In this study, we assessed the diagnostic value of intracranial time-of-flight (TOF) MRA to predict extracranial ICA stenosis (ICAS). Methods We retrospectively analyzed consecutive patients with acute ischemic stroke or TIA and middle- (50-69%) or high-grade (70-99%) unilateral extracranial ICAS according to NASCET criteria assessed by ultrasound between January 2016 and August 2018. The control group consisted of patients without extracranial ICAS. Intraluminal signal intensities (SI) of the intracranial ICA on the side of the extracranial stenosis were compared to the contralesional side on TOF-MRA source images. SI ratios (SIR) of contralesional:lesional side were compared between groups. Results In total, 151 patients were included in the main analysis. Contralesional:lesional SIR in the intracranial C4-segment was significantly higher in patients with ipsilateral extracranial ICA stenosis (n = 51, median 74 years, 57% male) compared to the control group (n = 100, median 68 years, 48% male). Mean SIR was 1.463 vs. 1.035 (p < 0.001) for right-sided stenosis and 1.362 vs. 1.000 (p < 0.001) for left-sided stenosis. Receiver-operating characteristic curve demonstrated a cut-off value of 1.086 for right-sided [sensitivity/specificity 75%/81%; area under the curve (AUC) 0.81] and 1.104 for left-sided stenosis (sensitivity/specificity 70%/84%; AUC 0.80) in C4 as a good predictor for high-grade extracranial ICAS. Conclusions SIR on TOF-MRA can be a marker of extracranial ICAS.
CRIS-Team WoS Importer:2021-11-19

Can Perfusion-Based Brain Tissue Oxygenation MRI Support the Understanding of Cerebral Abscesses In Vivo? - Knott, Michael; Hölter, Philip; Soder, Liam; Schlaffer, Sven-Martin; Hoffmanns, Sophia; Lang, Roland; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2023)
Purpose: The clinical condition of a brain abscess is a potentially life-threatening disease. The combination of MRI-based imaging, surgical therapy and microbiological analysis is critical for the treatment and convalescence of the individual patient. The aim of this study was to evaluate brain tissue oxygenation measured with dynamic susceptibility contrast perfusion weighted imaging (DSC-PWI) in patients with brain abscess and its potential benefit for a better understanding of the environment in and around brain abscesses. Methods: Using a local database, 34 patients (with 45 abscesses) with brain abscesses treated between January 2013 and March 2021 were retrospectively included in this study. DSC-PWI imaging and microbiological work-up were key inclusion criteria. These data were analysed regarding a correlation between DSC-PWI and microbiological result by quantifying brain tissue oxygenation in the abscess itself, the abscess capsula and the surrounding oedema and by using six different parameters (CBF, CBV, CMRO2, COV, CTH and OEF). Results: Relative cerebral blood flow (0.335 [0.18–0.613] vs. 0.81 [0.49–1.08], p = 0.015), relative cerebral blood volume (0.44 [0.203–0.72] vs. 0.87 [0.67–1.2], p = 0.018) and regional cerebral metabolic rate for oxygen (0.37 [0.208–0.695] vs. 0.82 [0.55–1.19], p = 0.022) were significantly lower in the oedema around abscesses without microbiological evidence of a specific bacteria in comparison with microbiological positive lesions. Conclusions: The results of this study indicate a relationship between brain tissue oxygenation status in DSC-PWI and microbiological/inflammatory status. These results may help to better understand the in vivo environment of brain abscesses and support future therapeutic decisions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: brain abscess; brain tissue oxygenation; DSC-PWI

C-Arm Conebeam CT Perfusion Imaging in the Angiographic Suite: A Comparison with Multidetector CT Perfusion Imaging - Niu, K.; Yang, P.; Wu, Y.; Struffert, Tobias; Dörfler, Arnd; Schafer, S.; Royalty, K.; Strother, C.; Chen, G. -H. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Perfusion imaging in the angiography suite may provide a way to reduce time from stroke onset to endovascular revascularization of patients with large-vessel occlusion. Our purpose was to compare conebeam CT perfusion with multidetector CT perfusion. MATERIALS AND METHODS: Data from 7 subjects with both multidetector CT perfusion and conebeam CT perfusion were retrospectively processed and analyzed. Two algorithms were used to enhance temporal resolution and temporal sampling density and reduce the noise of conebeam CT data before generating perfusion maps. Two readers performed qualitative image-quality evaluation on maps by using a 5-point scale. ROIs indicating CBF/CBV abnormalities were drawn. Quantitative analyses were performed by using the Sørensen-Dice coefficients to quantify the similarity of abnormalities. A noninferiority hypothesis was tested to compare conebeam CT perfusion against multidetector CT perfusion. RESULTS: Average image-quality scores for multidetector CT perfusion and conebeam CT perfusion images were 2.4 and 2.3, respectively. The average confidence score in diagnosis was 1.4 for both multidetector CT and conebeam CT; the average confidence scores for the presence of a CBV/CBF mismatch were 1.7 (κ = 0.50) and 1.5 (κ = 0.64). For multidetector CT perfusion and conebeam CT perfusion maps, the average scores of confidence in making treatment decisions were 1.4 (κ = 0.79) and 1.3 (κ = 0.90). The area under the visual grading characteristic for the above 4 qualitative quality scores showed an average area under visual grading characteristic of 0.50, with 95% confidence level cover centered at the mean for both readers. The Sørensen-Dice coefficient for CBF maps was 0.81, and for CBV maps, 0.55. CONCLUSIONS: After postprocessing methods were applied to enhance image quality for conebeam CT perfusion maps, the conebeam CT perfusion maps were not inferior to those generated from multidetector CT perfusion.
EVALuna2:33153

Carotid artery stenting - An update Karotisstents - eine Standortbestimmung - Gölitz, Philipp; Dörfler, Arnd (Radiologe, 2013)
Clinical/methodical issue: Therapy of carotid stenosis should be based on an accurate assessment of the stenosis and a differentiation between symptomatic and asymptomatic patients. Standard radiological methods: According to current guidelines carotid artery stenting (CAS) can be considered as an established therapeutic alternative to carotid endarterectomy (CEA). Methodical innovations: For the therapy of carotid stenosis CAS has become established as a minimally invasive alternative to CEA because the complication rate has been reduced due to growing experience, technical innovations and external quality assessment. Performance: The CAS procedure should be performed in centers with documented complication rates of < 3 % for asymptomatic and < 6 % for symptomatic stenoses. Achievements: Overall there are no significant differences between CAS and CEA in the treatment of carotid stenosis concerning the secondary prophylactic effect. Practical recommendations: Ideally an interdisciplinary approach should be chosen for the therapy regime. Revascularization of asymptomatic stenoses should be considered critically as these patients might profit from optimized conservative medicinal therapy. © 2013 Springer-Verlag Berlin Heidelberg. Schlüsselwörter: Angioplastie Karotisstenose Endarteriektomie Schlaganfallprävention Stentimplantation.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angioplasty; Carotid artery stenosis; Endarterectomy; Stent deployment; Stroke prevention

Cavernous sinus thrombosis as a rare cause of exophthalmos in childhood : A case report - Kamawal, A.; Schmidt, M. A.; Rompel, O.; Gusek-Schneider, G. C.; Mardin, C. Y.; Trollmann, Regina (Ophthalmologe, 2016)
Complications of acute bacterial sinusitis mostly occur in children and adolescents. In particular, intracranial spread of the infection can lead to severe even fatal courses of the disease. This article is a case report about a 13-year-old boy suffering from left-sided headache, meningismus and exophthalmos as presenting symptoms. Cranial magnetic resonance imaging (MRI) showed merely right-sided sphenoid sinusitis; however, the diffusion-weighted MRI sequence indicated a left-sided cavernous sinus thrombosis, which could be confirmed by computed tomography (CT) angiography. Cerebrospinal fluid diagnostics showed significant leukocytosis confirming secondary meningitis. Finally, exophthalmos was explained by parainfectious cavernous sinus thrombosis and periorbital edema. This case report highlights the importance of extended and specific diagnostic imaging in cases of clinically suspected complications in children and adolescents with sinusitis and the diagnostic significance of diffusion-weighted MRI.
EVALuna2:21321

CD133-Positive Membrane Particles in Cerebrospinal Fluid of Patients with Inflammatory and Degenerative Neurological Diseases - Bobinger, Tobias; May, Lisa-Sophie; Lücking, Hannes; Kloska, Stephan; Burkardt, Petra; Spitzer, Philipp; Maler, Juan M.; Corbeil, Denis; Huttner, Hagen (Frontiers in Cellular Neuroscience, 2017)
Background: Analysis of cerebrospinal fluid (CSF) is a frequently used diagnostic tool in a variety of neurological diseases. Recent studies suggested that investigating membrane particles enriched with the stem cell marker CD133 may offer new avenues for studying neurological disease. In this study, we evaluated the amount of membrane particle-associated CD133 in human CSF in neuroinflammatory and degenerative diseases. Methods: We compared the amount of membrane particle-associated CD133 in CSF samples collected from 45 patients with normal pressure hydrocephalus, parkinsonism, dementia, and cognitive impairment, chronic inflammatory diseases and 10 healthy adult individuals as controls. After ultracentrifugation of CSF, gel electrophoresis and immunoblotting using anti-CD133 monoclonal antibody 80B258 were performed. Antigen-antibody complexes were detected using chemiluminescence. Results: The amount of membrane particle-associated CD133 was significantly increased in patients with normal pressure hydrocephalus (p < 0.001), parkinsonism (p = 0.011) as well as in patients with chronic inflammatory disease (p = 0.008). Analysis of CSF of patients with dementia and cognitive impairment revealed no significant change compared with healthy individuals. Furthermore, subgroup analysis of patients with chronic inflammatory diseases demonstrated significantly elevated levels in individuals with relapsing-remitting multiple sclerosis (p = 0.023) and secondary progressive multiple sclerosis (SPMS; p = 0.010). Conclusion: Collectively, our study revealed elevated levels of membrane particle-associated CD133 in patients with normal pressure hydrocephalus, parkinsonism as well as relapsing-remitting and SPMS. Membrane glycoprotein CD133 may be of clinical value for several neurological diseases.
EVALuna2:22515

Central nervous system anomalies in two females with Borjeson-Forssman-Lehmann syndrome - Kasper, Burkhard; Dörfler, Arnd; Di Donato, Nataliya; Kasper, Ekkehard M.; Wieczorek, Dagmar; Hoyer, Juliane; Zweier, Christiane (Epilepsy and Behavior, 2017)
Borjeson-Forssman-Lehmann syndrome (BFLS) is a rare disorder caused by mutations in the PHF6 gene. It manifests as syndromic X-linked recessive intellectual disability (ID) in males and as sporadic ID due to de novo mutations in females. Clinical features include variable ID and a range of somatic manifestations constituting a distinct phenotype in both males and females, respectively, including seizures in a few. Central nervous system (CNS) imaging data are largely unavailable for BFLS. Here we report on CNS MRI findings from two female individuals with BFLS due to a de novo duplication in PHF6 who presented with typical BFLS and epilepsy. Brain findings encompass an intriguing combination of structural abnormalities including a simplified gyral pattern and aspects resembling subcortical band heterotopia as signs of malformation of cortical development (MCD). This finding is of note, since PHF6 has been suggested to play pivotal roles in CNS development including neuronal migration.
EVALuna2:9368

CENTRAL NERVOUS SYSTEM PAIN RESPONSE AND COMPONENTS OF DISEASE ACTIVITY IN RA PATIENTS AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO: A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Schenker, Hannah; Rech, Jürgen; Tascilar, K.; Hagen, Melanie; Schoenau, V.; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Cerebral aneurysm treatment using flow-diverting stents: in-vivo visualization of flow alterations by parametric colour coding to predict aneurysmal occlusion: preliminary results - Gölitz, Philipp; Struffert, Tobias; Roesch, Julie; Ganslandt, Oliver Thomas; Knossalla, Frauke; Dörfler, Arnd (European Radiology, 2015)
After deployment of flow-diverting stents (FDS), complete aneurysm occlusion is not predictable. This study investigated whether parametric colour coding (PCC) could allow in vivo visualization of flow alterations induced by FDS and identify favourable or adverse flow modulations.Thirty-six patients treated by FDS were analyzed. Preinterventional and postinterventional DSA-series were postprocessed by PCC and time-density curves (TDCs) were calculated. The parameters aneurysmal inflow, outflow, and relative time-to-peak (rTTP) were calculated. Preinterventional and postinterventional values were compared and related to occlusion rate.Postinterventional inflow showed a mean reduction of 37%, outflow of 51%, and rTTP a prolongation of 82%. Saccular aneurysm occlusion occurred if a reduction of at least 15% was achieved for inflow and 35% for outflow (sensitivity: 89%, specificity: 82%). Unchanged outflow and a slightly prolonged rTTP were associated with growth in one fusiform aneurysm.PCC allows visualization of flow alterations after FDS treatment, illustrating "flow diverting effects" by the TDC shape and indicating mainly aneurysmal outflow and lesser inflow changes. Quantifiable parameters (inflow, outflow, rTTP) can be obtained, thresholds for predicting aneurysm occlusion determined, and adverse flow modulations assumed. As a rapid intraprocedural tool, PCC might support the decision to implant more than one FDS.o After deployment of a flow-diverting stent, complete aneurysm occlusion is unpredictable. o Parametric colour coding offers new options for visualizing in vivo flow alterations non-invasively. o Quantifiable parameters, i.e., aneurysmal inflow/outflow can be obtained allowing prognostic stratification. o Rapid, intraprocedural application allows treatment monitoring, potentially contributing to patient safety.
EVALuna2:22356

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Cerebral lesion correlates of sympathetic cardiovascular activation in multiple sclerosis - Winder, Klemens; Linker, Ralf A.; Seifert, Frank; Wang, Ruihao; Lee, De Hyung; Engelhorn, Tobias; Dörfler, Arnd; Fröhlich, Katharina; Hilz, Max-Josef (Human Brain Mapping, 2019)
Cardiovascular autonomic dysfunction is common in multiple sclerosis (MS) and contributes significantly to disability. We hypothesized that cerebral MS-lesions in specific areas of the central autonomic network might account for imbalance of the sympathetic and parasympathetic cardiovascular modulation. Therefore, we used voxel-based lesion symptom mapping (VLSM) to determine associations between cardiovascular autonomic dysfunction and cerebral MS-related lesion sites. In 74 MS-patients (mean age 37.0 ± 10.5 years), we recorded electrocardiographic RR-intervals and systolic and diastolic blood pressure. Using trigonometric regressive spectral analysis, we assessed low (0.04–0.15 Hz) and high (0.15–0.5 Hz) frequency RR-interval-and blood pressure-oscillations and determined parasympathetically mediated RR-interval–high-frequency modulation, mainly sympathetically mediated RR-interval–low-frequency modulation, sympathetically mediated blood pressure-low-frequency modulation, and the ratios of sympathetic and parasympathetic RR-interval-modulation as an index of sympathetic-parasympathetic balance. Cerebral MS-lesions were analyzed on imaging scans. We performed a VLSM-analysis correlating parameters of autonomic dysfunction with cerebral MS-lesion sites. The VLSM-analysis showed associations between increased RR-interval low-frequency/high-frequency ratios and lesions most prominently in the left insular, hippocampal, and right frontal inferior opercular region, and a smaller lesion cluster in the right middle cerebellar peduncle. Increased blood pressure-low-frequency powers were associated with lesions primarily in the right posterior parietal white matter and again left insular region. Our data indicate associations between a shift of cardiovascular sympathetic-parasympathetic balance toward increased sympathetic modulation and left insular and hippocampal lesions, areas of the central autonomic network. The VLSM-analysis further distinguished between right inferior fronto-opercular lesions disinhibiting cardiac sympathetic activation and right posterior parietal lesions increasing sympathetic blood pressure modulation.
CRIS-Team Scopus Importer:2019-08-23
Keywords: autonomic dysfunction; insular lesion; multiple sclerosis; visceral arousal; voxel-based lesion symptom mapping

Cerebral lesions sites in neurosarcoidosis: a lesion mapping study - Fröhlich, Kilian; Mrochen, Anne; Wang, Ruihao; Haupenthal, David; Macha, Kosmas; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Schwab, Stefan; Winder, Klemens (Journal of Neurology, 2023)
Background and purpose: Sarcoidosis is a granulomatous disease of unknown etiology affecting the central nervous system in up to 15% of the patients. Diagnosis of neurosarcoidosis is very challenging due to the heterogeneity of its clinical manifestation. This study intended to evaluate the distribution of cerebral lesion sites and the potential presence of specific lesion clusters in neurosarcoidosis patients using voxel-based lesion symptom mapping (VLSM). Methods: Patients with neurosarcoidosis were retrospectively identified and included between 2011 and 2022. Cerebral lesion sites were correlated voxel-wise with presence and absence of neurosarcoidosis using non-parametric permutation test. Multiple sclerosis patients served as controls for the VLSM-analysis. Results: Thirty-four patients (mean age 52 ± 15 years) of whom 13 were diagnosed with possible, 19 with probable and 2 with confirmed neurosarcoidosis were identified. Lesion overlap of neurosarcoidosis patients demonstrated a distribution of white matter lesions in all brain areas, with a periventricular predilection similar to multiple sclerosis. In contrast to multiple sclerosis controls, no propensity for lesions in proximity of the corpus callosum was observed. Neurosarcoidosis lesions appeared smaller and lesion volume was lower in the neurosarcoidosis cohort. The VLSM analysis showed minor associations between neurosarcoidosis and damaged voxels in the bilateral frontobasal cortex. Conclusions: The VLSM analysis yielded significant associations in the bilateral frontal cortex, suggesting that leptomeningeal inflammatory disease with following cortical involvement is a quite specific feature in neurosarcoidosis. Lesion load was lower in neurosarcoidosis than in multiple sclerosis. However, no specific pattern of subcortical white matter lesions in neurosarcoidosis was revealed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cerebral lesions; Neurosarcoidosis; Sarcoidosis; Voxel-based lesion symptom mapping

Cerebral lipogranuloma: A penetrating traumatic brain injury - Hagen, Manuel; Coras, Roland; Engelhorn, Tobias; Schwab, Stefan; Seifert, Frank (Neurology, 2020)
CRIS-Team Scopus Importer:2020-12-11

Cerebral Microinfarcts in Primary Open-Angle Glaucoma Correlated With DTI-Derived Integrity of Optic Radiation - Schoemann, Johannes; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; El-Rafei, Ahmed Mohamed Ibrahim; Michelson, Georg (Investigative Ophthalmology & Visual Science, 2014)
To evaluate the correlation between the extent of cerebral white matter lesions (WMLs) and the integrity of the visual pathway represented by fractional anisotropy (FA) in patients with primary open-angle glaucoma (POAG).This case-control study included a total of 61 German patients (39 POAG patients, 22 controls) matched for age and sex. Fractional anisotropy of the optic radiation was determined by 3-Tesla diffusion tensor imaging. White matter lesions and brain volumes were manually measured by using a T2-weighted, 3-D fluid-attenuated inversion recovery sequence.In POAG patients WML volumes were significantly (P = 0.04) increased in the subcortical area. This applied for both absolute and relative units to the specific patient's brain volume, compared to controls. The WML volumes were significantly (P = 0.003) greater in middle-aged (40-59 years) POAG patients than control patients. In controls there was a significant age correlation of WML volumes in the total brain, subcortical, and optic radiation regions of interest. There was a significant correlation between FA and WML in POAG regarding the total brain, the periventricular region, and the optic radiation in both hemispheres. In POAG, FA left and right optic radiation correlated significantly with age (P = 0.002).We were able to demonstrate that (1) POAG patients aged 40 to 60 years had higher volumes of cerebral microinfarcts and (2) POAG patients showed a significant correlation between cerebral microinfarcts and degeneration of the optic radiation. This indicates that cerebral microinfarcts might be an intracerebral risk factor for glaucomatous optic nerve atrophy.
EVALuna2:21212

Cerebral Networks Linked to Itch-related Sensations Induced by Histamine and Capsaicin - Vierow, Verena; Forster, Clemens; Vogelgsang, Rebekka; Dörfler, Arnd; Handwerker, Hermann Otto (Acta Dermato-Venereologica, 2015)
This functional magnetic resonance imaging (fMRI) study explored the central nervous processing of itch induced by histamine and capsaicin, delivered via inactivated cowhage spicules, and the influence of low-dose naltrexone. Scratch bouts were delivered at regular intervals after spicule insertion in order temporarily to suppress the itch. At the end of each trial the subjects rated their itch and scratch-related sensations. Stepwise multiple regression analyses were employed for identifying cerebral networks contributing to the intensities of "itching", "burning", "stinging", "pricking" and "itch relief by scratching". In the capsaicin experiments a network for "burning" was identified, which included the posterior insula, caudate and putamen. In the histamine experiments networks for "itching" and "itch relief" were found, which included operculum, hippocampus and amygdala. Naltrexone generally reduced fMRI activation and the correlations between fMRI signal and ratings. Furthermore, scratching was significantly less pleasant under naltrexone.
EVALuna2:2447

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Cerebrovascular complications of immunologically mediated heparin-induced thrombocytopenia - Macha, K.; Kloska, Stephan; Dörfler, Arnd; Raaz-Schrauder, D.; Schwab, Sibylle; Köhrmann, Martin; Seifert, Frank (Fortschritte der Neurologie - Psychiatrie, 2014)
Immunologically mediated heparin-induced thrombocytopenia (HIT) is a thrombotic disease caused by antibodies occurring after heparin exposure. Thrombocytopenia occurs within a few days after heparin exposure, about half of HIT-patients develop venous or arterial thrombotic complications. Neurological complications of HIT are mainly ischaemic stroke and sinus vein thrombosis. To ensure the primary clinical diagnosis functional and immunological assays for antibody detection are available. The probability for the occurrence of HIT depends on the nature of heparin employed (LMWH vs. UFH) and individual patient characteristics such as gender and primary disease (medical vs. surgical patients). In the case of suspected HIT heparin administration should be discontinued immediately and replaced by an alternative anticoagulation to prevent the expansion or development of further thrombotic complications. Herein we report a case of a patient suffering from HIT-associated embolic cerebral ischaemic stroke.
EVALuna2:22326

Change your Angle of View Sinusoidal C-Arm Movement in Cranial Flat-panel CT to Improve Image Quality - Lücking, Hannes; Hölter, Philip; Lang, Stefan; Schmidt, Manuel; Eisenhut, Felix; Dörfler, Arnd (Clinical Neuroradiology, 2022)
Background Artifacts from surrounding bony structures, especially from the petrous bones, regularly impair soft tissue computed tomography (CT) imaging of the middle and posterior fossa. This affects flat-panel CT in particular. Sinusoidal movement of the C-arm during acquisition (i.e. craniocaudal tilting along with semicircular rotation) is supposed to reduce artifacts, thus enhancing soft tissue imaging quality. Methods In the work-up of ischemic stroke or subarachnoid hemorrhage 40 patients underwent multi-slice CT (MS-CT) and either plain circular (cFP-CT; n = 20) or sinusoidal (sFP-CT; n = 20) flat-panel CT within a short interval. Two independent readers analyzed MS-CT and FP-CT datasets for recognizability of eight different brain structures and three typical types of artifacts according to a predetermined score. Results Interrater reliability was moderate for cFP-CT (kappa = 0.575) and good to very good for ratings of MS-CT and sFP-CT (kappa = 0.651 to kappa = 1). MS-CT was rated to be significantly better than cFP-CT and sFP-CT (p < 0.0001) in the overall score. Yet, sFP-CT was rated to be significantly superior to cFP-CT (overall p < 0.0001) regarding most anatomical regions and petrous bone artifacts. Conclusion Compared to a standard circular protocol, sinusoidal C-arm movement in cranial FP-CT can significantly reduce artifacts in the posterior fossa and, moreover, can improve visualization of most supratentorial and infratentorial anatomical structures.
CRIS-Team WoS Importer:2022-05-20

Chapter 6: Epidemiology S3-leitlinie extracranielle carotisstenose: kapitel 6: epidemiologie - Sander, D.; Diehm, C.; Eckstein, H. -H.; Kuehnl, A.; Berkefeld, J.; Diel, R.; Dörfler, Arnd; Kopp, I.; Langhoff, R.; Lawall, H.; Ringleb, P.; Storck, Martin (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 7: Symptoms and diagnosis of carotid stenosis S3-leitlinie extracranielle carotisstenose: kapitel 7: symptome und diagnostik von carotisstenosen - Ringleb, P.; Goertler, M.; Nabavi, D. G.; Arning, C.; Sander, D.; Eckstein, H. -H.; Kuehnl, A.; Berkefeld, J.; Diel, R.; Dörfler, Arnd; Kopp, I.; Langhoff, R.; et al. (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 8.13: Which materials (catheters, stents, protection systems) are to be preferred in CAS? S3-Leitlinie Extracranielle Carotisstenose: Kapitel 8.13: Welche Materialien (Katheter, Stents, Protektionssysteme) sind bei CAS zu bevorzugen? - Berkefeld, J.; Dörfler, Arnd (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 8.14: What is to be taken into account for an optimal peri-interventional management? S3-Leitlinie Extracranielle Carotisstenose: Kapitel 8.14: Was ist zu beachten für ein optimales periinterventionelles Management? - Berkefeld, J.; Dörfler, Arnd (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 8.15: How does the optimal management of peri-interventional complications look like? S3-Leitlinie Extracranielle Carotisstenose: Kapitel 8.15: Wie sieht das optimale Management periinterventioneller Komplikationen aus? - Berkefeld, J.; Dörfler, Arnd (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 8.19: Which requirements on further education and structural quality are to be imposed on institutions in which angiographies or operative/endovascular revascularizations of the carotid artery are conducted? S3-Leitlinie Extracranielle Carotisstenose: Kapitel 8.19: Welche Anforderungen an Weiterbildung und Strukturqualität ist an Einrichtungen zu stellen, in denen Angiographien oder operative/endovaskuläre Revaskularisationen der A. Carotis durchgeführt werden? - Storck, Martin; Berkefeld, J.; Dörfler, Arnd (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 8.20: Is there a connection among qualification, volume (individual, hospital) and outcome for the operative or endovascular treatment? S3-Leitlinie Extracranielle Carotisstenose: Kapitel 8.20: Gibt es einen Zusammenhang zwischen Qualifikation, Volume (individuell, Klinik) und Outcome für die operative oder endovaskuläre Therapie - Eckstein, H. -H.; Berkefeld, J.; Dörfler, Arnd (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 8.5: Is PTA alone compared with PTA with stent associated with varyingly high rates of success, complications and relapses in patients with high-grade extracranial carotid stenosis? S3-leitlinie extracranielle carotisstenose: Kapitel 8.5: Ist bei patienten mit einer hochgradigen extracraniellen carotisstenose die alleinige PTA im vergleich zur PTA mit stent mit unterschiedlich hohen erfolgs-, komplikations- und rezidivraten assoziiert? - Berkefeld, J.; Dörfler, Arnd (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Chapter 9: Aftercare, relapse treatment and quality of life S3-Leitlinie Extracranielle Carotisstenose: Kapitel 9: Nachsorge, Rezidivtherapie und Lebensqualität - Lawall, H.; Goertler, M.; Ringleb, P.; Sander, D.; Eckstein, H. -H.; Kuehnl, A.; Berkefeld, J.; Diel, R.; Dörfler, Arnd; Kopp, I.; Langhoff, R.; Storck, Martin (Gefässchirurgie, 2012)
CRIS-Team Scopus Importer:2022-08-05

Characteristics in Non-Vitamin K Antagonist Oral Anticoagulant-Related Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Hagen, Manuel; Knappe, Ruben U.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Stroke, 2019)
Background and Purpose Given inconclusive studies, it is debated whether clinical and imaging characteristics, as well as functional outcome, differ among patients with intracerebral hemorrhage (ICH) related to vitamin K antagonists (VKA) versus non-vitamin K antagonist (NOAC)-related ICH. Notably, clinical characteristics according to different NOAC agents and dosages are not established.
CRIS-Team WoS Importer:2019-06-18

Characterization of the murine orthotopic adamantinomatous craniopharyngioma PDX model by MRI in correlation with histology - Hoelsken, Annett; Schwarz, Marc; Gillmann, Clarissa; Pfister, Christina; Uder, Michael; Dörfler, Arnd; Buchfelder, Michael; Schlaffer, Sven-Martin; Fahlbusch, Rudolf; Buslei, Rolf; Bäuerle, Tobias (PLoS ONE, 2018)
PURPOSE: Adamantinomatous craniopharyngiomas (ACP) as benign sellar brain tumors are challenging to treat. In order to develop robust in vivo drug testing methodology, the murine orthotopic craniopharyngioma model (PDX) was characterized by magnetic resonance imaging (MRI) and histology in xenografts from three patients (ACP1-3). METHODS: In ACP PDX, multiparametric MRI was conducted to assess morphologic characteristics such as contrast-enhancing tumor volume (CETV) as well as functional parameters from dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) including area-under-the-curve (AUC), peak enhancement (PE), time-to-peak (TTP) and apparent diffusion coefficient (ADC). These MRI parameters evaluated in 27 ACP PDX were correlated to histological features and percentage of vital tumor cell content. RESULTS: Qualitative analysis of MRI and histology from PDX revealed a similar phenotype as seen in patients, although the MRI appearance in mice resulted in a more solid tumor growth than in humans. CETV were significantly higher in ACP2 xenografts relative to ACP1 and ACP3 which correspond to respective average vitality of 41%, <10% and 26% determined histologically. Importantly, CETV prove tumor growth of ACP2 PDX as it significantly increases in longitudinal follow-up of 110 days. Furthermore, xenografts from ACP2 revealed a significantly higher AUC, PE and TTP in comparison to ACP3, and significantly increased ADC relative to ACP1 and ACP3 respectively. Overall, DCE-MRI and DWI can be used to distinguish vital from non-vital grafts, when using a cut off value of 15% for vital tumor cell content. CONCLUSIONS: MRI enables the assessment of craniopharyngioma PDX vitality in vivo as validated histologically.
EVALuna2:34588

Chronic Kidney Disease and Clinical Outcomes in Patients with Intracerebral Hemorrhage - Beuscher, Vanessa D.; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Madzar, Dominik; Reindl, Caroline; Lücking, Hannes; Lang, Stefan; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2020)
Background and Purpose: The influence of chronic kidney disease (CKD) on functional outcome in intracerebral hemorrhage (ICH) is scarcely investigated and reported findings are conflicting mostly because of nonaccounting for imbalances. Aim of the present study was to determine the impact of CKD on functional long-term outcome in ICH-patients. Methods: In this observational cohort study of spontaneous ICH-patients admitted to our Department of Neurology between 2006 and 2015 we investigated retrospectively as primary outcome the dichotomized functional status (modified-Rankin-Scale = 0-3-versus-4-6) at 12 months according to renal function (CKD versus non-CKD), including categorial estimates of the glomerular filtration rate subanalyses. Confounding was addressed by propensity-score(ps)-matching and adjusted multivariable regression analyses. Results: We identified 1076 eligible ICH-patients, of which 131 (12.2%) suffered from CKD on hospital admission. Confounders associated with CKD consisted of hypertension (P = .023), Diabetes mellitus (P = .001), prior ischemic stroke and/or transitory ischemic attack (TIA) (P = .021), congestive heart failure (P < .01), impaired liver function (P < .01), antiplatelet therapy (P = .01), poorer premorbid functional status (P < .01), and deep ICH-location (P = .006). After balancing for confounding, patients with CKD showed a significantly decreased rate of favorable functional outcome at 12 months (CKD:29 of 111(26.1%)-versus-non-CKD:78 of 206 (37.9%); P = .035). Subanalyses showed that stages of CKD were evenly associated with mortality at 12 months (GFR category G3a, OR:2.811; CI (1.130-6.994); P = .026; GFR category G3b, OR:1.874; CI (.694-5.058); P = .215; GFR category G4, OR:10.316; CI (1.976-53.856); P = .006; GFR category G5, OR:8.989; CI (1.900-42.518); P = .006). Conclusions: As compared to ICH-patients without CKD, those with CKD show increased rates of mortality and worse functional outcomes even after statistical correction for imbalanced baseline characteritsics. This finding is presumably linked to comorbidity and warrants further investigation in prospective studies.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Chronic kidney disease; critical care; intracerebral hemorrhage; mortality; outcome

Classification-based summation of cerebral digital subtraction angiography series for image post-processing algorithms - Schuldhaus, Dominik; Spiegel, Martin; Redel, T.; Polyanskaya, Maria; Struffert, Tobias; Hornegger, Joachim; Dörfler, Arnd (Physics in Medicine and Biology, 2011)
X-ray-based 2D digital subtraction angiography (DSA) plays a major role in the diagnosis, treatment planning and assessment of cerebrovascular disease, i.e. aneurysms, arteriovenous malformations and intracranial stenosis. DSA information is increasingly used for secondary image post-processing such as vessel segmentation, registration and comparison to hemodynamic calculation using computational fluid dynamics. Depending on the amount of injected contrast agent and the duration of injection, these DSA series may not exhibit one single DSA image showing the entire vessel tree. The interesting information for these algorithms, however, is usually depicted within a few images. If these images would be combined into one image the complexity of segmentation or registration methods using DSA series would drastically decrease. In this paper, we propose a novel method automatically splitting a DSA series into three parts, i.e. mask, arterial and parenchymal phase, to provide one final image showing all important vessels with less noise and moving artifacts. This final image covers all arterial phase images, either by image summation or by taking the minimum intensities. The phase classification is done by a two-step approach. The mask/arterial phase border is determined by a Perceptron-based method trained from a set of DSA series. The arterial/parenchymal phase border is specified by a threshold-based method. The evaluation of the proposed method is two-sided: (1) comparison between automatic and medical expert-based phase selection and (2) the quality of the final image is measured by gradient magnitudes inside the vessels and signal-to-noise (SNR) outside. Experimental results show a match between expert and automatic phase separation of 93%/50% and an average SNR increase of up to 182% compared to summing up the entire series. © 2011 Institute of Physics and Engineering in Medicine.

Classification of neurovascular compression in glossopharyngeal neuralgia: Three-dimensional visualization of the glossopharyngeal nerve - Tanrikulu, Levent; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Surgical Neurology International, 2015)
Background: We introduce a method of noninvasive topographical analysis of the neurovascular relationships of the glossopharyngeal nerve (CN IX) by three-dimensional (3D) visualization. Patients with glossopharyngeal neuralgia (GN) resulting from neurovascular compression (NVC) were studied. Methods: 15 patients with GN were prospectively examined with 3D visualization using high-resolution magnetic resonance imaging with constructive interference in steady state (MR-CISS). The datasets were segmented and visualized with the real, individual neurovascular relationships by direct volume rendering. Segmentation and 3D visualization of the CN IX and corresponding blood vessels were performed. The 3D visualizations were interactively compared with the intraoperative setup during microvascular decompression (MVD) in order to verify the results by the observed surgical-anatomical findings. Results: 15 patients (female/male: 5/10) were examined. All of them underwent MVD (100%). Microvascular details were documented. The posterior inferior cerebellar artery (PICA) was the most common causative vessel in 12 of 15 patients (80%), the vertebral artery (VA) alone in one case (6.7%), and the combination of compression by the VA and PICA in 3 patients (13.3%). We identified three distinct types of NVC within the root entry zone of CN IX. Conclusion: 3D visualization by direct volume rendering of MR-CISS data offers the opportunity of noninvasive exploration and anatomical categorization of the CN IX. It proves to be advantageous in supporting to establish the diagnosis and microneurosurgical interventions by representing original, individual patient data in a 3D fashion. It provides an excellent global individual view over the entire neurovascular relationships of the brainstem and corresponding nerves in each case.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Classification; glossopharyngeal nerve; glossopharyngeal neuralgia; image processing; neurovascular compression

Classification of primary cerebral lymphoma and glioblastoma featuring dynamic susceptibility contrast and apparent diffusion coefficient - Eisenhut, Felix; Schmidt, Manuel; Putz, Florian; Lettmaier, Sebastian; Fröhlich, Kilian; Arinrad, Soheil; Coras, Roland; Lücking, Hannes; Lang, Stefan; Fietkau, Rainer; Dörfler, Arnd (Brain Sciences, 2020)
This study aimed to differentiate primary central nervous system lymphoma (PCNSL) and glioblastoma (GBM) via multimodal MRI featuring radiomic analysis. MRI data sets of patients with histological proven PCNSL and GBM were analyzed retrospectively. Diffusion-weighted imaging (DWI) and dynamic susceptibility contrast (DSC) perfusion imaging were evaluated to differentiate contrast enhancing intracerebral lesions. Selective (contrast enhanced tumor area with the highest mean cerebral blood volume (CBV) value) and unselective (contouring whole contrast enhanced lesion) Apparent diffusion coefficient (ADC) measurement was performed. By multivariate logistic regression, a multiparametric model was compiled and tested for its diagnostic strength. A total of 74 patients were included in our study. Selective and unselective mean and maximum ADC values, mean and maximum CBV and ratioCBV as quotient of tumor CBV and CBV in contralateral healthy white matter were significantly larger in patients with GBM than PCNSL; minimum CBV was significantly lower in GBM than in PCNSL. The highest AUC for discrimination of PCNSL and GBM was obtained for selective mean and maximum ADC, mean and maximum CBV and ratioCBV. By integrating these five in a multiparametric model 100% of the patients were classified correctly. The combination of perfusion imaging (CBV) and tumor hot-spot selective ADC measurement yields reliable radiological discrimination of PCNSL from GBM with highest accuracy and is readily available in clinical routine.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ADC; DSC; Glioblastoma; MRI; Multimodal; Primary central nervous system lymphoma

Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clinical Comparison of FD-CT and MS-CT in Aneurysmal Subarachnoid Haemorrhage: A Single Center Experience - Eisenhut, Felix; Heidelbach, Cornelius; Heynold, Elisabeth; Manhart, Michael; Struffert, Tobias; Brandner, Sebastian; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Single-center comparison of postinterventional multislice computed tomography (MS-CT) and flat-detector computed tomography (FD-CT) in patients with subarachnoid haemorrhage (SAH) and endovascularly treated cerebral aneurysms with a focus on detection of posttherapeutical complications. Patients with endovascularly treated aneurysmal SAH undergoing both MS-CT and FD-CT within 24 h after intervention were included. Datasets were compared regarding image quality (IQ) as well as qualitative (detection of SAH, intracerebral haemorrhage [ICH], intraventricular haemorrhage [IVH], external ventricular drain [EVD] position, acute obstructive hydrocephalus [AOH]) and quantitative (cella media distance [CMD], modified Graeb score [GS]) parameters. 410 patients with endovascularly treated aneurysmal SAH were included. IQ was equal between MS-CT and FD-CT. FD-CT allowed equal detection of SAH and ICH in comparison to MS-CT. FD-CT allowed excellent detection of IVH and delineation of EVD position with strong agreement to MS-CT findings. FD-CT allowed equal detection of AOH in comparison to MS-CT. There was no significant difference of CMD and GS between FD-CT and MS-CT. Postinterventional FD-CT yields equivalent diagnostic value in patients with endovascular treated SAH as MS-CT. Enabling reliable detection of SAH-associated complications within the angiosuite, FD-CT might be an efficient and safe imaging modality in these clinical emergencies.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cerebral aneurysm; endovascular treatment; flat-detector computed tomography; multislice computed tomography; subarachnoid haemorrhage

Clinical Evaluation of an Innovative Metal-Artifact-Reduction Algorithm in FD-CT Angiography in Cerebral Aneurysms Treated by Endovascular Coiling or Surgical Clipping - Eisenhut, Felix; Schmidt, Manuel; Kalik, Alexander; Struffert, Tobias; Feulner, Julian; Schlaffer, Sven-Martin; Manhart, Michael; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Treated cerebral aneurysms (IA) require follow-up imaging to ensure occlusion. Metal artifacts complicate radiologic assessment. Our aim was to evaluate an innovative metal-artifact-reduction (iMAR) algorithm for flat-detector computed tomography angiography (FD-CTA) regarding image quality (IQ) and detection of aneurysm residua/reperfusion in comparison to 2D digital subtraction angiography (DSA). Patients with IAs treated by endovascular coiling or clipping underwent both FD-CTA and DSA. FD-CTA datasets were postprocessed with/without iMAR algorithm (MAR+/MAR−). Evaluation of all FD-CTA and DSA datasets regarding qualitative (IQ, MAR) and quantitative (coil package diameter/CPD) parameters was performed. Aneurysm occlusion was assessed for each dataset and compared to DSA findings. In total, 40 IAs were analyzed (ncoiling = 24; nclipping = 16). All iMAR+ datasets demonstrated significantly better IQ (pIQ coiling < 0.0001; pIQ clipping < 0.0001). iMAR significantly reduced the metal-artifact burden but did not affect the CPD. iMAR significantly improved the detection of aneurysm residua/reperfusion with excellent agreement with DSA (naneurysm detection MAR+/MAR−/DSA = 22/1/26). The iMAR algorithm significantly improves IQ by effective reduction of metal artifacts in FD-CTA datasets. The proposed algorithm enables reliable detection of aneurysm residua/reperfusion with good agreement to DSA. Thus, iMAR can help to reduce the need for invasive follow-up in treated IAs.
CRIS-Team Scopus Importer:2022-05-27
Keywords: cerebral aneurysm; endovascular coiling; flat-detector computed tomography angiography; metal-artifact-reduction algorithm; surgical clipping

Clinical evaluation of semi-automatic landmark-based lesion tracking software for CT-scans - Dankerl, Peter; Dietzel, Matthias; Tsymbal, Alexey; Kramer, Martin; Seifert, Sascha; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Cancer Imaging, 2014)
To evaluate a semi-automatic landmark-based lesion tracking software enabling navigation between RECIST lesions in baseline and follow-up CT-scans.The software automatically detects 44 stable anatomical landmarks in each thoraco/abdominal/pelvic CT-scan, sets up a patient specific coordinate-system and cross-links the coordinate-systems of consecutive CT-scans. Accuracy of the software was evaluated on 96 RECIST lesions (target- and non-target lesions) in baseline and follow-up CT-scans of 32 oncologic patients (64 CT-scans). Patients had to present at least one thoracic, one abdominal and one pelvic RECIST lesion. Three radiologists determined the deviation between lesions' centre and the software's navigation result in consensus.The initial mean runtime of the system to synchronize baseline and follow-up examinations was 19.4 ± 1.2 seconds, with subsequent navigation to corresponding RECIST lesions facilitating in real-time. Mean vector length of the deviations between lesions' centre and the semi-automatic navigation result was 10.2 ± 5.1 mm without a substantial systematic error in any direction. Mean deviation in the cranio-caudal dimension was 5.4 ± 4.0 mm, in the lateral dimension 5.2 ± 3.9 mm and in the ventro-dorsal dimension 5.3 ± 4.0 mm.The investigated software accurately and reliably navigates between lesions in consecutive CT-scans in real-time, potentially accelerating and facilitating cancer staging.
EVALuna2:14438

Clinically compatible subject-specific dynamic parallel transmit pulse design for homogeneous fat saturation and water-excitation at 141657T: Proof-of-concept for 14165CEST MRI of the brain - Levy, Simon; Herrler, Jürgen; Liebert, Andrzej; Tkotz, Katharina; Fabian, Moritz; Eisen, Christian; Grodzki, David; Uder, Michael; Dörfler, Arnd; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the benefits and challenges of dynamic parallel transmit (pTx) pulses for fat saturation (FS) and water-excitation (WE), in the context of CEST MRI. Methods "Universal" k(T)-points (for FS) and spiral non-selective (for WE) trajectories were optimized offline for flip angle (FA) homogeneity. Routines to optimize the pulse shape online, based on the subject's fields maps, were implemented (target FA of 110 degrees/0 degrees for FS, 0 degrees/5 degrees for WE at fat/water frequencies). The pulses were inserted in a CEST sequence with a pTx readout. The different fat suppression schemes and their effects on CEST contrasts were compared in 12 volunteers at 7T. Results With a 25%-shorter pulse duration, pTx FS largely improved the FA homogeneity (root-mean-square-error (RMSE) = 12.3 degrees vs. 53.4 degrees with circularly-polarized mode, at the fat frequency). However, the spectral selectivity was degraded mainly in the cerebellum and close to the sinuses (RMSE = 5.8 degrees vs. 0.2 degrees at the water frequency). Similarly, pTx WE showed a trade-off between FA homogeneity and spectral selectivity compared to pTx non-selective pulses (RMSE = 0.9 degrees and 1.1 degrees at the fat and water frequencies, vs. 4.6 degrees and 0.5 degrees). In the brain, CEST metrics were reduced by up to 31.9% at -3.3 ppm with pTx FS, suggesting a mitigated lipid-induced bias. Conclusion This clinically compatible implementation of dynamic pTx pulses improved the fat suppression homogeneity at 7T taking into account the subject-specific B-0 heterogeneities online. This study highlights the lipid-induced biases on the CEST z-spectrum. The results are promising for body applications where B-0 heterogeneities and fat are more substantial.
CRIS-Team WoS Importer:2022-09-30

Clinically significant CMV (re)activation during or after radiotherapy/chemotherapy of the brain : Correlation with neurological deterioration and improvement upon antiviral treatment - Goerig, Nicole; Semrau, S.; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Dörfler, Arnd; Putz, Florian; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
For both patients with high-grade gliomas and multiple cerebral metastases, radio(chemo)therapy is the standard therapy. Neurological decline during treatment is rarely attributed to infections of the brain but to tumor progression or side effects of radiotherapy.We present 4 cases of cytomegalovirus (CMV) viremia associated with neurological deterioration, which occurred during or shortly after radiotherapy and/or chemotherapy of the brain (brain metastases 2, high-grade glioma 1, carcinoma infiltrating brain 1). In all cases, neurological decline was sudden and unexpected, and causes such as increased intracranial pressure or tumor progression could be excluded radiologically. Treatment with dexamethasone and mannitol had no or only very short-term effects. General infections were either excluded or receding before the neurological symptoms occurred. All patients presented with decreasing levels of thrombocytes. In all cases, CMV (re)activation could be proven using blood test for CMV-DNA. The anti-CMV-IgG status suggested reactivation rather than a primary infection. One patient died within 72 h of onset of the symptoms (results of CMV tests were received postmortem). Diagnosis of 3 patients allowed successful administration of antiviral treatment, which greatly improved the general and neurological conditions of the patients within 48 h.Neurological deterioration during RT is hardly ever attributed to viral infections. These cases suggest that CMV reactivation and subsequent infection might actually be causative and has to be considered and treated.Further prospective studies verifying and investigating this observation in terms of frequency and clinical relevance seem indicated.
EVALuna2:8302

Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
Contradictory results were reported for the outcome after endovascular recanalization (ERT) in acute anterior circulation ischemic stroke. We assessed whether a clinical/perfusion CT cerebral blood volume (CBV) mismatch concept (CPM) can identify patients who will benefit from reperfusion therapy.Imaging and clinical data of 58 consecutive ERT cases with acute anterior circulation stroke (ICA, M1, proximal M2) undergoing intraarterial thrombectomy within 4.5h after symptom onset were analyzed retrospectively. CPM was defined as NIHSS>=8 and PCT CBV ASPECTS>=7. Minor CBV lesion was defined as PCT CBV ASPECTS>=7.All baseline characteristics other than blood glucose did not differ between the paired groups. Revascularization was achieved in 87.9% of all patients without significant difference between the paired groups. Favorable clinical outcome after 3 months (mRS<=2) resulted in 29.3% of all patients, in contrast to 47.4% of the CPM positive and 52.2% of the minor CBV lesion groups.CPM can identify patients who will benefit from reperfusion therapy in acute anterior circulation ischemic stroke.
EVALuna2:14386

Clinical/scientific notes - Möller, Sebastian; Hilz, Max-Josef; Blinzler, C.; Köhn, Julia; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (Neurology, 2012)
CRIS-Team Scopus Importer:2022-08-05

CLIPPERS with longitudinally extensive transverse myelitis: Role of T versus B cells - Olmes, David G.; Metz, Imke; Lee, De-Hyung; Rosenwald, Andreas; Dörfler, Arnd; Brueck, Wolfgang; Linker, Ralf (Journal of the Neurological Sciences, 2018)
EVALuna2:35521

Clot Burden and Collaterals in Anterior Circulation Stroke: Differences Between Single-Phase CTA and Multi-phase 4D-CTA - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Siegfried; Dörfler, Arnd (Clinical Neuroradiology, 2014)
It has been reported that the extent of intravascular thrombi and the quality of collateral filling in computed tomography (CT) angiography are predictive for the clinical outcome in patients with acute stroke. We hypothesized that multi-phase four-dimensional CTA (4D-CTA) allows better assessment of clot burden and collateral flow compared with arterial single-phase CTA (CTA).In 49 patients (33 female; age: 77 ± 12 years) with acute anterior circulation stroke, CTA and 4D-CTA reconstructed from dynamic perfusion CT data were analyzed for absolute thrombus length (TL), clot burden score (CBS), and collateral score (CS). The length of the filling defect was also defined on thin-slice nonenhanced CT as corresponding hyperdense middle cerebral artery sign (HMCAS) when present.There was good correlation (r = 0.62, p < 0.01) between the length of HMCAS (1.29 ± 0.62 cm) and TL in 4D-CTA (1.22 ± 0.51 cm). 4D-CTA and CTA significantly varied (p < 0.01) in TL (1.42 ± 0.73 cm (CTA) versus 1.11 ± 0.62 cm (4D-CTA)), CBS (median: 5, interquartile range: 4-7 (CTA) versus median: 6, interquartile range: 5-8 (4D-CTA); p < 0.001), and CS (median: 2, interquartile range: 1-2 (CTA) versus median: 3, interquartile range: 2-3 (4D-CTA); p < 0.001). Accordingly, CTA significantly overrated clot burden and underestimated collateral flow.4D-CTA more closely defines clot burden and collateral supply in anterior circulation stroke than CTA, implicating an additional diagnostic benefit.
EVALuna2:22276

Cluster Analysis of Glaucoma Patients Using the Retinal Nerve Fiber Layer Thickness of the Optic Nerve and DTI Parameters of the Optic Radiation - Michelson, Georg; Wärntges, Simone; Engelhorn, Tobias; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Clinical and Experimental Ophthalmology, 2011)

c-MRI findings after crystal meth abuse - Möbius, Cornelia; Kustermann, Andreas; Struffert, Tobias; Kornhuber, Johannes; Mueller, Helge H. (Journal of Addiction Medicine, 2014)
We describe a case of intoxication with N-methylamphetamine (Crystal-METH) after withdrawal. Crystal-METH abuse was associated with persisting neurological symptoms and impressive structural white matter alterations. Magnetic resonance imaging should be recommended to document the possible extensive changes in amphetamine abuse, which increases dramatically.
EVALuna2:22312

Comparative analysis of titanium clip prostheses for partial ossiculoplasty - Mantsopoulos, Konstantinos; Thimsen, Vivian; Taha, Lava; Eisenhut, Felix; Müller-Hübner, Sarina; Sievert, Matti; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
Objectives: The aim of our study was to perform a comparative analysis in our cases with titanium partial clip ossiculoplasty in terms of audiometric outcome and extrusion rates as well as to review the literature for relevant information on this surgical issue. Materials and methods: The records of all patients who had undergone primary partial ossiculoplasty with the implantation of a CliP® Partial Prosthesis Dresden Type (CPPDT, group A) or a CliP Partial FlexiBAL® (CPF, Group B, both Heinz Kurz GmbH, Dusslingen, Germany) between 2012 and 2020 were studied retrospectively. Results: 274 patients made up our study sample (148 men, 126 women, male to female ratio: 1.17). Their mean age at the time of first surgery was 39.6 years (range: 4–79 years). The mean preoperative air-bone gap (ABG) was 22.7dΒ ± 10.5 dB. Mean follow-up was approximately 4 months (1–12 months). The mean postoperative ABG was 15.7 ± 8.1 dB. In total, the postoperative ABG was significantly improved compared to preoperative values (P < 0.001). Surgical success, defined as an ABG ≤ 20 dB, was achieved in the majority of our study patients (210/274, 76.6%). Extrusion of the prosthesis was detected in 3/216 CPF and 5/58 CPPDT cases (p = 0.012). Comparison of both prosthesis groups revealed a significantly better audiological outcome for the patients with ossicular reconstruction using CPF. A significantly better audiological outcome was detected in the cases with a normal aeration of the middle ear. Discussion: Titanium clip partial ossiculoplasty is a reliable component of modern tympanoplasty, allowing a satisfying audiologic outcome. The higher adaptability of the CPF to the changing postoperative circumstances and the frequently defective aeration of the middle ear is reflected in the better audiologic outcome for this prosthesis.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Air-bone gap; Middle ear; Ossiculoplasty; Outcome; Partial prosthesis; PORP

Comparative fMRI and MEG localization of cortical sensorimotor function: Bimodal mapping supports motor area reorganization in glioma patients - Zimmermann, Max; Roessler, Karl; Kaltenhaeuser, Martin; Grummich, Peter; Brandner, Nadja; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (PLoS ONE, 2019)
Introduction
CRIS-Team WoS Importer:2019-03-26

Comparing 1.5 T and 3.0 T MR data for 3D visualization of neurovascular relationships in the posterior fossa - Hastreiter, Peter; Maliachova, Olga; Fahlbusch, Rudolf; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Acta Neurochirurgica, 2023)
Background: Neurovascular relationships in the posterior fossa are more frequently investigated due to the increasing availability of 3.0 Tesla MRI. For an assessment with 3D visualization, no systematic analyzes are available so far and the question arises as to whether 3.0 Tesla MRI should be given preference over 1.5 Tesla MRI. Methods: In a prospective study, a series of 25 patients each underwent MRI investigations with 3D-CISS and 3D-TOF at 1.5 and 3.0 Tesla. For both field strengths separately, blood vessel information from the TOF data was fused into the CISS data after segmentation and registration. Four visualizations were created for each field strength, with and without optimization before and after fusion, which were evaluated with a rating system and verified with the intraoperative situation. Results: When only CISS data was used, nerves and vessels were better visualized at 1.5 Tesla. After fusion, flow and pulsation artifacts were reduced in both cases, missing vessel sections were supplemented at 3.0 Tesla and 3D visualization at 1.5 and 3.0 Tesla led to anatomically comparable results. By subsequent manual correction, the remaining artifacts were further eliminated, with the 3D visualization being significantly better at 3.0 Tesla, since the higher field strength led to sharper contours of small vessel and nerve structures. Conclusion: 3D visualizations at 1.5 Tesla are sufficiently detailed for planning microvascular decompression and can be used without restriction. Fusion further improves the quality of 3D visualization at 3.0 Tesla and enables an even more accurate delineation of cranial nerves and vessels.
CRIS-Team Scopus Importer:2023-12-29
Keywords: 1.5 and 3.0 Tesla; 3D Visualization; Compression syndromes; Data fusion; Neurovascular relationships; Posterior fossa

Comparing the effects of isocaloric oral and i.v. application of nutrient solutions on olfactory functioning - Bachlechner, Stephan; Denzer-Lippmann, M.; Wielopolski, Jan; Fische, Mr; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Georg; Kornhuber, Johannes; Thürauf, Norbert (2016)
EVALuna2:33154

Comparison of conventional CTA and volume perfusion CTA in evaluation of cerebral arterial vasculature in acute stroke - Saake, Marc; Gölitz, Philipp; Struffert, Tobias; Breuer, Lorenz; Volbers, Bastian; Dörfler, Arnd; Kloska, Stephan (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: CTA-like datasets can be reconstructed from whole-brain VPCTA. The aim of our study was to compare VPCTA with CTA for detection of intracranial stenosis and occlusion in stroke patients. Omitting CTA from stroke CT could reduce radiation dose. MATERIALS AND METHODS: One hundred sixty-three patients were included in this retrospective analysis. Inclusion criterion was suspected stroke within 4.5 hours after onset of symptoms. All examinations were performed on a 128-section multidetector CT scanner. Axial, coronal, and sagittal maximum intensity projections were reconstructed from CTA and from peak arterial phase of VPCTA. Images were scored for quality and presence of intracranial stenosis >50% or occlusion. For statistical analysis, the Wilcoxon signed-rank test and Fisher exact test were used, with a 2-tailed P value of .05 or less for statistical significance. RESULTS: Average image quality was superior in CTA (P < .05). However, image quality dichotomized for diagnostic significance was without difference between CTA and VPCTA (P > .05). Comparative statistical analysis revealed no significant difference for detection of intracranial stenosis and occlusion between CTA and VPCTA (P > .05). Substitution of intracranial CTA by VPCTA would lower radiation dose by 0.5 mSv. CONCLUSIONS: VPCTA is suited to assess the intracranial vasculature in patients with stroke and might have the potential to decrease radiation dose by substituting for intracranial CTA in stroke CT. Additional studies are necessary to further evaluate potential benefits of the dynamic nature of VPCTA.
CRIS-Team Scopus Importer:2022-08-05

Comparison of Diagnostic Performance and Image Quality between Topup-Corrected and Standard Readout-Segmented Echo-Planar Diffusion-Weighted Imaging for Cholesteatoma Diagnostics - Wiesmüller, Marco; Wüst, Wolfgang; Mennecke, Angelika; May, Matthias; Heiß, Rafael; Führes, Tobit; Janka, Rolf Matthias; Uder, Michael; Dörfler, Arnd; Laun, Frederik Bernd (Diagnostics, 2023)
This study compares the diagnostic performance and image quality of single-shot turbo spin-echo DWI (tseDWI), standard readout-segmented DWI (rsDWI), and a modified rsDWI version (topupDWI) for cholesteatoma diagnostics. Thirty-four patients with newly suspected unilateral cholesteatoma were examined on a 1.5 Tesla MRI scanner. Diagnostic performance was evaluated by calculating and comparing the sensitivity and specificity using histopathological results as the standard of reference. Image quality was independently reviewed by two readers using a 5-point Likert scale evaluating image distortions, susceptibility artifacts, image resolution, lesion conspicuity, and diagnostic confidence. Twenty-five cholesteatomas were histologically confirmed after surgery and originated in the study group. TseDWI showed the highest sensitivity with 96% (95% confidence interval (CI): 88–100%), followed by topupDWI with 92% (95% CI: 81–100%) for both readers. The sensitivity for rsDWI was 76% (95% CI: 59–93%) for reader 1 and 84% (95% CI: 70–98%) for reader 2, respectively. Both tseDWI and topupDWI revealed a specificity of 100% (95% CI: 66–100%) and rsDWI of 89% (95% CI: 52–100%). Both tseDWI and topupDWI showed fewer image distortions and susceptibility artifacts compared to rsDWI. Image resolution was consistently rated best for topupDWI, followed by rsDWI, which both outperformed tseDWI. TopupDWI and tseDWI showed comparable results for lesions’ conspicuity and diagnostic confidence, both outperforming rsDWI. Modified readout-segmented DWI using the topup-correction method is preferable to standard rsDWI and may be regarded as an accurate alternative to single-shot turbo spin-echo DWI in cholesteatoma diagnostics.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cholesteatoma; diffusion-weighted imaging; DWI; echo-planar imaging; EPI; readout-segmented; reduced susceptibility-induced distortions; topup correction; TSE; turbo spin-echo

Comparison of Intracranial Aneurysms Treated by 2-D Versus 3-D Coils: A Matched-Pairs Analysis - Lang, Stefan; Rösch, Julie; Gölitz, Philipp; Kloska, Stephan; Struffert, Tobias; Dörfler, Arnd (Clinical Neuroradiology, 2017)
OBJECTIVE: Knowledge on the influence of 2D and 3D coils to occlude intracranial aneurysms is poor. Therefore, aim of our analysis was to evaluate whether the use of 3-D versus 2-D coils alone may improve the efficacy of endovascular aneurysm treatment. PATIENTS AND METHODS: We performed a matched pair analysis comparing aneurysms treated by 3-D coils as initial "framing" coils to aneurysms treated exclusively by 2-D coils. Number of coils, implanted coil length/volume, and associated packing density were calculated. Aneurysmal occlusion was assessed and monitored 6 months (DSA; magnetic resonance angiography (MRA)) and 18 months (MRA) after embolization. Periprocedural complications and retreatment rate of each group were analyzed. RESULTS: Our retrospective analysis revealed 50 pairs. Concerning the 3-D group, number of coils (353 in total, median 7; p = 0.002), implanted coil length (55.69 ± 48.4 cm), implanted coil length per volume (5.92 mm/mm3), and packing density (30 %; p = 0.017) was higher than in the 2-D group (259 in total, median 5 coils; 38.52 ± 43.13 cm; 4.54 mm/mm3; 23 %). Occlusion was not significantly different immediately after treatment but at 6 and 18 months follow-up in favor of 3-D coils. Retreatment was performed in 2 cases of the 3-D group and in 3 cases of the 2-D group and therefore in a similar range (p = 0.564). CONCLUSION: Initial use of 3-D coils revealed a higher packing density and a higher long-term occlusion. Therefore, we recommend initial use of 3-D coils.
EVALuna2:33475

Comparison of optimized intensity correction methods for 23Na MRI of the human brain using a 32-channel phased array coil at 7 Tesla - Lachner, Sebastian; Ruck, Laurent; Niesporek, Sebastian C.; Utzschneider, Matthias; Lott, Johanna; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Zeitschrift für Medizinische Physik, 2019)
Purpose: To correct for the non-homogeneous receive profile of a phased array head coil in sodium magnetic resonance imaging (23Na MRI). Methods: 23Na MRI of the human brain (n = 8) was conducted on a 7T MR system using a dual-tuned quadrature 1H/23Na transmit/receive birdcage coil, equipped with a 32-channel receive-only array. To correct the inhomogeneous receive profile four different methods were applied: (1) the uncorrected phased array image and an additionally acquired birdcage image as reference image were low-pass filtered and divided by each other. (2) The second method substituted the reference image by a support region. (3) By averaging the individually calculated receive profiles, a universal sensitivity map was obtained and applied. (4) The receive profile was determined by a pre-scanned large uniform phantom. The calculation of the sensitivity maps was optimized in a simulation study using the normalized root-mean-square error (NRMSE). All methods were evaluated in phantom measurements and finally applied to in vivo 23Na MRI data sets. The in vivo measurements were partial volume corrected and for further evaluation the signal ratio between the outer and inner cerebrospinal fluid compartments (CSFout:CSFin) was calculated. Results: Phantom measurements show the correction of the intensity profile applying the given methods. Compared to the uncorrected phased array image (NRMSE = 0.46, CSFout:CSFin = 1.71), the quantitative evaluation of simulated and measured intensity corrected human brain data sets indicates the best performance utilizing the birdcage image (NRMSE = 0.39, CSFout:CSFin = 1.00). However, employing a support region (NRMSE = 0.40, CSFout:CSFin = 1.17), a universal sensitivity map (NRMSE = 0.41, CSFout:CSFin = 1.05) or a pre-scanned sensitivity map (NRMSE = 0.42, CSFout:CSFin = 1.07) shows only slightly worse results. Conclusion: Acquiring a birdcage image as reference image to correct for the receive profile demonstrates the best performance. However, when aiming to reduce acquisition time or for measurements without existing birdcage coil, methods that use a support region as reference image, a universal or a pre-scanned sensitivity map provide good alternatives for correction of the receive profile.
CRIS-Team Scopus Importer:2019-12-31
Keywords: 7 Tesla; Intensity correction; Multi-channel array coil; Phased array coil; Receive profile; Sodium MRI

Comparison of ped and fred flow diverters for posterior circulation aneurysms: a propensity score matched cohort study - Griessenauer, Christoph J.; Enriquez-Marulanda, Alejandro; Xiang, Sissi; Hong, Tao; Zhang, Hongqi; Taussky, Philipp; Grandhi, Ramesh; Waqas, Muhammad; Tutino, Vincent M.; Siddiqui, Adnan H.; Levy, Elad I.; Ogilvy, Christopher S.; et al. (Journal of Neurointerventional Surgery, 2020)
Background: Flow diversion is a common endovascular treatment for cerebral aneurysms, but studies comparing different types of flow diverters are scarce. Objective: To perform a propensity score matched cohort study comparing the Pipeline Embolization Device (PED) and Flow Redirection Intraluminal Device (FRED) for posterior circulation aneurysms. Methods: Consecutive aneurysms of the posterior circulation treated at 25 neurovascular centers with either PED or FRED were collected. Propensity score matching was used to control for age, duration of follow-up imaging, adjunctive coiling, and aneurysm location, size, and morphology; previously ruptured aneurysms were excluded. The two devices were compared for the following outcomes: procedural complications, aneurysm occlusion, and functional outcome. Results: A total of 375 aneurysms of the posterior circulation were treated in 369 patients. The PED was used in 285 (77.2%) and FRED in 84 (22.8%) procedures. Aneurysms treated with the PED were more commonly fusiform and larger than those treated with FRED. To account for these important differences, propensity score matching was performed resulting in 33 PED and FRED unruptured aneurysm pairs. No differences were found in occlusion status and neurologic thromboembolic or hemorrhagic complications between the two devices. The proportion of patients with favorable functional outcome was higher with FRED (100% vs 87.9%, p=0.04). Conclusion: Comparative analysis of PED and FRED for the treatment of unruptured posterior circulation aneurysms did not identify significant differences in aneurysm occlusion or neurologic complications. Variations in functional outcomes warrant additional investigations.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Aneurysm; Embolic; Flow diverter; Intervention; Posterior fossa

Comparison of Pipeline Embolization Device and Flow Re-Direction Endoluminal Device Flow Diverters for Internal Carotid Artery Aneurysms: A Propensity Score-Matched Cohort Study - Griessenauer, Christoph J.; Thomas, Ajith J.; Enriquez-Marulanda, Alejandro; Deshmukh, Aviraj; Jain, Abhi; Ogilvy, Christopher S.; Kocer, Naci; Engelhorn, Tobias; Möhlenbruch, Markus; Holtmannspötter, Markus; Janssen, Hendrik; Finkenzeller, Thomas; et al. (Neurosurgery, 2019)
BACKGROUND: Flow diversion has become an accepted endovascular treatment modality for intracranial aneurysms. Studies comparing different types of flow diverters are currently lacking. OBJECTIVE: To perform a propensity score-matched cohort study comparing the Pipeline Embolization Device (PED; Medtronic, Dublin, Ireland) and Flow Redirection Endoluminal Device (FRED; MicroVention, Aliso Viejo, California). METHODS: Aneurysms of the internal carotid artery proximal to the communicating segment treated with PED at 2 neurovascular centers in the United States were matched with aneurysms treated in the European FRED study using propensity scoring. Aneurysms treated in the setting of subarachnoid hemorrhage were excluded from matching. Occlusion rates and complications were evaluated. RESULTS: Two hundred twenty-one internal carotid artery aneurysms were treated with PED and 282 with FRED. Propensity score matching controlling for age, sex, aneurysm size, location, number of flow diverters, and adjunctive coiling resulted in 55 matched pairs. Median angiographic follow-up was nonsignificantly longer for FRED compared to PED (12.2 vs 7.5 mo, P = .28). The rate of complete occlusion did not differ between flow diverters (80% vs 80%, P > .99). Functional outcome and complications were comparable for PED and FRED. CONCLUSION: Propensity score-matched analysis of PED and FRED for internal carotid artery aneurysms revealed comparable angiographic complete occlusion and complication rates. Whether FRED has an advantage in terms of near complete aneurysm occlusion warrants further investigation. Limitations include the retrospective design and lack of an independent assessment of radiographic outcome in a core-laboratory and functional outcomes, among others, and the results should be interpreted as such.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Aneurysm; Embolization; Flow diversion; Stent

Comparison of Two Automated Computed Tomography Perfusion Applications to Predict the Final Infarct Volume After Thrombolysis in Cerebral Infarction 3 Recanalization - Mühlen, Iris; Sprügel, Maximilian; Hölter, Philip; Hock, Stefan; Knott, Michael; Huttner, Hagen; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (Stroke, 2022)
Background: Several automated computed tomography perfusion software applications have been developed to provide support in the definition of ischemic core and penumbra in acute ischemic stroke. However, the degree of interchangeability between software packages is not yet clear. Our study aimed to evaluate 2 commonly used automated perfusion software applications (Syngo.via and RAPID) for the indication of ischemic core with respect to the follow-up infarct volume (FIV) after successful recanalization and with consideration of the clinical impact. Methods: Retrospectively, 154 patients with large vessel occlusion of the middle cerebral artery or the internal carotid artery, who underwent endovascular therapy with a consequent Thrombolysis in Cerebral Infarction 3 result within 2 hours after computed tomography perfusion, were included. Computed tomography perfusion core volumes were assessed with both software applications with different thresholds for relative cerebral blood flow (rCBF). The results were compared with the FIV on computed tomography within 24 to 36 hours after recanalization. Bland-Altman was applied to display the levels of agreement and to evaluate systematic differences. Results: Highest correlation between ischemic core volume and FIV without significant differences was found at a threshold of rCBF<38% for the RAPID software (r=0.89, P<0.001) and rCBF<25% for the Syngo software (r=0.87, P<0.001). Bland-Altman analysis revealed best agreement in these settings. In the vendor default settings (rCBF<30% for RAPID and rCBF<20% for Syngo) correlation between ischemic core volume and FIV was also high (RAPID: r=0.88, Syngo: r=0.86, P<0.001), but mean differences were significant (P<0.001). The risk of critical overestimation of the FIV was higher with rCBF<38% (RAPID) and rCBF<25% (Syngo) than in the default settings. Conclusions: By adjusting the rCBF thresholds, comparable results with reliable information on the FIV after complete recanalization can be obtained both with the RAPID and Syngo software. Keeping the software specific default settings means being more inclusive in patient selection, but forgo the highest possible accuracy in the estimation of the FIV.
CRIS-Team WoS Importer:2022-05-13

Consecutive Lacunar Strokes Mimicking Brainstem Symptoms in a Patient With Pseudobulbar Palsy - Stocker, Alexander; Struffert, Tobias; Engelhorn, Tobias; Huttner, Hagen (Neurologist, 2015)
The pseudobulbar palsy affects both corticobulbar tracts leading to symptoms of the caudal brain nerves. These bulbar symptoms often may be misinterpreted and lead to a false localization of the ischemic lesion. Here we report on a patient with an acute small lacunar ischemic lesion who presented clinically with severe affection because of an identical old contralateral lesion.The patient presented with sudden onset of dysphagia, anarthria, and glossplegia. The clinical examination was suspicious of a brainstem lesion, however, stroke magnetic resonance imaging revealed a small ischemic lacuna within the right internal capsule. However, because of an old ischemic lesion within the left internal capsule, both corticobulbar tracts were involved and this pseudobulbar palsy was mimicking bulbar brainstem symptoms.Patients who suffer from a pseudobulbar palsy usually have–compared with the rather small lesions within the central nervous system–clinically dramatic presentations and due to bulbar symptoms severe medical secondary complications and social-economic consequences to deal with.
EVALuna2:22360

Consider Various Therapy Options Reply - Etminan, Nima; Dörfler, Arnd; Steinmetz, Helmuth (Deutsches Ärzteblatt international, 2020)
CRIS-Team WoS Importer:2020-11-27

Contrast-enhanced angiographic computed tomography for detection of aneurysm remnants after clipping: a comparison with digital subtraction angiography in 112 clipped aneurysms - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver Thomas; Lang, Stefan; Knossalla, Frauke; Dörfler, Arnd (Neurosurgery, 2014)
For preclusion of remnants after aneurysm clipping, a reliable, noninvasive imaging technique is desirable.To evaluate the reliability of optimized angiographic computed tomography with intravenous contrast agent injection (ivACT) in detecting remnants after aneurysmal clipping compared with digital subtraction angiography (DSA), the gold standard.We included 84 patients with 112 clipped cerebral aneurysms of the anterior circulation. For treatment, 116 clips of cobalt and 57 clips of titanium alloy were used. In each patient, we performed an ivACT with dual rotational acquisition and a DSA. Data from ivACT were postprocessed with a dual-volume technique with newly implemented reconstructions modes. Aneurysm remnants were measured, classified, and correlated with DSA by 2 raters.In total, 12 remnants were revealed by DSA, meaning a prevalence of 11%. IvACT demonstrated a sensitivity of 75% to 92% and a specificity of 99% in detecting remnants up to a minimal size of 0.7 × 0.3 mm. Classification of remnants by ivACT was identical to that by DSA, and assessment of size showed a significant correlation with DSA (P < .001). No significant differences between cobalt and titanium alloy were revealed concerning artifacts.Optimized ivACT with enhanced postprocessing demonstrated high sensitivity and specificity in detecting remnants after aneurysm clipping in the anterior circulation. Classification and assessment of remnant size and detection of relevant parent artery stenosis showed high accuracy of ivACT compared with DSA. Our results indicate that ivACT might become a noninvasive alternative to DSA for postsurgical control.
EVALuna2:22328

Contrast-to-noise ratio analysis of microscopic diffusion anisotropy indices in q-space trajectory imaging - Martin, Jan; Endt, Sebastian; Wetscherek, Andreas; Kuder, Tristan Anselm; Dörfler, Arnd; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Zeitschrift für Medizinische Physik, 2019)
Diffusion anisotropy in diffusion tensor imaging (DTI) is commonly quantified with normalized diffusion anisotropy indices (DAIs). Most often, the fractional anisotropy (FA) is used, but several alternative DAIs have been introduced in attempts to maximize the contrast-to-noise ratio (CNR) in diffusion anisotropy maps. Examples include the scaled relative anisotropy (sRA), the gamma variate anisotropy index (GV), the surface anisotropy (UA surf ), and the lattice index (LI). With the advent of multidimensional diffusion encoding it became possible to determine the presence of microscopic diffusion anisotropy in a voxel, which is theoretically independent of orientation coherence. In accordance with DTI, the microscopic anisotropy is typically quantified by the microscopic fractional anisotropy (μFA). In this work, in addition to the μFA, the four microscopic diffusion anisotropy indices (μDAIs) μsRA, μGV, μUA surf , and μLI are defined in analogy to the respective DAIs by means of the average diffusion tensor and the covariance tensor. Simulations with three representative distributions of microscopic diffusion tensors revealed distinct CNR differences when differentiating between isotropic and microscopically anisotropic diffusion. q-Space trajectory imaging (QTI) was employed to acquire brain in-vivo maps of all indices. For this purpose, a 15 min protocol featuring linear, planar, and spherical tensor encoding was used. The resulting maps were of good quality and exhibited different contrasts, e.g. between gray and white matter. This indicates that it may be beneficial to use more than one μDAI in future investigational studies.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Contrast-to-noise ratio; Diffusion; Microstructure; Multidimensional; q-Space trajectory

Convolution-Based Truncation Correction for C-Arm CT Using Scattered Radiation - Bier, Bastian; Schwemmer, Chris; Maier, Andreas; Hofmann, Hannes; Xia, Yan; Hornegger, Joachim; Struffert, Tobias (Bildverarbeitung für die Medizin 2013, 2013)

Cooling in intracerebral hemorrhage (CINCH) trial: Protocol of a randomized German-Austrian clinical trial - Kollmar, Rainer; Juettler, Eric; Huttner, Hagen; Dörfler, Arnd; Staykov, Dimitre; Kallmünzer, Bernd; Schmutzhard, Erich; Schwab, Stefan; Broessner, Gregor (International Journal of Stroke, 2012)
Background: Intracerebral hemorrhage accounts for up to 15% of all strokes and is frequently associated with poor functional outcome and high mortality. So far, there is no clear evidence for a specific therapy, apart from general stroke unit or neurointensive care and management of secondary complications. Promising experimental and pilot clinical data support the use of therapeutic hypothermia after intracerebral hemorrhage. Aims: The study aims to determine if therapeutic hypothermia improves survival rates and reduces cerebral lesion volume after large intracerebral hemorrhage compared with conventional treatment. Material and methods: The Cooling in IntraCerebral Hemorrhage trial is a prospective, multicenter, interventional, randomized, parallel, two-arm (1:1) phase II trial with blinded end-point adjudication. Enrolment: 50 patients (age: 18 to 65 years) with large (25 to 64ml on cranial computertomography), primary intracerebral hemorrhage of the basal ganglia or thalamus within 6 to 18h after symptom onset are randomly allocated to therapeutic hypothermia for eight-days or conventional temperature management. In the therapeutic hypothermia group, a target temperature of 35·0°C is achieved by endovascular catheters and followed by slow controlled rewarming. Data analysis is based on the intent-to-treat population. The primary outcome measure of the study is the development in total lesion volume on cranial computertomography (intracerebral hemorrhage plus perihemorrhagic edema on day 8±0·5 and day 11±0·5 after intracerebral hemorrhage) and the mortality after 30 days. Secondary end-points are the in-hospital mortality, mortality, and functional outcome (modified Rankin Scale and Barthel-Index) after 90 and 180 days. Safety measures include any adverse events associated with therapeutic hypothermia. Discussion: In the face of a lack of evidence-based therapies for patients with large intracerebral hemorrhage, new promising approaches are desperately needed, but need evaluation in randomized controlled trials. Conclusion: The results of Cooling in IntraCerebral Hemorrhage trial are believed to directly influence future therapy of large intracerebral hemorrhage. © 2012 The Authors. International Journal of Stroke © 2012 World Stroke Organization.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Edema; Hypothermia; Intracerebral hemorrhage; Neuroprotection; Stroke

Coregistrating magnetic source and magnetic resonance imaging for epilepsy surgery in focal cortical dysplasia - Kasper, Burkhard; Roessler, Karl; Hamer, Hajo; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Rösch, Julie; Mennecke, Angelika; Wellmer, Joerg; Sommer, Bjoern; Lorber, Bogdan; Lang, Johannes D.; et al. (NeuroImage: Clinical, 2018)
Background: Epilepsy surgery for focal cortical dysplasia type II (FCD II) offers good chances for seizure freedom, but remains a challenge with respect to lesion detection, defining the epileptogenic zone and the optimal resection strategy. Integrating results from magnetic source imaging from magnetoencephalography (MEG) with magnetic resonance imaging (MRI) including MRI postprocessing may be useful for optimizing these goals. Methods: We here present data from 21 adult FCD II patients, investigated during a 10 year period and evaluated including magnetic source imaging. 16 patients had epilepsy surgery, i.e. histopathologically verified FCD II, and a long follow up. We present our analysis of epileptogenic zones including MEG in relation to structural data according to MRI data and relate these results to surgical outcomes. Results: FCD II in our cohort was characterized by high MEG yield and localization accuracy and MEG showed impact on surgical success-rates. MEG source localizations were detected in 95.2% of patients and were as close as 12.3 ± 8,1 mm to the MRI-lesion. After a mean follow up of >3 years, we saw >80% Engel I outcomes, with more favourable outcomes when the MEG source was completely resected (Fishers exact test 0,033). Conclusion: We argue for a high value of conducting a combined MEG-MRI approach in the presurgical workup and the resection strategy in patients with FCD II related epilepsy.
EVALuna2:35523

Correction to: Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT (Clinical Neuroradiology, (2021), 31, 2, (367-372), 10.1007/s00062-020-00922-1) - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2021)
The article “Evaluation After Cochlear Implant Surgery” written by Annika Stock, Victoria Bozzato, Stephan P. Kloska, Alessandro Bozzato, Ulrich Hoppe, Joachim Hornung, Arnd Dörfler and Tobias Struffert was originally published Online First without Open Access. After publication in volume 31, issue 2, page 367–372 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made.
CRIS-Team Scopus Importer:2021-09-10

Correlation between clinical severity and extent of autonomic cardiovascular impairment in the acute phase of subarachnoid hemorrhage - Borutta, Matthias; Gerner, Stefan T.; Möser, Philip; Hölter, Philip; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen B.; Schwab, Stefan; Kuramatsu, Joji; Köhn, Julia (Journal of Neurology, 2022)
Background and aim: To assess associations between clinical severity and possible dysfunction of autonomic cardiovascular modulation within the acute phase after spontaneous subarachnoid hemorrhage (SAH). Methods: In this prospective observational study, in 51 patients with spontaneous SAH, Hunt-and-Hess scores (H&H) were assessed and cardiovascular autonomic modulation was monitored within 24 h after SAH-onset. From 5 min time-series of R–R-intervals (RRI) and blood-pressure (BP) recordings, we calculated autonomic parameters including time-domain [RRI-coefficient-of-variation (RRI-CV) and square-root-of-the-mean-squared-differences-of-successive-RRIs (RMSSD)] and frequency-domain parameters [low- and high-frequency-powers of RRI- and BP-modulation (RRI-LF-, RRI-HF-, SBP-LF-powers) and RRI-total-powers]. Data were compared to those of 20 healthy volunteers. Results: RRI- and BP-values did not differ between groups. Yet, parameters of sympathetic (RRI-LF-powers 141.0 (18.9–402.4) ms2 vs 442.3 (246.8–921.2) ms2, p = 0.001) and total autonomic modulation (RRI-CV 2.4 (1.2–3.7) ms2 vs 3.7 (3.1–5.3) ms2, p = 0.001) were significantly lower in patients than in controls. Subgroup analyses (patients with H&H < 3 vs H&H ≥ 3) and Spearman-rank-correlations revealed increasing loss of sympathetic (RRI-LF-powers 338.6 (179.7–710.4) ms2 vs 72.1 (10.1–175.9) ms2, p = 0.001, rho = − 0.524) and total autonomic modulation (RRI-CV 3.5 (2.3–5.4) ms2 vs 1.6 (1.0–2.8) ms2, p < 0.001, rho = − 0.519) with higher H&H-scores. Multiple-logistic-regression underlined the significant influence of H&H-scores on sympathetic (RRI-LF-powers, p = 0.033) and total autonomic modulation (RRI-CV, p = 0.040) compared to possible confounders (e.g., age, intubation). Conclusion: Within the acute phase, spontaneous SAH induces a decrease in sympathetic and total autonomic cardiovascular modulation. Higher H&H-scores were associated with increasing autonomic dysfunction and may therefore augment the risk of cardiovascular complications and poor clinical outcome.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Autonomic nervous system; Heart rate variability; Hunt and Hess; Subarachnoid hemorrhage

Corrigendum: Feasibility and Diagnostic Accuracy of Ischemic Stroke Territory Recognition Based on Two-dimensional Projections of Three-dimensional Diffusion MRI Data - Wrosch, Jana Katharina; Volbers, Bastian; Gölitz, Philipp; Gilbert, Daniel; Schwab, Stefan; Dörfler, Arnd; Kornhuber, Johannes; Groemer, Teja Wolfgang (Frontiers in Neurology, 2017)
[This corrects the article on p. 239 in vol. 6, PMID: 26635717.].
EVALuna2:22534

Data fusion and 3D visualization for optimized representation of neurovascular relationships in the posterior fossa - Hastreiter, Peter; Bischoff, Barbara; Fahlbusch, Rudolf; Dörfler, Arnd; Buchfelder, Michael; Naraghi, Ramin (Acta Neurochirurgica, 2022)
Background: Reliable 3D visualization of neurovascular relationships in the posterior fossa at the surface of the brainstem is still critical due to artifacts of imaging. To assess neurovascular compression syndromes more reliably, a new approach of 3D visualization based on registration and fusion of high-resolution MR data is presented. Methods: A total of 80 patients received MRI data with 3D-CISS and 3D-TOF at 3.0 Tesla. After registration and subsequent segmentation, the vascular information of the TOF data was fused into the CISS data. Two 3D visualizations were created for each patient, one before and one after fusion, which were verified with the intraoperative situation during microvascular decompression (MVD). The reproduction quality of vessels was evaluated with a rating system. Results: In all cases, the presented approach compensated for typical limitations in the 3D visualization of neurovascular compression such as the partial or complete suppression of larger vessels, suppression of smaller vessels at the CSF margin, and artifacts from heart pulsation. In more than 95% of the cases of hemifacial spasm and glossopharyngeal neuralgia, accurate assessment of the compression was only possible after registration and fusion. In more than 50% of the cases with trigeminal neuralgia, the presented approach was crucial to finding the actually offending vessel. Conclusions: 3D visualization of fused image data allows for a more complete representation of the vessel-nerve situation. The results from this approach are reproducible and the assessment of neurovascular compression is safer. It is a powerful tool for planning MVD.
CRIS-Team Scopus Importer:2022-01-21
Keywords: 3D visualization; Compression syndromes; Data fusion; Neurovascular relationships; Posterior fossa

DCE-MRI of the breast in a stand-alone setting outside a complementary strategy - results of the TK-study - Kaiser, Clemens G.; Reich, C.; Dietzel, M.; Baltzer, P. A. T.; Krammer, J.; Wasser, K.; Schoenberg, S. O.; Kaiser, W. A. (European Radiology, 2015)
To evaluate the accuracy of MRI of the breast (DCE-MRI) in a stand-alone setting with extended indications.According to the inclusion criteria, breast specialists were invited to refer patients to our institution for DCE-MRI. Depending on the MR findings, patients received either a follow-up or biopsy. Between 04/2006 and 12/2011 a consecutive total of 1,488 women were prospectively examined.Of 1,488 included patients, 393 patients were lost to follow-up, 1,095 patients were evaluated. 124 patients were diagnosed with malignancy by DCE-MRI (76 TP, 48 FP, 971 TN, 0 FN cases). Positive cases were confirmed by histology, negative cases by MR follow-ups or patient questionnaires over the next 5 years in 1,737 cases (sensitivity 100 %; specificity 95.2 %; PPV 61.3 %; NPV 100 %; accuracy 95.5 %). For invasive cancers only (DCIS excluded), the results were 63 TP; 27 FP; 971 TP and 0 FN (sensitivity 100 %; specificity 97.2 %; PPV 70 %; NPV 100 %; accuracy 97.5 %).The DCE-MRI indications tested imply that negative results in DCE-MRI reliably exclude cancer. The results were achieved in a stand-alone setting (single modality diagnosis). However, these results are strongly dependent on reader experience and adequate technical standards as prerequisites for optimal diagnoses.o DCE-MRI of the breast has a high accuracy in finding breast cancer. o The set of indications for DCE-MRI of the breast is still very limited. o DCE-MRI can achieve a high accuracy in a 'screening-like' setting. o Accuracy of breast DCE-MRI is strongly dependent on technique and reader experience. o A negative DCE-MRI effectively excludes cancer.
EVALuna2:23006

DeepCEST 7 T: Fast and homogeneous mapping of 7 T CEST MRI parameters and their uncertainty quantification - Hunger, Leonie; Rajput, Junaid Rasool; Klein, Kiril; Mennecke, Angelika; Fabian, Moritz; Schmidt, Manuel; Glang, Felix; Herz, Kai; Liebig, Patrick; Nagel, Armin Michael; Scheffler, Klaus; Dörfler, Arnd; et al. (Magnetic Resonance in Medicine, 2022)
Purpose In this work, we investigated the ability of neural networks to rapidly and robustly predict Lorentzian parameters of multi-pool CEST MRI spectra at 7 T with corresponding uncertainty maps to make them quickly and easily available for routine clinical use. Methods We developed a deepCEST 7 T approach that generates CEST contrasts from just 1 scan with robustness against B-1 inhomogeneities. The input data for a neural feed-forward network consisted of 7 T in vivo uncorrected Z-spectra of a single B-1 level, and a B-1 map. The 7 T raw data were acquired using a 3D snapshot gradient echo multiple interleaved mode saturation CEST sequence. These inputs were mapped voxel-wise to target data consisting of Lorentzian amplitudes generated conventionally by 5-pool Lorentzian fitting of normalized, denoised, B-0- and B-1-corrected Z-spectra. The deepCEST network was trained with Gaussian negative log-likelihood loss, providing an uncertainty quantification in addition to the Lorentzian amplitudes. Results The deepCEST 7 T network provides fast and accurate prediction of all Lorentzian parameters also when only a single B-1 level is used. The prediction was highly accurate with respect to the Lorentzian fit amplitudes, and both healthy tissues and hyperintensities in tumor areas are predicted with a low uncertainty. In corrupted cases, high uncertainty indicated wrong predictions reliably. Conclusion The proposed deepCEST 7 T approach reduces scan time by 50% to now 6:42 min, but still delivers both B-0- and B-1-corrected homogeneous CEST contrasts along with an uncertainty map, which can increase diagnostic confidence. Multiple accurate 7 T CEST contrasts are delivered within seconds.
CRIS-Team WoS Importer:2022-12-02

Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

Denoising and artefact reduction in dynamic flat detector CT perfusion imaging using high speed acquisition: first experimental and clinical results - Manhart, Michael; Aichert, André; Struffert, Tobias; Deuerling-Zheng, Yu; Kowarschik, Markus; Maier, Andreas; Hornegger, Joachim; Dörfler, Arnd (Physics in Medicine and Biology, 2014)
Flat detector CT perfusion (FD-CTP) is a novel technique using C-arm angiography systems for interventional dynamic tissue perfusion measurement with high potential benefits for catheter-guided treatment of stroke. However, FD-CTP is challenging since C-arms rotate slower than conventional CT systems. Furthermore, noise and artefacts affect the measurement of contrast agent flow in tissue. Recent robotic C-arms are able to use high speed protocols (HSP), which allow sampling of the contrast agent flow with improved temporal resolution. However, low angular sampling of projection images leads to streak artefacts, which are translated to the perfusion maps. We recently introduced the FDK-JBF denoising technique based on Feldkamp (FDK) reconstruction followed by joint bilateral filtering (JBF). As this edge-preserving noise reduction preserves streak artefacts, an empirical streak reduction (SR) technique is presented in this work. The SR method exploits spatial and temporal information in the form of total variation and time-curve analysis to detect and remove streaks. The novel approach is evaluated in a numerical brain phantom and a patient study. An improved noise and artefact reduction compared to existing post-processing methods and faster computation speed compared to an algebraic reconstruction method are achieved. © 2014 Institute of Physics and Engineering in Medicine.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.denois_8
Keywords: 3D reconstruction; flat detector CT; noise reduction; perfusion imaging; stroke treatment

Deriving Neural Network Architectures Using Precision Learning: Parallel-to-Fan Beam Conversion - Syben-Leisner, Christopher; Stimpel, Bernhard; Lommen, Jonathan; Würfl, Tobias; Dörfler, Arnd; Maier, Andreas (40th German Conference on Pattern Recognition, GCPR 2018, 2019)
Keywords: Hybrid MRI/X-ray imaging; Precision learning; Machine learning

Detektion einer in der Standard-Mehrzeilen-CT nicht abgrenzbaren Felsenbeinquerfraktur mittels Flachdetektor-CT: ein Fallbericht - Eisenhut, Felix; Wiesmüller, Marco; Lang, Stefan; Taha, Lava (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
CRIS-Team Scopus Importer:2022-08-05

Development of pre-syrinx state and syringomyelia following a minor injury: a case report - Kleindienst, Andrea; Engelhorn, Tobias; Röckelein, Verena; Buchfelder, Michael (Journal of Medical Case Reports, 2020)
Background: A generally accepted rule is that posttraumatic syringomyelia (PTS) results from spinal cord injury (SCI). Case presentation: Here, we report the development of syringomyelia without SCI in a 54-year-old Caucasian man following a mild motor vehicle accident. The computed tomography on admission excluded an injury of the spine. Because of neck and back pain, magnetic resonance imaging was performed on day 3 post-injury and demonstrated minimal changes from a ligamentous strain at the cervicothoracic transition. Any traumatic affection of the bone, vertebral discs, intraspinal compartment, or spinal cord were excluded. Some limb weakness and neurogenic bladder dysfunction started manifesting within the following weeks. Repeated MRIs following the accident demonstrated arachnoid adhesions at the C1–2 level and spinal cord edema equivalent to a pre-syrinx state at 12 months and syrinx formation at 24 months. Because of further deterioration, decompression was performed at 36 months. Conclusions: We conclude that even after a minor trauma PTS can occur and that medullary edema (pre-syrinx state) may precede syrinx formation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Pre-syrinx; Spinal cord injury; Syringomyelia; Trauma; Treatment

Diagnostic imaging in cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias Martin; Schwarz, Marc; Dörfler, Arnd; Budinsky, Lubos; Heß, Andreas; Schmidt, Wolfgang; Jurgons, Roland; Alexiou, Christoph (Springer Proceedings in Physics, 2012)
The unfavorable application-to-tumor-dose-ratio is a drawback of conventional systemic chemotherapy, implying an often insufficient drug dose in the tumor being associated with severe side effects for the patient. The use of chemotherapeutics bound to magnetic nanoparticles offers several advantages. On the one hand it is possible to concentrate the chemotherapeutics in the tumor region by the use of magnetic fields, like it is done in Magnetic Drug Targeting (MDT). On the other hand magnetic particles can serve as contrast agent for magnetic resonance imaging (MRI) that is bound to the therapeutics. Hence, the particles possibly are opening an insight into drug distribution in the tumor region directly after administration. Another important factor for a successful MDT-application is detailed knowledge about tumor vascularization. In this pilot study we investigated vascularization and size of an tumor in an experimental in vivo tumor model via flat-panel angiography and DYNA-CT before MDT and the particle distribution with MRI after MDT. We could show that the tumor could be displayed by MRI and DYNA-CT before and after MDT. Flat panel angiography revealed clearly the pathological tumor vascularization before MDT, while MRI imaging afterwards displayed the tumor as well as the particle distribution in the tumor.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Magnetic Nanoparticles; Tumor Region; Magnetic Resonance Imaging Imaging; Signal Extinction; Left Hind Limb

Diagnostic Performance of 0.55 T MRI for Intracranial Aneurysm Detection - Osmanodja, Filiz; Rösch, Julie; Knott, Michael; Dörfler, Arnd; Grodzki, David; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Intracranial aneurysm (IA) is the main cause of subarachnoid hemorrhages. Time-of-flight (TOF) magnetic resonance angiography (MRA) at 1.5 T or 3 T magnetic resonance imaging (MRI) is a well-established method for the diagnosis of IA. The aim of this prospective study was to evaluate the performance of a modern 0.55 T MRI in the diagnosis of IAs in comparison to digital subtraction angiography (DSA) as a standard of reference. MATERIALS AND METHODS: Seventeen patients with suspicion of single or multiple IAs underwent TOF MRA at 0.55 T MRI 1 day before DSA. Two neuroradiologists independently measured the aneurysm neck, width, and height on 0.55 T, 1.5 T, and 3 T 3D-TOF MRA source images and 2D/3D rotational angiography. The main analysis assessed the intermodality agreement between 0.55 T TOF MRA and DSA using Bland-Altman plots, a Wilcoxon test, and the intraclass correlation coefficient (ICC). In a secondary analysis, aneurysm dimensions were compared between 0.55 T TOF MRA and 1.5/3 T TOF MRA. Interreader agreement was evaluated by ICC. A third neuroradiologist blinded to patient history screened 0.55 T TOF MRA data sets of the aforementioned 17 patients and 15 additional healthy patients for the presence and location of aneurysms. RESULTS: A total of 19 aneurysms in 16 patients were identified in both 0.55 T MRA and DSA. Measurements of the 2 nonblinded readers showed no significant differences between 0.55 T TOF MRA and DSA in the overall aneurysm size (calculated as the mean from height/width/neck) ( P = 0.178), as well as in the mean width ( P = 0.778) and neck values ( P = 0.190). The mean height was significantly larger in 0.55 T TOF MRA in comparison to DSA ( P = 0.020). Intermodality (1.5/3 T TOF MRA) and interrater agreement were excellent (ICC > 0.94). Of the 32 data sets of patients with and without IA, the blinded reader detected all aneurysms correctly by using 0.55 T images. CONCLUSIONS: TOF-MRA acquired with a modern 0.55 T MRI is a reliable tool for the detection and initial assessment of IAs.
CRIS-Team Scopus Importer:2023-01-20

Diagnostik und Behandlung von Carotisstenosen: Die neue S3-Leitlinie aus radiologischer Sicht - Gross-Fengels, W.; Dörfler, Arnd; Berkefeld, J.; Huppert, P. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
CRIS-Team Scopus Importer:2022-08-05

Differences in metabolism of fiber tract alterations in gliomas: A combined fiber density mapping and magnetic resonance spectroscopic imaging study - Stadlbauer, Andreas; Hammen, Thilo; Buchfelder, Michael; Bachmair, Johanna; Dörfler, Arnd; Nimsky, Christopher; Ganslandt, Oliver (Neurosurgery, 2012)
BACKGROUND: Gliomas propagate diffusely throughout and along white matter structures. Glioma-related changes in structural integrity and metabolism are not detectable by standard magnetic resonance (MR) imaging. OBJECTIVE: To investigate differences in the metabolism of fiber tract alterations between gliomas grade II to IV by correlation of fiber density values with metabolite concentrations measured by fiber density mapping and MR spectroscopic imaging. METHODS: Fiber density mapping and MR spectroscopic imaging were performed in 48 patients with gliomas WHO grade II to IV. Fiber density mapping data were used to define fiber tracts in tumoral and peritumoral areas. Structural integrity of fiber tracts was assessed as fiber density ipsilateral-to-contralateral ratio (FD ICR). Metabolite concentrations for choline-containing compounds and N-acetyl-aspartate were computed and correlated to FD ICR values after coregistration with anatomic MR imaging. RESULTS: In tumoral areas, choline-containing compound concentrations of altered fiber tracts were significantly different between low- and high-grade glioma and showed different courses for the correlations of FD ICR and choline-containing czeompounds. In high-grade glioma, increasing fiber destruction was associated with a massive progression in cell membrane proliferation. Peritumoral fiber structures showed significantly decreased N-acetyl-aspartate concentrations for all patients, but only patients with glioblastoma multiforme had significantly decreased fiber density compared with the contralateral side. Glioma grades II and III had significantly higher peritumoral FD ICR than glioblastoma multiforme. CONCLUSION: A multiparametric MR imaging strategy providing information about both structural integrity and metabolism of the tumor is required for detailed assessment of glioma-related fiber tract alterations, which in turn is essential for treatment planning. Copyright © 2012 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain tumor; Diffusion tensor; Fiber density; Magnetic resonance spectroscopy

Diffusion tensor imaging of the visual pathway in glaucomatous optic nerve atrophy - Engelhorn, Tobias; A. Schmidt, M.; Dörfler, Arnd; Michelson, Georg (Ophthalmologe, 2017)
In Germany more than one million inhabitants suffer from glaucoma, more than 100,000 are threatened with blindness because glaucoma is often diagnosed too late or not at all. Diagnosis and monitoring is usually carried out "only" by examination of the retina and not the whole visual pathway. However, the eye is just "the tip of the iceberg" of the actual visual pathway, which extends through the brain to the visual cortex. The interdisciplinary holistic assessment of the whole visual pathway in glaucoma is of crucial importance because glaucoma is a complex neurodegenerative disease. Subtypes, such as normal tension glaucoma (NTG), seem to originate from primary damage to the intracranial visual pathway with secondary retrograde retinal degeneration. Recent studies including glaucoma patients and healthy controls could show that diffusion tensor imaging with calculation of diffusion coefficients, i.e. fractional anisotropy (FA), mean and radial diffusivity (MD and RD) as markers of axonal integrity, provide the potential to assess the intracranial visual pathway with a high correlation to established ophthalmological examinations. In particular, calculation of FA maps of the visual pathway and accompanying voxel-based approaches, can be integrated into clinical routine. Thus, detection of glaucoma-related intracranial alterations, even in early stages of the disease, as well as differentiation of different glaucoma subtypes, is made possible. Furthermore, the diagnosis of normal tension glaucoma seems to be possible much earlier with these new imaging techniques compared to established ophthalmological work-up. Moreover, holistic imaging provides new insights into the pathophysiology of this form of glaucoma. This review article gives an overview of these novel magnetic resonance imaging techniques for assessment of the visual pathway in glaucomatous optic nerve atrophy and reveals the potential of an interdisciplinary approach.
EVALuna2:21333

Direct imaging of white matter ultrashort T2∗ components at 7 Tesla - Müller, Max; Egger, Nico; Sommer, Stefan; Wilferth, Tobias; Meixner, Christian; Laun, Frederik Bernd; Mennecke, Angelika; Schmidt, Manuel; Huhn, Konstantin; Rothhammer, Veit; Uder, Michael; Dörfler, Arnd; et al. (Magnetic Resonance Imaging, 2022)
Purpose: To demonstrate direct imaging of the white matter ultrashort T2∗ components at 7 Tesla using inversion recovery (IR)-enhanced ultrashort echo time (UTE) MRI. To investigate its characteristics, potentials and limitations, and to establish a clinical protocol. Material and methods: The IR UTE technique suppresses long T2∗ signals within white matter by using adiabatic inversion in combination with dual-echo difference imaging. Artifacts arising at 7 T from long T2∗ scalp fat components were reduced by frequency shifting the IR pulse such that those frequencies were inverted likewise. For 8 healthy volunteers, the T2∗ relaxation times of white matter were then quantified. In 20 healthy volunteers, the UTE difference and fraction contrast were evaluated. Finally, in 6 patients with multiple sclerosis (MS), the performance of the technique was assessed. Results: A frequency shift of −1.2 ppm of the IR pulse (i.e. towards the fat frequency) provided a good suppression of artifacts. With this, an ultrashort compartment of (68 ± 6) % with a T2∗ time of (147 ± 58) μs was quantified with a chemical shift of (−3.6 ± 0.5) ppm from water. Within healthy volunteers' white matter, a stable ultrashort T2∗ fraction contrast was calculated. For the MS patients, a significant fraction reduction in the identified lesions as well as in the normal-appearing white matter was observed. Conclusions: The quantification results indicate that the observed ultrashort components arise primarily from myelin tissue. Direct IR UTE imaging of the white matter ultrashort T2∗ components is thus feasible at 7 T with high quantitative inter-subject repeatability and good detection of signal loss in MS.
Created from Fastlane, Scopus look-up
Keywords: 7 Tesla; Multiple sclerosis; Myelin; Relaxometry; Ultrashort echo time (UTE); White matter

Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24

Disability-Adjusted Life-Years Associated with Intracerebral Hemorrhage and Secondary Injury - Haupenthal, David; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (JAMA Network Open, 2021)
Importance: Intracerebral hemorrhage (ICH) contributes significantly to the global burden of disease. Objective: To examine the association of ICH and secondary injury with disability-adjusted life-years (DALYs) for the individual patient. Design, Setting, and Participants: This cohort study was conducted using data from the Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage study. Consecutive patients admitted to a single tertiary care center from January 1, 2006, to December 31, 2015, were included. The sample comprised patients with oral anticoagulation-associated ICH (OAC-ICH) or primary spontaneous ICH (non-OAC-ICH). Statistical analysis was conducted from October 1 to December 31, 2020. Exposures: ICH occurrence and secondary injury. Main Outcomes and Measures: DALYs, years of life lost (YLL), and years lived with disability (YLD) were analyzed by hematoma location, ICH volume, and secondary injury (ie, hematoma expansion [HE], intraventricular hemorrhage [IVH], and perihemorrhagic edema [PHE]). Results: Among 1322 patients with ICH, 615 (46.5%) were women and the mean (SD) age at hospital admission was 71 (13) years; ICH was associated with a mean (SD) of 9.46 (8.08) DALYs, 5.72 (8.29) YLL, and 3.74 (5.95) YLD. There were statistically significant differences in mean (SD) DALYs by extent of hematoma volume (< 10 mL ICH: 7.05 [6.79] DALYs; 10-30 mL ICH: 9.91 [8.35] DALYs; >30 mL ICH: 12.42 [8.47] DALYs; P <.001) and ICH location (deep location: 10.60 [8.35] DALYs; lobar location: 8.18 [7.63] DALYs; cerebellum: 8.14 [6.80] DALYs; brainstem: 12.63 [9.21] DALYs; P <.001). Regarding population-level disease burden of secondary injuries after ICH, there was a statistically significant difference in mean (SD) by injury type, with 0.94 (3.19) DALYs for HE, 2.45 (4.16) DALYs for IVH, and 1.96 (2.66) DALYs for PHE (P <.001) among the entire ICH cohort. Regarding individual-level exposure to secondary injuries after ICH, there were a mean (SD) 7.14 (6.62) DALYs for HE, 4.58 (4.75) DALYs for IVH, and 3.35 (3.28) DALYs for PHE among patients with ICH affected by secondary injuries. Conclusions and Relevance: These findings suggest that there is a high burden of disability associated with ICH and secondary injuries, and the findings may guide public health strategies. The study findings further suggest that IVH and PHE may be relevant for the overall outcome of patients with ICH, that DALYs may represent a viable outcome parameter for studies to evaluate treatment outcomes in ICH research, and that IVH and PHE may represent potential treatment targets..
CRIS-Team Scopus Importer:2021-07-30

Doppler pulsatility index in spontaneous intracerebral hemorrhage - Kiphuth, Ines C.; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Köhrmann, Martin (European neurology, 2013)
Background and Purpose: Elevated intracranial pressure (ICP) as a result of intracerebral hemorrhage (ICH) and perihematomal edema often leads to tissue shift, which can be identified in cross-sectional imaging and presents a known predictor of functional outcome. Pulsatility indices (PIs) of the intracranial arteries as measured by transcranial Doppler sonography (TCD) may serve as surrogate parameters for ICP. This study aims to investigate whether PI correlates with ICP and midline shift and serves as a reliable predictor of functional outcome in patients with ICH. Methods: Within a 1-year period between April 2009 and April 2010, 136 patients with acute spontaneous, supratentorial ICH were admitted to our tertiary care hospital. One-hundred and twenty-four patients fulfilled the inclusion criteria and were eligible for analysis. TCD and transcranial duplex sonography were performed on admission and at least once more during hospital stay. Functional outcome was assessed 6 months after discharge. Correlation analyses, logistic regression analyses and receiver operating characteristic curves were calculated. Results: One-hundred and twenty-four patients were included in the analysis. Six-month mortality amounted to 39.5%. The ICH score and PIs of the middle cerebral artery were independent predictors of outcome 6 months after discharge. Conclusions: Early PI monitoring by TCD correlated with ICP and may be used to predict the outcome after 6 months. Copyright © 2013 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Functional outcome; Intracerebral hemorrhage; Midline shift; Pulsatility index; Transcranial duplex sonography

DSC Brain Perfusion Using Advanced Deconvolution Models in the Diagnostic Work-Up of Dementia and Mild Cognitive Impairment: A Semiquantitative Comparison with HMPAO-SPECT-Brain Perfusion - Schmidt, Manuel; Engelhorn, Tobias; Lang, Stefan; Lücking, Hannes; Hölter, Philip; Fröhlich, Kilian; Ritt, Philipp; Maler, Juan Manuel; Kuwert, Torsten; Kornhuber, Johannes; Dörfler, Arnd (Journal of Clinical Medicine, 2020)
Background: SPECT (single-photon emission-computed tomography) is used for the detection of hypoperfusion in cognitive impairment and dementia but is not widely available and related to radiation dose exposure. We compared the performance of DSC (dynamic susceptibility contrast) perfusion using semi- and fully adaptive deconvolution models to HMPAO-SPECT (99mTc-hexamethylpropyleneamine oxime-SPECT). Material and Methods: Twenty-seven patients with dementia of different subtypes including frontotemporal dementia (FTD) and mild cognitive impairment (MCI) received a multimodal diagnostic work-up including DSC perfusion at a clinical 3T high-field scanner and HMPAO-SPECT. Nineteen healthy control individuals received DSC perfusion. For calculation of the hemodynamic parameter maps, oscillation-index standard truncated singular value decomposition (oSVD, semi-adaptive) as well as Bayesian parameter estimation (BAY, fully adaptive) were performed. Results: Patients showed decreased cortical perfusion in the left frontal lobe compared to controls (relative cerebral blood volume corrected, rBVc: 0.37 vs. 0.27,p= 0.048, adjusted for age and sex). Performance of rBVc (corrected for T1 effects) was highest compared to SPECT for detection of frontal hypoperfusion (sensitivity 83%, specificity 80% for oSVD and BAY, area under curve (AUC) = 0.833 respectively,p< 0.05) in FTD and MCI. For nonleakage-corrected rBV and for rBF (relative cerebral blood flow), sensitivity of frontal hypoperfusion was above 80% for oSVD and for BAY (rBV: sensitivity 83%, specificity 75%, AUC = 0.908 for oSVD and 0.917 for BAY,p< 0.05 respectively; rBF: sensitivity 83%, specificity 65%, AUC = 0.825,p< 0.05 for oSVD). Conclusion: Advanced deconvolution DSC can reliably detect pathological perfusion alterations in FTD and MCI. Hence, this widely accessible technique has the potential to improve the diagnosis of dementia and MCI as part of an interdisciplinary multimodal imaging work-up. Advances in knowledge: Advanced DSC perfusion has a high potential in the work-up of suspected dementia and correlates with SPECT brain perfusion results in dementia and MCI.
CRIS-Team WoS Importer:2020-07-31

DTI analysis in patients with primary open-angle glaucoma: impact of registration on Voxel-Wise statistics - Schmidt, Manuel; Mennecke, Angelika; Michelson, Georg; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2014)
Tract-based spatial statistics (TBSS) has been used to assess the integrity of the visual pathway in glaucoma patients. TBSS uses the subjects' FA data to create a mean FA skeleton of white matter tracts before running voxel-wise cross-subject statistics. We compared four different approaches of registration of FA maps to create the skeleton and evaluated alignment and subsequently the impact of the chosen registration on voxel-wise statistics.Our study comprised 69 subjects, i.e. 46 patients with primary open angle glaucoma (POAG) and a healthy, age-matched control group of 23 subjects. Mean FA skeletons were created using the following registration approaches: registration to a standard template (T), registration to the group mean (GM), registration to a group-wise atlas (GW) and registration to the most typical subject (N). Subsequently, maps of standard deviation of the 4D images were created to assess the alignment. Voxel-wise statistics for each registration approach were performed.We found distinct differences in voxel-wise statistics depending on the chosen registration approach. Best alignment results were achieved by registration to a study specific template, i.e. to the group mean (GM) or to a group-wise atlas (GW). Overall alignment did not differ between these two approaches. However, voxel-wise statistics showed clusters of significantly decreased FA values in the T and GM approach, which were not significant after GW registration. These voxels of significantly decreased FA values after T and GM registration did not represent white matter tracts and correlated with higher standard deviation in FA maps across subjects, thus implying registration errors, especially in the optic radiation.Registration to a study-specific template, i.e. to the group mean or a group-wise atlas seems to be the method of choice in TBSS-analysis of glaucoma patients as it shows better alignment of the optic radiation and helps to rule out registration errors due to misalignment.
EVALuna2:21168

DTI parameters of axonal integrity and demyelination of the optic radiation correlate with glaucoma indices - Michelson, Georg; Engelhorn, Tobias; Wärntges, Simone; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Graefes Archive For Clinical and Experimental Ophthalmology, 2013)
EVALuna2:21070

Duration of Ischemia Affects Outcomes Independent of Infarct Size in Stroke. - Kim, Youngran; Khose, Swapnil; Zaidat, Osama O.; Hassan, Ameer E.; Fifi, Johanna T.; Nanda, Ashish; Atchie, Benjamin; Woodward, Britton; Dörfler, Arnd; Tomasello, Alejandro; Yoo, Albert J.; Sheth, Sunil A. (Stroke: Vascular and Interventional Neurology, 2022)
BACKGROUND: Delays in endovascular reperfusion for patients with large vessel occlusion stroke are known to worsen outcomes, and the mechanism is believed to be time-dependent expansion of the ischemic infarction. In this study, we hypothesize that delays in onset to reperfusion (OTR) assert an effect on outcomes independent of effects of final infarct (FI). METHODS: We performed a subgroup analysis from the prospective multicenter COMPLETE (International Acute Ischemic Stroke Registry With the Penumbra System Aspiration Including the 3D Revascularization Device; Penumbra, Inc) registry for 257 patients with anterior circulation large vessel occlusion who underwent endovascular therapy with successful reperfusion (modified treatment in cerebral infarction score 2b/3). FI was measured by Alberta Stroke Program Early CT score and volume on 24- to 48-hour computed tomography or magnetic resonance imaging. The likelihood of 90-day good functional outcome (modified Rankin scale 0-2) was assessed by OTR and absolute risk difference (ARD) was estimated using multivariable logistic regressions adjusting for patient characteristics including FI. RESULTS: In univariable analysis, longer OTR was associated with a decreased likelihood of good functional outcome (ARD -3% [95% CI -4.5 to -1.0]/h delay). In multivariable analysis accounting for FI, the association between OTR and functional outcome remained significant (ARD -2% [95% CI -3.5 to -0.4]/h delay) with similar ARD. This finding was maintained in the subset of patients with FI imaging using CT only, using Alberta Stroke Program Early CT Score or volumetric FI measurements, and also in patients with larger versus smaller FIs. CONCLUSIONS: The impact of OTR on outcomes appears to be mostly through a mechanism that is independent of FI. Our findings suggest that although the field has moved toward imaging infarct core definitions of eligibility for endovascular treatment, time remains an important predictor of outcome, independent of infarct core.
EVALuna2:547252

Dynamic Angiography and Perfusion Imaging Using Flat Detector CT in the Angiography Suite: A Pilot Study in Patients with Acute Middle Cerebral Artery Occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Kloska, Stephan; Engelhorn, Tobias; Lang, Sabine; Mennecke, Angelika; Manhart, M.; Strother, C. M.; Schwab, Sibylle; Dörfler, Arnd (American Journal of Neuroradiology, 2015)
Perfusion and angiographic imaging using intravenous contrast application to evaluate stroke patients is now technically feasible by flat detector CT performed by the angiographic system. The aim of this pilot study was to show the feasibility and qualitative comparability of a novel flat detector CT dynamic perfusion and angiographic imaging protocol in comparison with a multimodal stroke MR imaging protocol.In 12 patients with acute stroke, MR imaging and the novel flat detector CT protocol were performed before endovascular treatment. Perfusion parameter maps (MTT, TTP, CBV, CBF) and MIP/volume-rendering technique images obtained by using both modalities (MR imaging and flat detector CT) were compared.Comparison of MIP/volume-rendering technique images demonstrated equivalent visibility of the occlusion site. Qualitative comparison of perfusion parameter maps by using ASPECTS revealed high Pearson correlation coefficients for parameters CBF, MTT, and TTP (0.95-0.98), while for CBV, the coefficient was lower (0.49).We have shown the feasibility of a novel dynamic flat detector CT perfusion and angiographic protocol for the diagnosis and triage of patients with acute ischemic stroke. In a qualitative comparison, the parameter maps and MIP/volume-rendering technique images compared well with MR imaging. In our opinion, this flat detector CT application may substitute for multisection CT imaging in selected patients with acute stroke so that in the future, patients with acute stroke may be directly referred to the angiography suite, thereby avoiding transportation and saving time.
EVALuna2:22353

Dysmorphic neurons as cellular source for phase-amplitude coupling in Focal Cortical Dysplasia Type II - Rampp, Stefan; Rössler, Karl; Hamer, Hajo; Illek, Margit; Buchfelder, Michael; Dörfler, Arnd; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Kölble, Konrad; Peixoto-Santos, Jose Eduardo; Blümcke, Ingmar; et al. (Clinical Neurophysiology, 2021)
Objective: Reliable localization of the epileptogenic zone is necessary for successful epilepsy surgery. Neurophysiological biomarkers include ictal onsets and interictal spikes. Furthermore, the epileptic network shows oscillations with potential localization value and pathomechanistic implications. The cellular origin of such markers in invasive EEG in vivo remains to be clarified. Methods: In the presented pilot study, surgical brain samples and invasive EEG recordings of seven patients with surgically treated Focal Cortical Dysplasia (FCD) type II were coregistered using a novel protocol. Dysmorphic neurons and balloon cells were immunohistochemically quantified. Evaluated markers included seizure onset, spikes, and oscillatory activity in delta, theta, gamma and ripple frequency bands, as well as sample entropy and phase-amplitude coupling between delta, theta, alpha and beta phase and gamma amplitude. Results: Correlations between histopathology and neurophysiology provided evidence for a contribution of dysmorphic neurons to interictal spikes, fast gamma activity and ripples. Furthermore, seizure onset and phase-amplitude coupling in areas with dysmorphic neurons suggests preserved connectivity is related to seizure initiation. Balloon cells showed no association. Conclusions: Phase-amplitude coupling, spikes, fast gamma and ripples are related to the density of dysmorphic neurons and localize the seizure onset zone. Significance: The results of our pilot study provide a new powerful tool to address the cellular source of abnormal neurophysiology signals to leverage current and novel biomarkers for the localization of epileptic activity in the human brain.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Electrophysiological markers; Epilepsy; Focal cortical dysplasia; Invasive EEG

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Easy detection of MS-CT-invisible temporal bone fracture via FD-CT: a case report - Eisenhut, Felix; Taha, Lava; Wiesmüller, Marco; Lang, Stefan (Laryngo-Rhino-Otologie, 2023)
CRIS-Team WoS Importer:2023-05-19

Editorial for: “ΔADC Analysis of the Brain in Idiopathic Normal Pressure Hydrocephalus Before and After Cerebrospinal Fluid Drainage” - Mennecke, Angelika; Dörfler, Arnd (Journal of Magnetic Resonance Imaging, 2020)
CRIS-Team Scopus Importer:2020-12-04

Effective dose to patient measurements in flat-detector and multislice computed tomography: a comparison of applications in neuroradiology - Struffert, Tobias; Hauer, Michael; Banckwitz, Rosemarie; Koehler, Christoph; Royalty, Kevin; Dörfler, Arnd (European Radiology, 2014)
Flat-detector CT (FD-CT) is used for a variety of applications. Additionally, 3D rotational angiography (3D DSA) is used to supplement digital subtraction angiography (DSA) studies. The aim was to measure and compare the dose of (1) standard DSA and 3D DSA and (2) analogous FD-CT and multislice CT (MSCT) protocols.Using an anthropomorphic phantom, the effective dose to patients (according to ICRP 103) was measured on an MSCT and a flat-detector angiographic system using standard protocols as recommended by the manufacturer.(1) Evaluation of DSA and 3D DSA angiography protocols: ap.-lat. Standard/low-dose series 1/0.8 mSv, enlarged oblique projection 0.3 mSv, 3D DSA 0.9 mSv (limited coverage length 0.3 mSv). (2) Comparison of FD-CT and MSCT: brain parenchyma imaging 2.9 /1.4 mSv, perfusion imaging 2.3/4.2 mSv, temporal bone 0.2 /0.2 mSv, angiography 2.9/3.3 mSv, limited to the head using collimation 0.5/0.5 mSv.The effective dose for an FD-CT application depends on the application used. Using collimation for FD-CT applications, the dose may be reduced considerably. Due to the low dose of 3D DSA, we recommend using this technique to reduce the number of DSA series needed to identify working projections.Effective dose of FD-CT in comparison to MSCT is in comparable range. Collimation decreases the dose of FD-CT effectively. Effective dose of 3-D angiography is identical to 2-D DSA. Different FD-CT programs have different dose.
EVALuna2:22994

Effect of oral bolus versus sustained release application of nutrient solution on olfaction - Denzer-Lippmann, Melanie; Bachlechner, S.; Wielopolski, Jan; Fischer, M.; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Gerald; Kornhuber, Johannes; Thürauf, Norbert (2016)
EVALuna2:33155

Effects of different isocaloric oral nutrient solutions on olfactory functioning, hunger and food craving - Thürauf, Norbert; Denzer-Lippmann, Melanie; Bachlechner, Stephan; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Gerald; Kornhuber, Johannes (2017)
EVALuna2:33148

Efficacy and safety of combined intraventricular fibrinolysis with lumbar drainage for prevention of permanent shunt dependency after intracerebral hemorrhage with severe ventricular involvement: A randomized trial and individual patient data meta-analysi - Staykov, Dimitre; Kuramatsu, Joji; Bardutzky, Juergen; Volbers, Bastian; Gerner, Stefan; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Annals of Neurology, 2017)
Intraventricular hemorrhage (IVH) is a negative prognostic factor in intracerebral hemorrhage (ICH) and is associated with permanent shunt dependency in a substantial proportion of patients post-ICH. IVH treatment by intraventricular fibrinolysis (IVF) was recently linked to reduced mortality rates in the CLEAR III study and IVF represents a safe and effective strategy to hasten clot resolution that may reduce shunt rates. Additionally, promising results from observational studies reported reductions in shunt dependency for a combined treatment approach of IVF plus lumbar drains (LDs). The present randomized, controlled trial investigated efficacy and safety of a combined strategy-IVF plus LD versus IVF alone-on shunt dependency in patients with ICH and severe IVH.This randomized, open-label, parallel-group study included patients aged 18 to 85 years, prehospital modified Rankin Scale <=3, ICH volume < 60ml, Glasgow Coma Scale of <9, and severe IVH with tamponade of the third and fourth ventricles requiring placement of external ventricular drainage (EVD). Over a 3-year recruitment period, patients were allocated to either standard treatment (control group receiving IVF consisting of 1mg of recombinant human tissue plasminogen activator every 8 hours until clot clearance of third and fourth ventricles) or a combined treatment approach of IVF and-upon clot clearance of third and fourth ventricles-subsequent placement of an LD for drainage of cerebrospinal fluid (CSF; intervention group). The primary endpoint consisted of permanent shunt placement indicated after a total of three unsuccessful EVD clamping attempts or need for CSF drainage longer than 14 days in both groups. Secondary endpoints included IVF- and LD-related safety, such as bleeding or infections, and functional outcome at 90 and 180 days. Conducted endpoint analyses used individual patient data meta-analyses. The study was registered at clinicaltrials.gov (NCT01041950).The trial was stopped upon predefined interim analysis after 30 patients because of significant efficacy of tested intervention. The primary endpoint was analyzed without dropouts and was reached in 43% (7 of 16) of the control group versus 0% (0 of 14) of the intervention group (p = 0.007). Meta-analyses were based on overall 97 patients, 45 patients receiving IVF plus LD versus 42 with IVF only. Meta-analyses on shunt dependency showed an absolute risk reduction of 24% for the intervention (LD, 2.2% [1 of 45] vs no-LD, 26.2% [11 of 42]; odds ratio [OR] = 0.062; confidence interval [CI], 0.011-0.361; p = 0.002). Secondary endpoints did not show significant differences for CSF infections (OR = 0.869;CI, 0.445-1.695; p = 0.680) and functional outcome at 90 days (OR = 0.478; CI, 0.190-1.201; p = 0.116), yet bleeding complications were significantly reduced in favor of the intervention (OR = 0.401; CI, 0.302-0.532; p < 0.001).The present trial and individual patient data meta-analyses provide evidence that, in patients with severe IVH, as compared to IVF alone, a combined approach of IVF plus LD treatment is feasible and safe and significantly reduces rates of permanent shunt dependency for aresorptive hydrocephalus post-ICH. ANN NEUROL 2017;81:93-103.
EVALuna2:22478

Efficient drug-delivery using magnetic nanoparticles–biodistribution and therapeutic effects in tumour bearing rabbits. - Peukert, Wolfgang; Tietze, Rainer; Lyer, Stefan; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias; Schwarz, Marc; Eckert, Elisabeth; Göen, Thomas; Vasylyev, Serhiy; Trahms, Lutz; Dörfler, Arnd; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2013)
To treat tumours efficiently and spare normal tissues, targeted drug delivery is a promising alternative to conventional, systemic administered chemotherapy. Drug-carrying magnetic nanoparticles can be concentrated in tumours by external magnetic fields, preventing the nanomaterial from being cleared by metabolic burden before reaching the tumour. Therefore in Magnetic Drug Targeting (MDT) the favoured mode of application is believed to be intra-arterial. Here, we show that a simple yet versatile magnetic carrier-system (hydrodynamic particles diameter <200nm) accumulates the chemotherapeutic drug mitoxantrone efficiently in tumours. With MDT we observed the following drug accumulations relative to the recovery from all investigated tissues: tumour region: 57.2%, liver: 14.4%, kidneys: 15.2%. Systemic intra-venous application revealed different results: tumour region: 0.7%, liver: 14.4 % and kidneys: 77.8%. The therapeutic outcome was demonstrated by complete tumour remissions and a survival probability of 26.7% (P=0.0075). These results are confirming former pilot experiments and implying a milestone towards clinical studies. FROM THE CLINICAL EDITOR This team of investigators studied drug carrying nanoparticles for magnetic drug targeting (MDT), demonstrating the importance of intra-arterial administration resulting in improved clinical outcomes in the studied animal model compared with intra-venous.
Keywords: treatment; drug; delievery; magnetic; nanoparticles

Endovascular interventions for subarachnoid hemorrhage - Dörfler, Arnd (Cambridge University Press, 2013)
The primary treatment goal of cerebral aneurysms is prevention of rupture. Surgical clipping has been the treatment modality of choice for both ruptured and unruptured cerebral aneurysms for decades. Just over 20 years ago endovascular treatment was mainly restricted to those patients with aneurysms unsuitable or inaccessible for clipping due to size or location, or in whom surgical clipping was contraindicated because of the general medical condition. Nowadays, the increasing experience and development of appropriate devices has widened the indications, and endovascular therapy has become more than an alternative to surgical treatment. Attempts to induce thrombosis of systemic aneurysms either by introducing foreign bodies or by application of electrical or thermic injury date back to the first half of the 19th century. Velpeau (1831) independently described a method of introducing arterial thrombosis by inserting a needle into the aneurysmal lumen and withdrawing it after thrombus had formed. In 1941 Werner et al. reported successful electrothermic thrombosis of an acute ruptured intracranial aneurysm through a transorbital approach. In 1963 Gallagher proposed a technique of inducing thrombosis of intracranial aneurysms by high-speed delivery of dog or horse hairs into the aneurysm using a pneumatic gun (‘pilojection’). However, despite encouraging early results these methods did not gain acceptance.
CRIS-Team Scopus Importer:2022-08-05

Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke

Endovascular treatment of patient with multiple extracranial large vessel stenosis and coexistent unruptured wide-neck intracranial aneurysm using a WEB device and Szabo-technique - Cherednychenko, Yurii; Engelhorn, Tobias; Miroshnychenko, Andrii; Zorin, Mikola; Dzyak, Liudmila; Tsurkalenko, Olena; Cherednychenko, Natalia (Radiology Case Reports, 2020)
The coexistence of severe extracranial large vessel stenosis and unruptured intracranial aneurysms is not rare. There are different treatment approaches for these conditions, such as initial treatment of the aneurysm before revascularization of the stenosis; single-stage endovascular treatment of both lesions; stenosis eliminating followed by treatment of the aneurysm, or without treating the aneurysm. But, taking into account the risk of aneurysm rupture on the one hand and the risk of ischemic stroke on the other, it is sometimes difficult to choose the right management strategy. Despite this fact, there are still no guidelines or consensus on the management of these coexistent lesions. The article describes a clinical case of endovascular treatment of multiple extracranial stenosis and coexistent unruptured wide-neck aneurysm of the middle cerebral artery. The endovascular treatment of the carotid stenosis and aneurysm using a woven endobridge device was performed in one session; endovascular treatment of vertebral artery stenosis with Szabo technique was performed in another session.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Cerebral aneurysm; Endovascular treatment; Stenosis of extracranial vessel; Szabo-technique; WEB device

Endovascular Versus Medical Management of Posterior Cerebral Artery Occlusion Stroke: The PLATO Study. - Nguyen, Thanh N.; Qureshi, Muhammad M.; Strambo, Davide; Strbian, Daniel; Räty, Silja; Herweh, Christian; Abdalkader, Mohamad; Olive-Gadea, Marta; Ribo, Marc; Psychogios, Marios; Fischer, Urs; Nguyen, Anh; et al. (Stroke, 2023)
BACKGROUND: The optimal management of patients with isolated posterior cerebral artery occlusion is uncertain. We compared clinical outcomes for endovascular therapy (EVT) versus medical management (MM) in patients with isolated posterior cerebral artery occlusion. METHODS: This multinational case-control study conducted at 27 sites in Europe and North America included consecutive patients with isolated posterior cerebral artery occlusion presenting within 24 hours of time last well from January 2015 to August 2022. Patients treated with EVT or MM were compared with multivariable logistic regression and inverse probability of treatment weighting. The coprimary outcomes were the 90-day modified Rankin Scale ordinal shift and ≥2-point decrease in the National Institutes of Health Stroke Scale. RESULTS: Of 1023 patients, 589 (57.6%) were male with median (interquartile range) age of 74 (64-82) years. The median (interquartile range) National Institutes of Health Stroke Scale was 6 (3-10). The occlusion segments were P1 (41.2%), P2 (49.2%), and P3 (7.1%). Overall, intravenous thrombolysis was administered in 43% and EVT in 37%. There was no difference between the EVT and MM groups in the 90-day modified Rankin Scale shift (aOR, 1.13 [95% CI, 0.85-1.50]; P=0.41). There were higher odds of a decrease in the National Institutes of Health Stroke Scale by ≥2 points with EVT (aOR, 1.84 [95% CI, 1.35-2.52]; P=0.0001). Compared with MM, EVT was associated with a higher likelihood of excellent outcome (aOR, 1.50 [95% CI, 1.07-2.09]; P=0.018), complete vision recovery, and similar rates of functional independence (modified Rankin Scale score, 0-2), despite a higher rate of SICH and mortality (symptomatic intracranial hemorrhage, 6.2% versus 1.7%; P=0.0001; mortality, 10.1% versus 5.0%; P=0.002). CONCLUSIONS: In patients with isolated posterior cerebral artery occlusion, EVT was associated with similar odds of disability by ordinal modified Rankin Scale, higher odds of early National Institutes of Health stroke scale improvement, and complete vision recovery compared with MM. There was a higher likelihood of excellent outcome in the EVT group despite a higher rate of symptomatic intracranial hemorrhage and mortality. Continued enrollment into ongoing distal vessel occlusion randomized trials is warranted.
EVALuna2:536990

Erratum to 'Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke' (Clinical Neurology and Neurosurgery (2014) 121, (39-45)) - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
CRIS-Team Scopus Importer:2022-08-05

Erratum zu: Interdisziplinäre neurovaskuläre Netzwerke: eine Standortbestimmung - Röther, J.; Busse, O.; Berlis, A.; Dörfler, Arnd; Groden, Ch; Hamann, G.; Jansen, O.; Meixensberger, J.; Müller, O.; Regelsberger, J.; Steinmetz, H.; Vatter, H.; et al. (Der Nervenarzt, 2020)
CRIS-Team Scopus Importer:2020-11-13

Essentials in intraoperative indocyanine green videoangiography assessment for intracranial aneurysm surgery: conclusions from 295 consecutively clipped aneurysms and review of the literature - Roessler, Karl; Krawagna, Maximilian; Dörfler, Arnd; Buchfelder, Michael; Ganslandt, Oliver (Neurosurgical Focus, 2014)
Indocyanine green (ICG) videoangiography (VA) in cerebral aneurysm surgery allows confirmation of blood flow in parent, branching, and perforating vessels as well as assessment of remnant aneurysm parts after clip application. A retrospective analysis and review of the literature were conducted to determine the current essential advantages of ICG-VA in aneurysm surgery.The authors retrospectively evaluated all aneurysm cases treated with the aid of intraoperative ICG-VA at a single institution between 2007 and 2013. They also analyzed the literature published since the initial description of ICG-VA in 2003.Two hundred forty-six procedures were performed in 232 patients harboring 295 aneurysms. The patients, whose mean age was 54 years, consisted of 159 women and 73 men. One hundred twenty-four surgeries were performed after subarachnoid hemorrhage, and 122 were performed for incidental aneurysms. Single aneurysms were clipped in 185 patients, and multiple aneurysms were clipped in 47 (mean aneurysm diameter 6.9 mm, range 2-40 mm). No complications associated with ICG-VA occurred. Intraoperative microvascular Doppler ultrasonography was performed before ICG-VA in all patients, and postoperative digital subtraction angiography (DSA) studies were available in 121 patients (52.2%) for retrospective comparative analysis. In 22 (9%) of 246 procedures, the clip position was modified intraoperatively as a consequence of ICG-VA. Stenosis of the parent vessels (16 procedures) or occlusion of the perforators (6 procedures), not detected by micro-Doppler ultrasonography, were the most common problems demonstrated on ICG-VA. In another 11 procedures (4.5%), residual perfusion of the aneurysm was observed and one or more additional clips were applied. Vessel stenosis or a compromised perforating artery occurred independent of aneurysm location and was about equally common in middle cerebral artery and anterior communicating artery aneurysms. In 2 procedures (0.8%), aneurysm puncture revealed residual blood flow within the lesion, which had not been detected by the ICG-VA. In the postoperative DSA studies, unexpected small (< 2 mm) aneurysm neck remnants, which had not been detected on intraoperative ICG-VA, were found in 11 (9.1%) of 121 patients. However, these remnants remained without consequence except in 1 patient with a 6-mm residual aneurysm dome, which was subsequently embolized with coils.In a large cohort of consecutive patients, ICG-VA proved to be a helpful intraoperative tool and led to a significant intraoperative clip modification rate of 15%. However, small, < 2-mm-wide neck remnants and a 6-mm residual aneurysm were missed by intraoperative ICG-VA in up to 10% of patients. Results in this study confirm that DSA is indispensable for postoperative quality assessment in complex aneurysm surgery.
EVALuna2:22828

Etiological aspects of posterior epilepsies - Kasper, Burkhard; Roessler, Karl; Dörfler, Arnd (Zeitschrift für Epileptologie, 2020)
Background Posterior epilepsies (PE), i.e. focal epilepsies with epileptogenic zones within the posterior parts of the neocortical mantle (parietal, occipital and dorsal temporal lobes), represent a diagnostic and therapeutic challenge encompassing a wide spectrum of possible etiologies. Objective The etiological spectrum of PE is presented. Material and methods Illustration based on the longstanding personal expertise of the authors with examples of findings in personal cases. Results The PE is complex. Knowledge of the broad spectrum of possible etiologies is important in order to be able to reliably identify a PE including its etiology and to offer targeted treatment to selected patients. Successful epilepsy surgery is often possible.
CRIS-Team WoS Importer:2021-01-15

European Multicenter Study for the Evaluation of a Dual-Layer Flow-Diverting Stent for Treatment of Wide-Neck Intracranial Aneurysms: The European Flow-Redirection Intraluminal Device Study - Killer-Oberpfalzer, Monika; Kocer, N.; Griessenauer, C. J.; Janssen, H.; Engelhorn, Tobias; Holtmannspotter, Markus; Buhk, J. H.; Finkenzeller, Thomas; Fesl, G.; Trenkler, J.; Reith, W.; Berlis, A.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Endoluminal reconstruction with flow-diverting stents represents a widely accepted technique for the treatment of complex intracranial aneurysms. This European registry study analyzed the initial experience of 15 neurovascular centers with the Flow-Redirection Intraluminal Device (FRED) system. MATERIALS AND METHODS: Consecutive patients with intracranial aneurysms treated with the FRED between February 2012 and March 2015 were retrospectively reviewed. Complications and adverse events, transient and permanent morbidity, mortality, and occlusion rates were evaluated. RESULTS: During the defined study period, 579 aneurysms in 531 patients (median age, 54 years; range, 13-86 years) were treated with the FRED. Seven percent of patients were treated in the acute phase (≤3 days) of aneurysm rupture. The median aneurysm size was 7.6 mm (range, 1-36.6 mm), and the median neck size 4.5 mm (range, 1-30 mm). Angiographic follow-up of >3 months was available for 516 (89.1%) aneurysms. There was progressive occlusion witnessed with time, with complete occlusion in 18 (20%) aneurysms followed for up to 90 ± 14 days, 141 (82.5%) for 180 ± 20 days, 116 (91.3%) for 1 year ± 24 days, and 122 (95.3%) aneurysms followed for >1 year. Transient and permanent morbidity occurred in 3.2% and 0.8% of procedures, respectively. The overall mortality rate was 1.5%. CONCLUSIONS: This retrospective study in real-world patients demonstrated the safety and efficacy of the FRED for the treatment of intracranial aneurysms. In most cases, treatment with a single FRED resulted in complete angiographic occlusion at 1 year.
EVALuna2:34271

Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2020)
Purpose: Assessment of the cochlear implant (CI) electrode array position using flat-detector computed tomography (FDCT) to test dependence of postoperative outcome on intracochlear electrode position. Methods: A total of 102 patients implanted with 107 CIs underwent FDCT. Electrode position was rated as 1) scala tympani, 2) scala vestibuli, 3) scalar dislocation and 4) no deconvolution. Two independent neuroradiologists rated all image data sets twice and the scalar position was verified by a third neuroradiologist. Presurgical and postsurgical speech audiometry by the Freiburg monosyllabic test was used to evaluate auditory outcome after 6 months of speech rehabilitation. Results: Electrode array position was assessed by FDCT in 107 CIs. Of the electrodes 60 were detected in the scala tympani, 21 in the scala vestibuli, 24 electrode arrays showed scalar dislocation and 2 electrodes were not placed in an intracochlear position. There was no significant difference in rehabilitation outcomes between scala tympani and scala vestibuli inserted patients. Rehabilitation was also possible in patients with dislocated electrodes. Conclusion: The use of FDCT is a reliable diagnostic method to determine the position of the electrode array. In our study cohort, the electrode position had no significant impact on postoperative outcome except for non-deconvoluted electrode arrays.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cochlear implantation; Deafness; Dyna-CT; Misplaced cochlear implant electrode array; Rehabilitation

Evaluation of a metal artifact reduction algorithm applied to post-interventional flat detector CT in comparison to pre-treatment CT in patients with acute subarachnoid haemorrhage - Mennecke, Angelika; Svergun, Stanislav; Scholz, Bernhard; Royalty, Kevin; Dörfler, Arnd; Struffert, Tobias (European Radiology, 2017)
OBJECTIVES: Metal artefacts can impair accurate diagnosis of haemorrhage using flat detector CT (FD-CT), especially after aneurysm coiling. Within this work we evaluate a prototype metal artefact reduction algorithm by comparison of the artefact-reduced and the non-artefact-reduced FD-CT images to pre-treatment FD-CT and multi-slice CT images. METHODS: Twenty-five patients with acute aneurysmal subarachnoid haemorrhage (SAH) were selected retrospectively. FD-CT and multi-slice CT before endovascular treatment as well as FD-CT data sets after treatment were available for all patients. The algorithm was applied to post-treatment FD-CT. The effect of the algorithm was evaluated utilizing the pre-post concordance of a modified Fisher score, a subjective image quality assessment, the range of the Hounsfield units within three ROIs, and the pre-post slice-wise Pearson correlation. RESULTS: The pre-post concordance of the modified Fisher score, the subjective image quality, and the pre-post correlation of the ranges of the Hounsfield units were significantly higher for artefact-reduced than for non-artefact-reduced images. Within the metal-affected slices, the pre-post slice-wise Pearson correlation coefficient was higher for artefact-reduced than for non-artefact-reduced images. CONCLUSION: The overall diagnostic quality of the artefact-reduced images was improved and reached the level of the pre-interventional FD-CT images. The metal-unaffected parts of the image were not modified. KEY POINTS: • After coiling subarachnoid haemorrhage, metal artefacts seriously reduce FD-CT image quality. • This new metal artefact reduction algorithm is feasible for flat-detector CT. • After coiling, MAR is necessary for diagnostic quality of affected slices. • Slice-wise Pearson correlation is introduced to evaluate improvement of MAR in future studies. • Metal-unaffected parts of image are not modified by this MAR algorithm.
EVALuna2:33150

Evaluation of an Artificial Intelligence-Based 3D-Angiography for Visualization of Cerebral Vasculature - Lang, Stefan; Schmidt, Manuel; Eisenhut, Felix; Kaethner, Christian; Kowarschik, Markus; Lücking, Hannes; Dörfler, Arnd; Hölter, Philip (Clinical Neuroradiology, 2019)
Purpose: The three-dimensional digital subtraction angiography (3D DSA) technique is the current standard and is based on both mask and fill runs to enable the subtraction technique. Artificial intelligence (AI)-based 3D angiography (3DA) was developed to reduce radiation dosage because only one contrast-enhanced run of the C‑arm system is required for reconstruction of DSA-like 3D volumes. The aim was the evaluation of this algorithm regarding its diagnostic information. Methods: 3D DSA datasets without pathologic findings were reconstructed both with subtraction technique and with the AI-based algorithm. Corresponding reconstructions were evaluated by 2 neuroradiologists with respect to image quality (IQ), visualization of major segments of the circle of Willis (ICA = C4-C7; OphA; ACA = A1-A2, MCA = M1-M2; VA = V4; BA; AICA; SUCA; PCA = P1-P2), identifiability of perforators (lenticulostriate/thalamoperforating arteries) and vessel diameters (ICA = C4; MCA = M1; BA; PCA = P1). Results: In total 15 datasets were successfully reconstructed as 3D DSA and 3DA with diagnostic image quality. All major segments of the circle of Willis and perforators were comparably visualized with 3DA. Quantitative analysis of vessel diameters in 3D DSA and 3DA datasets was equivalent and did not show relevant differences (rICA = 0.901, p = 0.001; rM1 = 0.951, p = 0.001; rBA = 0.906, p = 0.001; rP1 = 0.991, p = 0.001). Conclusions: The use of 3DA demonstrated reliable visualization of cerebral vasculature with respect to quantitative and qualitative parameters. Therefore, 3DA is a promising method that might help to reduce patient radiation.
CRIS-Team Scopus Importer:2019-11-01
Keywords: 3D angiography; Artificial intelligence; Deep learning; Dose reduction; Flat-detector computed tomography

Evaluation of Collaterals and Clot Burden Using Time-Resolved C-Arm Conebeam CT Angiography in the Angiography Suite: A Feasibility Study - Yang, P.; Niu, K.; Wu, Y.; Struffert, Tobias; Dörfler, Arnd; Holter, P.; Aagaard-Kienitz, Beverly; Strother, C.; Chen, G. -H. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: The assessment of collaterals and clot burden in patients with acute ischemic stroke provides important information about treatment options and clinical outcome. Time-resolved C-arm conebeam CT angiography has the potential to provide accurate and reliable evaluations of collaterals and clot burden in the angiographic suite. Experience with this technique is extremely limited, and feasibility studies are needed to validate this technique. Our purpose was to present such a feasibility study. MATERIALS AND METHODS: Ten C-arm conebeam CT perfusion datasets from 10 subjects with acute ischemic stroke acquired before endovascular treatment were retrospectively processed to generate time-resolved conebeam CTA. From time-resolved conebeam CTA, 2 experienced readers evaluated the clot burden and collateral flow in consensus by using previously reported scoring systems and assessed the clinical value of this novel imaging technique independently. Interobserver agreement was analyzed by using the intraclass correlation analysis method. RESULTS: Clot burden and collateral flow can be assessed by using the commonly accepted scoring systems for all eligible cases. Additional clinical information (eg, the quantitative dynamic information of collateral flow) can be obtained from this new imaging technique. Two readers agreed that time-revolved C-arm conebeam CTA is the preferred method for evaluating the clot burden and collateral flow compared with other conventional imaging methods. CONCLUSIONS: Comprehensive evaluations of clot burden and collateral flow are feasible by using time-resolved C-arm conebeam CTA data acquired in the angiography suite. This technique further enriches the imaging tools in the angiography suite to enable a "one-stop- shop" imaging workflow for patients with acute ischemic stroke.
EVALuna2:33146

Evaluation of Functional Recovery Following Thrombectomy in Patients With Large Vessel Occlusion and Prestroke Disability - Sprügel, Maximilian; Sembill, Jochen; Kremer, Svenja; Gerner, Stefan; Knott, Michael; Hock, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Huttner, Hagen; Schwab, Stefan (JAMA Network Open, 2022)
IMPORTANCE It is uncertain whether thrombectomy is associated with benefits in patients with prestroke disability.
CRIS-Team WoS Importer:2022-09-02

Evaluation of the influence of susceptibility-induced magnetic field distortions on the precision of contouring intracranial organs at risk for stereotactic radiosurgery - Mengling, Veit; Putz, Florian; Laun, Frederik Bernd; Perrin, Rosalind; Eisenhut, Felix; Dörfler, Arnd; Fietkau, Rainer; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2020)
Background and purpose: Magnetic resonance imaging (MRI) is a crucial factor in optimal treatment planning for stereotactic radiosurgery. To further the awareness of possible errors in MRI, this work aimed to investigate the magnitude of susceptibility induced MRI distortions for intracranial organs at risk (OARs) and test the effectiveness of actively shimming these distortions. Materials and methods: Distortion maps for 45 exams of 42 patients (18 on a 1.5 T MRI scanner, 27 on a 3 T MRI scanner) were calculated based on a high-bandwidth double-echo gradient echo sequence. The investigated OARs were brainstem, chiasm, eyes, and optic nerves. The influence of active shimming was investigated by comparing unshimmed 1.5 T data with shimmed 3 T data and comparing the results to a model based prediction. Results: The median distortion for the different OARs was found to be between 0.13 and 0.18 mm for 1.5 T and between 0.11 and 0.13 mm for 3 T. The maximum distortion was found to be between 1.3 and 1.7 mm for 1.5 T and between 1.1 and 1.4 mm for 3 T. The variation of values was much higher for 1.5 T than for 3 T across all investigated OARs. Active shimming was found to reduce distortions by a factor of 2.3 to 2.9 compared to the expected values. Conclusions: Using a safety margin for OARs of 1 mm would have encompassed 99.8% of the distortions. Since distortions are inversely proportional to the readout bandwidth, they can be further reduced by increasing the bandwidth. Additional error sources like gradient nonlinearities need to be addressed separately.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Brain; MRI; PRV; Safety margins; Stereotactic; Susceptibility artifacts

Evidence for improved survival with bevacizumab treatment in recurrent high-grade gliomas: a retrospective study with ("pseudo-randomized") treatment allocation by the health insurance provider - Hofmann, Susanne; Schmidt, Manuel; Weissmann, Thomas; Eyüpoglu, Ilker Yasin; Strnad, Annedore; Semrau, Sabine; Fietkau, Rainer; Putz, Florian; Lettmaier, Sebastian (Journal of Neuro-Oncology, 2020)
Introduction Despite a large number of trials, the role of bevacizumab (BEV) in the treatment of recurrent high-grade gliomas is still controversial. Evidence regarding an effect on overall survival in this context is ultimately inconclusive. At the Department of Radiation Oncology at Erlangen, Germany we treated a large cohort of patients with recurrent gliomas where bevacizumab use was determined exclusively by the health care provider's approval of reimbursement. Methods 61 patients (between 06/2008 and 01/2014) with recurrent high-grade gliomas had reimbursement requests for BEV sent to their health insurance. 37 patients out of 61 (60.7%) had their requests approved and therefore received bevacizumab (BEV-arm) as part of their treatment. The remaining 24 (39.3%) patients received standard therapy without bevacizumab (non-BEV-arm). Survival endpoints were defined with reference to the first BEV request to the health insurance provider. Results Median overall survival (OS) for the whole cohort was 7.0 months. OS was significantly better for BEV vs. Non-BEV patients (median, 10.3 vs. 4.2 months, logrank p = 0.023). There was an increased BEV benefit in cases of higher-order recurrences (first order recurrence BEV vs. Non-BEV, 12.5 vs. 10.2 months, p = 0.578) (second or higher order of recurrence, 9.9 vs. 2.6 months, p = 0.010). On multivariate analysis for overall survival the prognostic impact of bevacizumab (HR = 0.43, p = 0.034) remained significant. Conclusion Our results suggest an influence of BEV on overall survival in a heavily pretreated patient population suffering from high-grade gliomas with BEV benefit being greatest in case of second or later recurrence.
CRIS-Team WoS Importer:2020-05-29

Extended Multimodal Flat Detector CT Imaging in Acute Ischemic Stroke: A Pilot Study - Hölter, Philip; Lang, Stefan; Beuscher, Vanessa; Kallmünzer, Bernd; Manhart, Michael; Schwab, Stefan; Dörfler, Arnd (Journal of Digital Imaging, 2023)
By using Flat detector computed tomography (FD-CT), a one-stop-shop approach in the diagnostic workup of acute ischemic stroke (AIS) might be achieved. Although information on upstream vessels is warranted, dedicated FD-CT protocols which include the imaging of the cervical vasculature are still lacking. We aimed to prospectively evaluate the implementation of a new multimodal FD-CT protocol including cervical vessel imaging in AIS patients. In total, 16 patients were included in this study. Eight patients with AIS due to large vessel occlusion (LVO) prospectively received a fully multimodal FD-CT imaging, including non-enhanced flat detector computed tomography (NE-FDCT), dynamic perfusion flat detector computed tomography (FD-CTP) and flat detector computed tomography angiography (FD-CTA) including cervical imaging. For comparison of time metrics and image quality, eight AIS patients, which received multimodal CT imaging, were included retrospectively. Although image quality of NE-FDCT and FD-CTA was rated slightly lower than NE-CT and CTA, all FD-CT datasets were of diagnostic quality. Intracerebral hemorrhage exclusion and LVO detection was reliably possible. Median door-to-image time was comparable for the FD-CT group and the control group (CT:30 min, IQR27-58; FD-CT:44.5 min, IQR31-55, p = 0.491). Door-to-groin-puncture time (CT:79.5 min, IQR65-90; FD-CT:59.5 min, IQR51-67; p = 0.016) and image-to-groin-puncture time (CT:44 min, IQR30-50; FD-CT:14 min, IQR12-18; p < 0.001) were significantly shorter, when patients were directly transferred to the angiosuite, where FD-CT took place. Our study indicates that using a new fully multimodal FD-CT approach including imaging of cervical vessels for first-line imaging in AIS patients is feasible and comparable to multimodal CT imaging with substantial potential to streamline the stroke workflow.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Flat Detector Computed Tomography; Interventional; Stroke; Workflow

Extracranial temporal bone paragangliomas: Re-defining the role of otologic surgery within the scope of function-preserving multimodal concepts - Mantsopoulos, Konstantinos; Thimsen, Vivian; Eisenhut, Felix; Weissmann, Thomas; Putz, Florian; Fietkau, Rainer; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2022)
Introduction: The aim of this study was to present our concept in the management of extracranial temporal bone paragangliomas and demonstrate the outcome after primary surgical management of the middle ear component, with an individualized indication for adjuvant radiotherapy. Materials and methods: The records of all patients treated for extracranial jugulotympanic paragangliomas by means of primary surgical management between 2010 and 2021 were studied retrospectively. Results: Twenty-nine patients made up our study sample (mean age 58.8 years). 15 cases were managed solely by means of surgery. Out of the remaining 14 cases with reduction of the middle ear component, adjuvant irradiation was performed in 11 cases, whereas a wait-and-scan strategy was adopted at the patient's request in three cases. No further growth was detected in our study cases. Conclusion: Our protocol seems to be associated with an acceptable quality of life and a satisfactory oncologic outcome.
CRIS-Team WoS Importer:2021-10-15

Fan-to-Parallel Beam Conversion: Deriving Neural Network Architectures Using Precision Learning - Syben-Leisner, Christopher; Stimpel, Bernhard; Lommen, Jonathan; Würfl, Tobias; Dörfler, Arnd; Maier, Andreas (Informatik aktuell, 2019)
CRIS-Team Scopus Importer:2019-05-14

Fast Adaptive Regularization for Perfusion Parameter Computation - Manhart, Michael; Maier, Andreas; Hornegger, Joachim; Dörfler, Arnd (Bildverarbeitung für die Medizin, 2015)
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD5.fastad_9

Fast adaptive regularization for perfusion parameter computation: Tuning the Tikhonov regularization parameter to the SNR by regression - Manhart, Michael; Maier, Andreas; Hornegger, Joachim; Dörfler, Arnd (Informatik aktuell, 2015)
Computation of perfusion parameters by deconvolution from contrast-enhanced time-resolved CT or MR perfusion data sets is an illconditioned problem. Thus, adequate regularization and determination of corresponding regularization parameters is required. We present a novel method for Tikhonov regularization for perfusion imaging to locally adapt parameters to the SNR level by using a regression function. In an numerical evaluation our simple approach provided similar or even superior results compared to methods applying computationally more demanding L-curve analysis.
CRIS-Team Scopus Importer:2022-08-05

Fast online-customized (FOCUS) parallel transmission pulses: A combination of universal pulses and individual optimization - Herrler, Jürgen; Liebig, Patrick; Gumbrecht, Rene; Ritter, Dieter; Schmitter, Sebastian; Maier, Andreas; Schmidt, Manuel; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To mitigate spatial flip angle (FA) variations under strict specific absorption rate (SAR) constraints for ultra-high field MRI using a combination of universal parallel transmit (pTx) pulses and fast subject-specific optimization. Methods: Data sets consisting of B0, (Formula presented.) maps, and virtual observation point (VOP) data were acquired from 72 subjects (study groups of 48/12 healthy Europeans/Asians and 12 Europeans with pathological or incidental findings) using an 8Tx/32Rx head coil on a 7T whole-body MR system. Combined optimization values (COV) were defined as combination of spiral-nonselective (SPINS) trajectory parameters and an energy regularization weight. A set of COV was optimized universally by simulating the individual RF pulse optimizations of 12 training data sets (healthy Europeans). Subsequently, corresponding universal pulses (UPs) were calculated. Using COV and UPs, individually optimized pulses (IOPs) were calculated during the sequence preparation phase (maximum 15 s). Two different UPs and IOPs were evaluated by calculating their normalized root-mean-square error (NRMSE) of the FA and SAR in simulations of all data sets. Seven additional subjects were examined using an MPRAGE sequence that uses the designed pTx excitation pulses and a conventional adiabatic inversion. Results: All pTx pulses resulted in decreased mean NRMSE compared to a circularly polarized (CP) pulse (CP = 28%, UPs = 17%, and IOPs = 12%). UPs and IOPs improved homogeneity for all subjects. Differences in NRMSE between study groups were much lower than differences between different pulse types. Conclusion: UPs can be used to generate fast online-customized (FOCUS) pulses gaining lower NRMSE and/or lower SAR values.
CRIS-Team Scopus Importer:2021-01-15
Keywords: 7 T; k; parallel transmission (pTx); SPINS; ultra-high-field MRI; universal pulses

Fatal Encephalitis Associated with Borna Disease Virus 1 - Korn, Klaus; Coras, Roland; Bobinger, Tobias; Herzog, Sibylle M.; Lücking, Hannes; Stoehr, Roland; Huttner, Hagen; Hartmann, Arndt; Enßer, Armin (New England Journal of Medicine, 2018)
EVALuna2:34851

Fatal lymphomatoid granulomatosis with primary CNS-involvement in an immunocompetent 80-year-old woman - Olmes, David G.; Agaimy, Abbas; Kloska, Stephan; Linker, Ralf (BMJ Case Reports, 2014)
An 80-year-old woman presented with weight loss, fatigue, dizziness and a brain stem lesion. Extensive work-up revealed lymphomatoid granulomatosis (LYG) with primary clinical manifestation in the central nervous system (CNS), a rare Epstein-Barr virus-driven multisystem lymphoproliferative disorder, to be causative for the symptoms. Immunochemotherapy consisting of rituximab and temozolomide was started, but the disease progressed and the patient subsequently died. Histology, diagnostic criteria, differential diagnosis and treatment options for LYG with CNS involvement are discussed. This case demonstrates that LYG with CNS involvement may necessitate more aggressive treatment approaches than combination therapy with rituximab and temozolomide.
EVALuna2:6736

Feasibility of cerebral blood volume mapping by flat panel detector CT in the angiography suite: First experience in patients with acute middle cerebral artery occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Koehrmann, M.; Schwab, S.; Strother, C. M.; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: A new FPCT application offers the possibility of perfusion (FPCT CBV) and parenchymal (FPCT) imaging within the angiography suite. We tested the hypothesis that findings in FPCT CBV and FPCT would correlate with those obtained using MSCT and PCT. MATERIALS AND METHODS: In 16 patients with acute MCA occlusion, FPCT CBV was performed immediately posttreatment. The volume of tissue having abnormal CBV values was determined by FPCT CBV and PCT images. Stroke volume on follow-up MSCT was determined, CBV values in the effected parenchyma were measured, and FPCT images were reviewed. RESULTS: In 6 cases, we found a FPCT CBV value identical or higher (hyperemia) in comparison with the contralateral side. In 10 cases, we found CBV lesions with values lower (oligemia) than the contralateral brain tissue. We found a high correlation of CBV lesion volume on FPCT CBV images to stroke volume on follow-up MSCT (r = 0.9, P < .05) in the oligemia group. Absolute FPCT CBV and PCT CBV values were comparable and showed good correlation (r = 0.9, P < .05). In 8 patients, contrast medium extravasation was visible. CONCLUSIONS: The new FPCT application allows assessment of CBV in acute stroke patients. Our initial results indicate that these measurements may predict final infarct volume. The ability to assess this key parameter of cerebral perfusion within the angiographic suite may improve the management of these patients.
CRIS-Team Scopus Importer:2022-08-05

Fibrinolysis Treatment for Cerebral Intraventricular Hemorrhage: A Temporal and Spatial Voxel-Based Analysis - Strinitz, Marc; Kuramatsu, Joji; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Seifert, Frank (Journal of Neuroimaging, 2016)
A voxel-based statistical approach on computer tomographic data in patients with intracerebral hemorrhage (ICH) and acute intraventricular hemorrhage (IVH) was used to evaluate spatial and temporal patterns of intraventricular blood in patients treated with intraventricular fibrinolysis (IVF) or without.IVH shapes were systematically assessed three dimensionally in patients with supratentorial ICH at three intervals of time (day of admission, day 4 ± 1, day 7+). The boundaries of the intraventricular blood clot were delineated on computed tomography (CT) scans using dedicated software. The CT scan and the IVH shape were transferred into stereotaxic space. In a second step, voxel-based statistics on group level were used to correlate the distribution of intraventricular blood with the interval and the treatment group.Altogether 45 patients, 29 with IVF therapy and 16 without, were eligible to be included into this study. We found significant (false discovery rate [FDR] correction, q < .05) reduction of the intraventricular blood between day of admission and day 7 + for the third and fourth ventricle and parts of both lateral ventricles. In addition, we were able to show a significant difference between the IVF therapy and the conventionally treated group at day 4 ± 1 for the third ventricle.The data indicate that voxel-based analysis on group level can be used to compare the time course and the distribution of intraventricular hemorrhage. This technique could be an interesting tool for future research on ICH with IVH.
EVALuna2:22457

First German Guideline on Diagnostics and Therapy of Clinically Non-Functioning Pituitary Tumors - Deutschbein, Timo; Jaursch-Hancke, Cornelia; Knappe, Ulrich J.; Saeger, Wolfgang; Flitsch, Joerg; Bojunga, Joerg; Buchfelder, Michael; Ditzen, Beate; Gerlach, Ruediger; Gertzen, Elfriede; Honegger, Juergen; Horstmann, Gerhard A.; et al. (Experimental and Clinical Endocrinology and Diabetes, 2021)
Although non-functioning pituitary tumors are frequent, diagnostic and therapeutic concepts are not well standardized. We here present the first German multidisciplinary guideline on this topic. The single most important message is to manage the patients by a multidisciplinary team (consisting at least of an endocrinologist, a neurosurgeon, and a (neuro-) radiologist). The initial diagnostic work-up comprises a detailed characterization of both biochemical (focusing on hormonal excess or deficiency states) and morphological aspects (with magnetic resonance imaging of the sellar region). An ophthalmological examination is only needed in presence of symptoms or large tumors affecting the visual system. Asymptomatic, hormonally inactive tumors allow for a 'wait and scan' strategy. In contrast, surgical treatment by an experienced pituitary surgeon is standard of care in case of (impending) visual impairment. Therapeutic options for incompletely resected or recurrent tumors include re-operation, radiotherapy, and observation; the individual treatment plan should be developed multidisciplinary. Irrespective of the therapeutic approach applied, patients require long-term follow-up. Patient with larger pituitary tumors or former surgery/radiotherapy should be regularly counseled regarding potential symptoms of hormonal deficiency states.
CRIS-Team WoS Importer:2021-04-02

FLAIRfusion Processing with Contrast Inversion : Improving Detection and Reading Time of New Cerebral MS Lesions - Schmidt, Manuel; Linker, Ralf; Lang, S.; Lücking, Hannes; Engelhorn, Tobias; Kloska, Stephan; Uder, Michael; Dörfler, Arnd; Dankerl, Peter; Cavallaro, Alexander Josef (Clinical Neuroradiology, 2017)
To evaluate the performance of an innovative image processing approach for detection of T2-weighted hyperintense multiple sclerosis (MS) lesions.In this study 20 consecutive patients with inflammatory demyelinating lesions were retrospectively evaluated of whom 10 patients featured progressive disease and 10 a stable lesion load. 3 mm transversal FLAIRfusion imaging was processed and archived. Image processing was performed through landmark-based 3D co-registration of the previous and current isotropic FLAIR examination followed by inversion of image contrast. Thereby, the hyperintense signals of the unchanged MS plaques extinguish each other, while newly developed lesions appear bright on FLAIRfusion. Diagnostic performance was evaluated by 4 experienced readers. Consensus reading supplied the reference standard. Sensitivity, specificity, NPV (negative predictive value), PPV (positive predictive value), interreader agreement and reading time were the outcome measures analyzed.Combined sensitivity was 100% at a specificity of 88.2%, with PPV ranging from 83.3% to 90.1% and NPV at 100%. Reading time was nearly 5-fold faster than conventional side by side comparison (35.6 s vs. 163.7 s, p < 0.001). Cohen's kappa was excellent (>0.75; p < 0.001) and Cronbach's alpha was 0.994.FLAIRfusion provides reliable detection of newly developed MS lesions along with strong interreader agreement across all levels of expertise in 35 s of reading time.
EVALuna2:14615

Flat detector computed tomography angiography with intravenous contrast application: Feasibility for visualization of cerebral arterial vasculature - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Ott, Sabine; Struffert, Tobias; Dörfler, Arnd (Journal of Neuroimaging, 2013)
BACKGROUND AND PURPOSE: The aim of our study was to evaluate flat detector computed tomography angiography with peripheral intravenous contrast material application (FD-CTA) for visualization of cerebral arteries in comparison with intravenous multidetector computed tomography angiography (CTA) and intraarterial digital subtraction angiography (DSA). METHODS: The study was approved by the local institutional review board and informed consent was obtained by all participants. Ten patients underwent FD-CTA, CTA, and DSA of the cerebral arterial vasculature for suspected cerebrovascular disease. The image data were evaluated by two readers in consensus for the visualization of cerebral arterial segments on a 5-point scale (0 = vessel cannot be distinguished; 4 = excellent image quality). The Wilcoxon signed-rank test was used for statistical analysis. Note that P < .05 was considered to indicate a significant difference. RESULTS: The depiction of cerebral arterial segments with FD-CTA was significantly superior compared to CTA in most vessel segments (P < .05 in 20 of 23 anatomic regions) and was without significant difference compared with DSA in large and medium intracranial vessels. CONCLUSIONS: The results suggest that the cerebral arteries can be visualized by FD-CTA in high resolution, in many vessel segments comparable to DSA. © 2012 by the American Society of Neuroimaging.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Cerebral; Computed tomography; Flat detector; Intravenous

Flat-detector computed tomography evaluation in an experimental animal aneurysm model after endovascular treatment: A pilot study - Ott, Sabine; Gölitz, Philipp; Adamek, Edyta; Royalty, Kevin; Dörfler, Arnd; Struffert, Tobias (Interventional Neuroradiology, 2015)
We compared flat-detector computed tomography angiography (FD-CTA) to multislice computed tomography (MS-CTA) and digital subtracted angiography (DSA) for the visualization of experimental aneurysms treated with stents, coils or a combination of both.In 20 rabbits, aneurysms were created using the rabbit elastase aneurysm model. Seven aneurysms were treated with coils, seven with coils and stents, and six with self-expandable stents alone. Imaging was performed by DSA, MS-CTA and FD-CTA immediately after treatment. Multiplanar reconstruction (MPR) was performed and two experienced reviewers compared aneurysm/coil package size, aneurysm occlusion, stent diameters and artifacts for each modality.In aneurysms treated with stents alone, the visualization of the aneurysms was identical in all three imaging modalities. Residual aneurysm perfusion was present in two cases and visible in DSA and FD-CTA but not in MS-CTA. The diameter of coil-packages was overestimated in MS-CT by 56% and only by 16% in FD-CTA compared to DSA (p < 0.05). The diameter of stents was identical for DSA and FD-CTA and was significantly overestimated in MS-CTA (p < 0.05). Beam/metal hardening artifacts impaired image quality more severely in MS-CTA compared to FD-CTA.MS-CTA is impaired by blooming and beam/metal hardening artifacts in the visualization of implanted devices. There was no significant difference between measurements made with noninvasive FD-CTA compared to gold standard of DSA after stenting and after coiling/stent-assisted coiling of aneurysms. FD-CTA may be considered as a non-invasive alternative to the gold standard 2D DSA in selected patients that require follow up imaging after stenting.
EVALuna2:14478

Flat-Panel Computed Tomography (DYNA-CT) in Neuroradiology. From High-Resolution Imaging of Implants to One-Stop-Shopping for Acute Stroke - Dörfler, Arnd; Gölitz, Philipp; Engelhorn, Tobias; Kloska, Stephan; Struffert, Tobias (Clinical Neuroradiology, 2015)
Originally aimed at improving standard radiography by providing higher absorption efficiency and a wider dynamic range, flat-panel detector technology has meanwhile got widely accepted in the neuroradiological community. Especially flat-panel detector computed tomography (FD-CT) using rotational C-arm mounted flat-panel detector technology is capable of volumetric imaging with a high spatial resolution. By providing CT-like images of the brain within the angio suite, FD-CT is able to rapidly visualize hemorrhage and may thus improve complication management without the need of patient transfer. As "Angiographic CT" FD-CT may be helpful during many diagnostic and neurointerventional procedures and for noninvasive monitoring and follow-up. In addition, spinal interventions and high-resolution imaging of the temporal bone might also benefit from FD-CT. Finally, using novel dynamic perfusion and angiographic protocols, FD-CT may provide functional information on brain perfusion and vasculature with the potential to replace standard imaging in selected acute stroke patients.
EVALuna2:22997

Flat panel detector angiographic CT for stent-assisted coil embolization of broad-based cerebral aneurysms - Richter, Gregor; Engelhorn, Tobias; Struffert, Tobias; Dölken, Marc; Ganslandt, Oliver; Hornegger, Joachim; Kalender, Willi Alfred; Dörfler, Arnd (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The purpose of this work was to evaluate angiographic CT (ACT) in the combined application of a self-expanding neurovascular stent and detachable platinum coils in the management of broad-based and fusiform intracranial aneurysms. MATERIALS AND METHODS: Eleven patients harboring wide-necked intracranial aneurysms were treated with a flexible self-expanding neurovascular stent and subsequent aneurysm embolization with platinum microcoils. ACT was performed after the interventional procedure to analyze stent position and the relationship of coils to the stent. Postprocessing included multiplanar reconstructions (MPRs) and maximum intensity projections (MIPs). ACT volume datasets were postprocessed for soft tissue visualization. RESULTS: Accurate stent placement with subsequent coil occlusion of the aneurysms was feasible in all of the patients. Similar to nonsubtracted digital subtraction angiography (DSA) images, radiopaque platinum stent markers showed excellent visibility in ACT as well. The stent struts themselves, hardly visible in nonsubtracted DSA, were visible in MPRs and MIPs of ACT in all of the patients. In aneurysms larger than 10 mm in diameter, accurate stent assessment at the level of the coils was limited due to beam hardening artifacts. Postprocedural ACT in all of the patients did not reveal any evidence of procedure-related intracranial hemorrhage. CONCLUSION: ACT provides cross-sectional, 3D visualization of endovascular stents otherwise hardly visible with plain fluoroscopy. ACT enables us to accurately determine stent position, which may be helpful in complex stent-assisted aneurysm coiling procedures. However, in aneurysms larger than 10 mm in diameter, beam hardening artifacts caused by the endoaneurysmal coil package impair visibility of the stent. Further data are necessary to evaluate the usefulness of ACT in stent-assisted aneurysm coiling.

Flat Panel Detector Computed Tomography-Guided Placement of External Ventricular Drains Using the BrainLAB Headband and Precalibrated Disposable Stylet Instrument: A Cadaveric Feasibility Study - Feulner, Julian; Lang, Stefan; Buder, Thomas; Struffert, Tobias; Buchfelder, Michael; Brandner, Sebastian (World Neurosurgery, 2018)
BACKGROUND: The standard freehand method for the insertion of external ventricular drains (EVDs) is associated with high rates of incorrect placement. Use of neuronavigation has been shown to reduce the rates of inaccurately positioned EVDs. We present a novel neuronavigation-based approach for EVD placement using flat panel detector computed tomography (FDCT) imaging. METHODS: Four cadaveric heads were used for neuronavigated placement of EVDs using the BrainLAB reference headband in combination with laser surface registration and the precalibrated disposable stylet. In 2 cases, conventional multislice CT imaging was performed to reference neuronavigation. In the other 2 cases, preprocedural imaging was performed with FDCT. After inserting the EVDs, all heads were examined again with the identical imaging method as used before the procedure, followed by evaluation of catheter position. RESULTS: Our data demonstrate that FDCT imaging provides adequate image quality for referencing neuronavigation and performing navigated neurosurgery. All EVDs showed an optimal position in the ipsilateral frontal horn. Use of a BrainLAB reference headband combined with laser surface registration and the precalibrated disposable stylet affords the advantage of not requiring rigid fixation in a clamp. CONCLUSIONS: Our presented method is fast, accurate, and easy to use. Furthermore, this study is the first to demonstrate that navigated neurosurgery can be performed on the basis of FDCT imaging.
EVALuna2:212791

Flow-diverting stents allow efficient treatment of unruptured, intradural dissecting aneurysms of the vertebral artery: An explanatory approach using in vivo flow analysis - Gölitz, Philipp; Struffert, Tobias; Eyüpoglu, Ilker Yasin; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Interventional Neuroradiology, 2016)
Our study aimed to evaluate the efficiency of flow-diverting stents (FDS) in treating unruptured, intradural dissecting aneurysms of the vertebral artery (VADAs). Additionally, the effect of FDS on the aneurysmal flow pattern was investigated by performing in vivo flow analysis using parametric color coding (PCC).We evaluated 11 patients with unruptured, intradural VADAs, treated with FDS. Pre- and postinterventional DSA-series were postprocessed by PCC, and time-density curves were calculated. The parameters aneurysmal inflow-velocity, outflow-velocity and relative time-to-peak (rTTP) were calculated. Pre- and postinterventional values were compared and correlated with the occlusion rate after six months.Follow-up DSA detected 10 aneurysms occluded, meaning an occlusion rate of 91%. No procedure-related morbidity and mortality was found. Flow analyses revealed a significant reduction of aneurysmal inflow- velocity and prolongation of rTTP after FDS deployment. Concerning aneurysm occlusion, the postinterventional outflow-velocity turned out to be a marginally statistically significant predictor. A definite threshold value (-0.7 density change/s) could be determined for the outflow-velocity that allows prediction of complete aneurysm occlusion with high sensitivity and specificity (100%).Using FDS can be considered an efficient and safe therapy option in treating unruptured, intradural VADA. From in vivo flow analyses the postinterventional aneurysmal outflow-velocity turned out to be a potential predictor for later complete aneurysm occlusion. Here, it might be possible to determine a threshold value that allows prediction of aneurysm occlusion with high specificity and sensitivity. As fast, applicable and easy-to-handle tool, PCC could be used for procedural monitoring and might contribute to further treatment optimization.
EVALuna2:22441

Fluid flow simulation on the Cell Broadband Engine using the lattice Boltzmann method - Stürmer, Markus; Götz, Jan; Richter, G.; Dörfler, Arnd; Rüde, Ulrich (Computers & Mathematics with Applications, 2009)
In this paper we present a fast lattice Boltzmann fluid solver that has been performance optimized and tailored for the Cell Broadband Engine Architecture. Many design decisions were motivated by the long range objective to simulate blood flow in human blood vessels, especially in aneurysms, but have proven to be much more generally applicable. After explaining implementation details and how they were influenced by the target platform, the performance and memory requirements of this prototype solver are evaluated. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.IMMD.lsinfs.fluidf
Keywords: Aneurysm; Blood flow; CBEA; Cell processor; Hemodynamics; High performance computing; Lattice Boltzmann

Fluid suppression in amide proton transfer-weighted (APTw) CEST imaging: New theoretical insights and clinical benefits - Schüre, Jan-Rüdiger; Casagranda, Stefano; Sedykh, Maria; Liebig, Patrick; Papageorgakis, Christos; Mancini, Laura; Bisdas, Sotirios; Nichelli, Lucia; Pinter, Nandor; Mechtler, Laszlo; Jafari, Ramin; Boddaert, Nathalie; et al. (Magnetic Resonance in Medicine, 2023)
Purpose: Amide proton transfer-weighted (APTw) MRI at 3T provides a unique contrast for brain tumor imaging. However, APTw imaging suffers from hyperintensities in liquid compartments such as cystic or necrotic structures and provides a distorted APTw signal intensity. Recently, it has been shown that heuristically motivated fluid suppression can remove such artifacts and significantly improve the readability of APTw imaging. Theory and Methods: In this work, we show that the fluid suppression can actually be understood by the known concept of spillover dilution, which itself can be derived from the Bloch-McConnell equations in comparison to the heuristic approach. Therefore, we derive a novel post-processing formula that efficiently removes fluid artifact, and explains previous approaches. We demonstrate the utility of this APTw assessment in silico, in vitro, and in vivo in brain tumor patients acquired at MR scanners from different vendors. Results: Our results show a reduction of the CEST signals from fluid environments while keeping the APTw-CEST signal intensity almost unchanged for semi-solid tissue structures such as the contralateral normal appearing white matter. This further allows us to use the same color bar settings as for conventional APTw imaging. Conclusion: Fluid suppression has considerable value in improving the readability of APTw maps in the neuro-oncological field. In this work, we derive a novel post-processing formula from the underlying Bloch-McConnell equations that efficiently removes fluid artifact, and explains previous approaches which justify the derivation of this metric from a theoretical point of view, to reassure the scientific and medical field about its use.
CRIS-Team Scopus Importer:2023-12-22
Keywords: APTw CEST imaging; fluid suppression; MTRasym; post-processing

FRED Flow Diverter: A Study on Safety and Efficacy in a Consecutive Group of 50 Patients - Lücking, Hannes; Engelhorn, Tobias; Lang, Stefan; Gölitz, Philipp; Kloska, Stephan; Roessler, Karl; Dörfler, Arnd (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Endovascular flow diverters are increasingly used for the treatment of cerebral aneurysms. We assessed the safety and efficacy of the Flow-Redirection Endoluminal Device (FRED) in a consecutive series of 50 patients. MATERIALS AND METHODS: Inclusion criteria were wide-neck, blister-like, or fusiform/dissecting aneurysms independent of size, treated with the FRED between February 2014 and May 2015. Assessment criteria were aneurysm occlusion, manifest ischemic stroke, bleeding, or death. The occlusion rate was assessed at 3 months with flat panel CT and at 6 months with DSA by using the Raymond classification and the O'Kelly-Marotta grading scale. RESULTS: Fifty patients with 52 aneurysms were treated with 54 FREDs; 20 patients were treated with the FRED and coils. Aneurysm size ranged from 2.0 to 18.5 mm. Deployment of the FRED was successful in all cases. There were no device-associated complications. One patient developed mild stroke symptoms that fully receded within days. There have been no late-term complications so far and no treatment-related mortality. Initial follow-up at 3 months showed complete occlusion in 72.3% of the overall study group, Six-month follow-up showed total and remnant-neck occlusion in 87.2% of patients, distributed over 81.5% of the FRED-only cases and 95.0% of the cases with combined treatment. CONCLUSIONS: The FRED flow diverter is a safe device for the treatment of cerebral aneurysms of various types. Our data reveal high occlusion rates at 3 and 6 months, comparable with those in other flow diverters. Long-term occlusion rates are expected.
EVALuna2:33142

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

FSRT vs. SRS in Brain Metastases—Differences in Local Control and Radiation Necrosis—A Volumetric Study - Putz, Florian; Weissmann, Thomas; Oft, Dominik; Schmidt, Manuel; Roesch, Johannes; Siavooshhaghighi, Hadi; Filimonova, Irina; Schmitter, Charlotte; Mengling, Veit; Bert, Christoph; Frey, Benjamin; Lettmaier, Sebastian; et al. (Frontiers in Oncology, 2020)
Background: While the role of stereotactic radiotherapy for brain metastases is increasing, evidence on the comparative efficacy and safety of fractionated stereotactic radiotherapy (FSRT) and single-session radiosurgery (SRS) is scarce. Methods: Longitudinal volumetric analysis was performed in a consecutive cohort of 120 patients and 190 brain metastases (>0.065 cm3 in volume / > 5 mm in diameter) treated exclusively with FSRT (n = 98) and SRS (n = 92), respectively. A total of 972 tumor segmentations was used, averaging 5.1 time points per metastasis. Progression was defined using a volumetric extension of the RANO-BM criteria. Local control and radionecrosis were compared for lesions treated with FSRT and SRS, respectively. Results: Metastases treated with FSRT were significantly larger at baseline (mean, 4.66 vs. 0.40 cm3, p < 0.001). Biologically effective dose (BED) for metastases (α/β = 12, linear-quadratic-cubic model) was significantly associated with local control, whereas BED for normal brain (α/β = 2, linear-quadratic model) was significantly associated with radionecrosis. Median time to local progression was 22.9 months in the FSRT group compared to 14.5 months in the SRS group (p = 0.022). Overall radionecrosis rate at 12 months was 3.4% for FSRT and 14.8% for SRS (p = 0.010). Radionecrosis °IV requiring resection with histologic proof of radiation necrosis also was significantly reduced in the FSRT group (FSRT 0.0% vs. SRS 3.9%, p = 0.041). In multivariate analysis, FSRT was associated with reduced risk of progression (HR 0.47, p = 0.015) and reduced risk of radionecrosis (HR 0.18, p = 0.045). Conclusions: This volumetric study provides initial evidence that the improvements in therapeutic ratio expected for FSRT in larger brain metastases, might equally extend into the domain of smaller metastases, traditionally less considered for fractionated treatment. FSRT might constitute an important tool to further increase local control and reduce radionecrosis risk in stereotactic radiotherapy for brain metastases, that should be assessed in randomized intervention trials.
CRIS-Team Scopus Importer:2020-10-30
Keywords: brain metastases; fractionated stereotactic radiotherapy; radiobiological aspects; segmentation; stereotactic radiosurgery (SRS); stereotactic radiotherapy (SRT); volumetric analysis

Functional Brain Imaging Reveals Rapid Blockade of Abdominal Pain Response Upon Anti-TNF Therapy in Crohn's Disease - Heß, Andreas; Roesch, Julie; Saake, Marc; Sergeeva, Marina; Hirschmann, Simon; Neumann, Helmut; Dörfler, Arnd; Neurath, Markus; Atreya, Raja (Gastroenterology, 2015)
EVALuna2:2003

Functional connectivity reveals altered activation of distinct brain areas in pruritus of cholestasis - Kremer, Andreas; Buchwald, Theresa; Vetter, Marcel; Dörfler, Arnd; Forster, Clemens (JOURNAL OF HEPATOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-26

Functional Long-Term Outcome after Left- versus Right-Sided Intracerebral Hemorrhage - Beuscher, Vanessa D.; Kuramatsu, Joji; Gerner, Stefan; Kohn, Julia; Lücking, Hannes; Kloska, Stephan; Huttner, Hagen (Cerebrovascular Diseases, 2017)
Hemispheric location might influence outcome after intracerebral hemorrhage (ICH). INTERACT suggested higher short-term mortality in right hemispheric ICH, yet statistical imbalances were not addressed. This study aimed at determining the differences in long-term functional outcome in patients with right- vs. left-sided ICH with a priori-defined sub-analysis of lobar vs. deep bleedings.Data from a prospective hospital registry were analyzed including patients with ICH admitted between January 2006 and August 2014. Data were retrieved from institutional databases. Outcome was assessed using the modified Rankin Scale (mRS) score. Outcome measures (long-term mortality and functional outcome at 12 months) were correlated with ICH location and hemisphere, and the imbalances of baseline characteristics were addressed by propensity score matching.A total of 831 patients with supratentorial ICH (429 left and 402 right) were analyzed. Regarding clinical baseline characteristics in the unadjusted overall cohort, there were differences in disfavor of right-sided ICH (antiplatelets: 25.2% in left ICH vs. 34.3% in right ICH; p < 0.01; previous ischemic stroke: 14.7% in left ICH vs. 19.7% in right ICH; p = 0.057; and presence/extent of intraventricular hemorrhage: 45.0% in left ICH vs. 53.0% in right ICH; p = 0.021; Graeb-score: 0 [0-4] in left ICH vs. 1 [0-5] in right ICH; p = 0.017). While there were no differences in mortality and in the proportion of patients with favorable vs. unfavorable outcome (mRS 0-3: 142/375 [37.9%] in left ICH vs. 117/362 [32.3%] in right ICH; p = 0.115), patients with left-sided ICH showed excellent outcome more frequently (mRS 0-1: 64/375 [17.1%] in left ICH vs. 43/362 [11.9%] in right ICH; p = 0.046) in the unadjusted analysis. After adjusting for confounding variables, a well-balanced group of patients (n = 360/hemisphere) was compared showing no differences in long-term functional outcome (mRS 0-3: 36.4% in left ICH vs. 33.9% in right ICH; p = 0.51). Sub-analyses of patients with deep vs. lobar ICH revealed also no differences in outcome measures (mRS 0-3: 53/151 [35.1%] in left deep ICH vs. 53/165 [32.1%] in right deep ICH; p = 0.58).Previously described differences in clinical end points among patients with left- vs. right-hemispheric ICH may be driven by different baseline characteristics rather than by functional deficits emerging from different hemispheric functions affected. After statistical corrections for confounding variables, there was no impact of hemispheric location on functional outcome after ICH.
EVALuna2:22480

Fusion of Preoperative MRI and Postoperative FD-CT for Direct Evaluation of Cochlear Implants: An Analysis at 1.5 T and 3 T - Eisenhut, Felix; Kleibe, Isabella; Hornung, Joachim; Iro, Heinrich; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Clinical Neuroradiology, 2019)
Aim: This study was carried out to evaluate the diagnostic value of merging preoperative magnetic resonance imaging (MRI) with postoperative flat-panel computed tomography (FD-CT) and compare it to standard postoperative FD-CT for assessment of cochlear implant (CI) insertion. Methods: The T2-weighted (T2w) constructive interference in steady state (CISS) data sets of preoperative 1.5 T and 3 T MRI scans of CI patients with both regular and adverse implant spiralization were co-registered with the corresponding postoperative FD-CT data sets using defined anatomic landmarks. These merged FD-CT/MRI volumes (CMV) were compared to the corresponding postoperative FD-CT MPRs in consensus reading with respect to qualitative, i.e. scala tympani spiralization, scala vestibuli spiralization, scalar translocation and quantitative, i.e. distance of the last electrode to the lateral cochlea wall (D1) distance of the 2nd/5th electrode to the basal cochlear wall (D2) and the transition point (TP) of the scalar translocation, parameters. Results: In total 30 patients (n 1.5T MRI = 18 patients; n 3T MRI = 12 patients) were included in the analysis. In all cases both CMVs and FD-CT MPRs were generated. Qualitative analysis of intracochlear CI position with CMVs (both 1.5 T and 3 T) and FD-CT was equivalent: In 20 patients the CI showed a regular implant spiralization, in 10 cases a scalar translocation was identified with both CMVs and FD-CT. Quantitative analysis showed a high level of congruency between CMVs (both 1.5 T and 3T) and FD-CT for fusion accuracy (D1: mean FD-CT D1 = 1.30 ± 0.7 mm; mean CMV D1 = 1.27 ± 0.77 mm, correlation r = 0.94, p < 0.0001; D2: mean FD-CT D2 = 1.17 ± 0.34 mm; mean CMV D2 = 1.10 ± 0.31 mm, correlation r = 0.89, p < 0.0001) and TP of the scalar translocation (mean FD-CT = 126.0 ± 59.25°, mean CMV = 117.0 ± 52.82°, correlation r = 0.95, p < 0.0001). Conclusion: The co-registration of preoperative 1.5 and 3 T MRI with postoperative FD-CT enables a direct evaluation of the position of a CI equivalent to the current standard FD-CT. Despite the fact that CMV provided no additional diagnostic value in this series, regardless whether preoperative 1.5 or 3 T MRI was used for co-registration, it might help to simplify postoperative CI diagnostics.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Cochlear implant; Flat panel computed tomography; Magnetic resonance imaging; Merging; Scalar translocation

Germany’s journey toward 14 Tesla human magnetic resonance - Ladd, Mark E.; Quick, Harald H.; Speck, Oliver; Bock, Michael; Dörfler, Arnd; Forsting, Michael; Hennig, Jürgen; Ittermann, Bernd; Möller, Harald E.; Nagel, Armin M.; Niendorf, Thoralf; Remy, Stefan; et al. (Magnetic Resonance Materials in Physics Biology and Medicine, 2023)
Multiple sites within Germany operate human MRI systems with magnetic fields either at 7 Tesla or 9.4 Tesla. In 2013, these sites formed a network to facilitate and harmonize the research being conducted at the different sites and make this technology available to a larger community of researchers and clinicians not only within Germany, but also worldwide. The German Ultrahigh Field Imaging (GUFI) network has defined a strategic goal to establish a 14 Tesla whole-body human MRI system as a national research resource in Germany as the next progression in magnetic field strength. This paper summarizes the history of this initiative, the current status, the motivation for pursuing MR imaging and spectroscopy at such a high magnetic field strength, and the technical and funding challenges involved. It focuses on the scientific and science policy process from the perspective in Germany, and is not intended to be a comprehensive systematic review of the benefits and technical challenges of higher field strengths.
CRIS-Team Scopus Importer:2023-04-21
Keywords: 14T; Extremely high field; GUFI; MRI; Ultrahigh field

Glaucoma classification based on histogram analysis of diffusion tensor imaging measures in the optic radiation - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Springer-verlag, 2011)
Glaucoma is associated with axonal degeneration of the optic nerve leading to visual impairment. This impairment can progress to a complete vision loss. The transsynaptic disease spread in glaucoma extends the degeneration process to different parts of the visual pathway. Most of glaucoma diagnosis focuses on the eye analysis, especially in the retina. In this work, we propose a system to classify glaucoma based on visual pathway analysis. The system utilizes diffusion tensor imaging to identify the optic radiation. Diffusion tensor-derived indices describing the underlying fiber structure as well as the main diffusion direction are used to characterize the optic radiation. Features are extracted from the histograms of these parameters in regions of interest defined on the optic radiation. A support vector machine classifier is used to rank the extracted features according to their discrimination ability between glaucoma patients and healthy subjects. The seven highest ranked features are used as inputs to a logistic regression classifier. The system is applied to two age-matched groups of 39 glaucoma subjects and 27 normal controls. The evaluation is performed using a 10-fold cross validation scheme. A classification accuracy of 81.8% is achieved with an area under the ROC curve of 0.85. The performance of the system is competitive to retina based classification systems. However, this work presents a new direction in detecting glaucoma using visual pathway analysis. This analysis is complementary to eye examinations and can result in improvements in glaucoma diagnosis, detection, and treatment. © 2011 Springer-Verlag.

Glaucoma classification based on visual pathway analysis using diffusion tensor imaging - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Magnetic Resonance Imaging, 2013)
Most of the existing methods for diagnosing glaucoma analyze the eye with a main focus on the retina, despite the transsynaptic nature of the fiber degeneration caused by glaucoma. Thus, they ignore a significant part of the visual system represented by the visual pathway in the brain. The advances in neuroimaging, especially diffusion tensor imaging (DTI), enable the identification and characterization of white matter fibers. In this work, we propose a system based on DTI analysis of the visual pathway fibers in the optic radiation for detecting and discriminating different glaucoma entities. The optic radiation is identified semi-automatically. DTI provides information about the fiber orientation as well as a set of derived parameters describing the degree of diffusion anisotropy and diffusivity. Features for each DTI derived measure are extracted from a specified region of interest on the optic radiation. The features are grouped into three sets: Histogram, co-occurrence matrices, and Laws features. For feature selection, the features are ranked using a support vector machine classifier. The highest ranked features are used for classification. A support vector machine classifier is used for classification in a 10-fold cross validation setup. The system is applied to three age-matched subjects' categories containing 27 healthy, 39 primary open angle glaucoma (POAG), and 18 normal tension glaucoma (NTG) subjects. The discrimination accuracy between healthy and glaucoma (POAG and NTG) subjects is 94.1% with an area under the ROC of 0.97. Classification accuracy of 92.4% is obtained for the normal and the POAG groups while it increased to 100% in case of healthy and NTG groups. In addition, the system could differentiate between glaucoma types (POAG and NTG) with an accuracy of 98.3%. A complementary analysis was performed to estimate the selection bias in the obtained accuracy. The bias ranged from 10% to 20% depending on the group pair under consideration. The classification results indicate the high performance of the system compared to retina-based glaucoma detection systems. The proposed approach utilizes visual pathway analysis rather than the conventional eye analysis which presents a new trend in glaucoma detection. Analyzing the entire visual system could provide significant information that can improve the glaucoma examination flow and treatment. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Diffusion tensor imaging; Glaucoma; Optic radiation; Visual pathway; Classification; Texture features

Grehlin concentrations correlate with hunger and craving ratings following oral ingestion of macronutrients - Thürauf, Norbert; Bachlechner, Stephan; Denzer-Lippmann, Melanie; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes (CHEMICAL SENSES, 2019)
CRIS-Team WoS Importer:2019-03-26

Guided Noise Reduction for Spectral CT with Energy-Selective Photon Counting Detectors - Manhart, Michael; Fahrig, Rebecca; Hornegger, Joachim; Dörfler, Arnd; Maier, Andreas (Proceedings of the Third CT Meeting, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.guided_6

Guided Noise Reduction with Streak Removal for High Speed Flat Detector CT Perfusion - Manhart, Michael; Aichert, André; Kowarschik, Markus; Deuerling-Zheng, Yu; Struffert, Tobias; Dörfler, Arnd; Maier, Andreas; Hornegger, Joachim (Proceedings NSS/MIC 2013, 2013)
Tissue perfusion measurement using C-arm angiography systems capable of CT-like imaging (flat detector CT (FD-CT)) is a novel technique with high potential benefit for catheter-guided treatment of stroke in the interventional suite. New high speed protocols (HSP) with increased C-arm rotation speed enable fast acquisitions of FD-CT volumes and allow for sampling the contrast flow with improved temporal resolution. However, the peak contrast attenuation values of brain tissue typically lie in a range of 5-30 HU. Thus perfusion imaging is very sensitive to noise. Recently we introduced the FDK-JBF denoising technique based on Feldkamp (FDK) reconstruction followed by denoising in volume space using joint bilateral filtering (JBF). In the evaluation FDK-JBF achieved comparable results to algebraic techniques, but is computationally less costly. Yet the angular sampling of the projection data in the HSP is coarse, which leads to streak artifacts in the reconstructed volumes. Mask volumes are subtracted from the contrast agent enhanced (bolus) volumes and the streak artifacts are subtracted out if the patient does not move during the acquisition. However, in case of motion the streak artifacts will not be identical in the mask and bolus volumes. We show that these streaks can lead to severe artifacts in the perfusion maps and describe a novel technique for streak removal (SR), which is based on streak detection by using time-contrast curve analysis.We evaluated the FDK-SR-JBF algorithm in a phantom and a patient study and show that noise and streaks can be reduced within a short computation time. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD5.guided_5
Keywords: Flat detector CT; noise reduction; Perfusion imaging; stroke treatment

Heart Failure in Ischemic Stroke: Relevance for Acute Care and Outcome - Siedler, Gabriela; Sommer, Kim; Macha, Kosmas; Marsch, Armin; Breuer, Lorenz; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd; Arnold, Martin (Stroke, 2019)
Background and Purpose- Heart failure (HF) in patients with acute ischemic stroke constitutes the source of various detrimental pathophysiologic mechanisms including prothrombotic and proinflammatory states, worsening of cerebral tissue oxygenation, and hemodynamic impairment. In addition, HF might affect the safety and efficacy of the acute recanalization stroke therapies. Methods- Patients treated with intravenous recombinant tissue-type plasminogen activator or mechanical recanalization at a universitary stroke center were included into a prospective registry. Patients received cardiological evaluation, including echocardiography, during acute care. Functional outcome was assessed after 90 days by structured telephone interviews. Safety and efficacy of intravenous thrombolysis and mechanical thrombectomy were investigated among patients with HF and compared with patients with normal cardiac function after propensity score matching. Results- One thousand two hundred nine patients were included. HF was present in 378 patients (31%) and an independent predictor of unfavorable functional outcome. Recanalization rates were equal among patients with HF after intravenous thrombolysis and after mechanical recanalization or combined treatment. The rate of secondary intracranial hemorrhage was not different (7% versus 8%; P=0.909 after thrombolysis and 15% versus 20%, P=0.364 after mechanical recanalization or combined therapy). Early mortality within 48 hours after admission was equal (<1.5% in both groups). Conclusions- In this real-world cohort of patients with stroke, HF was an independent predictor of unfavorable functional long-term outcome, while the safety and efficacy of intravenous thrombolysis and mechanical recanalization appeared unaffected.
EVALuna2:204477

Hematoma Characteristics and Functional Outcome Do Not Differ in NOAC- Versus VKA-Associated Intracerebral Hemorrhage - Gerner, Stefan; Lücking, Hannes; Köhrmann, Martin; Huttner, Hagen (2016)
EVALuna2:22585

Hematoma enlargement characteristics in deep versus lobar intracerebral hemorrhage - Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Sprügel, Maximilian; Röder, Sebastian; Madžar, Dominik; Hagen, Manuel; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Annals of Clinical and Translational Neurology, 2020)
Objective: Hematoma enlargement (HE) is associated with clinical outcomes after supratentorial intracerebral hemorrhage (ICH). This study evaluates whether HE characteristics and association with functional outcome differ in deep versus lobar ICH. Methods: Pooled analysis of individual patient data between January 2006 and December 2015 from a German-wide cohort study (RETRACE, I + II) investigating ICH related to oral anticoagulants (OAC) at 22 participating centers, and from one single-center registry (UKER-ICH) investigating non-OAC-ICH patients. Altogether, 1954 supratentorial ICH patients were eligible for outcome analyses, which were separately conducted or controlled for OAC, that is, vitamin-K-antagonists (VKA, n = 1186) and non-vitamin-K-antagonist-oral-anticoagulants (NOAC, n = 107). Confounding was addressed using propensity score matching, cox regression modeling and multivariate modeling. Main outcomes were occurrence, extent, and timing of HE (>33%/>6 mL) and its association with 3-month functional outcome. Results: Occurrence of HE was not different after deep versus lobar ICH in patients with non-OAC-ICH (39/356 [11.0%] vs. 36/305 [11.8%], P = 0.73), VKA-ICH (249/681 [36.6%] vs. 183/505 [36.2%], P = 0.91), and NOAC-ICH (21/69 [30.4%] vs. 12/38 [31.6%], P = 0.90). HE extent did not differ after non-OAC-ICH (deep:+59% [40–122] vs. lobar:+74% [37–124], P = 0.65), but both patients with VKA-ICH and NOAC-ICH showed greater HE extent after deep ICH [VKA-ICH, deep: +94% [54–199] vs. lobar: +56% [35–116], P < 0.001; NOAC-ICH, deep: +74% [56–123] vs. lobar: +40% [21–49], P = 0.001). Deep compared to lobar ICH patients had higher HE hazard during first 13.5 h after onset (Hazard ratio [HR]: 1.85 [1.03–3.31], P = 0.04), followed by lower hazard (13.5–26.5 h, HR: 0.46 [0.23–0.89], P = 0.02), and equal hazard thereafter (HR: 0.96 [0.56–1.65], P = 0.89). Odds ratio for unfavorable outcome was higher after HE in deep (4.31 [2.71–6.86], P < 0.001) versus lobar ICH (2.82 [1.71–4.66], P < 0.001), and only significant after small-medium (1st volume-quarter, deep: 3.09 [1.52–6.29], P < 0.01; lobar: 3.86 [1.35–11.04], P = 0.01) as opposed to large-sized ICH (4th volume-quarter, deep: 1.09 [0.13–9.20], P = 0.94; lobar: 2.24 [0.72–7.04], P = 0.17). Interpretation: HE occurrence does not differ among deep and lobar ICH. However, compared to lobar ICH, HE after deep ICH is of greater extent in OAC-ICH, occurs earlier and may be of greater clinical relevance. Overall, clinical significance is more apparent after small–medium compared to large-sized bleedings.
CRIS-Team Scopus Importer:2020-03-17

Heparin for prophylaxis of venous thromboembolism in intracerebral haemorrhage - Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2019)
Objective: To determine the occurrence of intracranial haemorrhagic complications (IHC) on heparin prophylaxis (low-dose subcutaneous heparin, LDSH) in primary spontaneous intracerebral haemorrhage (ICH) (not oral anticoagulation-associated ICH, non-OAC-ICH), vitamin K antagonist (VKA)-associated ICH and non-vitamin K antagonist oral anticoagulant (NOAC)-associated ICH. Methods: Retrospective cohort study (RETRACE) of 22 participating centres and prospective single-centre study with 1702 patients with VKA-associated or NOAC-associated ICH and 1022 patients with non-OAC-ICH with heparin prophylaxis between 2006 and 2015. Outcomes were defined as rates of IHC during hospital stay among patients with non-OAC-ICH, VKA-ICH and NOAC-ICH, mortality and functional outcome at 3 months between patients with ICH with and without IHC. Results: IHC occurred in 1.7% (42/2416) of patients with ICH. There were no differences in crude incidence rates among patients with VKA-ICH, NOAC-ICH and non-OAC-ICH (log-rank p=0.645; VKA-ICH: 27/1406 (1.9%), NOAC-ICH 1/130 (0.8%), non-OAC-ICH 14/880 (1.6%); p=0.577). Detailed analysis according to treatment exposure (days with and without LDSH) revealed no differences in incidence rates of IHC per 1000 patient-days (LDSH: 1.43 (1.04-1.93) vs non-LDSH: 1.32 (0.33-3.58), conditional maximum likelihood incidence rate ratio: 1.09 (0.38-4.43); p=0.953). Secondary outcomes showed differences in functional outcome (modified Rankin Scale=4-6: IHC: 29/37 (78.4%) vs non-IHC: 1213/2048 (59.2%); p=0.019) and mortality (IHC: 14/37 (37.8%) vs non-IHC: 485/2048 (23.7%); p=0.045) in disfavour of patients with IHC. Small ICH volume (OR: volume <4.4 mL: 0.18 (0.04-0.78); p=0.022) and low National Institutes of Health Stroke Scale (NIHSS) score on admission (OR: NIHSS <4: 0.29 (0.11-0.78); p=0.014) were significantly associated with fewer IHC. Conclusions: Heparin administration for venous thromboembolism (VTE) prophylaxis in patients with ICH appears to be safe regarding IHC among non-OAC-ICH, VKA-ICH and NOAC-ICH in this observational cohort analysis. Randomised controlled trials are needed to verify the safety and efficacy of heparin compared with other methods for VTE prevention.
CRIS-Team Scopus Importer:2019-05-02
Keywords: cerebrovascular disease; critical care; intracerebral heamorrhage; stroke

High Detection Accuracy of an optimized 3D Convolutional Neural Network for Auto Detection and Auto Segmentation of Brain Metastases - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmitter, Charlotte; Semrau, Sabine; Lettmaier, Sebastian; Masitho, Siti; Grigo, Johanna; Schmidt, Manuel; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

High-Resolution 3D-constructive interference in steady-state MR imaging and 3D time-of-flight MR angiography in neurovascular compression: A comparison between 3T and 1.5T - Dörfler, Arnd; Garcia, M.; Naraghi, Ramin; Zumbrunn, T.; Roesch, J.; Hastreiter, Peter (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: High-resolution MR imaging is useful for diagnosis and preoperative planning in patients with NVC. Because high-field MR imaging promises higher SNR and resolution, the aim of this study was to determine the value of high-resolution 3D-CISS and 3D-TOF MRA at 3T compared with 1.5T in patients with NVC. MATERIALS AND METHODS: Forty-seven patients with NVC, trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia were examined at 1.5T and 3T, including high-resolution 3D-CISS and 3D-TOF MRA sequences. Delineation of anatomic structures, overall image quality, severity of artifacts, visibility of NVC, and assessment of the SNR and CNR were compared between field strengths. RESULTS: SNR and CNR were significantly higher at 3T (P < .001). Significantly better anatomic conspicuity, including delineation of CNs, nerve branches, and assessment of small vessels, was obtained at 3T (P < .02). Severity of artifacts was significantly lower at 3T (P < .001). Consequently, overall image quality was significantly higher at 3T. NVC was significantly better delineated at 3T (P < .001). Six patients in whom NVC was not with certainty identifiable at 1.5T were correctly diagnosed at 3T. CONCLUSIONS: Patients with NVC may benefit from the higher resolution and greater sensitivity of 3T for preoperative assessment of NVC, and 3T may be of particular value when 1.5T is equivocal.
CRIS-Team Scopus Importer:2022-08-05

High-resolution diffusion tensor-imaging indicates asymmetric microstructural disorganization within substantia nigra in early Parkinson's disease - Knossalla, Frauke; Kohl, Zacharias; Winkler, Jürgen; Schwab, Stefan; Schenk, Thomas; Engelhorn, Tobias; Dörfler, Arnd; Gölitz, Philipp (Journal of Clinical Neuroscience, 2018)
BACKGROUND AND PURPOSE: Parkinson's disease (PD) is characterised by neuropathological degenerative changes in the substantia nigra (SN). Our study aimed to evaluate whether high-resolution diffusion tensor-imaging (DTI) can detect anatomical biomarkers in early-stage PD, and has the potential to visualize asymmetry effects comparable to the 123I-FP-CIT SPECT (DaTSCAN). METHODS: Ten early-stage PD patients with mild disease severity and ten age- and gender-matched healthy controls were examined with a high-resolution DTI protocol at a 3 Tesla MRI scanner to assess fractional anisotropy (FA) values in the ventral, middle and dorsal region of SN. In addition, a subgroup of 5 PD patients underwent a DaTSCAN. RESULTS: PD subjects showed reduced FA values in all SN regions compared to controls, but post hoc analysis revealed a significant reduction (p = .032) in the dorsal region. There was no significant correlation between clinical data and FA values. Subgroup analysis of PD patients with asymmetric radioligand uptake in the DaTSCAN demonstrated also significant asymmetric FA values (p = .027) in the dorsal region of SN. CONCLUSIONS: Our results provide preliminary evidence that high-resolution DTI can detect in early-stage PD patients with mild disease severity an anatomical biomarker in the dorsal region of SN, indicating microstructural disorganization. This biomarker, discriminating potentially in vivo between patients and healthy people, could be valuable for early PD diagnosis. If asymmetric radioligand uptake in the DaTSCAN was present, also asymmetry effects in the dorsal region of SN were obtained by DTI. These findings might contribute to improve effectiveness in diagnosing and monitoring PD.
EVALuna2:34272

High-resolution magnetic resonance imaging in isolated, traumatic oculomotor nerve palsy: A case report - Eisenhut, Felix; Gerner, Stefan; Gölitz, Philipp; Dörfler, Arnd; Seifert, Frank (Radiology Case Reports, 2021)
Traumatic, isolated oculomotor nerve palsy is a rare clinical finding and only few reports demonstrate associated magnetic resonance imaging (MRI) findings. Here, we present the case of a 70-year-old woman with left-sided oculomotor nerve palsy following a mild head trauma due to an e-bike accident. Post-traumatic cerebral computed tomography revealed punctiform hemorrhage in the left interpeduncular cistern and the following MRI confirmed an intraneural hemorrhage of the left oculomotor nerve. Nine weeks later, the follow-up MRI showed progressive atrophy and contrast-enhancement of the left oculomotor nerve. To support functional recovery, a treatment with intravenous corticosteroids was started. Six months later, the patient presented with improved oculomotor nerve function and partial recovery of ptosis and diplopia. In accordance, MRI demonstrated recurrent contrast-enhancement of the atrophic nerve. In conclusion, high-resolution MRI allows the reliable delineation of the oculomotor nerve and can support diagnosis in trauma patients with isolated oculomotor nerve palsy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Case report; Magnetic resonance imaging; Oculomotor nerve; Traumatic nerve palsy

High resolution time-of-flight MR-angiography at 7 T exploiting VERSE saturation, compressed sensing and segmentation - Meixner, Christian; Liebig, Patrick; Speier, Peter; Forman, Christoph; Hensel, Bernhard; Schmidt, Manuel; Saake, Marc; Uder, Michael; Dörfler, Arnd; Heidemann, Robin M.; Schmitter, Sebastian; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
Background: 3D Time-of-Flight (TOF) MR-angiography (MRA) substantially benefits from ultra-high magnetic field strengths (≥7 T) due to increased Signal-to-Noise ratio and improved contrast. However, high-resolution TOF-MRA usually requires long acquisition times. In addition, specific absorption rate constraints limit the choice of optimal pulse sequence parameters, especially if venous saturation is employed. Purpose: To implement and evaluate an arterial TOF-MRA for accelerated high-resolution angiography at ultra-high magnetic field strength. Field strengths/sequence: 7 T modified gradient-echo TOF sequence including venous saturation using Variable-Rate Selective Excitation (VERSE), Compressed Sensing (CS) and sparse application of saturation pulses, called segmentation, were included for acceleration. Assessment: To analyze the acceleration techniques all volunteers were examined with the same protocols. CS with different sampling patterns and regularization factors as well as segmentation were applied for acceleration. For comparison, conventional acceleration techniques were applied (GRAPPA PAT 3 and Partial Fourier (6/8 in slice/phase encoding)). Images were co-registered and 40 mm thick transversal maximum intensity projections were created to calculate the relative number of vessels. To analyze the visibility of small vessels, the lenticulostriate arteries (LSA) were examined. This was done via multiscale vessel enhancement filtering in a VOI and quantification via Fiji ImageJ as well as qualitatively evaluation by two radiologists. Additionally, the venous/arterial vessel-to-background ratios (vVBR/aVBR) were calculated for chosen protocols. Results: For the acceleration of a high resolution TOF-MRA (0.31 mm isotropic), under-sampling of 9.6 showed aliasing artifacts, whereas 7.2 showed no aliasing. The regularization factor R had a strong impact on the image quality according to smoothing (R = 0.01 to R = 0.005) and noise (R = 0.0005 to R = 0.00005). With the alternating sampling patterns it was shown that the k-space center should not be under-sampled too much. Additionally segmentation could be verified to be feasible for stronger acceleration with sufficient venous suppression. Conclusion: The combination of several independent techniques (VERSE, CS with acceleration factor 7.2, R = 0.001, Poisson disc radius of 80%, 3 segments) enables the application of high-resolution (0.31 mm isotropic) TOF-MRA with venous saturation at 7 T in clinical time settings (TA ≈ 5 min) and within the SAR limits.
CRIS-Team Scopus Importer:2019-08-30
Keywords: 7 Tesla; Compressed sensing; MR-angiography; Time-of-flight; Ultra-high field; VERSE

High-speed flat-detector computed tomography for temporal bone imaging and postoperative control of cochlear implants - Eisenhut, Felix; Manhart, Michael; Thimsen, Vivian; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Neuroradiology, 2022)
Purpose: Flat-detector computed tomography (FD-CT) is the standard for cochlear implant (CI) imaging. FD-CT systems differ in technical characteristics. Our aim was an evaluation of two different FD-CT generations with different protocols and hardware regarding image quality, radiation dose, and scan time. Methods: Two temporal bone specimens (− / + CI = TB0/TB1) were scanned using three different scanners: two FD-CT systems with different scanning protocols (standard FD-CT: 20 s 70 kV, 20 s 109 kV; high-speed FD-CT [HS-FD-CT]: 7 s 109 kV, 9 s 109 kV, 14 s 72 kV) and MS-CT (5 s 120 kV). Acquired datasets were evaluated in consensus reading regarding qualitative and quantitative parameters: addressing CI- and cochlea-specific parameters, cochlea delineation, lamina spiralis ossea visibility, distinction of single CI electrodes, determination of intracochlear implant position, stapes delineation, and mastoidal septation were assessed. Addressing protocol-specific parameters, radiation dose (dose-length-product/DLP), and scan time were assessed. Results: Two HS-FD-CT protocols (14 s/9 s) provide higher or equivalent diagnostic information regarding CI- and cochlea-specific parameters compared to both standard FD-CT protocols. The fastest HS-FD-CT protocol (7 s)—providing inferior diagnostic information compared to all other FD-CT protocols—still exceeds MS-CT. The highest DLP was recorded for the 14 s HS-FD-CT protocol (TB1 = 956 mGycm); the lowest DLPs were recorded for the 7 s HS-FD-CT protocol (TB0 = 188 mGycm) and for MS-CT (TB0 = 138 mGycm), respectively. HS-FD-CT allows a significant reduction of scan time compared to standard FD-CT. Conclusion: High-speed FD-CT improves visualization of temporal bone anatomy and postoperative assessment of CIs by combining excellent image quality, fast scan time, and reasonable radiation exposure.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Anatomy; Cochlear implant; Flat-detector computed tomography; Postoperative control; Temporal bone

Hybrid B1+-shimming and gradient adaptions for improved pseudo-continuous arterial spin labeling at 7 Tesla - Meixner, Christian; Eisen, Christian; Schmitter, Sebastian; Müller, Max; Herrler, Jürgen; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To improve pseudo-continuous arterial spin labeling (pcASL) at 7T by exploiting a hybrid homogeneity- and efficiency-optimized (Formula presented.) -shim with adapted gradient strength as well as background suppression. Methods: The following three experiments were performed at 7T, each employing five volunteers: (1) A hybrid (ie, homogeneity-efficiency optimized) (Formula presented.) -shim was introduced and evaluated for variable-rate selective excitation pcASL labeling. Therefore, (Formula presented.) -maps in the V3 segment and time-of-flight images were acquired to identify the feeding arteries. For validation, a gradient-echo sequence was applied in circular polarized (CP) mode and with the hybrid (Formula presented.) -shim. Additionally, the gray matter (temporal) signal-to-noise ratio (tSNR) in pcASL perfusion images was evaluated. (2) Bloch simulations for the pcASL labeling were conducted and validated experimentally, with a focus on the slice-selective gradients. (3) Background suppression was added to the (Formula presented.) -shimmed, gradient-adapted 7T sequence and this was then compared to a matched sequence at 3T. Results: The (Formula presented.) -shim improved the signal within the labeling plane (23.6%) and the SNR/tSNR increased (+11%/+11%) compared to its value in CP mode; however, the increase was not significant. In accordance with the simulations, the adapted gradients increased the tSNR (35%) and SNR (45%) significantly. Background suppression further improved the perfusion images at 7T, and this protocol performed as well as a resolution-matched protocol at 3T. Conclusion: The combination of the proposed hybrid (Formula presented.) -phase-shim with the adapted slice-selective gradients and background suppression shows great potential for improved pcASL labeling under suboptimal (Formula presented.) conditions at 7T.
CRIS-Team Scopus Importer:2021-08-27
Keywords: 7 Tesla; B1 shimming; pcASL; pTx; ultra-high field strengths; VERSE

Hyponatremia is an independent predictor of in-hospital mortality in spontaneous intracerebral hemorrhage - Kuramatsu, Joji; Bobinger, Tobias; Volbers, Bastian; Staykov, Dimitre; Lücking, Hannes; Kloska, Stephan; Köhrmann, Martin; Huttner, Hagen (Stroke, 2014)
Hyponatremia is the most frequent electrolyte disturbance in critical care. Across various disciplines, hyponatremia is associated with increased mortality and longer hospital stay, yet in intracerebral hemorrhage (ICH) no data are available. This the first study that investigated the prevalence and clinical associations of hyponatremia in patients with ICH.This observational study included all consecutive spontaneous ICH patients (n=464) admitted during a 5-year period to the Department of Neurology. Patient characteristics, in-hospital measures, mortality, and functional outcome (90 days and 1 year) were analyzed to determine the effects of hyponatremia (Na<135 mEq/L). Multivariable regression analyses were calculated for factors associated with hyponatremia and predictors of in-hospital mortality.The prevalence of hyponatremia on hospital admission was 15.6% (n=66). Normonatremia was achieved and maintained in almost all hyponatremia patients<48 hours. In-hospital mortality was roughly doubled in hyponatremia compared with nonhyponatremia patients (40.9%; n=27 versus 21.1%; n=75), translating into a 2.5-fold increased odds ratio (P<0.001). Multivariable analyses identified hyponatremia as an independent predictor of in-hospital mortality (odds ratio, 2.2; 95% confidence interval, 1.05-4.62; P=0.037). Within 90 days after ICH, hyponatremia patients surviving hospital stay were also at greater risk of death (odds ratio, 4.8; 95% confidence interval, 2.1-10.6; P<0.001); thereafter, mortality rates were similar.Hyponatremia was identified as an independent predictor of in-hospital mortality with a fairly high prevalence in spontaneous ICH patients. The presence of hyponatremia at hospital admission is related to an increased short-term mortality in patients surviving acute care, possibly reflecting a preexisting condition that is linked to worse outcome due to greater comorbidity. Correction of hyponatremia does not seem to compensate its influence on mortality, which strongly warrants future research.
EVALuna2:22304

Hypoxia and microvascular alterations are early predictors of IDH-mutated anaplastic glioma recurrence - Stadlbauer, Andreas; Oberndorfer, Stefan; Heinz, Gertraud; Zimmermann, Max; Kinfe, Thomas Mehari; Dörfler, Arnd; Buchfelder, Michael; Kremenevski, Natalia; Marhold, Franz (Cancers, 2021)
Anaplastic gliomas (AG) represents aggressive brain tumors that often affect young adults. Although isocitrate-dehydrogenase (IDH) gene mutation has been identified as a more favorable prognostic factor, most IDH-mutated AG patients are confronted with tumor recurrence. Hence, increased knowledge about pathophysiological precursors of AG recurrence is urgently needed in order to develop precise diagnostic monitoring and tailored therapeutic approaches. In this study, 142 physiological magnetic resonance imaging (phyMRI) follow-up examinations in 60 AG patients after standard therapy were evaluated and magnetic resonance imaging (MRI) biomarker maps for microvascular architecture and perfusion, neovascularization activity, oxygen metabolism, and hypoxia calculated. From these 60 patients, 34 patients developed recurrence of the AG, and 26 patients showed no signs for AG recurrence during the study period. The time courses of MRI biomarker changes were analyzed regarding early pathophysiological alterations over a one-year period before radiological AG recurrence or a one-year period of stable disease for patients without recurrence, respectively. We detected intensifying local tissue hypoxia 250 days prior to radiological recurrence which initiated upregulation of neovascularization activity 50 to 70 days later. These changes were associated with a switch from an avascular infiltrative to a vascularized proliferative phenotype of the tumor cells another 30 days later. The dynamic changes of blood perfusion, microvessel density, neovascularization activity, and oxygen metabolism showed a close physiological interplay in the one-year period prior to radiological recurrence of IDH-mutated AG. These findings may path the wave for implementing both new MR-based imaging modalities for routine follow-up monitoring of AG patients after standard therapy and furthermore may support the development of novel, tailored therapy options in recurrent AG.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Anaplastic glioma; Hypoxia; IDH gene mutation; Isocitrate-dehydrogenase; Neovascularization; Physiological MRI; Recurrence; Treatment failure; Vascular cooption

Identification of anatomic risk factors for scalar translocation in cochlear implant patients - Eisenhut, Felix; Lang, Stefan; Hölter, Philip; Wiesmüller, Marco; Uder, Michael; Iro, Heinrich; Dörfler, Arnd; Hornung, Joachim; Taha, Lava (Zeitschrift für Medizinische Physik, 2021)
Aim: Microanatomical evaluation of cochlear implant (CI) patients to identify anatomical risk factors for a scalar translocation. Methods: CI patients with both a regular scala tympani spiralization (group A) and a scalar translocation (group B) were identified via postoperative flat-detector computed tomography (FD-CT). Then, the corresponding preoperative multislice computed tomography (MS-CT) and postoperative FD-CT datasets were assessed: First, the cochleae were separated in 6 segments of 45° each. Next, quantitative (cochlea height, length, depth, cochlear duct diameter [CD] per segment; percentual tapering of the CD per segment named cochlear geometry index [CGI]) and qualitative (identifiability of the CI model; CI-integrity; intracochlear array position) parameters were evaluated and compared for both groups. Receiver-operating-characteristics (ROC) analysis was performed for the CGI. Results: In total, 40 preoperative MS-CT and postoperative FD-CT datasets (nA = 20; nB = 20) were analysed. Model “CI 512” was successfully identified and CI-integrity has been confirmed in all cases. Quantitative analysis showed a significant difference of both the CD at 0° (CDA 0°= 2.06 ± 0.23 mm; CDB 0°= 2.19 ± 0.18 mm; p0°= 0.04) and the CGI of the first segment (CGIA 0° -45°= 18.87 ± 6.04%; CGIB 0°-45°= 28.89 ± 8.58%; p0°-45°= 0.0001). For all other 5 cochlear segments there was no significant difference of CD and CGI; there was no significant difference of external cochlea diameters. The area under the curve (AUC) of the CGI0-45° was 0.864 with 24.50° as the optimal cut-off value to discriminate patients with a scala tympani spiralization and a scalar translocation. CGI0-45° of > 24.50° allowed the correct identification of 85% of patients with a scalar translocation. Conclusion: CI insertion trauma is associated with a significantly higher narrowing of the proximal basal cochlea turn (BCT). The CGI as percentual tapering of the BCT turned out as reliable, clinically applicable parameter for identification of patients with an increased risk for a scalar translocation.
CRIS-Team Scopus Importer:2021-03-12
Keywords: anatomical parameters; Cochlear implant; flat-detector computed tomography; insertion trauma; scalar translocation

Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967

Immunological and clinical consequences of splenectomy in a multiple sclerosis patient treated with natalizumab - Lee, De-Hyung; Waschbisch, Anne; Laemmer, Alexandra B.; Dörfler, Arnd; Schwab, Stefan; Linker, Ralf (Journal of Neuroinflammation, 2013)
Objective: Here we report a case of a splenectomized white woman with natalizumab-associated progressive multifocal leukoencephalopathy (PML), occurring as early as after 11 infusions and provide blood fluorescence-activated cell sorting (FACS) analyses before and after natalizumab treatment.Design: This is a report of a single case with immunological studies.Methods: Methods comprised neurologic examination, magnetic resonance imaging, and cerebrospinal fluid (CSF) studies as well as immune cell FACS analyses from blood.Results: Diagnosis of PML was established after positive John Cunningham virus (JCV) DNA was detected in the CSF. An immune reconstitution inflammatory syndrome was treated with repeated cycles of steroid pulses and intravenous immunoglobulins. Reduced numbers of memory B cells, which might play an important role in antiviral immune response, were detected in the blood. Moreover the percentage of CD19+ B cells was elevated in our post-splenectomy patient as compared to a control cohort of multiple sclerosis (MS) patients under natalizumab therapy.Conclusion: Splenectomy may increase the risk for the development of natalizumab-associated PML via effects on the B cell compartment. It may be regarded as a risk factor in MS patients independent from the duration of disease. © 2013 Lee et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CD19 positive B cells; Multiple sclerosis; Natalizumab; Progressive multifocal leukoencephalopathy; Splenectomy

Impact of Hypothermia Initiation and Duration on Perihemorrhagic Edema Evolution After Intracerebral Hemorrhage - Volbers, Bastian; Herrmann, Sabrina; Willfarth, Wolfgang; Lücking, Hannes; Kloska, Stephan; Dörfler, Arnd; Huttner, Hagen; Kuramatsu, Joji; Schwab, Stefan; Staykov, Dimitre (Stroke, 2016)
Intracerebral hemorrhage (ICH) causes high morbidity and mortality. Recently, perihemorrhagic edema (PHE) has been suggested as an important prognostic factor. Therapeutic hypothermia may be a promising therapeutic option to treat PHE. However, no data exist about the optimal timing and duration of therapeutic hypothermia in ICH. We examined the impact of therapeutic hypothermia timing and duration on PHE evolution.In this retrospective, single-center, case-control study, we identified patients with ICH treated with mild endovascular hypothermia (target temperature 35°C) from our institutional database. Patients were grouped according to hypothermia initiation (early: days 1-2 and late: days 4-5 after admission) and hypothermia duration (short: 4-8 days and long: 9-15 days). Patients with ICH matched for ICH volume, age, ICH localization, and intraventricular hemorrhage were identified as controls. Relative PHE, temperature, and intracranial pressure course were analyzed. Clinical outcome on day 90 was assessed using the modified Rankin scale (0-3=favorable and 4-6=poor).Thirty-three patients with ICH treated with hypothermia and 37 control patients were included. Early hypothermia initiation led to relative PHE decrease between admission and day 3, whereas median relative PHE increased in control patients (-0.05 [interquartile range, -0.4 to 0.07] and 0.07 [interquartile range, -0.07 to 0.26], respectively; P=0.007) and patients with late hypothermia initiation (0.22 [interquartile range 0.12-0.27]; P=0.037). After day 3, relative PHE increased in all groups without difference. Outcome was not different between patients treated with hypothermia and controls.Early hypothermia initiation after ICH onset seems to have an important impact on PHE evolution, whereas our data suggest only limited impact later than day 3 after onset.
EVALuna2:22477

Impact of interhospital transfer vs. direct admission on acute ischemic stroke patients: A subset analysis of the COMPLETE registry - Hassan, Ameer E.; Zaidat, Osama O.; Nanda, Ashish; Atchie, Benjamin; Woodward, Keith; Dörfler, Arnd; Tomasello, Alejandro; Fifi, Johanna T.; Complete Registry Investigators, (Frontiers in Neurology, 2022)
Background: Efficacy of thrombectomy treatment in acute ischemic stroke large vessel occlusion (AIS-LVO) patients is time dependent. Direct admission to thrombectomy centers (vs. interhospital transfer) may reduce time to treatment and improve outcomes. In this subset analysis of the COMPLETE registry, we compared outcomes between direct to thrombectomy center (Direct) vs. transfer from another hospital to thrombectomy center (Transfer) in AIS-LVO patients treated with aspiration thrombectomy. Methods: COMPLETE was a prospective, international registry that enrolled patients from July 2018 to October 2019, with a 90-day follow-up period that was completed in January 2020. Imaging findings and safety events were adjudicated by core lab and independent medical reviewers, respectively. Pre-defined primary endpoints included post-procedure angiographic revascularization (mTICI & GE;2b), 90-day functional outcome (mRS 0-2), and 90-day all-cause mortality. Planned collections of procedural time metrics and outcomes were used in the present post-hoc analysis to compare outcomes between transfer and direct patient cohorts. Results: Of 650 patients enrolled, 343 were transfer [52.8% female; mean (SD) age, 68.2 (13.9) years], and 307 were direct [55.4% female; 68.5 (14.5) years] admit. Median onset-to-puncture time took longer in the transfer vs. direct cohort (5.65 vs. 3.18 h: 2.33 h difference, respectively; p < 0.001). There was no significant difference in successful revascularization rate, mTICI & GE;2b (88.3 and 87.3%), sICH at 24 h (3.8 and 3.9%), median length of hospital stay (7 and 6 days), and 90-day mortality (16.9 and 14.0%) between transfer vs. direct patients, respectively. However, achieving 90-day functional independence was less likely in transfer compared with direct patients (mRS 0-2 was 50.3 vs. 61.7%, p = 0.0056). Conclusions: In the COMPLETE registry, direct to thrombectomy center was associated with significantly shorter onset-to-puncture times, and higher rates of good clinical outcome across different geographies. Additional research should focus on AIS-LVO detection to facilitate direct routing of patients to appropriate treatment centers.
CRIS-Team WoS Importer:2022-09-02

Impact of Perihemorrhagic Edema on Short-Term Outcome After Intracerebral Hemorrhage - Volbers, Bastian; Willfarth, Wolfgang; Schwab, Sibylle; Kuramatsu, J. B.; Huttner, Hagen; Struffert, Tobias; Dörfler, Arnd; Staykov, S. (Neurocritical Care, 2016)
Intracerebral hemorrhage (ICH) is a devastating disease with ICH volume being the main predictor of poor outcome. The prognostic role of perihemorrhagic edema (PHE) is still unclear; however, available data are mainly derived from analyses during the first days after symptom onset. As PHE growth may continue up to 14 days after ICH, we evaluated PHE over a longer period of time and investigated its impact on short-term clinical outcome.In this monocentric retrospective cohort study, patients with spontaneous supratentorial ICH were identified from our institutional data base. Different time points of CT scans were merged to time clusters for better comparison (day 1, 2-3, 4-6, 7-9, 10-12). Absolute volumes of ICH and PHE were obtained using a validated semiautomatic volumetric algorithm. Clinical outcome at discharge was assessed using the modified Rankin Scale (0-3 = favorable, 4-6 = poor).220 patients (83 with favorable, 137 with poor outcome) were included in the final analysis. Mean ICH volume on admission was 22.8 [standard deviation (SD) 24.6] cm(3). Mean absolute PHE volume on admission was 22.5 (SD 20.8) cm(3) and increased to a mean peak volume of 38.1 (SD 31.4) cm(3) during 6.7 (SD 4.1) days on average. Besides GCS on admission, functional status before ICH, peak hematoma volume, lobar localization and fever burden, and high peak PHE volume predicted poor outcome at discharge [OR 0.977 (95 % CI 0.957-0.998)] in the multivariable analysis.PHE may have a negative impact on short-term functional outcome after ICH and therefore represent a possible treatment target.
EVALuna2:22273

Impact of post-processing methods on apparent diffusion coefficient values - Zeilinger, Martin Georg; Lell, Michael; Baltzer, Pascal Andreas Thomas; Dörfler, Arnd; Uder, Michael; Dietzel, Matthias (European Radiology, 2016)
The apparent diffusion coefficient (ADC) is increasingly used as a quantitative biomarker in oncological imaging. ADC calculation is based on raw diffusion-weighted imaging (DWI) data, and multiple post-processing methods (PPMs) have been proposed for this purpose. We investigated whether PPM has an impact on final ADC values.Sixty-five lesions scanned with a standardized whole-body DWI-protocol at 3 T served as input data (EPI-DWI, b-values: 50, 400 and 800 s/mm(2)). Using exactly the same ROI coordinates, four different PPM (ADC_1-ADC_4) were executed to calculate corresponding ADC values, given as [10(-3) mm(2)/s] of each lesion. Statistical analysis was performed to intra-individually compare ADC values stratified by PPM (Wilcoxon signed-rank tests: ? = 1 %; descriptive statistics; relative difference/?; coefficient of variation/CV).Stratified by PPM, mean ADCs ranged from 1.136-1.206 *10(-3) mm(2)/s (? = 7.0 %). Variances between PPM were pronounced in the upper range of ADC values (maximum: 2.540-2.763 10(-3) mm(2)/s, ? = 8 %). Pairwise comparisons identified significant differences between all PPM (P <= 0.003; mean CV = 7.2 %) and reached 0.137 *10(-3) mm(2)/s within the 25th-75th percentile.Altering the PPM had a significant impact on the ADC value. This should be considered if ADC values from different post-processing methods are compared in patient studies.o Post-processing methods significantly influenced ADC values. o The mean coefficient of ADC variation due to PPM was 7.2 %. o To achieve reproducible ADC values, standardization of post-processing is recommended.
EVALuna2:14601

IMPACT OF STATINS ON HEMATOMA CHARACTERISTICS, PERIHEMORRHAGIC EDEMA, SEIZURES AND FUNCTIONAL RECOVERY AFTER INTRACEREBRAL HEMORRHAGE - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Sembill, Jochen; Saam, Justina; Gerner, Stefan; Balk, Stefanie; Hamer, Hajo; Lücking, Hannes; Hölter, Philip; Nolte, C.; Scheitz, J.; et al. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Impact of Statins on Hematoma, Edema, Seizures, Vascular Events, and Functional Recovery After Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Saam, Justina; Sembill, Jochen; Gerner, Stefan; Balk, Stefanie; Hamer, Hajo; Lücking, Hannes; Hölter, Philip; Nolte, Christian H.; Scheitz, Jan F.; et al. (Stroke, 2021)
BACKGROUND AND PURPOSE: The impact of statins on hematoma characteristics, perihemorrhagic edema (PHE), cardiovascular events, seizures, and functional recovery in patients with intracerebral hemorrhage (ICH) is insufficiently studied. METHODS: Patients with ICH of the prospective UKER-ICH (Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage) study (URL: https://www.clinicaltrials.gov; Unique identifier: NCT03183167) were analyzed by multivariable regression modeling and propensity score matching, and PHE volumes were volumetrically assessed. Outcomes comprised hematoma characteristics, the impact of continuation, discontinuation, and initiation of statins on peak PHE extent, and the influence of statin treatment on the occurrence of seizures, cardiovascular adverse events, and functional recovery after ICH. RESULTS: A total of 1275 patients with ICH with information on statin treatment were analyzed. Statin treatment on hospital admission (21.7%) was associated with higher rates of lobar versus nonlobar ICH (odds ratio, 1.57 [1.03-2.40]; P=0.038). Initiation of statins after ICH was associated with increased peak PHE (β=0.12, SE=0.06, P=0.008), whereas continuation versus discontinuation of prior statin treatment was not significantly associated with edema formation (P>0.10). There were no significant differences in the incidence of remote symptomatic seizures according to statin exposure during follow-up (statins: 11.5% versus no statins: 7.8%, subdistribution hazard ratio: 1.15 [0.80-1.66]; P=0.512). Patients on statins revealed less cardiovascular adverse events and more frequently functional recovery after 12 months (functional recovery: 57.7% versus 45.0%, odds ratio 1.67 [1.09-2.56]; P=0.019). CONCLUSIONS: Among statin users, lobar ICH occurs more frequently as compared with nonstatin users. While continuation of prior statin treatment appears to be safe regarding PHE formation, the initiation of statins during the first days after ICH may increase PHE extent. However, statins should be initiated thereafter (eg, at hospital discharge) to prevent cardiovascular events and potentially improve functional recovery.
CRIS-Team Scopus Importer:2021-03-19
Keywords: edema; hematoma; incidence; odds ratio; seizures

Impairment of the Visual System in Glaucoma - Schmidt, Manuel; Engelhorn, Tobias; Dörfler, Arnd; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2019)
MR Diffusion Tensor Imaging (DTI) enables visualisation of the visual system in glaucoma; it has been shown that the atrophy of the optic radiation is more pronounced in glaucoma than in age-matched controls. The atrophy of the optic radiation thereby correlates with OCT and visual field measures. Diffusion tensor imaging permits quantification of the axonal integrity of the optic radiation by calculation of fractional anisotropy (FA) and radial diffusivity (RD). Both within and also outside the visual system, there are substantial changes in FA and RD, changes suggesting a complex neurodegenerative disease. Metabolic MRI by specific Na+-coils and by the CEST-technique (CEST: chemical exchange saturation transfer) will enable visualisation of neuronal cell death and pathological protein accumulation in the visual system. It is proposed that glaucomatous atrophy of the visual system may be induced by antero- and retrograde axonal degeneration. In normal tension glaucoma and PEX glaucoma, retrograde degeneration is induced by ischemic lesions or pathological protein accumulation within the cerebral portion of the visual system. Magnetic resonance imaging of the visual system with DTI and metabolic imaging will potentially improve therapeutic monitoring and diagnosis of glaucoma.
CRIS-Team WoS Importer:2019-03-06

Improved Detection of Cavernous Sinus Invasion of Pituitary Macroadenomas with Ultra-High-Field 7 T MRI - Eisenhut, Felix; Schmidt, Manuel; Buchfelder, Michael; Dörfler, Arnd; Schlaffer, Sven-Martin (Life, 2023)
To compare 7 T magnetic resonance imaging (MRI) of pituitary macroadenomas (PMA) with standard MRI and intraoperative findings regarding tumor detection, localization, size, and extension. Patients with suspected pituitary adenoma underwent pre-operative 1.5 T or 3 T and 7 T MRI; 14 patients with a PMA were included. A qualitative (lesion detection, location, cavernous sinus infiltration) and quantitative (lesion size, depth of cavernous sinus infiltration) analysis of 1.5 T, 3 T and 7 T MRI was performed and compared with intraoperative findings. Both 1.5/3 T and 7 T MRI enabled the detection of all PMAs; lesion size determination was equal. 7 T MRI enables more precise assessments of cavernous sinus infiltration of PMA (ncorrect 7T = 78.6%, ncorrect 1.5/3T = 64.3%). Ultra-high-field MRI is a reliable imaging modality for evaluation of PMAs providing exact information on lesion location and size. 7 T MRI yielded more accurate information on cavernous sinus infiltration with better agreement with intraoperative findings than standard MRI.
CRIS-Team Scopus Importer:2023-01-27
Keywords: cavernous sinus infiltration; intraoperative findings; pituitary macroadenoma; ultra-high-field MRI

Improvement of Deep Learning-based Auto-detection of Brain Metastases by Integrating previous MRI Images - Dörfler, Arnd; Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Maier, Andreas; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Incidence, temporal profile and neuroanatomic correlates of poststroke epilepsy - Winder, Klemens; Bobinger, Tobias; Seifert, Frank; Mrochen, Anne; Haupenthal, David; Knott, Michael; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Fröhlich, Kilian (Journal of Neuroimaging, 2023)
Background and Purpose: The relationship between ischemic stroke site and occurrence of poststroke epilepsy (PSE) is incompletely understood. This study intended to evaluate incidence and temporal profiles of seizures and to correlate ischemic lesion sites with PSE using voxel-based lesion symptom mapping (VLSM). Methods: Patients with imaging-confirmed first-ever ischemic stroke without prior history of epilepsy were prospectively included. Demographic data, cardiovascular risk factors, and National Institute of Health Stroke Scale (NIHSS) scores were assessed. Data on seizures and modified Rankin scale scores were determined within a 90-day period after stroke onset. Ischemic lesion sites were correlated voxel wise with occurrence of PSE using nonparametric permutation test. Age- and sex-matched patients with first-ever ischemic strokes without PSE after 90 days served as controls for the VLSM analysis. Results: The stroke database contained 809 patients (mean age: 68.4 ± 14.2 years) with first-ever imaging-confirmed ischemic strokes without history of epilep. Incidence of PSE after 90-day follow-up was 2.8%. Five additional patients were admitted to the emergency department with a seizure after 90-day follow-up. Fifty percent of the seizures occurred in the acute phase after stroke. PSE patients had higher NIHSS scores and infarct volumes compared to controls without PSE (p <.05). PSE patients had infarcts predominantly involving the cerebral cortex. The hemisphere-specific VLSM analysis shows associations between PSE and damaged voxels in the left-hemispheric temporo-occipital transition zone. Conclusions: The data indicate that PSE occurs in a small proportion of patients with rather large ischemic strokes predominantly involving the cerebral cortex. Especially patients with ischemic lesions in the temporo-occipital cortex are vulnerable to develop PSE.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ischemic stroke; poststroke epilepsy; voxel-based lesion symptom mapping

Increased Neutrophil-to-Lymphocyte Ratio is Associated with Unfavorable Functional Outcome in Acute Ischemic Stroke - Giede-Jeppe, Antje; Madzar, Dominik; Sembill, Jochen; Sprügel, Maximilian; Atay, Selim; Lücking, Hannes; Huttner, Hagen; Bobinger, Tobias; Hölter, Philip (Neurocritical Care, 2019)
Background Inflammatory response is the hallmark of secondary brain injury in stroke patients. Neutrophil-to-lymphocyte ratio (NLR) emerged as a marker for functional outcome in several diseases. Objectives To investigate the association between NLR on admission and during hospital stay and functional outcome in acute ischemic stroke (AIS). Methods This observational study included all consecutive AIS patients admitted at a German stroke center covering 2011-2013. Patient characteristics and clinical data were retrieved from institutional databases. Multivariate analysis was conducted to investigate parameters associated with functional outcome. Receiver operating characteristic (ROC) analysis was performed to identify the best cutoff for NLR to discriminate between favorable and unfavorable functional outcome. To account for imbalances in baseline characteristics, propensity score matching was carried out to assess the influence of NLR on functional outcome. Results A total of 807 patients with AIS were included for analysis. Patients with worse functional outcome at 3 months were older and had worse clinical status on admission, higher rates of infectious complications, and an increased NLR. ROC analysis identified a NLR of 3.3 as best cutoff value to discriminate between favorable and unfavorable functional outcomes (area under the curve 0.693, p < 0.001, Youden's index = 0.318; p < 0.001; sensitivity 68.5%, specificity 63.9%). Propensity-matched analysis still demonstrated a higher rate of unfavorable functional outcome at 3 months in patients with NLR >= 3.3 [modified Rankin scale 3-6 at 3 months: NLR >= 3.3 51.5% vs. NLR < 3.3 36.4%; p = 0.002]. Conclusions In AIS patients we identified NLR as an important predictor for unfavorable functional outcome.
CRIS-Team WoS Importer:2019-10-25

Influence of antithrombotic pre-treatment and time window on hemorrhagic complications of ivt in ischemic stroke - Macha, Kosmas; Hölter, Philip; Sembill, Jochen; Hock, Stefan; Siedler, Gabriela; Mühlen, Iris; Haupenthal, David; Schwab, Stefan; Kallmünzer, Bernd; Dörfler, Arnd (EUROPEAN JOURNAL OF NEUROLOGY, 2022)
CRIS-Team WoS Importer:2022-07-22

Influence of Artifact Corrections on MRI Signal Intensity Ratios for Assessment of Gadolinium Brain Retention - Saake, Marc; Hepp, Tobias; Schmidle, Alexandra; Wüst, Wolfgang; Heiß, Rafael; Dörfler, Arnd; Uder, Michael; Bäuerle, Tobias (Academic Radiology, 2019)
Rationale and Objectives: Differences in brain signal intensity ratios (SIRs) of deep brain nuclei in T1-weighted (T1w) magnetic resonance images were reported as an indicator of gadolinium brain retention. Variable methods of image reconstruction and inhomogeneity correction for T1w images exist, which might affect the accuracy of SIRs. The aim of our prospective study was to investigate the effect of flow artifact compensation (FAC) and intensity inhomogeneity correction (IIC) on the dentate nucleus-to-pons and globus pallidus-to-thalamus SIRs in study participants who had previously received multiple doses of gadobutrol. Materials and Methods: This study included 76 participants who received five or more gadobutrol-enhanced scans between 2007 and 2017. A control group of 25 participants without gadolinium-based contrast agent application in their patient history was included for comparison. Unenhanced brain magnetic resonance imaging including two T1w spin-echo sequences with and without FAC was performed in all participants. Both sequences were reconstructed with and without IIC. Images were assessed for flow artifacts and SIRs were calculated. Results: Using FAC, a lower proportion of participants had to be excluded from the final analysis of dentate nucleus-to-pons SIR due to flow artifacts (15% versus 46%, p < 0.001). Without IIC, a difference was found between the study and the control group for the dentate nucleus-to-pons ratio (p = 0.004), but not for the same sequence reconstructed with IIC (p = 0.29). For the globus pallidus-to-thalamus ratio, no difference was found between the study and control group. Conclusion: The application of an IIC algorithm has significant impact on brain nuclei SIRs for the assessment of gadolinium brain retention.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Contrast Media; Gadolinium; Magnetic resonance imaging

Influence of different reconstruction parameters in the visualization of intracranial stents using C-arm flat panel CT angiography: experience in an animal model - Ott, Sabine; Struffert, Tobias; Saake, Marc; Gölitz, Philipp; Adamek, Edyta; Dörfler, Arnd (Acta Radiologica, 2016)
C-arm flat panel computed tomography angiography (CA-CTA) is a relatively new imaging modality. Consequently, knowledge about postprocessing parameters and their influence on image quality is still limited, especially for the visualization of implanted microstents.To optimize reconstruction parameters by evaluating the influence of these different parameters for CA-CTA visualization of microstents in an animal model.Eleven microstents were implanted within the left common carotid artery of 11 New Zealand white rabbits. Both CA-CTA, using intra-venous delivery of contrast material, and conventional digital subtraction angiography (DSA) was performed. CA-CTA datasets were reconstructed using three different image characteristics (normal, sharp, smooth). Two experienced neuroradiologists evaluated the image quality and performed measurements of inner and outer stent diameters as well as measurements of the lumen area.Stent deployment was performed successfully in all animals. Inter-observer correlation coefficient for all measurements was high (r = 0.87-0.92). Lumen area and inner stent diameter were significantly smaller in image characteristic "smooth" (P < 0.01) than in "sharp" and "normal". Outer stent diameter was larger in "smooth" than in "sharp" and "normal" (P < 0.01). Stent strut size was significantly wider using image characteristic "smooth". "Sharp" and "normal" compared best to DSA, with "sharp" providing the closest match to DSA measurements, with the trade-off of significantly more noise than in the "normal" reconstructions.The use of different image characteristics in the postprocessing of CA-CTA datasets has an influence on the visualization of implanted stents. Image characteristic "sharp" and "normal" compared best to DSA.
EVALuna2:14583

Influence of Early Enteral Nutrition on Clinical Outcomes in Neurocritical Care Patients With Intracerebral Hemorrhage - Peng, Jianhua; Volbers, Bastian; Sprugel, Maximilian I.; Hölter, Philip; Engelhorn, Tobias; Jiang, Yong; Kuramatsu, Joji; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Gerner, Stefan (Frontiers in Neurology, 2021)
Objective: Early enteral nutrition (EEN) represents the current standard of care for patients treated in general intensive care units (ICU). Specific nutritional recommendations for patients receiving dedicated neurocritical care are not established. This study investigated associations of EEN with clinical outcomes for patients suffering from intracerebral hemorrhage treated at a neurological ICU (NICU).
CRIS-Team WoS Importer:2021-05-14

Influence of image contrasts and reconstruction methods on the classification of multiple sclerosis-like lesions in simulated sodium magnetic resonance imaging - Ruck, Laurent; Mennecke, Angelika; Wilferth, Tobias; Lachner, Sebastian; Müller, Max; Egger, Nico; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the classifiability of small multiple sclerosis (MS)-like lesions in simulated sodium (Na-23) MRI for different Na-23 MRI contrasts and reconstruction methods. Methods Na-23 MRI and Na-23 inversion recovery (IR) MRI of a phantom and simulated brain with and without lesions of different volumes (V = 1.3-38.2 nominal voxels) were simulated 100 times by adding Gaussian noise matching the SNR of real 3T measurements. Each simulation was reconstructed with four different reconstruction methods (Gridding without and with Hamming filter, Compressed sensing (CS) reconstruction without and with anatomical H-1 prior information). Based on the mean signals within the lesion volumes of simulations with and without lesions, receiver operating characteristics (ROC) were determined and the area under the curve (AUC) was calculated to assess the classifiability for each lesion volume. Results Lesions show higher classifiability in Na-23 MRI than in Na-23 IR MRI. For typical parameters and SNR of a 3T scan, the voxel normed minimal classifiable lesion volume (AUC > 0.9) is 2.8 voxels for Na-23 MRI and 19 voxels for Na-23 IR MRI, respectively. In terms of classifiability, Gridding with Hamming filter and CS without anatomical H-1 prior outperform CS reconstruction with anatomical H-1 prior. Conclusion Reliability of lesion classifiability strongly depends on the lesion volume and the Na-23 MRI contrast. Additional incorporation of H-1 prior information in the CS reconstruction was not beneficial for the classification of small MS-like lesions in Na-23 MRI.
CRIS-Team WoS Importer:2022-11-25

Influence of Prior Nicotine and Alcohol Use on Functional Outcome in Patients after Intracerebral Hemorrhage - Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Beuscher, Vanessa D.; Giede-Jeppe, Antje; Stocker, Margarete; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2018)
Background: The influence of prior nicotine or alcohol use (legal drug use [LDU]) on outcome measures after intracerebral hemorrhage (ICH) is insufficiently established. We investigated drug-specific associations with (1) neuroradiologic and clinical parameters and (2) functional long-term outcome after ICH. Methods: This observational cohort study analyzed consecutive spontaneous patients with ICH (n = 554) from our prospective institutional registry over a 5-year study period (January 2010 to December 2014). We compared no-LDU patients with LDU patients, and patients using only nicotine, only alcohol, or both. To account for baseline imbalances, we reanalyzed cohorts after propensity score matching. Results: Prevalence of prior LDU was 197 of 554 (35.6%), comprising 94 of 554 (17.0%) with only nicotine use, 33 of 554 (6.0%) with only alcohol use, and 70 of 554 (12.6%) with alcohol and nicotine use. LDU patients were younger (65 [56-73] versus 75 [67-82], P < .01), less often female (n = 61 of 197 [31.0%] versus n = 188 of 357 [52.7%], P < .01), had more often prior myocardial infarction (n = 29 of 197 [14.7%] versus n = 24 of 357 [6.7%], P < .01), and in-hospital complications (sepsis or systemic inflammatory response syndrome: n = 95 of 197 [48.2%] versus n = 98 of 357 [27.5%], P < .01; pneumonia: n = 89 of 197 [45.2%] versus n = 110 of 357 [30.8%], P < .01). Except for an increased risk of pneumonia (odds ratio 2.22, confidence interval [1.04-4.75], P = .04) in patients using both nicotine and alcohol, we detected no significant differences upon reanalysis after propensity score matching of neuroradiologic or clinical parameters, complications, or long-term outcome between patients with and without LDU (mortality: n = 48 of 150 [32.0%] versus n = 45 of 150 [30.0%], P = .71; favorable outcome [modified Rankin Scale 0-3]: n = 56 of 150 [37.3%] versus n = 53 of 150 [35.3%], P = .72). Conclusions: Prior nicotine use, alcohol use, and their combination were associated with significant differences in baseline characteristics. However, adjusting for unevenly balanced baseline parameters revealed no differences in functional long-term outcome after ICH.
EVALuna2:34918

Influence of the Extent of Intraventricular Hemorrhage on Functional Outcome and Mortality in Intracerebral Hemorrhage - Röder, Sebastian; Sprügel, Maximilian; Sembill, Jochen; Giede-Jeppe, Antje; Macha, Kosmas; Madžar, Dominik; Lücking, Hannes; Gerner, Stefan; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2019)
Background and Objective: Intraventricular hemorrhage (IVH) is a verified independent prognostic parameter in patients with intracerebral hemorrhage (ICH). However, the impact of the extent of IVH on clinical outcomes is unestablished. Methods: We analyzed 1,112 consecutive primary ICH patients of the UKER-ICH cohort (NCT03183167) and hypothesized that there is no difference in outcome between patients without IVH and patients with minor IVH not leading to obstructive hydrocephalus. Propensity score matching and multivariable analyses were performed to account for imbalances in baseline characteristics. Primary outcome was defined as functional outcome 3 months after ICH -assessed using the modified Rankin Scale (mRS) dichotomized into favorable (mRS = 0-3) and unfavorable outcome (mRS = 4-6). Secondary outcomes included mortality at 3 months and a Graeb score-based threshold analysis for association of the extent of IVH with unfavorable clinical outcome. Results: Among the 461 out of 1,112 (41.5%) ICH patients with IVH, 191 out of 461 (41.4%) showed IVH without obstructive hydrocephalus and no requirement of external ventricular drain (EVD) placement. After adjusting for baseline imbalances we found no difference in functional outcome at 3 months between patients without IVH (No-IVH) and patients with IVH not requiring EVD (IVH-w/o-EVD): mRS 0-3: No-IVH 64/161 (39.8%) vs. IVH-w/o-EVD 53/170 (31.2%); p = 0.103. However, there was a trend toward a higher mortality in IVH-w/o-EVD patients (mRS 6: No IVH 40/161 [24.8%] vs. IVH-w/o-EVD 57/170 [33.5%]; p = 0.083). Multivariable analysis revealed that a Graeb score >2 was independently associated with unfavorable outcome (mRS 4-6: OR 3.16 [1.54-6.48]; p = 0.002), and higher mortality (mRS 6: OR 2.57 [1.40-4.74]; p = 0.002) in IVH patients. Conclusions: Small amounts of intraventricular blood (Graeb score ≤2) not leading to obstructive hydrocephalus are not associated with unfavorable outcome or death after ICH. Thus, IVH per se should not be considered a binary variable in outcome prediction for ICH patients.
CRIS-Team Scopus Importer:2019-07-02

Influence on Outcome and Treatment of Intracerebral Hematoma in Patients with Atraumatic Subarachnoid Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Reichl, Jonathan; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Engelhorn, Tobias; Schwab, Stefan; Huttner, Hagen (CEREBROVASCULAR DISEASES, 2019)
CRIS-Team WoS Importer:2020-02-21

Initiating anticoagulant therapy after ICH is associated with patient characteristics and treatment recommendations - Sembill, Jochen; Wieser, Claudia; Sprügel, Maximilian; Gerner, Stefan; Giede-Jeppe, Antje; Reindl, Caroline; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Journal of Neurology, 2018)
The proportion of patients with intracerebral hemorrhage (ICH) and concomitant indication for oral anticoagulant (OAC) therapy is increasing. Although recent studies documented a favorable risk-benefit profile of OAC initiation, deciding whether, when, and which OAC should be started remains controversial. We investigated (1) OAC recommendations, its implementation, and adherence and (2) factors associated with OAC initiation after ICH. This prospective observational study analyzed consecutive ICH patients (n = 246) treated at the neurological and neurosurgical department of the University-Hospital Erlangen, Germany over a 21-month inclusion period (05/2013-01/2015). We analyzed the influence of patient characteristics, in-hospital measures, and functional status on treatment recommendations and on OAC initiation during 12-month follow-up. In-hospital mortality of 24.8% (n = 61/246) left 185 patients discharged alive of which 34.1% (n = 63/185) had OAC indication. In these patients, OAC initiation was clearly recommended in only 49.2% (n = 31/63) and associated with favorable [modified Rankin Scale (mRS) = 0-3] functional discharge status [OR 7.18, CI (1.05-49.13), p = 0.04], less frequent heart failure [OR 0.19, CI (0.05-0.71), p = 0.01], and younger age [OR 0.95, CI (0.90-1.00), p = 0.05]. OAC was more often started if clearly recommended [n = 19/31 (61.3%) versus (no recommendation) n = 4/26 (15.4%), p < 0.001; (clearly not recommended, n = 6)] and associated with younger age [67 (58-74) versus 79 (73-83), p < 0.001], favorable functional outcome [n = 10/23 (43.5%) versus n = 5/40 (12.5%), p = 0.01], decreased mortality [n = 6/23 (26.1%) versus n = 19/40 (47.5%), p = 0.06], and functional improvement [n = 13/17 (76.5%) versus n = 7/21 (33.3%), p = 0.01]. We observed no differences in rates of intracranial complications [thromboembolism, n = 3/23 (13.0%) versus n = 4/40 (10.0%), p = 1.00; hemorrhage, n = 1/23 (4.3%) versus n = 3/40 (7.5%), p = 1.00]. Clear treatment recommendations by attending stroke physicians significantly influence OAC initiation after ICH. OAC were more frequently recommended and started in younger patients with better functional recovery independent from intracranial complications. This might represent an important determinant of observed beneficial associations, hinting towards an indication bias which might affect observational analyses.
EVALuna2:34916

Insular Cortical Thickness in Patients With Somatoform Pain Disorder: Are There Associations With Symptom Severity and Childhood Trauma? - Meyer, Elisabeth; Morawa, Eva; Nacak, Yeliz; Rösch, Julie; Dörfler, Arnd; Forster, Clemens; Erim, Yesim (Frontiers in Psychiatry, 2020)
Background: Studies show significant alterations in insular cortical thickness in patients with somatoform pain disorder (SPD). Additionally, associations between childhood maltreatment and morphometric alterations in insular cortex have been observed. Since patients with SPD often report about adverse childhood experiences, we were interested in the interrelationship of exposure to childhood maltreatment and insular cortical thickness in patients with SPD. Methods: Fifteen adult patients with SPD (ICD-10 F 45.40/41, DSM-Code 307.80) and thirteen healthy adult controls underwent T1-weighted MR brain imaging. In the voxel-based morphometry (VBM) analysis we compared whole brain cortical thickness between patients and controls using a Student’s two-sampled t-test (p <.05). Then we performed a secondary analysis to detect differences in cortical thickness levels in the insular cortex between both groups. For further analysis of differences in insular cortical thickness we used gender, age, depressive symptoms [Patient Health Questionnaire (PHQ)-9], and whole brain cortical thickness as nuisance covariates. Subsequently we explored associations between insular cortical thickness, symptom severity (PHQ-15) and past experiences of childhood maltreatment (CTQ) in both groups. Results: Patients showed reduced insular cortical thickness in a subregion of right Brodmann area (BA) 13 (anterior part of the insular cortex), whereas whole brain cortical thickness did not differ between groups. The between-group difference in the identified insular subregion of right BA 13 was not diminished by any of the covariates. This implies that the reduction in cortical thickness in the identified insular subregion might be due to a specific group effect. The effect sizes indicate that the group of patients experienced more childhood maltreatment than the control group. Nonetheless, significant correlations of insular cortical thickness with symptom severity and childhood maltreatment in the total collective could not be demonstrated for the group of patients. Conclusions: Our data suggest that alterations in the identified insular subregion of right BA 13 are associated with somatoform pain, independent of gender, age, or coincident depression levels. To identify significant associations of insular cortical thickness and experiences of childhood maltreatment in patients with SPD investigations within larger samples are highly recommended.
CRIS-Team Scopus Importer:2020-10-02
Keywords: childhood maltreatment; cortical thickness; insula; somatoform pain; voxel-based morphometry

Insular multiple sclerosis lesions are associated with erectile dysfunction - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Journal of Neurology, 2018)
Erectile function (EF) is frequently compromised in men with multiple sclerosis (MS). Functional neuroimaging in healthy men identified a network of brain areas, such as the insula, visual and somatosensory association areas, cingulate gyrus, prefrontal cortex, as well as subcortical regions, contributing to EF. This study intended to determine associations between EF deterioration during MS and cerebral MS-associated lesion sites. In 31 men with MS (mean age 38.2 ± 11.2 years), we evaluated MS-related EF deterioration by comparing scores of the 5-item International Index of Erectile Function-5 questionnaire (IIEF5) at the time of study and retrospectively, 3 months prior to MS diagnosis, by calculating score differences as DeltaIIEF5 (DeltaIIEF5 score < 0 indicated EF deterioration). To assess the impact of confounding factors of EF, patient age, disease duration, disease severity, depressiveness, bladder and bowel symptoms, and total cerebral MS lesion volume were correlated with DeltaIIEF5 scores (Spearman rank correlation) and compared between patients with and without EF deterioration (t tests or Mann-Whitney U test). MS lesions were assessed on T2-weighted magnetic resonance imaging (MRI; 1.5 or 3 T). We determined the lesion overlap (prevalence of identical lesion sites among patients), subtracted lesion overlaps in patients without EF deterioration from overlaps in patients with EF deterioration, and compared DeltaIIEF5 scores voxel-wise between patients with and without lesions in a given voxel (t test; significance: p < 0.05). In 14 patients (45.2%), DeltaIIEF5 scores indicated EF deterioration. DeltaIIEF5 scores were not associated with age (ρ = 0.06; p = 0.74), disease duration (ρ = 0.26; p = 0.15), disease severity (ρ = - 0.19; p = 0.31), depressiveness (ρ = 0.07; p = 0.72), bladder symptoms (ρ = - 0.11; p = 0.57), bowel symptoms (ρ = 0.17; p = 0.37), and total lesion volume (ρ = - 0.13; p = 0.47). The voxel-wise analysis showed associations between EF deterioration and MS lesions primarily in the bilateral, and predominantly left juxtacortical insular region. In conclusion, MS lesions particularly in the left insular region, which is activated with sexual arousal, contribute to erectile dysfunction.
EVALuna2:34021

Integrity/Demyelination of the optic radiation, morphology of the papilla, and contrast sensitivity in glaucoma patients - Michelson, Georg; Wärntges, Simone; Engelhorn, Tobias; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: In primary open angle glaucoma (POAG) and its non-barotraumatic subgroup, normal tension glaucoma (NTG), the pathophysiological differences are not clear. A participation of the 4th neuron of the visual pathway (optic radiation) appears possible on the basis of related experimental studies. The goal of the present study was the evaluation of the optic radiation by diffusion tensor imaging (DTI), which is based on the magnetic resonance imaging. The diffusion and anisotropy parameters of the optic radiation as a marker of axonal integrity and demyelination/damage of glial cells, respectively, were used to investigate the relation between the morphology of the papilla (BLDF, linear discriminant function of Burk) and the contrast sensitivity (FDT, frequency doubling test). Patients and Methods: In this prospective observational study 13 POAG patients, 13 NTG patients, and 7 control patients of the same mean age were included. For segmentation of the optic radiation a semi-automated algorithm was applied and the diffusion and anisotropy parameters were calculated. The importance of the covariates age, BLDF, and FDT for the DTI parameters was determined using partial correlation analysis. Results: Analysis of the covariates partially showed a clear autocorrelation. The correlations between the DTI parameters and BLDF were significant in all groups after correction of the measurement values for the covariates. FDT correlated with DTI parameters in controls and POAG. The NTG group did not show this correlation due to a strong spreading of the FDT values. Conclusion: After statistical elimination of the autocorrelation of the covariates age, BLDF, and FDT the morphology of the papilla correlated with the axonal integrity and demyelination/glia cell impairment of the optic radiation in controls and glaucoma. In NTG the impaired contrast sensitivity is highly variable and is not associated with the condition of the 3rd or 4th neuron, respectively, as compared to POAG. The autocorrelation between individual covariates represents an important element for the judgement of the visual pathway. © Georg Thieme Verlag KG · Stuttgart · New York.

Interdisziplinäre neurovaskuläre Netzwerke: eine Standortbestimmung - Röther, J.; Busse, O.; Berlis, A.; Dörfler, Arnd; Groden, Ch; Hamann, G.; Jansen, O.; Meixensberger, J.; Müller, O.; Regelsberger, J.; Steinmetz, H.; Vatter, H.; et al. (Der Nervenarzt, 2020)
Background: In order to treat the complete spectrum of neurovascular diseases at a high level of quality, which goes beyond the purely acute treatment of stroke, the German Stroke Society (DSG) together with the German Societies for Neurosurgery and Neuroradiology developed a certification procedure for neurovascular networks (NVN). Structurally, a NVN consists of a coordinating center with at least three neurovascular network partners with a certified stroke unit. From 2018 to 2020 a total of 15 NVN have so far been audited and certified according to this new standard. Objective: How efficient are the NVN? Are high standards maintained? Material and methods: The reports of the audits were analyzed. The data were taken from the period 2017–2019. Results: The 15 NVN treated a total of 86,510 stroke patients in the years examined and were networked with a total of 107 partner clinics, which were situated an average of 25 km from the coordinating center and transferred a total of 2726 patients. The coordinating centers performed 2463 thrombectomies and treated 2383 patients with nontraumatic intracerebral bleeding. In 712 patients with acute aneurysmatic subarachnoid hemorrhages endovascular treatment was carried out and clipping in 401. The audit was successful in the majority of the NVN. Conclusion: The certification process of NVN has been successfully established and the audits proved to be a useful instrument for quality control and improvement. The 15 NVN are highly efficient and treat more than one quarter of stroke patients in German stroke units.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Clipping; Endovascular treatment; Interhospital cooperation; Stroke unit; Thrombectomy

Interictal Electrical Source Imaging. - Rampp, Stefan; Müller-Voggel, Nadia; Hamer, Hajo; Dörfler, Arnd; Brandner, Sebastian; Buchfelder, Michael (Journal of Clinical Neurophysiology, 2024)
Interictal electrical source imaging (ESI) determines the neuronal generators of epileptic activity in EEG occurring outside of seizures. It uses computational models to take anatomic and neuronal characteristics of the individual patient into account. The presented article provides an overview of application and clinical value of interictal ESI in patients with pharmacoresistant focal epilepsies undergoing evaluation for surgery. Neurophysiological constraints of interictal data are discussed and technical considerations are summarized. Typical indications are covered as well as issues of integration into clinical routine. Finally, an outlook on novel markers of epilepsy for interictal source analysis is presented. Interictal ESI provides diagnostic performance on par with other established methods, such as MRI, PET, or SPECT. Although its accuracy benefits from high-density recordings, it provides valuable information already when applied to EEG with only a limited number of electrodes with complete coverage. Novel oscillatory markers and the integration of frequency coupling and connectivity may further improve accuracy and efficiency.
EVALuna2:547206

Interictal magnetoencephalography used in magnetic resonance imaging-negative patients with epilepsy - Wu, Xueqing; Rampp, Stefan; Buchfelder, Michael; Kuwert, Torsten; Blümcke, Ingmar; Zhou, D.; Stefan, Herrmann; Dörfler, Arnd (Acta Neurologica Scandinavica, 2013)
Purpose: This study aims to investigate the contributions of magnetoencephalography (MEG) in magnetic resonance imaging (MRI)-negative patients. Methods: A total of 18 MRI-negative patients diagnosed with refractory epilepsy, subjected to MEG investigation, and subsequently underwent surgery were selected for retrospective analysis. A 1.5-tesla Magnetom Sonata with an eight-channel head array coil was used. MEG data were obtained using a 74/248-channel system. Results: A total of 16 patients (16/18) had positive MEG results, comprising 12 patients with monofocal localizations, five with multifocal localizations, and one with unremarkable results in MEG. In addition, 12 patients had indicative single photon-emission computed tomography (SPECT), five had indicative fluorodeoxyglucose positron emission tomography (FDG-PET), and all the patients had intracranial electroencephalography (EEG) (14 with subdural electrodes and four with electrocorticography). The intracranial EEG recordings of nine patients were guided by MEG informative results. Among these 18 patients, 10 exhibited good postoperative outcomes (Engel I and II), four of which were completely seizure-free. All these ten patients had clear monofocal localization in MEG, including nine with accordant indicative metabolic changes in either SPECT or FDG-PET, or both. None of the five patients with multifocal localizations achieved good postoperative outcomes. Conclusion: For cases with negative MRI findings, epilepsy surgery may be an alternative option for pharmaco-resistant patients if epileptogenic focus localizations by MEG are present in multimodal evaluation. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Magnetic resonance imaging; Magnetoencephalography; Non-lesional epilepsy; Outcome

Intraparenchymal Hyperattenuations on Flat-Panel CT Directly After Mechanical Thrombectomy are Restricted to the Initial Infarct Core on Diffusion-Weighted Imaging. - Schneider, Tanja; Mahraun, Tobias; Schroeder, Julian; Froelich, Andreas; Hölter, Philip; Wagner, Marlies; Darcourt, Jean; Cognard, Christophe; Bonafe, Alain; Fiehler, Jens; Siemonsen, Susanne; Buhk, Jan-Hendrik (Clinical Neuroradiology, 2018)
PURPOSE: The presence of intraparenchymal hyperattenuations (IPH) on flat-panel computed tomography (FP-CT) after endovascular recanalization in stroke patients is a common phenomenon. They are thought to occur in ischemic areas with breakdown of the blood-brain barrier but previous studies that investigated a mutual interaction are scarce. We aimed to assess the relationship of IPH localization with prethrombectomy diffusion-weighted imaging (DWI) lesions. METHODS: This retrospective multicenter study included 27 acute stroke patients who underwent DWI prior to FP-CT following mechanical thrombectomy. After software-based coregistration of DWI and FP-CT, lesion volumetry was conducted and overlapping was analyzed. RESULTS: Two different patterns were observed: IPH corresponding to the DWI lesion and IPH exceeding the DWI lesion. The latter showed demarcated infarction of DWI exceeding IPH at 24 h. No major hemorrhage following IPH was observed. Most IPH were manifested within the basal ganglia and insular cortex. CONCLUSION: The IPH primarily appeared within the initial ischemic core and secondarily within the penumbral tissue that progressed to infarction. The IPH represent the minimum final infarct volume, which may help in periinterventional decision making.
EVALuna2:382841

Intraprocedural angiographic CT as a valuable tool in the course of endovascular treatment of direct sinus cavernous fistulas - Gölitz, Philipp; Struffert, Tobias; Saake, Marc; Knossalla, F.; Dörfler, Arnd (Interventional Neuroradiology, 2012)
This investigation aimed to demonstrate the potential of intraprocedural angiographic CT in monitoring complex endovascular coil embolization of direct carotid cavernous fistulas. Angiographic CT was performed as a dual rotational 5 s run with intraarterial contrast medium injection in two patients during endovascular coil embolization of direct carotid cavernous fistulas. Intraprocedural angiographic CT was considered helpful if conventional 2D series were not conclusive concerning coil position or if a precise delineation of the parent artery was impossible due to a complex anatomy or overlying coil material. During postprocessing multi-planar reformatted and dual volume images of angiographic CT were reconstructed. Angiographic CT turned out to be superior in the intraprocedural visualization of accidental coil migration into the parent artery where conventional 2D-DSA series failed to reliably detect coil protrusion. The delineation of coil protrusion by angiographic CT allowed immediate correct coil repositioning to prevent parent artery compromising. Angiographic CT can function as a valuable intraprocedurally feasible tool during complex coil embolizations of direct carotid cavernous fistulas. It allows the precise visualization of the cerebral vasculature and any accidental coil protrusion can be determined accurately in cases where conventional 2D-DSA series are unclear or compromised. Thus angiographic CT might contribute substantially to reduce procedural complications and to increase safety in the management of endovascular treatment of direct carotid cavernous fistulas.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Carotid cavernous fistula; Endovascular approach; Intraprocedural angiographic CT; Transarterial coil embolization

Intratumoral heterogeneity of oxygen metabolism and neovascularization uncovers 2 survival-relevant subgroups of IDH1 wild-type glioblastoma - Stadlbauer, Andreas; Zimmermann, Max; Dörfler, Arnd; Oberndorfer, Stefan; Buchfelder, Michael; Coras, Roland; Kitzwoegerer, Melitta; Roessler, Karl (Neuro-Oncology, 2018)
Background: The intratumoral heterogeneity of oxygen metabolism in combination with variable patterns of neovascularization (NV) as well as reprogramming of energy metabolism affects the landscape of tumor microenvironments (TMEs) in glioblastoma. Knowledge of the hypoxic and perivascular niches within the TME is essential for understanding treatment failure. Methods: Fifty-two patients with untreated glioblastoma (isocitrate dehydrogenase 1 wild type [IDH1wt]) were examined with a physiological MRI protocol including a multiparametric quantitative blood oxygen level dependent (qBOLD) approach and vascular architecture mapping (VAM). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of 6 different TMEs: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation (OxPhos), and glycolysis with/without neovascularization. Association of the different TME volume fractions with progression-free survival (PFS) was assessed using Kaplan-Meier analysis and Cox proportional hazards models. Results: A common spatial structure of TMEs was detected: central necrosis surrounded by tumor hypoxia (with defective and functional neovasculature) and different TMEs with a predominance of OxPhos and glycolysis for energy production, respectively. The percentage of the different TMEs on the total tumor volume uncovered 2 clearly different subtypes of glioblastoma IDH1wt: a glycolytic dominated phenotype with predominantly functional neovasculature and a necrotic/hypoxic dominated phenotype with approximately 50% of defective neovasculature. Patients with a necrotic/hypoxic dominated phenotype showed significantly shorter PFS (P = 0.035). Conclusions: Our non-invasive mapping approach allows for classification of the TME and detection of tumor-supportive niches in glioblastoma which may be helpful for both clinical patient management and research.
EVALuna2:36560

Intraventricular fibrinolysis does not increase perihemorrhagic edema after intracerebral hemorrhage - Volbers, Bastian; Wagner, Irina; Willfarth, Wolfgang; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (Stroke, 2013)
BACKGROUND AND PURPOSE - : Additional intraventricular hemorrhage leads to higher mortality and worse functional outcome after intracerebral hemorrhage (ICH). Intraventricular fibrinolysis (IVF) with recombinant tissue plasminogen activator (rtPA) is an emerging treatment strategy for such patients. However, experimental studies suggest that rtPA may exert proedematous effects and lead to increased perihemorrhagic edema (PHE) after ICH. We aimed to compare the course of PHE after ICH between patients who received IVF with rtPA and controls matched for ICH volume. METHODS - : Patients were identified retrospectively from our institutional ICH database. Sixty-four patients with ICH and intraventricular hemorrhage who were treated with IVF were compared with 64 controls, who did not receive IVF, matched for ICH volume. The course of PHE was assessed on computed tomography scans (day 1, days 2 and 3, days 4-6, 7-9, and 10-12) using a threshold-based semiautomatic volumetric algorithm. Relative PHE was calculated as a ratio of PHE volume and initial ICH volume. RESULTS - : The matching algorithm resulted in similar mean ICH volumes in both groups (20.01±17.5 mL, IVF vs 20.08±17.1 mL, control). Intraventricular hemorrhage volume was larger in the IVF group (26.8±19.2 mL vs 9.2±13.4 mL). The mean total rtPA dose used for IVF was 8±6 mg. PHE increased over time in both groups until day 12. At all investigated time points, there was no significant difference in relative PHE between the IVF group and controls (F=0.39; P=0.844). CONCLUSIONS - : IVF with rtPA did not lead to a relevant increase in PHE after ICH. rtPA doses used in the current study seem to be safe regarding PHE. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: intracerebral hemorrhage; intraventricular fibrinolysis; intraventricular hemorrhage; perihemorrhagicedema; recombinant tissue-type plasminogen activator; semiautomatic volumetry; X-ray computed tomography

Intraventricular fibrinolysis has no effects on shunt dependency and functional outcome in endovascular-treated aneurysmal SAH - Gerner, Stefan; Kuramatsu, Joji; Abel, Henning; Kloska, Stephan; Lücking, Hannes; Eyüpoglu, Ilker Yasin; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Neurocritical Care, 2014)
Intraventricular fibrinolysis (IVF) in subarachnoid hemorrhage (SAH) is an emerging strategy aiming to hasten clot lysis, treat hydrocephalus, and reduce permanent shunt rates. Because of clinical heterogeneity of investigated patient effects of IVF on permanent shunt incidence and functional outcome are widely debated. The present study is the first to investigate solely endovascular-treated SAH patients.Overall, 88 consecutive patients with aneurysmal SAH requiring external ventricular drain placement and endovascular aneurysm closure were included. Functional outcome and shunt dependency were assessed 90 days after event. A matched controlled sub-analysis was carried out to investigate the effects of IVF treatment (n = 14; matching criteria: age, neuro-status and imaging). Multivariate modeling was performed to identify independent predictors for permanent shunt dependency.In IVF-patients neurological status was significantly poorer [Hunt&Hess: IVF = 4(3-5) vs. non-IVF = 3(1-5); p = 0.035] and the extent of ventricular hemorrhage was increased [Graeb Score: IVF = 7(6-8) vs. non-IVF = 3(1-4); p <= 0.001]. Consecutive matched controlled sub-analysis revealed no significant therapeutic effect of IVF with respect to shunt dependency rate and functional outcome. Multivariate analysis revealed Graeb score [OR = 1.34(1.02-1.76); p = 0.035] and sepsis [OR = 11.23(2.28-55.27); p = 0.003] as independent predictors for shunt dependency, whereas IVF did not exert significant effects (p = 0.820).In endovascular-treated SAH patients IVF neither reduced permanent shunt dependency nor influenced functional outcome. Despite established effects on intraventricular clot resolution IVF appears less powerful in SAH as compared to ICH. Given the reported positive effects of lumbar drainage (LD) in SAH, a prospective analysis of a combined treatment approach of IVF and subsequent lumbar drain sOeems warranted aiming to reduce permanent shunting and improve functional outcome.
EVALuna2:22283

Invasiveness and Clinical Outcomes of Off-Hour Admissions in Patients with Intracerebral Hemorrhage - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Kuramatsu, Joji; Lücking, Hannes; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Journal of Stroke and Cerebrovascular Diseases, 2019)
BACKGROUND: Whether time of hospital admission-during or outside regular working hours-affects functional outcome in intracerebral hemorrhage (ICH) is unestablished as previous analyses have focused on mortality only. We here investigate whether on- versus off-hour hospital admission in ICH is associated with levels of invasiveness and clinical outcomes. METHODS: Based on the UKER registry (NCT03183167) we grouped ICH-patients according to on- versus off-hour hospital admission. Primary outcome measures was functional outcome after 3 months using the modified Rankin scale (mRS) dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6). Multivariate regression analyses were used to adjust for baseline imbalances, and subgroup analyses were performed to explore associations of on- versus off-hour admission with invasiveness of therapeutic interventions. RESULTS: A total of 438/1269 (34.5%) of ICH-patients were admitted during regular working hours. Mortality rates were not significantly different among patients with on- versus off-hour admission. On-hour patients showed a significantly larger proportion of patients with favorable outcome (on-hour: mRS = 0-3 after 3 months: 176/416 (42.3%) versus off-hour: 265/784 (33.8%); P = .004). Analysis of invasive therapeutic interventions revealed that likelihood of favorable outcome was significantly increased among on-hour admitted patients who did not require neurosurgical interventions (no external ventricular drain n = 349, OR: 1.67[1.13-2.48], P < .05; no hematoma evacuation surgery n = 423, OR: 1.51[1.07-2.14], P < .05). CONCLUSION: This study verified an "off-hour effect" in ICH that relates to functional outcome, rather than mortality, and which may be linked to different levels of invasive therapeutic interventions in patients admitted during off-hour.
EVALuna2:206735

Investigation of lateral geniculate nucleus volume and diffusion tensor imaging in patients with normal tension glaucoma using 7 tesla magnetic resonance imaging - Schmidt, Manuel; Knott, Michael; Heidemann, Robin; Michelson, Georg; Kober, Tobias; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2018)
BACKGROUND: There is evidence that glaucoma is a neurodegenerative disease involving the whole visual pathway. We prospectively examined potential benefits of volumetry of the lateral geniculate nucleus (LGN) and diffusion tensor imaging (DTI) using a new 7T scanner. METHODS: 20 patients with normal tension glaucoma and 16 control individuals were examined. LGN volume and fractional anisotropy (FA) of the optic tract (OT) and the optic radiation (OR) and their correlation with RNFL (retinal nerve fiber layer) thickness were analyzed. RESULTS: LGN volume was significantly reduced in NTG (60.9 vs 88.3; p < 0.05). FA of the OT (right: 0.35 vs 0.66, left: 0.36 vs 0.67; p < 0.05) and of the OR (right: 0.41 vs 0.70, left: 0.41 vs 0.69; p < 0.05) was also significantly reduced. Nasal RNFL thickness correlated with the volume of the contralateral LGN (r = 0.471, p = 0.05). Temporal RNFL thickness correlated with the volume of the ipsilateral LGN (r = 0.603, p = 0.015). CONCLUSION: NTG leads to significant atrophy of the LGN compared to controls. FA of the optic tract and the optic radiation is reduced in NTG as sign of axonal degeneration. RNFL thickness but not FA correlates with LGN volume.
EVALuna2:34502

Investigation of subdural electrode displacement in invasive epilepsy surgery workup using neuronavigation and intraoperative MRI - Sommer, Bjoern; Rampp, Stefan; Dörfler, Arnd; Stefan, Hermann; Hamer, Hajo; Buchfelder, Michael; Roessler, Karl (Neurological Research, 2018)
OBJECTIVES: One of the main obstacles of electrode implantation in epilepsy surgery is the electrode shift between implantation and the day of explantation. We evaluated this possible electrode displacement using intraoperative MRI (iopMRI) data and CT/MRI reconstruction. METHODS: Thirteen patients (nine female, four male, median age 26 ± 9.4 years) suffering from drug-resistant epilepsy were examined. After implantation, the position of subdural electrodes was evaluated by 3.0 T-MRI and thin-slice CCT for 3D reconstruction. Localization of electrodes was performed with the volume-rendering technique. Post-implantation and pre-explantation 1.5 T-iopMRI scans were coregistered with the 3D reconstructions to determine the extent of electrode dislocation. RESULTS: Intraoperative MRI at the time of explantation revealed a relevant electrode shift in one patient (8%) of 10 mm. Median electrode displacement was 1.7 ± 2.6 mm with a coregistration error of 1.9 ± 0.7 mm. The median accuracy of the neuronavigation system was 2.2 ± 0.9 mm. Six of twelve patients undergoing resective surgery were seizure free (Engel class 1A, median follow-up 37.5 ± 11.8 months). CONCLUSION: Comparison of pre-explantation and post-implantation iopMRI scans with CT/MRI data using the volume-rendering technique resulted in an accurate placement of electrodes. In one patient with a considerable electrode dislocation, the surgical approach and extent was changed due to the detected electrode shift. ABBREVIATIONS: ECoG: electrocorticography; EZ: epileptogenic zone; iEEG: invasive EEG; iopMRI: intraoperative MRI; MEG: magnetoencephalography; PET: positron emission tomography; SPECT: single photon emission computed tomography; 3D: three-dimensional.
EVALuna2:201939

Ischaemic stroke and Clostridium septicum sepsis and meningitis in a patient with occult colon carcinoma - a case report and review of the literature - Macha, Kosmas; Giede-Jeppe, Antje; Lücking, Hannes; Coras, Roland; Huttner, Hagen; Held, Jürgen (BMC Neurology, 2016)
Clostridium septicum is a rare cause of meningitis and brain abscess in children and adults. Gas production by the pathogen can lead to pneumocephalus and the overall mortality rate of Clostridium septicum CNS infection is as high as 74%. The most common entry site of the pathogen is the gastrointestinal tract.We describe a 74-year-old man who presented with a left-sided cerebral infarction in the middle cerebral artery territory. In addition the patient showed signs of Systemic Inflammatory Response Syndrome and Disseminated Intravascular Coagulation. Examination of blood cultures and cerebrospinal fluid led to the diagnosis of sepsis and meningitis caused by Clostridium septicum. Despite appropriate antibiotic therapy the condition of the patient deteriorated rapidly and he died on day 2 after admission. Autopsy revealed a previously unknown adenocarcinoma of the colon ascendens as entry site of the pathogen.Clostridium septicum should be considered as potential pathogen in patients with sepsis and meningitis. Gram stain morphology in conjunction with severe sepsis can rapidly point into the direction of this pathogen. CNS infections manifest either as meningoencephalitis/cerebritis or as brain abscess. Entry site of the pathogen is almost uniquely the gastrointestinal tract. In adults more than 50% suffer from colorectal carcinoma, therefore survivors of Clostridium septicum infections should be examined for underlying occult colorectal malignancy.
EVALuna2:7346

Ischemic stroke associated with the use of a synthetic cannabinoid (spice) - Möller, Sebastian; Luecke, Caroline; Struffert, Tobias; Schwarze, Bernhard; Gerner, Stefan; Schwab, Stefan; Köhrmann, Martin; Machold, Kristin; Philipsen, Alexandra; Mueller, Helge H. (Asian Journal of Psychiatry, 2017)
Synthetic cannabinoids, i.e. "spice", are psychoactive drugs with increasing use worldwide. Spice may have harmful neuropsychiatric and physical side effects. Here, we present the case of a 25-year-old man with ischemic stroke after smoking spice on the previous evening. Diagnostic work-up was negative for other common causes of stroke. Toxicology screen unveiled the cannabimimetic ADB-FUBINACA in the drug sample and in patient's urine. The cardiac sympathomimetic effect of spice might have triggered an unnoticed episode of tachyarrhythmia and resulted in stroke via cardioembolic etiology. Thus, in absence of other risk factors, a careful patient history of spice use is recommended for patients with acute neurological deficits.
EVALuna2:22545

Is Hypothermia Helpful in Severe Subarachnoid Hemorrhage? An Exploratory Study on Macro Vascular Spasm, Delayed Cerebral Infarction and Functional Outcome after Prolonged Hypothermia - Kuramatsu, Joji; Kollmar, Rainer; Gerner, Stefan; Madzar, Dominik; Pisarcikova, Andrea; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (Cerebrovascular Diseases, 2015)
Therapeutic hypothermia (TH) is an established treatment after cardiac arrest and growing evidence supports its use as neuroprotective treatment in stroke. Only few and heterogeneous studies exist on the effect of hypothermia in subarachnoid hemorrhage (SAH). A novel approach of early and prolonged TH and its influence on key complications in poor-grade SAH, vasospasm and delayed cerebral ischemia (DCI) was evaluated.This observational matched controlled study included 36 poor-grade (Hunt and Hess Scale >3 and World Federation of Neurosurgical Societies Scale >3) SAH patients. Twelve patients received early TH (<48 h after ictus), mild (35°C), prolonged (7 ± 1 days) and were matched to 24 patients from the prospective SAH database. Vasospasm was diagnosed by angiography, macrovascular spasm serially evaluated by Doppler sonography and DCI was defined as new infarction on follow-up CT. Functional outcome was assessed at 6 months by modified Rankin Scale (mRS) and categorized as favorable (mRS score 0-2) versus unfavorable (mRS score 3-6) outcome.Angiographic vasospasm was present in 71.0% of patients. TH neither influenced occurrence nor duration, but the degree of macrovascular spasm as well as peak spastic velocities were significantly reduced (p < 0.05). Frequency of DCI was 87.5% in non-TH vs. 50% in TH-treated patients, translating into a relative risk reduction of 43% and preventive risk ratio of 0.33 (95% CI 0.14-0.77, p = 0.036). Favorable functional outcome was twice as frequent in TH-treated patients 66.7 vs. 33.3% of non-TH (p = 0.06).Early and prolonged TH was associated with a reduced degree of macrovascular spasm and significantly decreased occurrence of DCI, possibly ameliorating functional outcome. TH may represent a promising neuroprotective therapy possibly targeting multiple pathways of DCI development, notably macrovascular spasm, which strongly warrants further evaluation of its clinical impact.
EVALuna2:22357

Isolated meningomyeloradiculitis following infection with tick borne encephalitis virus - Racz, Attila; Schaller, Gerd; Lunkenheimer, Jens; Engelhorn, Tobias; Dörfler, Arnd; Sperling, Wolfgang; Schwab, Stefan; Maihöfner, Christian (Clinical Neurology and Neurosurgery, 2012)
CRIS-Team Scopus Importer:2022-08-05
Keywords: Meningomyeloradiculitis; Myelitis; Polyradiculitis; Tick borne encephalitis virus

Isolated Unilateral Strabismus Sursoadductorius (Congenital Trochlear Palsy) with and without Hypotrophia of the Superior Oblique Muscle-Orthoptic Differences in Adulthood - Gusek-Schneider, Gabriele-Charlotte; Kaestle, Nicola; Reil, Franziska; Schuerhoff, Sabine; Engelhorn, Tobias (Klinische Monatsblätter für Augenheilkunde, 2018)
PURPOSE: The clinical feature of unilateral decompensating strabismus sursoadductorius (dSSA; often called congenital superior oblique palsy, CSOP) is not an etiologically uniform entity. Hypotrophy of the superior oblique muscle (HMOS) is a frequent and immediate cause of dSSA/CSOP. In this study, clinical characteristics of dSSA/CSOP with and without HMOS are compared. PATIENTS AND METHODS: Twenty-five consecutive patients (age 14 - 69 years; median 43 years) were included in this study, 14 with 3T MRI-proven HMOS (group 1) and 11 without HMOS (group 2). HMOS was defined as a reduction of the medio-lateral (ML) as well as based on ML and cranio-caudal (CC) diameter calculated area = (ML · CC/4) · π of the affected superior oblique muscle (SOM) < 80% in comparison to the contralateral SOM (measured on the single coronal image on which the muscle has its greatest extent). The two groups were compared in terms of head tilt, cyclo- and vertical deviation and the Bielschowsky head tilt test. Patients were classified according the Knapp's classification. RESULTS: Both the incidence of head tilt with 14/14 vs. 5/11 (χ2 = 0.003) and its degree: 11.1 ± 4.5° vs. 3.2 ± 4.1° (p < 0.001) was higher in group 1 than in group 2, as well as the Bielschowsky head tilt test: 9.3 ± 4.3° vs. 3.8 ± 4.9° (p = 0.008). The average amount of hypertropia was larger in group 1 than in group 2 during adduction: 16.7 ± 5.3° vs. 9.3 ± 3.4° (p < 0.001) as well as during adduction and downgaze of the affected eye: 14.6 ± 7.1 vs. 7.2 ± 3.7° (p = 0.03). In the sagittal plane, the increase of vertical deviation was larger in group 1 than in group 2: 2.8 ± 7.8 vs. - 2.4 ± 4.2 (p = 0.04); the excyclodeviation was larger in group 1 in all three planes (sagittal plane, adduction and abduction) in comparison to group 2: 1.3 ± 4.1 vs. - 2.9 ± 2.8 (p = 0.006), 2.4 ± 5.2 vs. - 2.2 ± 2.9 (p = 0.01), 0.5 ± 3.8 vs. - 2.7 ± 3.9 (p = 0.05). Knapp's class II was found in 6 of 15 patients in group 1 and only in this patient group (χ2 = 0.03). CONCLUSIONS: In both groups, the vertical deviation showed a great dispersion. In patients without HMOS (group 2), vertical deviation in adduction did not exceed 15°. Patients with HMOS (group 1) do not show the typical features of a later acquired trochlear palsy due to an early developed compensating innervation. A vertical deviation in adduction of more than 15°, increasing excyclodeviation towards downgaze in all three planes (sagittal plane, adduction and abduction) and Knapp's class II are relatively reliable predictors of a hypoplasia of the SOM. An internationally uniform term for this group of patients, such as superior oblique weakness or superior oblique hypotrophy, would be desirable.
EVALuna2:34915

Is "prepectoral edema" a morphologic sign for malignant breast tumors? - Kaiser, Clemens G.; Herold, Michael; Baltzer, Pascal A. T.; Dietzel, Matthias; Krammer, Julia; Gajda, Mieczyslaw; Camara, Oumar; Schoenberg, Stefan O.; Kaiser, Werner A.; Wasser, Klaus (Academic Radiology, 2015)
A variety of morphologic and kinetic signs of benign or malignant breast lesions contribute to a final diagnosis and differential diagnosis in magnetic resonance (MR) mammography (MRM). As a new sign, prepectoral edema (PE) in patients without any history of previous biopsy, operation, radiation, or chemotherapy was detected during routine breast MR examinations. The purpose of this study was to retrospectively evaluate the role of this morphologic sign in the differential diagnosis of breast lesions.Between January 2005 and October 2006, a total of 1109 consecutive MRM examinations have been performed in our institution. In this study, only patients who would later be biopsied or operated in our own hospital were included. They had no previous operation, biopsy, intervention, chemotherapy, hormone replacement therapy, or previous mastitis. In total, 162 patients with 180 lesions were included, histologically correlated later-on by open biopsy (124 patients and 136 lesions) or core biopsy (38 patients and 44 lesions). The evaluations were performed by four experienced radiologists in consensus.One hundred eighty evaluated lesions included 104 malignant lesions (93 invasive and 11 noninvasive cancers) and 76 benign lesions. PE was detected in 2.6% of benign lesions (2 of 76), in none of the Ductal cacinoma in situ (DCIS) cases (0 of 11), and in 25.8% of malignant lesions (24 of 93; P < .000). PE was found significantly more frequently in presence of malignant tumors >2 cm in diameter (48.5%, 17 of 35 vs. 13.8%, 8 of 58; P < .001). PE was not statistically associated to malignant tumor type, presence or absence of additional DCIS, and number of lesions. This resulted in the following diagnostic parameters for PE as an indicator for malignancy: sensitivity of 19.3%, specificity of 97.3%, positive predictive value (PPV) of 92.3%, negative predictive value of 48%, and accuracy of 57.7%.In case of occurrence, the "PE sign" seems to be a specific indicator for malignant tumors with a high PPV, independent from its entity.
EVALuna2:23002

IV-Thrombolysis in Ischemic Stroke With Unknown Time of Onset—Safety and Outcomes in Posterior vs. Anterior Circulation Stroke - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Wang, Ruihao; Knott, Michael; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Mühlen, Iris; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background: rt-PA for ischemic stroke in the unknown or extended time window beyond the first 4. 5 h after symptom onset is safe and effective for certain patients after selection by multimodal neuroimaging. However, the evidence for this approach comes mainly from patients with anterior circulation stroke (ACS), while the data on posterior circulation stroke (PCS) are scarce. Methods: Ischemic stroke patients treated with IV-thrombolysis in the unknown or extended time window between January 2011 and May 2019 were identified from an institutional registry. The patients were categorized into PCS or ACS based on clinico-radiological findings. We analyzed the hemorrhagic complications, clinical and imaging efficacy outcomes, and mortality rates by comparing the PCS and ACS patient groups. Adjusted outcome analyses were performed after propensity score matching for the relevant factors. Results: Of the 182 patients included, 38 (20.9%) had PCS and 144 (79.1%) had ACS. Symptomatic acute large vessel occlusion (LVO) was present in 123 patients on admission [27 (22.0%) PCS and 96 (78.0%) ACS]. The score on the National Institutes of Health Stroke Scale (NIHSS), the time from last seen normal, and the door-to-needle times were similar in PCS and ACS. In patients with LVO, the NIHSS score was lower [8 (5–15) vs. 14 (9–18), p = 0.005], and infarction visible on follow-up imaging was less common [70.4 vs. 87.5%; aRD, −18.9% (−39.8 to −2.2%)] in the PCS patient group. There was a trend toward a lower risk for intracranial hemorrhage (ICH) following intravenous thrombolysis in PCS vs. ACS, without reaching a statistical significance [5.3 vs. 16.9%; aRD, −10.4% (−20.4 to 4.0%)]. The incidence of symptomatic ICH [according to the ECASS III criteria: 2.6 vs. 3.5%; aRD, −2.9% (−10.3 to 9.2%)], efficacy outcomes, and mortality rates were similar in PCS and ACS patients. Conclusions: In this real-world clinical cohort, the safety and the efficacy of rt-PA for ischemic stroke in the unknown or extended time window did not show relevant differences between PCS and ACS, with a trend toward less hemorrhagic complications in PCS. The findings reconfirm the clinician in the usage of rt-PA beyond the first 4.5 h also in selected patients with PCS.
CRIS-Team Scopus Importer:2021-10-01
Keywords: anterior circulation stroke; extended time window; IV-thrombolysis; posterior circulation stroke; wake-up stroke

Janus-faced spatacsin (SPG11): involvement in neurodevelopment and multisystem neurodegeneration - Pozner, Tatyana; Regensburger, Martin; Engelhorn, Tobias; Winkler, Jürgen; Winner, Beate (Brain, 2020)
Hereditary spastic paraplegia (HSP) is a heterogeneous group of rare motor neuron disorders characterized by progressive weakness and spasticity of the lower limbs. HSP type 11 (SPG11-HSP) is linked to pathogenic variants in the SPG11 gene and it represents the most frequent form of complex autosomal recessive HSP. The majority of SPG11-HSP patients exhibit additional neurological symptoms such as cognitive decline, thin corpus callosum, and peripheral neuropathy. Yet, the mechanisms of SPG11-linked spectrum diseases are largely unknown. Recent findings indicate that spatacsin, the 280 kDa protein encoded by SPG11, may impact the autophagy-lysosomal machinery. In this update, we summarize the current knowledge of SPG11-HSP. In addition to clinical symptoms and differential diagnosis, our work aims to link the different clinical manifestations with the respective structural abnormalities and cellular in vitro phenotypes. Moreover, we describe the impact of localization and function of spatacsin in different neuronal systems. Ultimately, we propose a model in which spatacsin bridges between neurodevelopmental and neurodegenerative phenotypes of SPG11-linked disorders.
CRIS-Team Scopus Importer:2020-09-04
Keywords: autophagy; hereditary spastic paraplegia; neurodegeneration; neurodevelopment; SPG11

Klinische und echographische Untersuchungsbefunde bei Patienten mit Carotis-Sinus-cavernosus-Fisteln - Huebner, L.; Struffert, T.; Mardin, Christian; Engelhorn, Tobias; Holbach, L.; Weller, J.; Hohberger, Bettina; Gusek-Schneider, Gabriele (Ophthalmologe, 2021)
Background: Symptoms and clinical findings in patients with carotid-cavernous fistulas are specific. Nevertheless, they can be very mildly expressed. This study aims to point out the potential diagnostic value of ultrasound of the orbit. Methods: A total of 25 patients with a reliable angiographic diagnosis of a fistula were reviewed retrospectively. We analyzed the symptoms, clinical findings and demonstrability in ultrasound of the orbit. Results: The most common clinical findings were nerve palsy, dilation of episcleral vessels and exophthalmos. If an ultrasound had been part of the examination a dilation of the superior ophthalmic vein could be demonstrated in all cases. Conclusion: The expeditious ultrasound investigation provides valuable information for the diagnosis of red eyes which are resistant to treatment. The examiner has to consider a fistula and perform an ultrasound especially when diplopia has newly occurred. Finally, the expedient neuroimaging can be arranged.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Diplopia; Echography; Exophthalmos; Red eye; Superior ophthalmic vein

Learning Curve for Flow Diversion of Posterior Circulation Aneurysms: A Long-Term International Multicenter Cohort Study - Adeeb, N.; Dibas, Mahmoud; Griessenauer, C. J.; Cuellar, H. H.; Salem, M. M.; Xiang, S.; Enriquez-Marulanda, A.; Hong, T.; Zhang, H.; Taussky, P.; Grandhi, R.; Waqas, M.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Flow diversion has gradually become a standard treatment for intracranial aneurysms of the anterior circulation. Recently, the off-label use of the flow diverters to treat posterior circulation aneurysms has also increased despite initial concerns of rupture and the suboptimal results. This study aimed to explore the change in complication rates and treatment outcomes across time for posterior circulation aneurysms treated using flow diversion and to further evaluate the mechanisms and variables that could potentially explain the change and outcomes. MATERIALS AND METHODS: A retrospective review using a standardized data set at multiple international academic institutions was performed to identify patients with ruptured and unruptured posterior circulation aneurysms treated with flow diversion during a decade spanning January 2011 to January 2020. This period was then categorized into 4 intervals. RESULTS: A total of 378 procedures were performed during the study period. Across time, there was an increasing tendency to treat more vertebral artery and fewer large vertebrobasilar aneurysms (P = .05). Moreover, interventionalists have been increasingly using fewer overlapping flow diverters per aneurysm (P = .07). There was a trend toward a decrease in the rate of thromboembolic complications from 15.8% in 2011?13 to 8.9% in 2018?19 (P = .34).CONCLUSIONS: This multicenter experience revealed a trend toward treating fewer basilar aneurysms, smaller aneurysms, and increased usage of a single flow diverter, leading to a decrease in the rate of thromboembolic and hemorrhagic complications.
CRIS-Team WoS Importer:2022-10-28

Lesion correlates of secondary paroxysmal dyskinesia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Huhn, Konstantin; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Schwab, Stefan; Seifert, Frank (Journal of Neurology, 2018)
Secondary paroxysmal dyskinesia is a rare but life-quality-compromising symptom in multiple sclerosis (MS) and might be associated with particular MS lesions. The present study intended to determine associations between paroxysmal dyskinesia and the MS-associated lesion site using a voxelwise lesion analysis. We conducted a retrospective study and sought MS patients with documented paroxysmal dyskinesia and controls without paroxysmal dyskinesia matched for age, disease severity, and disease duration in a local database. The MS lesions were analysed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T), manually outlined, and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of paroxysmal dyskinesia voxelwise between patients with and without lesions in a given voxel using the Liebermeister test with 4000 permutations. From 15,869 MS patient records screened, we identified 25 patients with paroxysmal dyskinesia. The voxelwise analysis in 22 subjects yielded associations between paroxysmal dyskinesia and MS lesions in the internal capsule, the basal ganglia, and another prominent lesion cluster in the posterior periventricular white matter. Our voxelwise analysis shows associations between paroxysmal dyskinesia and MS lesions in the internal capsule and basal ganglia, areas contributing to motor sequence programming. This association in another lesion site located in the posterior thalamic radiation suggests that lesions in subcortical sensory pathways may also contribute to paroxysmal dyskinesia in MS.
EVALuna2:34912

Lesion mapping of stroke-related erectile dysfunction - Winder, Klemens; Seifert, Frank; Köhrmann, Martin; Crodel, Carl; Kloska, Stephan; Dörfler, Arnd; Hoesl, Katharina M.; Schwab, Stefan; Hilz, Max-Josef (Brain, 2017)
Acute ischaemic stroke in brain areas contributing to male sexual function may impair erectile function depending on the lesion site. This study intended to determine associations between stroke-related erectile dysfunction and cerebral ischaemic lesion sites using voxel-based lesion mapping. In 52 males (mean age 60.5 ± 10.5 years) with first-ever ischaemic strokes, we assessed erectile function after and retrospectively 3 months prior to the stroke using scores of the 5-item International Index of Erectile Function-5 questionnaire. We assessed cardiovascular risk factors and determined clinical stroke severity and infarct volumes as well as total brain volume by neuroimaging. We calculated correlations between patient age, clinical stroke severity, infarct volumes as well as brain volumes and the difference between erectile dysfunction scores before and after stroke. Moreover, we compared patient age, prevalence of cardiovascular risk factors, clinical stroke severity, infarct volumes and brain volumes of patients with unchanged and deteriorated erectile function after stroke. The infarcts were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed subtraction analyses of lesions. In a voxel-based lesion analysis, the difference between erectile dysfunction scores before and after stroke was correlated with the lesion site using t-test statistics. Finally, we conducted a region of interest-based multivariate linear regression analysis that was adjusted for potential confounding factors including patient age, clinical stroke severity, imaging modality, lesion size and brain volume. In 32 patients (61.5%) erectile dysfunction scores declined after the stroke and therefore had stroke-related erectile dysfunction. Deterioration of erectile dysfunction scores was not associated with patient age, clinical stroke severity, infarct volume, brain volume, and cardiovascular risk factors. The voxel-wise subtraction analysis showed associations between stroke-related erectile dysfunction and lesion sites in the right occipito-parietal cortex and thalamus, as well as in the left insula and adjacent temporo-parietal areas. Using voxel-wise t-test statistics, we showed associations between deterioration of erectile function and lesion sites in the right occipital and thalamic region, and the left parietal association area. The linear regression analysis showed that stroke-related erectile dysfunction remained associated with lesions of the right occipital and left parietal association areas after adjusting for confounding factors. In conclusion, our voxel-wise analysis indicates that deteriorating erectile function after stroke is associated with lesions in the right occipito-parietal and thalamic areas integrating visual and somatosensory information, as well as lesions in the left insular and adjacent parieto-temporal areas contributing to generating and mapping visceral arousal states.
EVALuna2:22497

Lesion type and reader experience affect the diagnostic accuracy of breast MRI: a multiple reader ROC study - Baltzer, Pascal A. T.; Kaiser, Werner Alois; Dietzel, Matthias (European Journal of Radiology, 2015)
To evaluate the influence of lesion type (mass versus non-mass) and reader experience on the diagnostic performance of breast MRI (BMRI) in a non-screening setting.Consecutive patients (mean age, 55 ± 12 years) with breast lesions that were verified by biopsy or surgery, and who had had BMRI as part of their diagnostic workup, were eligible for this retrospective single-center study. Cancers diagnosed by biopsy before BMRI were excluded to eliminate biological and interpretation bias due to biopsy or chemotherapy effects (n=103). Six blinded readers (experience level, high (HE, n=2); intermediate (IE, n=2); and low (LE, n=2)) evaluated all examinations and assigned independent MRI BI-RADS ratings. Lesion type (mass, non-mass, focal) was noted. Receiver operating characteristics (ROC) and logistic regression analysis was performed to compare diagnostic accuracies.There were 259 histologically verified lesions (123 malignant, 136 benign) investigated. There were 169 mass (103 malignant, 66 benign) and 48 non-mass lesions (19 malignant, 29 benign). Another 42 lesions that met the inclusion criteria were biopsied due to conventional findings (i.e., microcalcifications, architectural distortions), but did not enhance on MRI (41 benign, one DCIS). ROC analysis revealed a total area under the curve (AUC) between 0.834 (LE) and 0.935 (HI). Logistic regression identified a significant effect of non-mass lesions (P<0.0001) and reader experience (P=0.005) on diagnostic performance.Non-mass lesion type and low reader experience negatively affect the diagnostic performance of breast MRI in a non-screening setting.
EVALuna2:23005

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Linear projection-based CEST parameter estimation - Glang, Felix; Fabian, Moritz S.; German, Alexander; Khakzar, Katrin; Mennecke, Angelika; Liebert, Andrzej; Herz, Kai; Liebig, Patrick; Kasper, Burkhard S.; Schmidt, Manuel; Zuazua Iriondo, Enrique; Nagel, Armin M.; et al. (NMR in Biomedicine, 2022)
Isolated evaluation of multi-parametric in vivo CEST MRI often requires complex computational processing for both correction of B0 and B1 inhomogeneity and contrast generation. For that, sufficiently densely sampled Z-spectra need to be acquired. The list of acquired frequency offsets largely determines the total CEST acquisition time, while potentially representing redundant information. In this work, a linear projection-based multi parametric CEST evaluation method is introduced that offers fast B0 and B1 inhomogeneity correction, contrast generation and feature selection for CEST data, enabling reduction of the overall measurement time. To that end, CEST data acquired at 7T in 6 healthy subjects and in one brain tumor patient were conventionally evaluated by interpolation-based inhomogeneity correction and Lorentzian curve fitting. Linear regression was used to obtain coefficient vectors that directly map uncorrected data to corrected Lorentzian target parameters. L1 regularization was applied to find subsets of the originally acquired CEST measurements that still allow for such a linear projection mapping. The linear projection method allows fast and interpretable mapping from acquired raw data to contrast parameters of interest, generalizing from healthy subject training data to unseen healthy test data and to the tumor patient dataset. The L1 regularization method shows that a fraction of the acquired CEST measurements is sufficient to preserve tissue contrasts, offering up to 2.8-fold reduction of scan time. Similar observations as for the 7T data can be made for data from a clinical 3T scanner. Being a fast and interpretable computation step, the proposed method is complementary to neural networks, which have been recently employed for similar purposes. The scan time acceleration offered by the L1 regularization (‘CEST-LASSO’) constitutes a step towards better applicability of multi parametric CEST protocols in clinical context.<br
Keywords: chemical exchange saturation transfer (CEST); feature selection; LASSO; APT; NOE; linear projection

Localization of beta power decrease as measure for lateralization in pre-surgical language mapping with magnetoencephalography, compared with functional magnetic resonance imaging and validated by Wada test - Herfurth, Kirsten; Harpaz, Yuval; Rösch, Julie; Müller, Nadia; Walther, Katrin; Kaltenhaeuser, Martin; Pauli, Elisabeth; Goldstein, Abraham; Hamer, Hajo; Buchfelder, Michael; Dörfler, Arnd; Prell, Julian; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Atypical patterns of language lateralization due to early reorganizational processes constitute a challenge in the pre-surgical evaluation of patients with pharmaco-resistant epilepsy. There is no consensus on an optimal analysis method used for the identification of language dominance in MEG. This study examines the concordance between MEG source localization of beta power desynchronization and fMRI with regard to lateralization and localization of expressive and receptive language areas using a visual verb generation task. Methods: Twenty-five patients with pharmaco-resistant epilepsy, including six patients with atypical language lateralization, and ten right-handed controls obtained MEG and fMRI language assessment. Fourteen patients additionally underwent the Wada test. We analyzed MEG beta power desynchronization in sensor (controls) and source space (patients and controls). Beta power decrease between 13 and 35 Hz was localized applying Dynamic Imaging of Coherent Sources Beamformer technique. Statistical inferences were grounded on cluster-based permutation testing for single subjects. Results: Event-related desynchronization of beta power in MEG was seen within the language-dominant frontal and temporal lobe and within the premotor cortex. Our analysis pipeline consistently yielded left language dominance with high laterality indices in controls. Language lateralization in MEG and Wada test agreed in all 14 patients for inferior frontal, temporal and parietal language areas (Cohen’s Kappa = 1, p < 0.001). fMRI agreed with Wada test in 12 out of 14 cases (85.7%) for Broca’s area (Cohen’s Kappa = 0.71, p = 0.024), while the agreement for temporal and temporo-parietal language areas were non-significant. Concordance between MEG and fMRI laterality indices was highest within the inferior frontal gyrus, with an agreement in 19/24 cases (79.2%), and non-significant for Wernicke’s area. Spatial agreement between fMRI and MEG varied considerably between subjects and brain regions with the lowest Euclidean distances within the inferior frontal region of interest. Conclusion: Localizing the desynchronization of MEG beta power using a verb generation task is a promising tool for the identification of language dominance in the pre-surgical evaluation of epilepsy patients. The overall agreement between MEG and fMRI was lower than expected and might be attributed to differences within the baseline condition. A larger sample size and an adjustment of the experimental designs are needed to draw further conclusions.
CRIS-Team Scopus Importer:2022-11-25
Keywords: beta power decrease; epilepsy; epilepsy surgery; functional magnetic resonance imaging (fMRI); intracarotid sodium amobarbital procedure (IAT); language lateralization; magnetoencephalography (MEG); Wada test

LONGITUDINAL CHANGE IN THE CENTRAL NERVOUS SYSTEM PAIN RESPONSE AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO. A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Hagen, Melanie; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Longitudinal Sodium MRI of Multiple Sclerosis Lesions: Is there Added Value of Sodium Inversion Recovery MRI - Mennecke, Angelika; Nagel, Armin Michael; Huhn, Konstantin; Linker, Ralf; Schmidt, Manuel; Rothhammer, Veit; Wilferth, Tobias; Linz, Peter; Wegmann, Julius; Eisenhut, Felix; Engelhorn, Tobias; Dörfler, Arnd (Journal of Magnetic Resonance Imaging, 2021)
Background Sodium enhancement has been demonstrated in multiple sclerosis (MS) lesions. Purpose To investigate sodium MRI with and without an inversion recovery pulse in acute MS lesions in an MS relapse and during recovery. Study Type Prospective. Subjects Twenty-nine relapsing-remitting MS patients with an acute relapse were included. Field Strength/Sequence A 3D density-adapted radial sodium sequence at 3 T using a dual-tuned (Na-23/H-1) head coil. Assessment Full-brain images of the tissue sodium concentration (TSC1, n = 29) and a sodium inversion recovery sequence (SIR1, n = 20) at the beginning of the anti-inflammatory therapy and on medium-term follow-up visits (days 27-99, n = 12 [TSC], n = 5 [SIR]) were measured. Regions of interest (RoIs) with contrast enhancement (T1CE+) and without change in T1-weighted imaging (FL + T1n) were normalized (nTSC and nSIR). To gain insight on the origin of the TSC enhancement at time point 1, it is investigated whether the nTSC enhancement of the lesions is accompanied by a change of the respective nSIR. Potential prognostic value of nSIR1 is examined referring to the nTSC progression. Statistical Tests nTSC and nSIR were compared regarding the type of lesion and the time point using a one-way ANOVA. Pearson's correlation coefficient was calculated for nTSC over nSIR and for nTSC1-nTSC2 over nSIR1. A P-value At the first measurement, all lesion types showed increased nTSC, while nSIR was decreased in the FL + T(1)n and the T1CE+ lesions in comparison to the normal-appearing white matter. For acute lesions, the difference between nTSC at baseline and nTSC at time point 2 showed a significant correlation with the baseline nSIR. Data Conclusion At time point 1, nTSC is increased, while nSIR is unchanged or decreased in the lesions. The mean sodium IR signal at baseline correlates with recovery or progression of an acute lesion. Evidence Level 2 Technical Efficacy Stage 4
CRIS-Team WoS Importer:2021-07-23

Long-Term Complications and Influence on Outcome in Patients Surviving Spontaneous Subarachnoid Hemorrhage - Gerner, Stefan; Reichl, Jonathan; Custal, Christina; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Hölter, Philip; Kallmünzer, Bernd; Huttner, Hagen (Cerebrovascular Diseases, 2020)
BACKGROUND: While the short-term clinical outcome of patients with subarachnoid hemorrhage (SAH) is well described, there are limited data on long-term complications and their impact on social reintegration. This study aimed to assess the frequency of complications post-SAH and to investigate whether these complications attribute to functional and self-reported outcomes as well as the ability to return to work in these patients. METHODS: This retrospective single-center study included patients with atraumatic SAH over a 5-year period at a tertiary care center. Patients received a clinical follow-up for 12 months. In addition to demographics, imaging data, and parameters of acute treatment, the rate and extent of long-term complications after SAH were recorded. The functional outcome was assessed using the modified Rankin Scale (mRS; favorable outcome defined as mRS = 0-2). Further outcomes comprised self-reported subjective health measured by the EQ-5D and return to work for SAH patients with appropriate age. Multivariable analyses including in-hospital parameters and long-term complications were conducted to identify parameters independently associated with outcomes in SAH survivors. RESULTS: This study cohort consisted of 505 SAH patients of whom 405 survived the follow-up period of 12 months (i.e., mortality rate of 19.8%). Outcome data were available in 359/405 (88.6%) patients surviving SAH. At 12 months, a favorable functional outcome was achieved in 287/359 (79.9%) and 145/251 (57.8%) SAH patients returned to work. The rates of post-acute complications were headache (32.3%), chronic hydrocephalus requiring permanent ventriculoperitoneal shunting (VP shunt 25.4%) and epileptic seizures (9.5%). Despite patient's and clinical characteristics, both presence of epilepsy and need for VP shunt were independently and negatively associated with a favorable functional outcome (epilepsy: adjusted odds ratio [aOR] (95% confidence interval [95% CI]): 0.125 [0.050-0.315]; VP shunt: 0.279 [0.132-0.588]; both p < 0.001) as well as with return to work (aOR [95% CI]: epilepsy 0.195 [0.065-0.584], p = 0.003; VP shunt 0.412 [0.188-0.903], p = 0.027). Multivariable analyses revealed presence of headache, VP shunt, or epilepsy to be significantly related to subjective health impairment (aOR [95% CI]: headache 0.248 [0.143-0.430]; epilepsy 0.223 [0.085-0.585]; VP shunt 0.434 [0.231-0.816]; all p < 0.01). CONCLUSIONS: Long-term complications occur frequently after SAH and are associated with an impairment of functional and social outcomes. Further studies are warranted to investigate if treatment strategies specifically targeting these complications, including preventive aspects, may improve the outcomes after SAH.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Long-term complications; Post-stroke outcomes; Social participation; Subarachnoid hemorrhage

Long-term course of anterior spinal cord herniation presenting with an upper motor neuron syndrome: Case report illustrating diagnostic and therapeutic implications - Regensburger, Martin; Schlachetzki, Johannes; Klekamp, Jörg; Dörfler, Arnd; Winkler, Jürgen (BMC Neurology, 2020)
Background: Anterior spinal cord herniation (aSCH) is a rare cause of myelopathy which may present as pure motor syndrome and mimic other degenerative diseases of the spinal cord. In slowly progressive cases, diagnosis may be impeded by equivocal imaging results and mistaken for evolving upper motor neuron disease. As early imaging studies are lacking, we aimed to provide a detailed description of imaging and neurophysiology findings in a patient with aSCH, focusing on the early symptomatic stages. Case presentation: We here present the case of a 51-year old male patient with an episode of pain in the right trunk and a normal spinal MRI. After a symptom-free interval of 8 years, spasticity and paresis evolved in the right leg. There was subtle ventral displacement and posterior indentation of the thoracic spinal cord on MRI which, in retrospect, was missed as an early sign of aSCH. After another 3 years, symptoms spread to the left leg and a sensory deficit of the trunk became evident. Follow-up MRI now clearly showed an aSCH. Neurosurgical intervention consisted of remobilization of the herniated spinal cord and patch closure of the dura defect. Over the following years, motor and sensory symptoms partially improved. Conclusions: The history of this patient with aSCH illustrates the importance of careful longitudinal clinical follow-up with repeated imaging studies in progressive upper motor neuron syndromes. Specific attention should be paid to a history of truncal pain and to MRI findings of a ventrally displaced spinal cord. Neurosurgical intervention may halt the progression of herniation.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Case Report; Evoked potentials; Spasticity; Spinal cord herniation

Lymphocytopenia Is an Independent Predictor of Unfavorable Functional Outcome in Spontaneous Intracerebral Hemorrhage - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Madzar, Dominik; Sembill, Jochen; Lücking, Hannes; Kloska, Stephan; Keil, Toni; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2016)
Stroke-associated immunosuppression is an increasingly recognized factor triggering infections and thus potentially influencing outcome after stroke. Specifically, lymphocytopenia after intracerebral hemorrhage (ICH) has only been addressed in small-sized retrospective studies of mixed intracranial bleedings. This cohort study investigated the natural course of lymphocytopenia, parameters associated with lymphocytopenia on admission (LOA) and during stay, and evaluated the clinical impact of lymphocytopenia in solely ICH patients.This observational study included 855 consecutive patients with ICH. Patient demographics, clinical and neuroradiological data as well as laboratory and in-hospital measures were retrieved from institutional prospective databases. Functional 3-month outcome was assessed by mailed questionnaires. Lymphocytopenia was defined as <1.0 (10(9)/L) and was correlated with patient's characteristics and outcome.Prevalence of LOA was 27.3%. Patients with LOA showed significant associations with poorer neurological status (18 [10-32] versus 13 [5-24]; P<0.001), larger hematoma volume (18.5 [6.2-46.2] versus 12.8 [4.4-37.8]; P=0.006), and unfavorable outcome (74.7% versus 63.3%; P=0.0018). Natural course of lymphocyte count during hospital stay revealed a lymphocyte nadir of 1.1 (0.80-1.53 [10(9)/L]) at day 5. Focusing on patients with day-5-lymphocytopenia, compared with patients with LOA, revealed increased rates of infections (63 [71.6] versus 113 [48.5]; P<0.001) and poorer functional outcome at 3 months (76 [86.4] versus 175 [75.1); P=0.029). Adjusting for baseline confounders, multivariable logistic and receiver operating characteristics analyses documented independent associations of day-5-lymphocytopenia with unfavorable outcome (day-5-lymphocytopenia: odds ratio, 2.017 [95% confidence interval, 1.029-3.955], P=0.041; LOA: odds ratio, 1.391 [0.795-2.432], P=0.248; receiver operating characteristics: day-5-lymphocytopenia: area under the curve=0.673, P<0.0001, Youden's index=0.290; LOA: area under the curve=0.513, P=0.676, Youden's index=0.084), whereas receiver operating characteristics analyses revealed no association of age or hematoma volume with day-5-lymphocytopenia (age: area under the curve=0.540, P=0.198, Youden's index=0.106; volume: area under the curve=0.550, P=0.0898, Youden's index=0.1224).Lymphocytopenia is frequently present in patients with ICH and may represent an independent parameter associated with unfavorable functional outcome. Developing lymphocytopenia affected outcome even stronger than LOA, a finding that may open up new therapeutic avenues in specific subsets of patients with ICH.
EVALuna2:22442

Machine Learning-Based Prediction of Glioma IDH Gene Mutation Status Using Physio-Metabolic MRI of Oxygen Metabolism and Neovascularization (A Bicenter Study) - Stadlbauer, Andreas; Nikolic, Katarina; Oberndorfer, Stefan; Marhold, Franz; Kinfe, Thomas Mehari; Meyer-Bäse, Anke; Bistrian, Diana Alina; Schnell, Oliver; Dörfler, Arnd (Cancers, 2024)
The mutational status of the isocitrate dehydrogenase (IDH) gene plays a key role in the treatment of glioma patients because it is known to affect energy metabolism pathways relevant to glioma. Physio-metabolic magnetic resonance imaging (MRI) enables the non-invasive analysis of oxygen metabolism and tissue hypoxia as well as associated neovascularization and microvascular architecture. However, evaluating such complex neuroimaging data requires computational support. Traditional machine learning algorithms and simple deep learning models were trained with radiomic features from clinical MRI (cMRI) or physio-metabolic MRI data. A total of 215 patients (first center: 166 participants + 16 participants for independent internal testing of the algorithms versus second site: 33 participants for independent external testing) were enrolled using two different physio-metabolic MRI protocols. The algorithms trained with physio-metabolic data demonstrated the best classification performance in independent internal testing: precision, 91.7%; accuracy, 87.5%; area under the receiver operating curve (AUROC), 0.979. In external testing, traditional machine learning models trained with cMRI data exhibited the best IDH classification results: precision, 84.9%; accuracy, 81.8%; and AUROC, 0.879. The poor performance for the physio-metabolic MRI approach appears to be explainable by site-dependent differences in data acquisition methodologies. The physio-metabolic MRI approach potentially supports reliable classification of IDH gene status in the presurgical stage of glioma patients. However, non-standardized protocols limit the level of evidence and underlie the need for a reproducible framework of data acquisition techniques.
CRIS-Team Scopus Importer:2024-04-05
Keywords: artificial intelligence; deep learning; glioma; IDH gene mutation; isocitrate dehydrogenase gene; machine learning; neurooncology; physio-metabolic MRI; preoperative classification

Magnetic resonance imaging biomarkers for clinical routine assessment of microvascular architecture in glioma - Stadlbauer, Andreas; Zimmermann, Max; Heinz, Gertraud; Oberndorfer, Stefan; Dörfler, Arnd; Buchfelder, Michael; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2017)
Knowledge about the topological and structural heterogeneity of the microvasculature is important for diagnosis and monitoring of glioma. A vessel caliber and type-dependent temporal shift in the magnetic resonance imaging signal forms the basis for vascular architecture mapping. This study introduced a clinically feasible approach for assessment of vascular pathologies in gliomas using vascular architecture mapping. Sixty consecutive patients with known or suspected gliomas were examined using vascular architecture mapping as part of the routine magnetic resonance imaging protocol. Maps of microvessel radius and density, which adapted to the vasculature-dependent temporal shift phenomenon, were calculated using a costume-made software tool. Microvessel radius and density were moderately to severely elevated in a heterogeneous, inversely correlated pattern within high-grade gliomas. Additionally, three new imaging biomarkers were introduced: Microvessel type indicator allowing differentiation between supplying arterial and draining venous microvasculature in high-grade gliomas. Vascular-induced bolus peak time shift may presumably be sensitive for early neovascularization in the infiltration zone. Surprisingly, curvature showed significant changes in peritumoral vasogenic edema which correlated with neovascularization in the tumor core of high-grade gliomas. These new magnetic resonance imaging biomarkers give insights into complexity and heterogeneity of vascular changes in glioma; however, histological validations in more well-defined patient populations are required.
EVALuna2:33149

Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10

Magnetic resonance imaging of intraductal papillomas: typical findings and differential diagnosis - Dietzel, Matthias; Kaiser, Clemens; Baltzer, Pascal A. T. (Journal of Computer Assisted Tomography, 2015)
Even upon core biopsy, accurate classification of benign intraductal papillomas (IPs) can be difficult. Accordingly, IPs are still frequently surgically resected. Therefore, accurate classification of IP by magnetic resonance mammography (MRM) would potentially optimize patient management. However, the few investigations assessing MRM of IP included small patient collectives, and overall accuracy is still unknown. We performed this investigation to analyze the morphologic and dynamic MRM profiles of IP in more detail and to identify the overall accuracy of MRM for differential diagnosis of IP versus malignant breast lesions.Consecutive patients scheduled for MRM (standardized scanning protocols: dynamic T1-weighted gradient echo before/after Gd-DTPA [gadolinium diethylenetriamine pentaacetate; 0.1 mmol/kg body weight]; T2-weighted turbo spin echo) with subsequent surgicopathologic verification were enrolled. For the detailed assessment of morphologic and dynamic profiles, 2 experienced radiologists (>500 MRM examinations; blinded to surgicopathologic verification) performed prospective evaluation of MRM, in consensus, applying 17 predefined MRM descriptors. From this database, all patients showing IP (n = 83) or malignant breast lesions (n = 648) were further evaluated statistically: univariate analyses (association of single descriptors with IP/breast cancer: contingency table statistics) and multivariate analyses were performed to identify accurate descriptor combinations (CHAID [CHi-squared Automatic Interaction Detection]) and overall accuracy of MRM for differential diagnosis of IP versus malignant breast lesions (logistic regression; receiver operating characteristics [ROC], area under the ROC curve).There were 82.4% of MRM descriptors significantly associated with IP (n = 14; P < 0.05). The accuracy of single descriptors (odds ratio [OR], <=10.6) could be further increased by descriptor combinations (double combination: OR <=12.7; triple combination: OR <=15.0). With area under the ROC curve = 0.90, there was a high overall accuracy of MRM for the differential diagnosis of IP versus malignant breast lesions.A detailed assessment of MRM allows precise characterization of benign IPs and accurate differentiation from malignant breast lesions.
EVALuna2:23003

Magnetoencephalography for epileptic focus localization in a series of 1000 cases. - Rampp, Stefan; Stefan, Hermann; Wu, Xintong; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard S.; Schwab, Stefan; Blümcke, Ingmar; Rössler, Karl; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
EVALuna2:204465

Magnetoencephalography for epileptic focus localization in a series of 1000 cases - Rampp, Stefan; Stefan, Hermann; Wu, Xueqing; Kaltenhäuser, Martin; Maess, Burkhard; Schmitt, Friedhelm C.; Wolters, Carsten H.; Hamer, Hajo; Kasper, Burkhard; Schwab, Stefan; Dörfler, Arnd; Blümcke, Ingmar; et al. (Brain, 2019)
The aim of epilepsy surgery in patients with focal, pharmacoresistant epilepsies is to remove the complete epileptogenic zone to achieve long-term seizure freedom. In addition to a spectrum of diagnostic methods, magnetoencephalography focus localization is used for planning of epilepsy surgery. We present results from a retrospective observational cohort study of 1000 patients, evaluated using magnetoencephalography at the University Hospital Erlangen over the time span of 28 years. One thousand consecutive cases were included in the study, evaluated at the University Hospital Erlangen between 1990 and 2018. All patients underwent magnetoencephalography as part of clinical workup for epilepsy surgery. Of these, 405 underwent epilepsy surgery after magnetoencephalography, with postsurgical follow-ups of up to 20 years. Sensitivity for interictal epileptic activity was evaluated, in addition to concordance of localization with the consensus of presurgical workup on a lobar level. We evaluate magnetoencephalography characteristics of patients who underwent epilepsy surgery versus patients who did not proceed to surgery. In operated patients, resection of magnetoencephalography localizations were related to postsurgical seizure outcomes, including long-term results after several years. In comparison, association of lesionectomy with seizure outcomes was analysed. Measures of diagnostic accuracy were calculated for magnetoencephalography resection and lesionectomy. Sensitivity for interictal epileptic activity was 72% with significant differences between temporal and extra-temporal lobe epilepsy. Magnetoencephalography was concordant with the presurgical consensus in 51% and showed additional or more focal involvement in an additional 32%. Patients who proceeded to surgery showed a significantly higher percentage of monofocal magnetoencephalography results. Complete magnetoencephalography resection was associated with significantly higher chances to achieve seizure freedom in the short and long-term. Diagnostic accuracy was significant in temporal and extra-temporal lobe cases, but was significantly higher in extra-temporal lobe epilepsy (diagnostic odds ratios of 4.4 and 41.6). Odds ratios were also higher in non-lesional versus lesional cases (42.0 versus 6.2). The results show that magnetoencephalography provides non-redundant information, which significantly contributes to patient selection, focus localization and ultimately long-term seizure freedom after epilepsy surgery. Specifically in extra-temporal lobe epilepsy and non-lesional cases, magnetoencephalography provides excellent accuracy.
CRIS-Team Scopus Importer:2019-10-08
Keywords: epilepsy; epilepsy surgery; long-term outcome; magnetic source imaging; magnetoencephalography

Management of therapeutic anticoagulation in patients with intracerebral haemorrhage and mechanical heart valves - Kuramatsu, Joji; Sembill, Jochen; Gerner, Stefan; Sprügel, Maximilian; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (European Heart Journal, 2018)
Aims Evidence is lacking regarding acute anticoagulation management in patients after intracerebral haemorrhage (ICH) with implanted mechanical heart valves (MHVs). Our objective was to investigate anticoagulation reversal and resumption strategies by evaluating incidences of haemorrhagic and thromboembolic complications, thereby defining an optimal time-window when to restart therapeutic anticoagulation (TA) in patients with MHV and ICH. Methods and results We pooled individual patient- data (n = 2504) from a nationwide multicentre cohort-study (RETRACE, conducted at 22 German centres) and eventually identified MHV-patients (n = 137) with anticoagulation-associated ICH for outcome analyses. The primary outcome consisted of major haemorrhagic complications analysed during hospital stay according to treatment exposure (restarted TA vs. no-TA). Secondary outcomes comprised thromboembolic complications, the composite outcome (haemorrhagic and thromboembolic complications), timing of TA, and mortality. Adjusted analyses involved propensity-score matching and multivariable cox-regressions to identify optimal timing of TA. In 66/137 (48%) of patients TA was restarted, being associated with increased haemorrhagic (TA = 17/66 (26%) vs. no-TA = 4/71 (6%); P < 0.01) and a trend to decreased thromboembolic complications (TA = 1/66 (2%) vs. no-TA = 7/71 (10%); P = 0.06). Controlling treatment crossovers provided an incidence rate-ratio [hazard ratio (HR) 10.31, 95% confidence interval (CI) 3.67-35.70; P < 0.01] in disadvantage of TA for haemorrhagic complications. Analyses of TA-timing displayed significant harm until Day 13 after ICH (HR 7.06, 95% CI 2.33-21.37; P < 0.01). The hazard for the composite-balancing both complications, was increased for restarted TA until Day 6 (HR 2.51, 95% CI 1.10-5.70; P = 0.03). Conclusion Restarting TA within less than 2 weeks after ICH in patients with MHV was associated with increased haemorrhagic complications. Optimal weighing-between least risks for thromboembolic and haemorrhagic complications-provided an earliest starting point of TA at Day 6, reserved only for patients at high thromboembolic risk.
EVALuna2:34917

Material Decomposition for Energy Resolving Detectors using Weighted Levenberg-Marquardt Optimization - Manhart, Michael; Maier, Andreas; Hornegger, Joachim; Dörfler, Arnd (Proceedings of the 1st Conference on Image Guided Interventions, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.materi_5

Measurement of quantifiable parameters by time-density curves in the elastase-induced aneurysm model: first results in the comparison of a flow diverter and a conventional aneurysm stent - Struffert, Tobias; Ott, Sabine; Kowarschik, Markus; Bender, Frederik; Adamek, Edyta; Engelhorn, Tobias; Gölitz, Philipp; Lang, Stefan; Strother, Charles M.; Dörfler, Arnd (European Radiology, 2013)
Quantifiable parameters to evaluate the effectiveness of flow diverters (FDs) are desirable. We measured time-density curves (TDCs) and calculated quantifiable parameters in the rabbit elastase-induced aneurysm model after stent (Neuroform [NF]) and FD (Pipeline embolisation device [PED]) treatment.Sixteen rabbit elastase-induced aneurysms were treated with FD (n = 9) or NF (n = 5). Angiography was performed before and after treatment and TDCs were created. The time to peak (TTP), the full width at half maximum (FWHM) and the average slope of the curve which represent the inflow (IF) and outflow (OF) were calculated.Mean values before treatment were TTP = 0.8 s, FWHM = 1.2 s, IF = 153.5 and OF = -54.9. After PED treatment, the TTP of 1.8 s and FWHM of 47.8 s were extended. The IF was 31.2 and the OF was -11.5 and therefore delayed. The values after NF treatment (TTP = 1.1 s, FWHM = 1.8 s, IF = 152.9, OF = -33.2) changed only slightly.It was feasible to create TDCs in the rabbit aneurysm model. Parameters describing the haemodynamic effect of PED and NF were calculated and were different according to the type of device used. These parameters could possibly serve as predictive markers for aneurysm occlusion.
EVALuna2:22984

Mechanical thrombectomy for acute ischemic stroke in COVID-19 patients: multicenter experience in 111 cases - Styczen, Hanna; Maus, Volker; Goertz, Lukas; Koehrmann, Martin; Kleinschnitz, Christoph; Fischer, Sebastian; Moehlenbruch, Markus; Mühlen, Iris; Kallmünzer, Bernd; Dorn, Franziska; Lakghomi, Asadeh; Gawlitza, Matthias; et al. (Journal of Neurointerventional Surgery, 2022)
Background Data on the frequency and outcome of mechanical thrombectomy (MT) for large vessel occlusion (LVO) in patients with COVID-19 is limited. Addressing this subject, we report our multicenter experience. Methods A retrospective cohort study was performed of consecutive acute stroke patients with COVID-19 infection treated with MT at 26 tertiary care centers between January 2020 and November 2021. Baseline demographics, angiographic outcome and clinical outcome evaluated by the modified Rankin Scale (mRS) at discharge and 90 days were noted. Results We identified 111 out of 11 365 (1%) patients with acute or subsided COVID-19 infection who underwent MT due to LVO. Cardioembolic events were the most common etiology for LVO (38.7%). Median baseline National Institutes of Health Stroke Scale score and Alberta Stroke Program Early CT Score were 16 (IQR 11.5-20) and 9 (IQR 7-10), respectively. Successful reperfusion (mTICI >= 2b) was achieved in 97/111 (87.4%) patients and 46/111 (41.4%) patients were reperfused completely. The procedure-related complication rate was 12.6% (14/111). Functional independence was achieved in 20/108 (18.5%) patients at discharge and 14/66 (21.2%) at 90 days follow-up. The in-hospital mortality rate was 30.6% (33/108). In the subgroup analysis, patients with severe acute COVID-19 infection requiring intubation had a mortality rate twice as high as patients with mild or moderate acute COVID-19 infection. Acute respiratory failure requiring ventilation and time interval from symptom onset to groin puncture were independent predictors for an unfavorable outcome in a logistic regression analysis. Conclusion Our study showed a poor clinical outcome and high mortality, especially in patients with severe acute COVID-19 infection undergoing MT due to LVO.
CRIS-Team WoS Importer:2022-04-01

Mechanical Thrombectomy Using the new Solitaire™ Platinum Stent-retriever: Reperfusion Results, Complication Rates and Early Neurological Outcome - Pfaff, Johannes; Rohde, Stefan; Engelhorn, Tobias; Dörfler, Arnd; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical Neuroradiology, 2019)
Background and Purpose: The application of radiopaque markers to the Solitaire™ stent-retriever for better visibility during mechanical thrombectomy (MT) has the potential to alter the well-known characteristics of the device; however, it is uncertain whether this adjustment influences efficacy or safety of the enhanced stent-retriever. Methods: Retrospective analysis of stroke databases of three comprehensive stroke centers. Our investigation was focused on technical and angiographic parameters, including procedure times, reperfusion results (thrombolysis in cerebral infarction, TICI), periprocedural complications and favorable early neurological recovery at discharge (modified Rankin scale ≤2 or National Institutes of Health Stroke Scale, NIHSS = 0 or ∆NIHSS ≥ 10), from consecutive patients with acute anterior circulation ischemic stroke treated with a Solitaire™ Platinum stent-retriever between October 2016 and March 2017. Results: A total of 75 patients (male: n = 27, 36%, age in years: mean (SD): 75 (±12), median baseline NIHSS: 17 (interquartile range IQR: 11–21), n = 41, 54.7% received additional i. v. thrombolytics) were treated with a median number of 2 device passes (range: 1–5). The median time from groin puncture to final TICI was 56 min (IQR: 41–79). In 69 patients (92%) TICI 2b-3 was achieved. Early neurological recovery was seen in 47 (62.7%) patients. The following periprocedural complications occurred: vasospasms (n = 7, 9.3%), emboli into a new territory (n = 4, 5.3%), symptomatic intracranial hemorrhage (n = 3, 4%), difficulties during device delivery/deployment (n = 1, 1.3%). Conclusion: The usage of the Solitaire™ Platinum stent-retriever for MT in acute ischemic stroke patients was highly effective and was not accompanied by an increased periprocedural complication rate.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Acute ischemic stroke; Mechanical thrombectomy; Solitaire™ Platinum; Stent-retriever; Visibility

MEG Node Degree Differences in Patients with Focal Epilepsy vs. Controls-Influence of Experimental Conditions - Vogel, Stephan; Kaltenhaeuser, Martin; Kim, Cora; Müller-Voggel, Nadia; Roessler, Karl; Dörfler, Arnd; Schwab, Stefan; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (Brain Sciences, 2021)
Drug-resistant epilepsy can be most limiting for patients, and surgery represents a viable therapy option. With the growing research on the human connectome and the evidence of epilepsy being a network disorder, connectivity analysis may be able to contribute to our understanding of epilepsy and may be potentially developed into clinical applications. In this magnetoencephalographic study, we determined the whole-brain node degree of connectivity levels in patients and controls. Resting-state activity was measured at five frequency bands in 15 healthy controls and 15 patients with focal epilepsy of different etiologies. The whole-brain all-to-all imaginary part of coherence in source space was then calculated. Node degree was determined and parcellated and was used for further statistical evaluation. In comparison to controls, we found a significantly higher overall node degree in patients with lesional and non-lesional epilepsy. Furthermore, we examined the conditions of high/reduced vigilance and open/closed eyes in controls, to analyze whether patient node degree levels can be achieved. We evaluated intraclass-correlation statistics (ICC) to evaluate the reproducibility. Connectivity and specifically node degree analysis could present new tools for one of the most common neurological diseases, with potential applications in epilepsy diagnostics.
CRIS-Team WoS Importer:2022-01-07

MEG Node Degree for Focus Localization: Comparison with Invasive EEG - Rampp, Stefan; Kaltenhaeuser, Martin; Müller-Voggel, Nadia; Dörfler, Arnd; Kasper, Burkhard S.; Hamer, Hajo; Brandner, Sebastian; Buchfelder, Michael (Biomedicines, 2023)
Epilepsy surgery is a viable therapy option for patients with pharmacoresistant focal epilepsies. A prerequisite for postoperative seizure freedom is the localization of the epileptogenic zone, e.g., using electro- and magnetoencephalography (EEG/MEG). Evidence shows that resting state MEG contains subtle alterations, which may add information to the workup of epilepsy surgery. Here, we investigate node degree (ND), a graph-theoretical parameter of functional connectivity, in relation to the seizure onset zone (SOZ) determined by invasive EEG (iEEG) in a consecutive series of 50 adult patients. Resting state data were subjected to whole brain, all-to-all connectivity analysis using the imaginary part of coherence. Graphs were described using parcellated ND. SOZ localization was investigated on a lobar and sublobar level. On a lobar level, all frequency bands except alpha showed significantly higher maximal ND (mND) values inside the SOZ compared to outside (ratios 1.11-1.20, alpha 1.02). Area-under-the-curve (AUC) was 0.67-0.78 for all expected alpha (0.44, ns). On a sublobar level, mND inside the SOZ was higher for all frequency bands (1.13-1.38, AUC 0.58-0.78) except gamma (1.02). MEG ND is significantly related to SOZ in delta, theta and beta bands. ND may provide new localization tools for presurgical evaluation of epilepsy surgery.
CRIS-Team WoS Importer:2023-03-24
Keywords: MEG; epilepsy; epilepsy surgery; connectivity; graph theory; focus localization

Meningioma growth dynamics assessed by radiocarbon retrospective birth dating - Huttner, Hagen B.; Bergmann, Olaf; Salehpour, Mehran; El Cheikh, Raouf; Nakamura, Makoto; Tortora, Angelo; Heinke, Paula; Coras, Roland; Englund, Elisabet; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Röder, Sebastian; et al. (EBioMedicine, 2018)
It is not known how long it takes from the initial neoplastic transformation of a cell to the detection of a tumor, which would be valuable for understanding tumor growth dynamics. Meningiomas show a broad histological, genetic and clinical spectrum, are usually benign and considered slowly growing. There is an intense debate regarding their age and growth pattern and when meningiomas should be resected. We have assessed the age and growth dynamics of 14 patients with meningiomas (WHO grade I: n=6 with meningothelial and n=6 with fibrous subtype, as well as n=2 atypical WHO grade II meningiomas) by combining retrospective birth-dating of cells by analyzing incorporation of nuclear-bomb-test-derived 14C, analysis of cell proliferation, cell density, MRI imaging and mathematical modeling. We provide an integrated model of the growth dynamics of benign meningiomas. The mean age of WHO grade I meningiomas was 22.1±6.5years, whereas atypical WHO grade II meningiomas originated 1.5±0.1years prior to surgery (p<0.01). We conclude that WHO grade I meningiomas are very slowly growing brain tumors, which are resected in average two decades after time of origination.
EVALuna2:34031

Merged Volume Rendered Flat-panel Computed Tomography for Postoperative Cochlear Implant Assessment - Eisenhut, Felix; Lang, Stefan; Dörfler, Arnd; Iro, Heinrich; Hornung, Joachim; Taha, Lava (Clinical Neuroradiology, 2019)
Purpose: Evaluation of a new postprocessing method for postoperative control of cochlear implants (CI) based on a single flat detector computed tomography (FD-CT) run and volume rendering of 3D models of the inner ear. Methods: The FD-CT datasets of CIs were selected and postprocessed to generate both standard multiplanar reconstructions (MPR) and merged volume-rendered 3D datasets (MRD) of the CIs. The MRDs consisted of two different reconstructions (bone/implant) that are automatically layered to avoid manual coregistration inaccuracy. Corresponding datasets were evaluated in consensus reading in terms of qualitative (integrity, position, configuration) and quantitative (insertion depth angle) CI parameters. Results: In total 20 FD-CTs with 20 CIs were successfully postprocessed. Qualitative evaluation of MPR and MRD demonstrated complete congruency (integrity: narray integrity = 20; position: nscala tympani = 13, nscalar translocation = 7; configuration: nharmonic spiralization = 16, ntip fold over = 3, nlooped implant = 1). Adverse intracochlear implant spiralization was identified in all 10 cases with MRD and MPR. Measurement of the insertion depth angle in MRD was equivalent to that in MPR (r = 0.99; P = <0.0001). Conclusion: The use of MRD is a helpful method for precise postoperative CI assessment and provides easy detection of incorrect intracochlear spiralization.
CRIS-Team Scopus Importer:2019-09-20
Keywords: CI; FD-CT; Postprocessing; Temporal bone; Three-dimensional

Microcatheters with extra-long detachable tip: A promising treatment option in dural arteriovenous fistulas - Gölitz, Philipp; Lücking, Hannes; Knott, Michael; Hock, Stefan; Brandner, Sebastian; Knossalla, Frauke; Dörfler, Arnd (Interventional Neuroradiology, 2022)
Purpose Treating cerebral dural arteriovenous fistulas (dAVFs) by transarterial embolization is an established endovascular approach but no data exist regarding the utility of using the newly introduced microcatheters with extra-long detachable tip. Aim of our study was to evaluate the value of these microcatheters and, additionally, of combining them with the simplified pressure cooker technique. Methods Twenty-nine patients treated for dAVF with transarterial embolization were enrolled. In a subgroup of fifteen patients the simplified pressure cooker technique was additionally applied. Demographics and characteristics were collected for patients and dAVFs and procedural details reviewed. The association between covariates and binary-coded occlusion status was evaluated. Results Microcatheter navigation into the target pedicle as well as application of the simplified pressure cooker technique were successful in all cases. Complete dAVF occlusion was reached in 69.0% at a single stage. In case of complete dAVF occlusion, embolization via only one pedicle was enough. Subgroup analysis revealed a higher occlusion status (80%) if using the simplified pressure cooker technique than if not (57%) but reached not significance level. Conclusion Using microcatheters with extra-long detachable tip for dAVF embolization seems to offer a safe and effective treatment option with exceptional high occlusion rate at a single stage. The high navigability facilitates catheterization of a single selected target pedicle that is often enough to reach complete dAVF occlusion. Combining these microcatheters with the simplified pressure cooker technique turned out to be safe and easy to handle and might allow an increasing dAVF occlusion rate.
CRIS-Team WoS Importer:2022-10-14

Microstructural abnormalities of the posterior thalamic radiation and the mediodorsal thalamic nuclei in females with anorexia nervosa - A voxel based diffusion tensor imaging (DTI) study - Frieling, Helge; Fischer, Julia; Wilhelm, Julia; Engelhorn, Tobias; Bleich, Stefan; Hillemacher, Thomas; Dörfler, Arnd; Kornhuber, Johannes; De Zwaan, Martina; Peschel, Thomas (Journal of Psychiatric Research, 2012)
Gray matter abnormalities have been found in anorexia nervosa (AN) in several brain regions. However, little is known about white matter abnormalities under the condition of AN. To comprehensively assess the microstructural integrity of white matter pathways in women with anorexia nervosa, we performed voxel-based Diffusion Tensor Imaging (DTI). 21 women with AN according to DSM-IV criteria (9 of them recovered) and 20 female age-matched healthy control subjects were enrolled in the study. The patients had a mean body mass index of 17.2 kg/m2 (controls: 19.6 kg/m2). High resolution T1 images (MP-RAGE) and DTI were performed on a 3 T Siemens-scanner. Images were pre-processed and analyzed using a modified protocol for DTI in SPM2. Fractional anisotropy (FA) maps were compared using t-tests (p < 0.05, corrected). Compared with controls, AN patients showed bilateral reductions of FA maps in the posterior thalamic radiation which includes the optic radiation, and the left mediodorsal thalamus. Our study is limited by the small sample size and its cross-sectional design. A longitudinal design with the same individuals assessed when acutely ill and recovered is warranted for future studies. For the first time, the findings of our DTI study identified disturbances of associational and commissural fibers in the bilateral occipitotemporal white matter. The results help narrowing the prevailing biological models of AN by suggesting that body image distortion is related to microstructural alterations of white matter tracts connecting the extrastriate visual cortex with other brain regions involved in body perception. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Anorexia nervosa; Extrastriate body area; Voxel-based apparent diffusivity coefficient mapping; Voxel-based diffusion tensor imaging

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

Mild prolonged hypothermia for large intracerebral hemorrhage - Staykov, Dimitre; Wagner, Irina; Volbers, Bastian; Dörfler, Arnd; Schwab, Stefan; Kollmar, Rainer (Neurocritical Care, 2013)
Background: Perihemorrhagic edema (PHE) develops after intracerebral hemorrhage (ICH). It can worsen the clinical situation by its additional mass effect. Therapeutic hypothermia (TH) might be an effective method to control PHE, but has not been sufficiently studied in ICH patients. Methods: We report data on n = 25 consecutive patients with large supratentorial ICH (volume > 25 ml) who were treated by mild TH of 35 C for 8-10 days. Body temperature was controlled by endovascular cooling catheters. We followed the clinical course during hospital stay and measured volumes of ICH and PHE in regularly performed serial cranial computed tomography. Outcome was assessed after 3 and 12 months. These data were compared to a historical group of n = 25 patients with large ICH. Results: While PHE continuously increased in the historical control group up to day 10, PHE volumes in the hypothermia group remained stable. There was a significant difference from day 3 after symptom onset. Shivering (36 %) and pneumonia (96 %) were the most frequent complications during TH. Mortality rate was 8.3 % in TH versus 16.7 % in the control group after 3 months and 28 versus 44 % after 1 year. Conclusions: These data support the promising results of our first case series on TH in large ICH. TH prevents the development of PHE and its complications. Side effects of TH appeared often, but could be treated sufficiently. Therefore, TH might represent a new therapy for PHE after large ICH, but has to be further tested in randomized trials. © 2012 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypothermia; Intracerebral hemorrhage; Perihemorrhagic edema

Monitoring of balloon test occlusion of the internal carotid artery by parametric color coding and perfusion imaging within the angio suite: first results - Struffert, Tobias; Deuerling-Zheng, Y.; Engelhorn, Tobias; Kloska, Stephan; Gölitz, Philipp; Bozzato, A.; Kapsreiter, M.; Strother, C. M.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Temporary balloon test occlusion (BTO) might be performed prior to procedures in which occlusion of the internal carotid artery (ICA) might be necessary. We tested the hypothesis that parametric color coding (PCC) of angiographic series (digital subtraction angiography (DSA)) along with the assessment of cerebral blood volume (CBV) in the angiography suite would simplify and enhance the identification of candidates who are most likely to tolerate occlusion.Fifteen patients underwent angiographic series (DSA) and perfusion imaging before and during BTO. Pre- and postocclusion DSA acquisitions were evaluated for venous delay by conventional methods ("eye balling") and by PCC measurements. Comparison of CBV values between the left and right hemisphere in 6 defined regions was performed.Values of venous delay by eye balling and PCC showed a high correlation (r = 0.87, p < 0.01). Bland-Altman plot indicated slightly lower values (-0.05 s) by the PCC method. One of the 15 patients developed an asymmetrical CBV map with an increase in CBV of more than one standard deviation in 3 of the 6 regions of interest (ROIs). Acquisition of angiographic series and perfusion imaging did not prolong the test occlusion time.PCC and CBV mapping are feasible during BTO. The use of PCC seems to simplify the ability to measure changes in venous filling delay. Perfusion imaging may show an increase in CBV in patients reaching the limits of cerebral autoregulation. These patients may be at risk for delayed infarction, even though they seem to tolerate temporary occlusion, and could be unsuitable candidates for permanent ICA occlusion.
EVALuna2:22981

Motion-corrected 23Na MRI of the human brain using interleaved 1H 3D navigator images - Wilferth, Tobias; Müller, Max; Gast, Lena; Ruck, Laurent; Meyerspeer, Martin; Kolkovsky, Alfredo L. Lopez; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose: To evaluate the feasibility of motion correction for sodium (23Na) MRI based on interleaved acquired 3D proton (1H) navigator images. Methods: A 3D radial density-adapted sequence for interleaved 23Na/1H MRI was implemented on a 7 Tesla whole-body MRI system. The 1H data obtained during the 23Na acquisition were used to reconstruct 140 navigator image volumes with a nominal spatial resolution of (2.5 mm)3 and a temporal resolution of 6 s. The motion information received from co-registration was then used to correct the 23Na image dataset, which also had a nominal spatial resolution of (2.5 mm)3. The approach was evaluated on six healthy volunteers, whose motion during the scans had different intensities and characteristics. Results: Interleaved acquisition of two nuclei did not show any relevant influence on image quality (SNR of 13.0 for interleaved versus 13.2 for standard 23Na MRI and 176.4 for interleaved versus 178.0 for standard 1H MRI). The applied motion correction increased the consistency between two consecutive scans for all examined volunteers and improved the image quality for all kinds of motion. The SD of the differences ranged between 2.30% and 6.96% for the uncorrected and between 2.13% and 2.67% for the corrected images. Conclusion: The feasibility of interleaved acquired 1H navigator images to be used for retrospective motion correction of 23Na images was successfully demonstrated. The approach neither affected the 23Na image quality nor elongated the scan time and can therefore be an important tool to improve the accuracy of quantitative 23Na MRI.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 23Na MRI; 7 Tesla; brain MRI; interleaved dual-nuclear MRI; motion correction; ultrahigh field strength

MRI assessment of experimental gliomas using 17.6 T - Schwarz, Marc A.; Pham, Mirko; Helluy, Xavier; Dörfler, Arnd; Engelhorn, Tobias (Neuroradiology, 2013)
Introduction: Using ultra-high-field contrast-enhanced magnetic resonance imaging (MRI), an increase of field strength is associated with a decrease of T 1 relaxivity. Yet, the impact of this effect on signal characteristics and contrast-enhanced pathology remains unclear. Hence, we evaluated the potential of a 17.6-T MRI to assess contrast-enhancing parts of experimentally induced rat gliomas compared to 3 T. Methods: A total of eight tumor-bearing rats were used for MRI assessments either at 17.6 T (four rats) or at 3 T (four rats) at 11 days after stereotactic implantation of F98 glioma cells into the right frontal lobe. T 1-weighted sequences were used to investigate signal-to-noise-ratios, contrast-to-noise-ratios, and relative contrast enhancement up to 16 min after double-dose contrast application. In addition, tumor volumes were calculated and compared to histology. Results: The 17.6-T-derived contrast-enhancing volumes were 31.5 ± 15.4 mm3 at 4 min, 38.8 ± 12.7 mm3 at 8 min, 51.1 ± 12.6 mm3 at 12 min, and 61.5 ± 10.8 mm3 at 16 min after gadobutrol injection. Corresponding histology-derived volumes were clearly higher (138.8 ± 8.4 mm3; P < 0.01). At 3 T, contrast-enhancing volumes were 85.2 ± 11.7 mm3 at 4 min, 107.3 ± 11.0 mm3 at 8 min, 117.0 ± 10.5 mm3 at 12 min, and 129.1 ± 10.0 mm3 at 16 min after contrast agent application. Averaged histology-derived volumes (139.1 ± 13.4 mm 3) in this group were comparable to the 16-min volume (P â† 16 min = 0.38). Compared to ultra-high-field MRI, all 3-T-derived volumes were significantly higher (P < 0.02). Conclusion: Compared to 3-T-derived images and histology, tumor volumes were underestimated by approximately 50 % at 17.6 T. Hence, contrast-enhanced 17.6-T MRI provided no further benefits in tumor measurement compared to 3 T. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: 17.6 T; 3 T; MRI; Rat brain; Tumor

MRI Brain Signal Intensity and Relaxation Times in Individuals with Prior Exposure to Gadobutrol - Saake, Marc; Schmidle, Alexandra; Kopp, Markus; Hanspach, Jannis; Hepp, Tobias; Nagel, Armin Michael; Dörfler, Arnd; Uder, Michael; Bäuerle, Tobias; Laun, Frederik Bernd (Radiology, 2019)
Purpose: To perform follow-up brain MRI in volunteer participants who had previously received multiple doses of gadobutrol and to assess for changes in signal intensities and relaxation times.
CRIS-Team WoS Importer:2019-03-06

MRI-Detected Brain Lesions and Cognitive Function in Patients With Atrial Fibrillation Undergoing Left Atrial Catheter Ablation in the Randomized AXAFA-AFNET 5 Trial - Hausler, Karl Georg; Eichner, Felizitas A.; Heuschmann, Peter U.; Fiebach, Jochen B.; Engelhorn, Tobias; Blank, Benjamin; Callans, David; Elvan, Arif; Grimaldi, Massimo; Hansen, Jim; Hindricks, Gerhard; Al-Khalidi, Hussein R.; et al. (Circulation, 2022)
BACKGROUND: We aimed to assess the prevalence of ischemic brain lesions detected by magnetic resonance imaging and their association with cognitive function 3 months after first-time ablation using continuous oral anticoagulation in patients with paroxysmal atrial fibrillation (AF).
CRIS-Team WoS Importer:2022-04-01

MRI in multiple sclerosis: an intra-individual, randomized and multicentric comparison of gadobutrol with gadoterate meglumine at 3 T - Saake, Marc; Langner, Soenke; Schwenke, Carsten; Weibart, Marina; Jansen, Olav; Hosten, Norbert; Dörfler, Arnd (European Radiology, 2016)
To compare contrast effects of gadobutrol with gadoterate meglumine for brain MRI in multiple sclerosis (MS) in a multicentre, randomized, prospective, intraindividual study at 3 T.Institutional review board approval was obtained. Patients with known or suspected active MS lesions were included. Two identical MRIs were performed using randomized contrast agent order. Four post-contrast T1 sequences were acquired (start time points 0, 3, 6 and 9 min). If no enhancing lesion was present in first MRI, second MRI was cancelled. Quantitative (number and signal intensity of enhancing lesions) and qualitative parameters (time points of first and all lesions enhancing; subjective preference regarding contrast enhancement and lesion delineation; global preference) were evaluated blinded.Seventy-four patients (male, 26; mean age, 35 years) were enrolled in three centres. In 45 patients enhancing lesions were found. Number of enhancing lesions increased over time for both contrast agents without significant difference (median 2 for both). Lesions signal intensity was significantly higher for gadobutrol (p < 0.05 at time points 3, 6 and 9 min). Subjective preference rating showed non-significant tendency in favour of gadobutrol.Both gadobutrol and gadoterate meglumine can be used for imaging of acute inflammatory MS lesions. However, gadobutrol generates higher lesion SI.o Contrast-enhanced MRI plays a key role in the management of multiple sclerosis. o Different gadolinium-based contrast agents are available. o Number of visibly enhancing lesions increases over time after contrast injection. o Gadobutrol and gadoterate meglumine do not differ in number of visible lesions. o Gadobutrol generates higher signal intensity than gadoterate meglumine.
EVALuna2:14582

MR Imaging-derived Oxygen Metabolism and Neovascularization Characterization for Grading and IDH Gene Mutation Detection of Gliomas - Stadlbauer, Andreas; Zimmermann, Max; Kitzwoegerer, Melitta; Oberndorfer, Stefan; Roessler, Karl; Dörfler, Arnd; Buchfelder, Michael; Heinz, Gertraud (Radiology, 2017)
Purpose To explore the diagnostic performance of physiological magnetic resonance (MR) imaging of oxygen metabolism and neovascularization activity for grading and characterization of isocitrate dehydrogenase (IDH) gene mutation status of gliomas. Materials and Methods This retrospective study had institutional review board approval; written informed consent was obtained from all patients. Eighty-three patients with histopathologically proven glioma (World Health Organization [WHO] grade II-IV) were examined with quantitative blood oxygen level-dependent imaging and vascular architecture mapping. Biomarker maps of neovascularization activity (microvessel radius, microvessel density, and microvessel type indicator [MTI]) and oxygen metabolism (oxygen extraction fraction [OEF] and cerebral metabolic rate of oxygen [CMRO2]) were calculated. Receiver operating characteristic analysis was used to determine diagnostic performance for grading and detection of IDH gene mutation status. Results Low-grade (WHO grade II) glioma showed areas with increased OEF (+18%, P < .001, n = 20), whereas anaplastic glioma (WHO grade III) and glioblastoma (WHO grade IV) showed decreased OEF when compared with normal brain tissue (-54% [P < .001, n = 21] and -49% [P < .001, n = 41], respectively). This allowed clear differentiation between low- and high-grade glioma (area under the receiver operating characteristic curve [AUC], 1) for the patient cohort. MTI had the highest diagnostic performance (AUC, 0.782) for differentiation between gliomas of grades III and IV among all biomarkers. CMRO2was decreased (P = .037) in low-grade glioma with a mutated IDH gene, and MTI was significantly increased in glioma grade III with IDH mutation (P = .013) when compared with the IDH wild-type counterparts. CMRO2showed the highest diagnostic performance for IDH gene mutation detection in low-grade glioma (AUC, 0.818) and MTI in high-grade glioma (AUC, 0.854) and for all WHO grades (AUC, 0.899) among all biomarkers. Conclusion MR imaging-derived oxygen metabolism and neovascularization characterization may be useful for grading and IDH mutation detection of gliomas and requires only 7 minutes of extra imaging time.©RSNA, 2016 Online supplemental material is available for this article.
EVALuna2:33140

MR imaging of neoplastic central nervous system lesions: Review and recommendations for current practice - Essig, Marco; Anzalone, Nicoletta; Combs, S. E.; Dörfler, Arnd; Lee, S. -K.; Picozzi, Piero; Rovira, Alex; Weller, Michael; Law, M. (American Journal of Neuroradiology, 2012)
MR imaging is the preferred technique for the diagnosis, treatment planning, and monitoring of patients with neoplastic CNS lesions. Conventional MR imaging, with gadolinium-based contrast enhancement, is increasingly combined with advanced, functional MR imaging techniques to offer morphologic, metabolic, and physiologic information. This article provides updated recommendations to neuroradiologists, neuro-oncologists, neurosurgeons, and radiation oncologists on the practical applications of MR imaging of neoplastic CNS lesions in adults, with particular focus on gliomas, based on a review of the clinical trial evidence and personal experiences shared at a recent international meeting of experts in neuroradiology, neuro-oncology, neurosurgery, and radio-oncology.
CRIS-Team Scopus Importer:2022-08-05

MR-projection imaging with perspective distortion as in X-ray fluoroscopy for interventional X/MR-hybrid applications - Lommen, Jonathan; Syben-Leisner, Christopher; Stimpel, Bernhard; Bayer, Siming; Nagel, Armin Michael; Fahrig, Rebecca; Dörfler, Arnd; Maier, Andreas (MR-projection imaging with perspective distortion as in X-ray fluoroscopy for interventional X/MR-hybrid applications, 2018)

MR to X-ray Projection Image Synthesis - Stimpel, Bernhard; Syben-Leisner, Christopher; Würfl, Tobias; Mentl, Katrin; Dörfler, Arnd; Maier, Andreas (Proceedings of the 5th International Conference on Image Formation in X-ray Computed Tomography (CT-Meeting), 2018)
UnivIS-Import:2018-09-06:Pub.2018.tech.IMMD.IMMD5.mrtoxr_0

MRzero - Automated discovery of MRI sequences using supervised learning - Loktyushin, A.; Herz, K.; Dang, N.; Glang, F.; Deshmane, A.; Weinmüller, Simon; Dörfler, Arnd; Scholkopf, B.; Scheffler, K.; Zaiss, M. (Magnetic Resonance in Medicine, 2021)
Purpose A supervised learning framework is proposed to automatically generate MR sequences and corresponding reconstruction based on the target contrast of interest. Combined with a flexible, task-driven cost function this allows for an efficient exploration of novel MR sequence strategies.
CRIS-Team WoS Importer:2021-04-16

MR-zero meets RARE MRI: Joint optimization of refocusing flip angles and neural networks to minimize T2-induced blurring in spin echo sequences - Dang, Hoai Nam; Endres, Jonathan; Weinmüller, Simon; Glang, Felix; Loktyushin, Alexander; Scheffler, Klaus; Dörfler, Arnd; Schmidt, Manuel; Maier, Andreas; Zaiß, Moritz (Magnetic Resonance in Medicine, 2023)
Purpose: An end-to-end differentiable 2D Bloch simulation is used to reduce T2 induced blurring in single-shot turbo spin echo sequences, also called rapid imaging with refocused echoes (RARE) sequences, by using a joint optimization of refocusing flip angles and a convolutional neural network. Methods: Simulation and optimization were performed in the MR-zero framework. Variable flip angle train and DenseNet parameters were optimized jointly using the instantaneous transverse magnetization, available in our simulation, at a certain echo time, which serves as ideal blurring-free target. Final optimized sequences were exported for in vivo measurements at a real system (3 T Siemens, PRISMA) using the Pulseq standard. Results: The optimized RARE was able to successfully lower T2-induced blurring for single-shot RARE sequences in proton density-weighted and T2-weighted images. In addition to an increased sharpness, the neural network allowed correction of the contrast changes to match the theoretical transversal magnetization. The optimization found flip angle design strategies similar to existing literature, however, visual inspection of the images and evaluation of the respective point spread function demonstrated an improved performance. Conclusions: This work demonstrates that when variable flip angles and a convolutional neural network are optimized jointly in an end-to-end approach, sequences with more efficient minimization of T2-induced blurring can be found. This allows faster single- or multi-shot RARE MRI with longer echo trains.
CRIS-Team Scopus Importer:2023-07-07
Keywords: DenseNet; joint-optimization; MR-zero; RARE; RF-pulse design; T2-blurring; TSE

Multicenter Validation of the max-ICH Score in Intracerebral Hemorrhage - Sembill, Jochen; Castello, Juan P.; Sprügel, Maximilian; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Biffi, Alessandro; Kuramatsu, Joji; Hölter, Philip (Annals of Neurology, 2020)
Objective: Outcome prognostication unbiased by early care limitations (ECL) is essential for guiding treatment in patients presenting with intracerebral hemorrhage (ICH). The aim of this study was to determine whether the max-ICH (maximally treated ICH) Score provides improved and clinically useful prognostic estimation of functional long-term outcomes after ICH. Methods: This multicenter validation study compared the prognostication of the max-ICH Score versus the ICH Score regarding diagnostic accuracy (discrimination and calibration) and clinical utility using decision curve analysis. We performed a joint investigation of individual participant data of consecutive spontaneous ICH patients (n = 4,677) from 2 retrospective German-wide studies (RETRACE I + II; anticoagulation-associated ICH only) conducted at 22 participating centers, one German prospective single-center study (UKER-ICH; nonanticoagulation-associated ICH only), and 1 US-based prospective longitudinal single-center study (MGH; both anticoagulation- and nonanticoagulation-associated ICH), treated between January 2006 and December 2015. Results: Of 4,677 included ICH patients, 1,017 (21.7%) were affected by ECL (German cohort: 15.6% [440 of 2,377]; MGH: 31.0% [577 of 1,283]). Validation of long-term functional outcome prognostication by the max-ICH Score provided good and superior discrimination in patients without ECL compared with the ICH Score (area under the receiver operating curve [AUROC], German cohort: 0.81 [0.78–0.83] vs 0.74 [0.72–0.77], p < 0.01; MGH: 0.85 [0.81–0.89] vs 0.78 [0.74–0.82], p < 0.01), and for the entire cohort (AUROC, German cohort: 0.84 [0.82–0.86] vs 0.80 [0.77–0.82], p < 0.01; MGH: 0.83 [0.81–0.85] vs 0.77 [0.75–0.79], p < 0.01). Both scores showed no evidence of poor calibration. The clinical utility investigated by decision curve analysis showed, at high threshold probabilities (0.8, aiming to avoid false-positive poor outcome attribution), that the max-ICH Score provided a clinical net benefit compared with the ICH Score (14.1 vs 2.1 net predicted poor outcomes per 100 patients). Interpretation: The max-ICH Score provides valid and improved prognostication of functional outcome after ICH. The associated clinical net benefit in minimizing false poor outcome attribution might potentially prevent unwarranted care limitations in patients with ICH. ANN NEUROL 2020.
CRIS-Team Scopus Importer:2020-12-25

Multi-modal 2D-3D non-rigid registration - Prümmer, Marcus; Hornegger, Joachim; Pfister, Marcus; Dörfler, Arnd (Medical Imaging 2006: Image Processing, 2006)
In this paper, we propose a multi-modal non-rigid 2D-3D registration technique. This method allows a non-rigid alignment of a patient pre-operatively computed tomography (CT) to few intra operatively acquired fluoroscopic X-ray images obtained with a C-arm system. This multi-modal approach is especially focused on the 3D alignment of high contrast reconstructed volumes with intra-interventional low contrast X-ray images in order to make use of up-to-date information for surgical guidance and other interventions. The key issue of non-rigid 2D-3D registration is how to define the distance measure between high contrast 3D data and low contrast 2D projections. In this work, we use algebraic reconstruction theory to handle this problem. We modify the Euler-Lagrange equation by introducing a new 3D force. This external force term is computed from the residual of the algebraic reconstruction procedures. In the multi-modal case we replace the residual between the digitally reconstructed radiographs (DRR) and observed X-ray images with a statistical based distance measure. We integrate the algebraic reconstruction technique into a variational registration framework, so that the 3D displacement field is driven to minimize the "reconstruction distance" between the volumetric data and its 2D projections using mutual information (MI). The benefits of this 2D-3D registration approach are its scalability in the number of used X-ray reference images and the proposed distance that can handle low contrast fluoroscopies as well. Experimental results are presented on both artificial phantom and 3D C-arm CT images.

Multimodal CT or MRI for IV thrombolysis in ischemic stroke with unknown time of onset - Macha, Kosmas; Hölter, Philip; Siedler, Gabriela; Knott, Michael; Schwab, Stefan; Dörfler, Arnd; Kallmünzer, Bernd; Engelhorn, Tobias (Neurology, 2020)
OBJECTIVE: To investigate differences in procedure times, safety, and efficacy outcomes comparing 2 different protocols to enable thrombolysis in the extended or unknown time window after stroke onset with either multimodal CT or MRI. METHODS: Patients with ischemic stroke in the extended or unknown time window who received IV thrombolysis between January 2011 and May 2019 were identified from an institutional registry. Imaging-based selection was done by multimodal CT or MRI according to institutional treatment algorithms. RESULTS: IV thrombolysis was performed in 100 patients (54.3%) based on multimodal CT imaging and in 84 patients (45.7%) based on MRI. Baseline clinical data, including stroke severity and time from last seen normal to hospital admission, were similar in patients with CT and MRI. Door-to-needle times were shorter in patients with CT-based selection (median [interquartile range] 45 [37-62] minutes vs 75 [59-90] minutes; mean difference [95% confidence interval (CI)] -28 minutes [-35 to -21]). No differences were detected regarding the incidence of symptomatic intracranial hemorrhage (2 [2.0%] vs 4 [4.8%]; adjusted odds ratio [aOR] [95% CI] 0.47 [0.08-2.83]) and favorable outcome at day 90 (25 [33.8%] vs 33 [42.9%]; aOR 0.95 [0.45-2.02]). CONCLUSION: IV thrombolysis in ischemic stroke in the unknown or extended time window appeared safe in CT- and MRI-selected patients, while the use of CT imaging led to faster door-to-needle times. CLASSIFICATION OF EVIDENCE: This study provides Class IV evidence that for patients with ischemic stroke in the extended or unknown time window, imaging-based selection for IV thrombolysis by multimodal CT compared to MRI led to shorter door-to-needle times.
CRIS-Team Scopus Importer:2020-12-11

Multi-Modal Deep Guided Filtering for Comprehensible Medical Image Processing Supplementary Material - Stimpel, Bernhard; Syben-Leisner, Christopher; Schirrmacher, Franziska; Hölter, Philip; Dörfler, Arnd; Maier, Andreas (IEEE Transactions on Medical Imaging, 2019)
EVALuna2:212806

Multi-Modal Super-Resolution with Deep Guided Filtering - Stimpel, Bernhard; Syben-Leisner, Christopher; Schirrmacher, Franziska; Dörfler, Arnd; Maier, Andreas; Hölter, Philip (Informatik aktuell, 2019)
Despite the visually appealing results, most Deep Learningbased super-resolution approaches lack the comprehensibility that is required for medical applications. We propose a modified version of the locally linear guided filter for the application of super-resolution in medical imaging. The guidance map itself is learned end-to-end from multimodal inputs, while the actual data is only processed with known operators. This ensures comprehensibility of the results and simplifies the implementation of guarantees. We demonstrate the possibilities of our approach based on multi-modal MR and cross-modal CT and MR data. For both datasets, our approach performs clearly better than bicubic upsampling. For projection images, we achieve SSIMs of up to 0.99, while slice image data results in SSIMs of up to 0.98 for four-fold upsampling given an image of the respective other modality at full resolution. In addition, end-to-end learning of the guidance map considerably improves the quality of the results.
CRIS-Team Scopus Importer:2019-05-14

Multiple interleaved mode saturation (MIMOSA) for B1+ inhomogeneity mitigation in chemical exchange saturation transfer - Liebert, Andrzej; Gumbrecht, Rene; Tkotz, Katharina; Linz, Peter; Schmitt, Benjamin; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael; Zaiss, Moritz; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2019)
Purpose: To mitigate (Formula presented.) inhomogeneity in quantitative CEST MRI at ultra-high magnetic field strengths (B 0 ≥ 7 Tesla) using a parallel transmit system. Methods: Multiple interleaved mode saturation employs interleaving of 2 complementary phase sets during the saturation pulse train. Phase differences of 45° (first mode) and 90° (second mode) between 2 adjacent transmitter coil channels are used. The influence of the new saturation scheme on the CEST contrast was analyzed using Bloch-McConnell simulations. The presented method was verified in phantom and in vivo measurements of the healthy human brain. The relayed nuclear Overhauser effect was evaluated, and the inverse magnetic transfer ratio metric was calculated. Results were compared to a published (Formula presented.) correction method. All measurements were conducted on a whole-body 7 Tesla MRI system using an 8 transmitter and 32 receiver channel head coil. Results: Simulations showed that the inverse magnetic transfer ratio metric contrast of relayed nuclear Overhauser effect shows a smaller dependency on the relative amplitudes of the 2 different modes than the contrasts of Cr and amide proton transfer. Measurements of an egg white phantom showed markedly improved homogeneity compared to the uncorrected inverse magnetic transfer ratio metric (relayed nuclear Overhauser effect) images and slightly improved results compared to (Formula presented.) corrected images. In vivo multiple interleaved mode saturation images showed similar contrast compared to (Formula presented.) corrected images. Conclusion: Multiple interleaved mode saturation can be used as a simple method to mitigate (Formula presented.) inhomogeneity effects in CEST MRI at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced because an additional scan, usually required for (Formula presented.) correction, can be omitted.
CRIS-Team Scopus Importer:2019-05-02
Keywords: 7 Tesla; B1 shimming; chemical exchange saturation transfer; parallel transmission (pTx); pulsed CEST; RF inhomogeneity; ultra-high-field MRI

Neural mechanisms of perceptive and affective processing of body stimuli in anorexia nervosa – are there developmental effects? - Horndasch, Stefanie; Rösch, Julie; Kratz, Oliver; Vogel, Anne; Heinrich, Hartmut; Graap, Holmer; Moll, Gunther; Dörfler, Arnd; Forster, Clemens (Psychiatry Research, 2020)
Different components of body image processing seem to be reflected by different neural mechanisms. A core symptom of Anorexia nervosa (AN) is a disturbance of body image with correlates found on a neural level. The present study focuses on the neural processing of visual body stimuli of different weight categories in adolescent and adult AN patients. Thirty-three adolescents aged 12–18 years (15 AN patients, 18 control participants) and 36 adult women (19 AN patients, 17 control participants) underwent functional magnetic resonance imaging (fMRI) while performing a perceptive and an affective body image task involving photographic stimuli of women belonging to different BMI categories. Differential effects on activation, depending on the BMI of the women shown in the pictures, were found in frontal brain regions, the thalamus, the caudate and the fusiform gyrus. Group effects differentiating between AN patients and control participants were seen mainly in the caudate and insula. No significant developmental effect was seen. During a perceptive task, diminished activation of regions involved in perceptive and evaluative functions as well as emotional reasoning was seen in AN. During an affective task there was a tendency towards activation differences reflecting reduced ability of size estimation and impaired integration of visual and body perception with emotions.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Adolescence; Body; Eating disorders; fMRI

Neural processing of food and emotional stimuli in adolescent and adult anorexia nervosa patients - Horndasch, Stefanie; Roesch, Julie; Forster, Clemens; Dörfler, Arnd; Lindsiepe, Silja; Heinrich, Hartmut; Graap, Holmer; Moll, Gunther; Kratz, Oliver (PLoS ONE, 2018)
BACKGROUND: A constant preoccupation with food and restrictive eating are main symptoms of anorexia nervosa (AN). Imaging studies revealed aberrant neural activation patterns in brain regions processing hedonic and reward reactions as well as-potentially aversive-emotions. An imbalance between so called "bottom-up" and "top-down" control areas is discussed. The present study is focusing on neural processing of disease-specific food stimuli and emotional stimuli and its developmental course in adolescent and adult AN patients and could offer new insight into differential mechanisms underlying shorter or more chronic disease. METHODS: 33 adolescents aged 12-18 years (15 AN patients, 18 control participants) and 32 adult women (16 AN patients, 16 control participants) underwent functional magnetic resonance imaging (fMRI, 3T high-field scanner) while watching pictures of high and low-calorie food and affective stimuli. Afterwards, they rated subjective valence of each picture. FMRI data analysis was performed using a region of interest based approach. RESULTS: Pictures of high-calorie food items were rated more negatively by AN patients. Differences in activation between patients and controls were found in "bottom up" and "top down" control areas for food stimuli and in several emotion processing regions for affective stimuli which were more pronounced in adolescents than in adults. CONCLUSION: A differential pattern was seen for food stimuli compared to generally emotion eliciting stimuli. Adolescents with AN show reduced processing of affective stimuli and enhanced activation of regions involved in "bottom up" reward processing and "top down" control as well as the insula with regard to food stimuli with a focus on brain regions which underlie changes during adolescent development. In adults less clear and less specific activation differences were present, pointing towards a high impact that regions undergoing maturation might have on AN symptoms.
EVALuna2:35832

Neuroanatomical correlates of intelligence in healthy young adults: the role of basal ganglia volume - Rhein, Cosima; Mühle, Christiane; Richter-Schmidinger, Tanja; Alexopoulos, Panagiotis; Dörfler, Arnd; Kornhuber, Johannes (PLoS ONE, 2014)
In neuropsychiatric diseases with basal ganglia involvement, higher cognitive functions are often impaired. In this exploratory study, we examined healthy young adults to gain detailed insight into the relationship between basal ganglia volume and cognitive abilities under non-pathological conditions.We investigated 137 healthy adults that were between the ages of 21 and 35 years with similar educational backgrounds. Magnetic resonance imaging (MRI) was performed, and volumes of basal ganglia nuclei in both hemispheres were calculated using FreeSurfer software. The cognitive assessment consisted of verbal, numeric and figural aspects of intelligence for either the fluid or the crystallised intelligence factor using the intelligence test Intelligenz-Struktur-Test (I-S-T 2000 R). Our data revealed significant correlations of the caudate nucleus and pallidum volumes with figural and numeric aspects of intelligence, but not with verbal intelligence. Interestingly, figural intelligence associations were dependent on sex and intelligence factor; in females, the pallidum volumes were correlated with crystallised figural intelligence (r = 0.372, p = 0.01), whereas in males, the caudate volumes were correlated with fluid figural intelligence (r = 0.507, p = 0.01). Numeric intelligence was correlated with right-lateralised caudate nucleus volumes for both females and males, but only for crystallised intelligence (r = 0.306, p = 0.04 and r = 0.459, p = 0.04, respectively). The associations were not mediated by prefrontal cortical subfield volumes when controlling with partial correlation analyses.The findings of our exploratory analysis indicate that figural and numeric intelligence aspects, but not verbal aspects, are strongly associated with basal ganglia volumes. Unlike numeric intelligence, the type of figural intelligence appears to be related to distinct basal ganglia nuclei in a sex-specific manner. Subcortical brain structures thus may contribute substantially to cognitive performance.
EVALuna2:22974

Neuroanatomical correlates of severe cardiac arrhythmias in acute ischemic stroke - Seifert, Frank; Kallmünzer, Bernd; Gutjahr, Isabell; Breuer, Lorenz; Winder, Klemens; Kaschka, Iris; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Journal of Neurology, 2015)
Neurocardiological interactions can cause severe cardiac arrhythmias in patients with acute ischemic stroke. The relationship between the lesion location in the brain and the occurrence of cardiac arrhythmias is still discussed controversially. The aim of the present study was to correlate the lesion location with the occurrence of cardiac arrhythmias in patients with acute ischemic stroke. Cardiac arrhythmias were systematically assessed in patients with acute ischemic stroke during the first 72 h after admission to a monitored stroke unit. Voxel-based lesion-symptom mapping (VLSM) was used to correlate the lesion location with the occurrence of clinically relevant severe arrhythmias. Overall 150 patients, 56 with right-hemispheric and 94 patients with a left-hemispheric lesion, were eligible to be included in the VLSM study. Severe cardiac arrhythmias were present in 49 of these 150 patients (32.7%). We found a significant association (FDR correction, q < 0.05) between lesions in the right insular, right frontal and right parietal cortex as well as the right amygdala, basal ganglia and thalamus and the occurrence of cardiac arrhythmias. Because left- and right-hemispheric lesions were analyzed separately, the significant findings rely on the 56 patients with right-hemispheric lesions. The data indicate that these areas are involved in central autonomic processing and that right-hemispheric lesions located to these areas are associated with an elevated risk for severe cardiac arrhythmias.
EVALuna2:22355

Neuroanatomic Correlates of Angioedema in stroke patients with thrombolysis - Winder, K.; Kallmünzer, Bernd; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, F.; Fröhlich, Kilian (EUROPEAN JOURNAL OF NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-06-16

Neuroanatomic Correlates of Female Sexual Dysfunction in Multiple Sclerosis - Winder, Klemens; Linker, Ralf; Seifert, Frank; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hoesl, Katharina M.; Hilz, Max-Josef (Annals of Neurology, 2016)
This study intended to determine associations between alterations of female sexual arousal as well as vaginal lubrication and the site of cerebral multiple sclerosis (MS) lesions.In 44 women with MS (mean age: 36.5 ± 9.9 years), we assessed their medical history and evaluated sexual function using the Female Sexual Function Index scores for arousal and vaginal lubrication. We determined potential confounding factors of sexual dysfunction: age; disease duration; physical disability; depression; bladder or urinary dysfunction; and total volume of cerebral lesions. Arousal and lubrication scores were correlated with one another and with potential confounding factors. Cerebral MS lesions were recorded on imaging scans. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating cerebral sites of MS lesions with arousal and lubrication scores.Decreased arousal scores correlated with decreased lubrication scores; decreased lubrication scores were associated with bladder or urinary symptoms. Arousal and lubrication scores were not associated with any other variables. Multivariate VLSM analysis, including arousal and lubrication scores as covariables of interest, showed right occipital lesions associated with impaired arousal and left insular lesions associated with decreased lubrication. Impaired lubrication remained associated with left insular lesions after adjustment for bladder or urinary dysfunction.Our data indicate that impaired female sexual arousal is associated with MS lesions in the occipital region, integrating visual information and modulating attention toward visual input. Impaired lubrication correlated with lesions in the left insular region, contributing to mapping and generating visceral arousal states. Ann Neurol 2016;80:490-498.
EVALuna2:22501

Neuroanatomic correlates of poststroke hyperglycemia - Winder, Klemens; Seifert, Frank; Ohnemus, Tessa; Sauer, Eva-Maria; Kloska, Stephan; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin (Annals of Neurology, 2015)
A study was undertaken to determine associations between ischemic stroke sites and poststroke hyperglycemia (PSH).Nondiabetic patients with first ever ischemic stroke confirmed by imaging were prospectively included. Blood glucose level (BGL), National Institute of Health Stroke Scale (NIHSS) score, and clinical parameters were assessed on admission. BGL was dichotomized for elevated versus normal levels using a cutoff value of >7.0 mmol/l. Clinical parameters were correlated with BGL and were compared between patient groups with elevated versus normal glucose values. A voxel-based lesion symptom mapping (VLSM) analysis adjusted for confounding variables was performed correlating sites of ischemic lesions with PSH.Of 1,281 stroke patients screened, 229 (mean age = 66.3 ± 15.9 years) met the inclusion criteria. Patients with elevated BGL were older, had higher NIHSS scores, and had larger infarcts compared to those without elevated glucose levels. Spearman rank analysis showed correlations between BGL and age, infarct size, heart rate (HR), and NIHSS scores (p <= 0.05). The VLSM analysis adjusted for these confounding factors demonstrated associations between PSH and damaged voxels in right hemispheric insular and opercular areas.The data indicate that damage in the right insulo-opercular areas contributes to PSH. The association between sympathetically mediated increase of HR and BGL suggests disinhibition of sympathetic outflow as a possible mechanism for PSH.
EVALuna2:22352

Neurochirurgische Operationsmöglichkeiten bei posteriorer Epilepsie - Rössler, Karl; Kasper, Burkhard; Tomschik, Matthias; Dörfler, Arnd; Buchfelder, Michael; Dorfer, Christian (Zeitschrift für Epileptologie, 2021)
Background: The surgical treatment of posterior epilepsy within the spectrum of epilepsy surgery represents a particular challenge. Objective: To present the different surgical options for epilepsy surgery of posterior epilepsies. Material and methods: The different surgical procedures are illustrated in the light of the historical development and recent technical developments. Results: Invasive monitoring (implantation of electrodes), resective and disconnective procedures in combination with new technical developments led to an improvement in seizure outcome in the surgical treatment of posterior epilepsies.
CRIS-Team Scopus Importer:2021-01-15
Keywords: ECoG; Epilepsy surgery; Lesionectomy; Posterior disconnection; Tailored lesionectomy

Neurocritical care complications and interventions influence the outcome in aneurysmal subarachnoid hemorrhage - Hammer, Alexander; Erbguth, Frank; Hohenhaus, Matthias; Hammer, Christian; Lücking, Hannes; Gesslein, Markus; Killer-Oberpfalzer, Monika; Steiner, Hans Herbert; Janssen, Hendrik (BMC Neurology, 2021)
Background: This observational study was performed to show the impact of complications and interventions during neurocritical care on the outcome after aneurysmal subarachnoid hemorrhage (SAH). Methods: We analyzed 203 cases treated for ruptured intracranial aneurysms, which were classified regarding clinical outcome after one year according to the modified Rankin Scale (mRS). We reviewed the data with reference to the occurrence of typical complications and interventions in neurocritical care units. Results: Decompressive craniectomy (odds ratio 21.77 / 6.17 ; p < 0.0001 / p = 0.013), sepsis (odds ratio 14.67 / 6.08 ; p = 0.037 / 0.033) and hydrocephalus (odds ratio 3.71 / 6.46 ; p = 0.010 / 0.00095) were significant predictors for poor outcome and death after one year beside “World Federation of Neurosurgical Societies” (WFNS) grade (odds ratio 3.86 / 4.67 ; p < 0.0001 / p < 0.0001) and age (odds ratio 1.06 / 1.10 ; p = 0.0030 / p < 0.0001) in our multivariate analysis (binary logistic regression model). Conclusions: In summary, decompressive craniectomy, sepsis and hydrocephalus significantly influence the outcome and occurrence of death after aneurysmal SAH.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Decompressive craniectomy; Intracranial aneurysm; Neurocritical care; Outcome; Subarachnoid hemorrhage; Vascular disorders

Neuroendocrine changes in patients with spontaneous supratentorial intracerebral hemorrhage - Huttner, Hagen; Kiphuth, Ines-Christine; Teuber, Linda; Lücking, Hannes; Kloska, Stephan; Staykov, Dimitre; Kuramatsu, Joji; Mauer, Christoph; Breuer, Lorenz; Dörfler, Arnd; Köhrmann, Martin (Neurocritical Care, 2013)
Background: Neuroendocrine changes have been reported after ischemic stroke, subarachnoid hemorrhage, and brain trauma. As there are no corresponding data in patients with intracerebral hemorrhage (ICH) we analyzed various neuroendocrine parameters to investigate possible alterations in hormone profiles of patients with ICH. Methods: Twenty patients with ICH were prospectively enrolled in the study. Patients were a priori parted into two groups: Ten non-ventilated patients treated on the stroke-unit (hemorrhage volumes <20 ml, "small ICH"), and 10 ventilated patients treated on the neurocritical care unit (hematoma volumes >20 ml with possible additional ventricular involvement ("large ICH"). Neuroendocrine parameters were compared between both groups referring to reference values. The following parameters were obtained over a period of 9 days in 20 patients with spontaneous supratentorial ICH: thyrotropin, free thiiodothyronine and thyroxine, human growth hormone, insulin-like growth factor 1, luteinizing hormone, follicle-stimulating hormone, testosterone, prolactin, adrenocorticotropic hormone, and cortisol. Results: Small ICH patients were in a median 71 (54-88) years old and had a mean ICH volume of 9.5 ± 6.5 ml, whereas large ICH patients were 65 (47-80) years old and showed a mean volume of 56 ± 30.2 ml. None of the patients revealed pathological alterations for thyrotropin, free thiiodothyronine, thyroxine, human growth hormone, insulin-like growth factor 1, and testosterone. There was only a mild decrease of adrenocorticotropic hormone and cortisol on day 3 in large ICH patients. Small ICH patients showed pathologically elevated levels of luteinizing and follicle-stimulating hormone throughout the observation period. Large ICH patients showed a marked increase of prolactin that developed during the course. Conclusions: Overall, neuroendocrine changes in ICH patients are not as profound as reported for ischemic stroke or subarachnoid hemorrhage. The clinical significance of increased LH and FSH levels in small ICH is unclear, whereas elevation of prolactin in large ICH was anticipated. Future randomized controlled trials should also focus on neuroendocrine parameters to clarify the impact of possible hormonal alterations on functional outcome. © 2011 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hormone profile; Intracerebral hemorrhage; Neuroendocrine

Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity

Neuromyelitis optica presenting with relapses under treatment with natalizumab: a case report - Lee, De Hyung; Laemmer, Alexandra B.; Waschbisch, Anne; Struffert, Tobias; Maihöfner, Christian; Schwab, Stefan; Linker, Ralf (Journal of Medical Case Reports, 2014)
Neuromyelitis optica is an inflammatory demyelinating disease of the central nervous system. To date, optimal therapeutic approaches for neuromyelitis optica have yet to be defined. Natalizumab is highly effective in relapsing-remitting multiple sclerosis and might be considered as an option.Here, we describe a 67-year-old Caucasian man with definite neuromyelitis optica with detection of anti-aquaporin-4 antibodies over the course of the disease. After initially discussing the diagnosis of multiple sclerosis at an outside hospital, our patient received interferon beta 1a as well as repeated corticosteroid pulses without success. Under subsequent therapy with natalizumab, he continued to present relapses. It was not until discontinuation of natalizumab, repeated cycles of plasma exchanges and initiation of therapy with rituxan that the disease course started to stabilize. Although B cells were completely depleted, our patient experienced another severe myelitis relapse during further follow-up and an additional immunosuppressive therapy with cyclophosphamide was started. Under this regimen, no further relapses occurred over the next 24 months.This case adds further evidence to the previously discussed notion that natalizumab, while highly effective in multiple sclerosis, may not work sufficiently in neuromyelitis optica. It further advocates for repetitive testing of anti-aquaporin-4 antibodies before and after treatment initiation.
EVALuna2:22348

Neuropsychology and MRI correlates of neurodegeneration in SPG11 hereditary spastic paraplegia - Utz, Kathrin; Kohl, Zacharias; Marterstock, Dominique; Dörfler, Arnd; Winkler, Jürgen; Schmidt, Manuel; Regensburger, Martin (Orphanet Journal of Rare Diseases, 2022)
Background: SPG11-linked hereditary spastic paraplegia is characterized by multisystem neurodegeneration leading to a complex clinical and yet incurable phenotype of progressive spasticity and weakness. Severe cognitive symptoms are present in the majority of SPG11 patients, but a systematic and multidimensional analysis of the neuropsychological phenotype in a larger cohort is lacking. While thinning of the corpus callosum is a well-known structural hallmark observed in SPG11 patients, the neuroanatomical pattern of cortical degeneration is less understood. We here aimed to integrate neuropsychological and brain morphometric measures in SPG11. Methods: We examined the neuropsychological profile in 16 SPG11 patients using a defined neuropsychological testing battery. Long-term follow up testing was performed in 7 patients. Cortical and subcortical degeneration was analyzed using an approved, artificial intelligence based magnetic resonance imaging brain morphometry, comparing patients to established reference values and to matched controls. Results: In SPG11 patients, verbal fluency and memory as well as frontal-executive functions were severely impaired. Later disease stages were associated with a global pattern of impairments. Interestingly, reaction times correlated significantly with disease progression. Brain morphometry showed a significant reduction of cortical and subcortical parenchymal volume following a rostro-caudal gradient in SPG11. Whereas performance in memory tasks correlated with white matter damage, verbal fluency measures showed strong associations with frontal and parietal cortical volumes. Conclusions: The present data will help define neuropsychological and imaging read out parameters in early as well as in advanced clinical stages for future interventional trials in SPG11.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Brain morphometry; Neuropsychology; Spastic paraplegia; SPG11; Verbal fluency

Neurovascular compression in arterial hypertension: Correlation of clinical data to 3d-visualizations of mri-findings - Manava, Panagiota; Hastreiter, Peter; Schmieder, Roland; Jung, Susanne; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael; Buchfelder, Michael; Naraghi, Ramin (Open Neuroimaging Journal, 2021)
Aims: In this study, we attempted to identify clinical parameters predicting the absence or presence of Neurovascular Compression (NVC) at the Ventrolateral Medulla (VLM) in arterial hypertension (HTN) in MRI findings. Background: Cardiovascular and pulmonary afferences are transmitted through the left vagus and glossopharyngeal nerve to the brain stem and vasoactive centers. Evidence supports the association between HTN and NVC at the left VLM. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left VLM. Image processing of MRI provides comprehensible detection of NVC. HTN affects hemodynamic parameters and organs. Objective: This study analyzes and correlates clinical data and MRI findings in patients with and without NVC at the VLM in treatment resistant HTN to obtain possible selection criteria for neurogenic hypertension. Methods: In 44 patients with treatment resistant HTN, we compared MRI findings of neurovascular imaging to demographic, clinical and lifestyle data, office and 24-hour ambulatory Blood Pressure (BP), and cardiovascular imaging and parameters. Results: Twenty-nine (66%) patients had evidence of NVC at the VLM in MRI. Sixteen patients (36%) had unilateral NVC on the left side, 7 (16%) unilateral right and 6 (14%) bilateral NVC. Fifteen (34%) had no evidence of NVC at the VLM. Patients with left sided NVC were significantly younger, than those without NVC (p=0.034). They showed a statistically significant variance in daytime (p=0.020) and nighttime diastolic BP (p<0.001) as the mean arterial pressure (p=0.020). Other measured parameters did not show significant differences between the two groups. Conclusion: We suggest to examine young adults with treatment resistant HTN for the presence of NVC at VLM, before signs of permanent organ damage appear. Clinical and hemodynamic parameters did not emerge as selection criteria to predict NVC. MVD as a surgical treatment of NVC in HTN is not routine yet as a surgical treatment of NVC in HTN is not routine yet. Detection of NVC by imaging and image processing remains the only criteria to suggest MVD, which should be indicated on an individual decision.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypertension; Image fusion; MRI; Neuroimaging; Neurovascular compression; Ventrolateral medulla

Neurovascular compression of medulla oblongata - Association for gestation-induced hypertension - Tanrikulu, Levent; Naraghi, Ramin; Ernst, Veronika; Voigt, Franziska; Hastreiter, Peter; Dörfler, Arnd; Buchfelder, Michael; Beckmann, Matthias; Goecke, Tamme W. (Medical Hypotheses, 2015)
Patients with essential hypertension may show neurovascular compression (NVC) at the rostral ventrolateral medulla oblongata (RVLM). Ectatic loops of the vertebral artery (VA) or the inferior posterior cerebellar artery (PICA) cause NVC. This study aims to show the existence and morphology of NVC in patients with gestation-induced hypertension. 17 females were prospectively examined between 19. +. 0 and 35. +. 6. weeks of gestation. 3 patients with chronic hypertension (group A), 10 patients with preeclampsia (group B), 3 patients with superimposed preeclampsia (chronic hypertension with preeclampsia; group C) and one normotensive patient were included. Groups B and C represented patients with gestation-induced hypertension. All 17 patients underwent imaging by high resolution magnetic resonance imaging (MR-CISS, constructive interference in the steady state). Image processing was done with segmentation and three-dimensional (3D)-visualization was implemented with direct volume rendering of the individual neurovascular details of each patient. 9 of 17 patients (53%) showed NVC of the RVLM. Right-sided NVC was seen in 7 patients (41%). Left-sided NVC was seen in 6 patients (35%). Bilateral NVC was seen in 4 patients (24%). NVC was missing in 8 of the examined 17 patients (47%). The existence of NVC with high-resolution MRI was analyzed in gestation-induced hypertensive pregnant females for the first time. Neurovascular conflicts were seen in hypertensive pregnants. It is possible that NVC is potentially associated in patients with gestation-induced hypertension.
CRIS-Team Scopus Importer:2022-08-05

Neutrophil-to-lymphocyte ratio as an independent predictor for unfavorable functional outcome in aneurysmal subarachnoid hemorrhage - Giede-Jeppe, Antje; Reichl, Jonathan; Sprügel, Maximilian; Lücking, Hannes; Hölter, Philip; Eyüpoglu, Ilker Yasin; Kuramatsu, Joji; Huttner, Hagen; Gerner, Stefan (Journal of Neurosurgery, 2019)
OBJECTIVEStroke-associated immunosuppression and inflammation are increasingly recognized as factors triggering infections and thus potentially influencing outcome after stroke. Several studies have demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes for patients with ischemic stroke or intracerebral hemorrhage. Thus far, in patients with subarachnoid hemorrhage the association between NLR and outcome is insufficiently established. The authors sought to investigate the association between NLR on admission and functional outcome in aneurysmal subarachnoid hemorrhage (aSAH).METHODSThis observational study included all consecutive aSAH patients admitted to a German tertiary center over a 5-year period (2008-2012). Data regarding patient demographics and clinical, laboratory, and in-hospital measures, as well as neuroradiological data, were retrieved from institutional databases. Functional outcome was assessed at 3 and 12 months using the modified Rankin Scale (mRS) score and categorized into favorable (mRS score 0-2) and unfavorable (mRS score 3-6). Patients' radiological and laboratory characteristics were compared between aSAH patients with favorable and those with unfavorable outcome at 3 months. In addition, multivariate analysis was conducted to investigate parameters independently associated with favorable outcome. Receiver operating characteristic (ROC) curve analysis was undertaken to identify the best cutoff for NLR to discriminate between favorable and unfavorable outcome in these patients. To account for imbalances in baseline characteristics, propensity score matching was carried out to assess the influence of NLR on outcome measures.RESULTSOverall, 319 patients with aSAH were included. Patients with unfavorable outcome at 3 months were older, had worse clinical status on admission (Glasgow Coma Scale score and Hunt and Hess grade), greater amount of subarachnoidal and intraventricular hemorrhage (modified Fisher Scale grade and Graeb score), and higher rates of infectious complications (pneumonia and sepsis). A significantly higher NLR on admission was observed in patients with unfavorable outcome according to mRS score (median [IQR] NLR 5.8 [3.0-10.0] for mRS score 0-2 vs NLR 8.3 [4.5-12.6] for mRS score 3-6; p < 0.001). After adjustments, NLR on admission remained a significant predictor for unfavorable outcome in SAH patients (OR [95% CI] 1.014 [1.001-1.027]; p = 0.028). In ROC analysis, an NLR of 7.05 was identified as the best cutoff value to discriminate between favorable and unfavorable outcome (area under the curve = 0.614, p < 0.001, Youden's index = 0.211; mRS score 3-6: 94/153 [61.4%] for NLR ≥ 7.05 vs 67/166 [40.4%] for NLR < 7.05; p < 0.001). Subanalysis of patients with NLR levels ≥ 7.05 vs < 7.05, performed using 2 propensity score-matched cohorts (n = 133 patients in each group), revealed an increased proportion of patients with unfavorable functional outcome at 3 months in patients with NLR ≥ 7.05 (mRS score 3-6 at 3 months: NLR ≥ 7.05 82/133 [61.7%] vs NLR < 7.05 62/133 [46.6%]; p = 0.014), yet without differences in mortality at 3 months (NLR ≥ 7.05 37/133 [27.8%] vs NLR < 7.05 27/133 [20.3%]; p = 0.131).CONCLUSIONSAmong aSAH patients, NLR represents an independent parameter associated with unfavorable functional outcome. Whether the impact of NLR on functional outcome is related to preexisting comorbidities or represents independent causal relationships in the context of stroke-associated immunosuppression should be investigated in future studies.
EVALuna2:204508

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor for In-Hospital Mortality in Spontaneous Intracerebral Hemorrhage - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Beuscher, Vanessa D.; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2017)
Stroke-associated immunosuppression and inflammation are increasingly recognized as factors that trigger infections and thus, potentially influence the outcome after stroke. Several studies demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes in patients with ischemic stroke. However, little is known about the impact of NLR on short-term mortality in intracerebral hemorrhage (ICH).This observational study included 855 consecutive ICH-patients. Patient demographics, clinical, laboratory, and in-hospital measures as well as neuroradiological data were retrieved from institutional databases. Functional 3-months-outcome was assessed and categorized as favorable (modified Rankin Scale [mRS] 0-3) and unfavorable (mRS 4-6). We (i) studied the natural course of NLR in ICH, (ii) analyzed parameters associated with NLR on admission (NLROA), and (iii) evaluated the clinical impact of NLR on mortality and functional outcome.The median NLROA of the entire cohort was 4.66 and it remained stable during the entire hospital stay. Patients with NLR >=4.66 showed significant associations with poorer neurological status (National Institute of Health Stroke Scale [NIHSS] 18 [9-32] vs. 10 [4-21]; p < 0.001), larger hematoma volume on admission (17.6 [6.9-47.7] vs. 10.6 [3.8-31.7] mL; p = 0.001), and more frequently unfavorable outcome (mRS 4-6 at 3 months: 317/427 [74.2%] vs. 275/428 [64.3%]; p = 0.002). Patients with an NLR under the 25th percentile (NLR <2.606) - compared to patients with NLR >2.606 - presented with a better clinical status (NIHSS 12 [5-21] vs. 15 [6-28]; p = 0.005), lower hematoma volumes on admission (10.6 [3.6-30.1] vs. 15.1 [5.7-42.3] mL; p = 0.004) and showed a better functional outcome (3 months mRS 0-3: 82/214 [38.3%] vs. 185/641 [28.9%]; p = 0.009). Patients associated with high NLR (>=8.508 = above 75th-percentile) showed the worst neurological status on admission (NIHSS 21 [12-32] vs. 12 [5-23]; p < 0.001), larger hematoma volumes (21.0 [8.6-48.8] vs. 12.2 [4.1-34.9] mL; p < 0.001), and higher proportions of unfavorable functional outcome at 3 months (mRS 4-6: 173/214 vs. 418/641; p < 0.001). Further, NLR was linked to more frequently occurring infectious complications (pneumonia 107/214 vs. 240/641; p = 0.001, sepsis: 78/214 vs. 116/641; p < 0.001), and increased c-reactive-protein levels on admission (p < 0.001; R2 = 0.064). Adjusting for the above-mentioned baseline confounders, multivariable logistic analyses revealed independent associations of NLROA with in-hospital mortality (OR 0.967, 95% CI 0.939-0.997; p = 0.029).NLR represents an independent parameter associated with increased mortality in ICH patients. Stroke physicians should focus intensely on patients with increased NLR, as these patients appear to represent a population at risk for infectious complications and increased short-mortality. Whether these patients with elevated NLR may benefit from a close monitoring and specially designed therapies should be investigated in future studies.
EVALuna2:22531

Neutrophil-to-lymphocyte ratio is associated with increased cerebral blood flow velocity in acute bacterial meningitis - Giede-Jeppe, Antje; Atay, Selim; Koehn, Julia; Mrochen, Anne; Lücking, Hannes; Hölter, Philip; Volbers, Bastian; Huttner, Hagen B.; Hueske, Lena; Bobinger, Tobias (Scientific Reports, 2021)
In community-acquired bacterial meningitis (CABM) intracranial vascular alterations are devastating complications which are triggered by neuroinflammation and result in worse clinical outcome. The Neutrophil-to-Lymphocyte ratio (NLR) represents a reliable parameter of the inflammatory response. In this study we analyzed the association between NLR and elevated cerebral blood flow velocity (CBFv) in CABM-patients. This study included all (CABM)-patients admitted to a German tertiary center between 2006 and 2016. Patients’ demographics, in-hospital measures, neuroradiological data and clinical outcome were retrieved from institutional databases. CBFv was assessed by transcranial doppler (TCD). Patients’, radiological and laboratory characteristics were compared between patients with/without elevated CBFv. Multivariate-analysis investigated parameters independently associated with elevated CBFv. Receiver operating characteristic(ROC-)curve analysis was undertaken to identify the best cut-off for NLR to discriminate between increased CBFv. 108 patients with CABM were identified. 27.8% (30/108) showed elevated CBFv. Patients with elevated CBFv and normal CBFv, respectively had a worse clinical status on admission (Glasgow Coma Scale: 12 [9–14] vs. 14 [11–15]; p = 0.005) and required more often intensive care (30/30 [100.0%] vs. 63/78 [80.8%]; p = 0.01).The causative pathogen was S. pneumoniae in 70%. Patients with elevated CBFv developed more often cerebrovascular complications with delayed cerebral ischemia (DCI) within hospital stay (p = 0.031). A significantly higher admission-NLR was observed in patients with elevated CBFv (median [IQR]: elevated CBFv:24.0 [20.4–30.2] vs. normal CBFv:13.5 [8.4–19.5]; p < 0.001). Multivariate analysis, revealed NLR to be significantly associated with increased CBFv (Odds ratio [95%CI] 1.042 [1.003–1.084]; p = 0.036). ROC-analysis identified a NLR of 20.9 as best cut-off value to discriminate between elevated CBFv (AUC = 0.713, p < 0.0001, Youden's Index = 0.441;elevated CBFv: NLR ≥ 20.9 19/30[63.5%] vs. normal CBFv: NLR > 20.9 15/78[19.2%]; p < 0.001). Intracranial vascular complications are common among CABM-patients and are a risk factor for unfavorable outcome at discharge. Elevated NLR is independently associated with high CBFv and may be useful in predicting patients’ prognosis.
CRIS-Team Scopus Importer:2021-06-18

New Clinical and Morphologic Aspects in Trigeminal Neuralgia - Tanrikulu, Levent; Hastreiter, Peter; Bassemir, Teresa; Bischoff, Barbara; Buchfelder, Michael; Dörfler, Arnd; Naraghi, Ramin (World Neurosurgery, 2016)
OBJECTIVE: High-resolution magnetic resonance imaging can be used to delineate the morphology of neurovascular compression (NVC) in detail. This study focuses on essential morphologic parameters in relation to the clinical appearance of patients with trigeminal neuralgia (TN). METHODS: A total of 180 patients with TN underwent magnetic resonance-constructive interference in steady state/time of flight. Parameters of the affected nerves (length) and causative vessels were examined: (1) the relationship between the NVC site (caudal/cranial/laterocaudal/mediocranial) and affected area (V1, V2, V3); (2) nerve deformity; (3) vascular loop; (4) existence of a "cerebrospinal fluid (CSF) sign" by a separation of trigeminal fascicles by a vessel; and (5) localization of the causative vessel. RESULTS: A total of 10 patients with V1 affection showed 6 caudal, 0 cranial and laterocaudal, and 4 mediocranial NVC; 26 patients with V2 affection showed 17 caudal, 0 cranial, 1 laterocaudal, and 8 mediocranial NVC; 29 patients with V3 affection showed 23 caudal, 1 cranial, 3 laterocaudal, and 2 mediocranial NVC; 25 patients with V1 and V2 affection showed 17 caudal, 1 cranial, 0 laterocaudal, and 7 mediocranial NVC; 36 patients with V2 and V3 affection showed 30 caudal, 3 cranial, 1 laterocaudal, and 2 mediocranial NVC; and 6 patients with V1, V2, and V3 affection showed 4 caudal, 1 cranial, 0 laterocaudal, and 1 mediocranial NVC. A total of 63 patients (35%) showed nerval deformity by distorsion of the trigeminal fascicles from compressing vessel; 37 of 39 patients (95%) with right-sided deformity showed right-sided TN; and 21 of 22 patients (95%) with left-sided TN showed left-sided nerve deformation. Two patients with bilateral nerve deformity showed bilateral TN. Rostral superior cerebellar artery (SCA) loop compression was seen in 24 patients (17%), caudal SCA loop compression was seen in 10 patients (7%), and double SCA loop compression was seen in 33 patients (23%). Sandwich compression was seen in 18 (12%), and a CSF sign was seen in 24 patients. All 24 patients (100%) with a CSF sign had V1 affection. CONCLUSIONS: The CSF sign is pathognomonic for V1 affection. Vascular loops from cranial on the nerve were the most frequent types of compression in all areas of pain, followed by mediocranial loops. This evaluation is reproducible and contributes to the role of magnetic resonance imaging and a classification of findings in the preoperative evaluation of NVC.
EVALuna2:33152

No evidence of disease activity status over 3 years in a real-world cohort of relapsing remitting MS patients in Germany - Huhn, Konstantin; Senger, Daniela; Utz, Kathrin S.; Schmidt, Manuel; Fröhlich, Katharina; Waschbisch, Anne; Seifert, Frank; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf A. (Multiple Sclerosis and Related Disorders, 2019)
BACKGROUND: Over the last decade, therapy of relapsing remitting multiple sclerosis (RRMS) has evolved with the approval of several new treatment concepts. Thus, treatment goals have become more ambitious aiming at "no evidence of disease activity" (NEDA). As NEDA-3, this concept comprises freedom of clinical disease progression and relapses as well as inflammatory MRI activity. So far, data on NEDA status mainly stem from post-hoc analyses of drug approval studies. Yet, less is known about the significance of NEDA in "real-world" clinical settings. Hence, our study aims at investigation of NEDA in a heterogeneous cohort of relapsing MS patients. METHODS: This is a retrospective single-center study at the Department of Neurology of the University Hospital Erlangen, Germany, including data of 306 patients with relapsing forms of MS (RMS) or clinical isolated syndrome (CIS) from 2009 to 2016. Inclusion required sufficient clinical information and in house cranial MRI follow-up data sets at baseline and at follow-up after one year with a potential extension to two and three year follow-up, if possible. NEDA-3 status, its correlation to clinical features, associated medication and NEDA failure (EDA) were analyzed. RESULTS: In a cohort of RMS patients at the early stages of the disease (median EDSS 1.5, mean disease duration 30 months) at baseline, 45% retained NEDA-3 status after one year. This percentage decreased in year two (29%) and three (21%) of follow-up. MRI criteria were responsible for loss of NEDA status in 64% of cases and CIS patients were more likely to sustain NEDA status. Therapy with monoclonal antibodies appeared superior in sustaining NEDA status as compared to injectables or oral treatment options. DISCUSSION: In our real-world analysis, we confirm the potential of NEDA for the evaluation and surveillance of MS disease activity, progression and therapy efficacy. Despite highly efficient immunomodulatory treatment, NEDA-3 was only preserved in a minority of patients. Monoclonal antibodies may yield best NEDA rates. Further studies are warranted to evaluate the value of the NEDA concept in real-world settings beyond standardized clinical studies.
EVALuna2:36277

Noise and dose reduction in CT brain perfusion acquisition by projecting time attenuation curves onto lower dimensional spaces - Kulvait, Vojtech; Hölter, Philip; Punzet, Daniel; Dörfler, Arnd; Rose, Georg (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2022)
CT perfusion imaging (CTP) plays an important role in decision making for the treatment of acute ischemic stroke with large vessel occlusion. Since the CT perfusion scan time is approximately one minute, the patient is exposed to a non-negligible dose of ionizing radiation. However, further dose reduction increases the level of noise in the data and the resulting perfusion maps. We present a method for reducing noise in perfusion data based on dimension reduction of time attenuation curves. For dimension reduction, we use either the fit of the first five terms of the trigonometric polynomial or the first five terms of the SVD decomposition of the time attenuation profiles. CTP data from four patients with large vessel occlusion and three control subjects were studied. To compare the noise level in the perfusion maps, we use the wavelet estimation of the noise standard deviation implemented in the scikit-image package. We show that both methods significantly reduce noise in the data while preserving important information about the perfusion deficits. These methods can be used to further reduce the dose in CT perfusion protocols or in perfusion studies using C-arm CT, which are burdened by high noise levels.
CRIS-Team Scopus Importer:2022-06-10
Keywords: CT perfusion imaging; dimension reduction; dose reduction; noise reduction; SVD decomposition

Noninvasive Collateral Flow Velocity Imaging in Acute Ischemic Stroke: Intraindividual Comparison of 4D-CT Angiography with Digital Subtraction Angiography - Mühlen, Iris; Kloska, Stephan P.; Gölitz, Philipp; Breuer, Lorenz; Ditt, Hendrik; Dörfler, Arnd; Hölter, Philip (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose The collateral status can be defined not only by its morphological extent but also by the velocity of collateral filling characterized by the relative filling time delay (rFTD). The aim of our study was to compare different methods of noninvasive visualization of rFTD derived from 4D-CT angiography (4D-CTA) with digital substraction angiography (DSA) and to investigate the correlation between functional and morphological collateral status on timing-invariant CTA.
CRIS-Team WoS Importer:2019-09-20

Nonparametric D-R1-R2 distribution MRI of the living human brain - Laun, Frederik Bernd; Martin, Jan; Reymbaut, Alexis; Schmidt, Manuel; Dörfler, Arnd; Topgaard, Daniel; Uder, Michael (2021)
Diffusion-relaxation correlation NMR can simultaneously characterize both the microstructure and the local chemical composition of complex samples that contain multiple populations of water. Recent developments on tensor-valued diffusion encoding and Monte Carlo inversion algorithms have made it possible to transfer diffusion-relaxation correlation NMR from small-bore scanners to clinical MRI systems. Initial studies on clinical MRI systems employed 5D D-R1 and D-R2 correlation to characterize healthy brain in vivo. However, these methods are subject to an inherent bias that originates from not including R2 or R1 in the analysis, respectively. This drawback can be remedied by extending the concept to 6D D-R1-R2 correlation. In this work, we present a sparse acquisition protocol that records all data necessary for in vivo 6D D-R1-R2 correlation MRI across 633 individual measurements within 25 min—a time frame comparable to previous lower-dimensional acquisition protocols. The data were processed with a Monte Carlo inversion algorithm to obtain nonparametric 6D D-R1-R2 distributions. We validated the reproducibility of the method in repeated measurements of healthy volunteers. For a post-therapy glioblastoma case featuring cysts, edema, and partially necrotic remains of tumor, we present representative single-voxel 6D distributions, parameter maps, and artificial contrasts over a wide range of diffusion-, R1-, and R2-weightings based on the rich information contained in the D-R1-R2 distributions.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Correlation; Diffusion; Microstructure; Relaxation; Signal inversion

No sex differences in long-term functional outcome after intracerebral hemorrhage - De Ridder, Inger; Kuramatsu, Joji; Gerner, Stefan; Madzar, Dominik; Lücking, Hannes; Kloska, Stephan; Dippel, Diederik; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2017)
Background There is conflicting evidence about the influence of sex on outcome after spontaneous intracerebral hemorrhage (sICH) and the majority of the research focused on mortality and short-term outcome only. We investigated sex differences in long-term functional outcome after sICH. Methods We used data from a prospective hospital registry and included all consecutive patients with ICH admitted to our institution between January 2006 and July 2014. Functional outcome was assessed by modified Rankin Scale evaluated 3 and 12 months after ICH. We explored the influence of sex on long-term functional outcome using multivariable regression models and additionally by means of propensity score matching. Results We analyzed 823 patients, of whom 380 (46%) women. Women were on average three years older (p < 0.001), men had more often deep hematomas (p = 0.01). Unadjusted mortality rates were significantly increased in women at three months (42% vs. 35%; odds ratio (OR): 1.35; 95% confidence interval (CI): 1.02-1.80). After adjusting for baseline prognostic factors there were no differences between men and women in short- and long-term mortality (OR = 1.01; 95% CI = 0.66-1.54 and OR = 1.04; 95%CI = 0.69-1.57, respectively) and short- and long-term unfavorable outcome (OR = 1.02; 95%CI = 0.67-1.55 and OR = 0.96; 95% CI = 0.62-1.48, respectively). Conclusion We found no sex-related differences in long-term functional outcome in patients with sICH. The apparently worse functional outcome in women can be explained by differences in age.
EVALuna2:22516

Novel Biallelic CTSD Gene Variants Cause Late-Onset Ataxia and Retinitis Pigmentosa - Regensburger, Martin; Minakaki, Georgia; Kettwig, Matthias; Huchzermeyer, Cord; Eisenhut, Felix; Haack, Tobias B.; Kohl, Zacharias; Winkler, Jürgen (Movement Disorders, 2020)
CRIS-Team Scopus Importer:2020-05-29

Novel Homozygous FA2H Variant Causing the Full Spectrum of Fatty Acid Hydroxylase-Associated Neurodegeneration (SPG35) - German, Alexander; Jukic, Jelena; Laner, Andreas; Arnold, Philipp; Socher, Eileen; Mennecke, Angelika; Schmidt, Manuel; Winkler, Jürgen; Abicht, Angela; Regensburger, Martin (Genes, 2023)
Fatty acid hydroxylase-associated neurodegeneration (FAHN/SPG35) is caused by pathogenic variants in FA2H and has been linked to a continuum of specific motor and non-motor neurological symptoms, leading to progressive disability. As an ultra-rare disease, its mutational spectrum has not been fully elucidated. Here, we present the prototypical workup of a novel FA2H variant, including clinical and in silico validation. An 18-year-old male patient presented with a history of childhood-onset progressive cognitive impairment, as well as progressive gait disturbance and lower extremity muscle cramps from the age of 15. Additional symptoms included exotropia, dystonia, and limb ataxia. Trio exome sequencing revealed a novel homozygous c.75C>G (p.Cys25Trp) missense variant in the FA2H gene, which was located in the cytochrome b5 heme-binding domain. Evolutionary conservation, prediction models, and structural protein modeling indicated a pathogenic loss of function. Brain imaging showed characteristic features, thus fulfilling the complete multisystem neurodegenerative phenotype of FAHN/SPG35. In summary, we here present a novel FA2H variant and provide prototypical clinical findings and structural analyses underpinning its pathogenicity.<br
Keywords: hereditary spastic paraplegia; SPG35; FA2H; FAHN; genetic variant modeling

On Admission Lymphopenia in ICH Patients Is Associated with Increased Mortality and Poor Functional Outcome - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Lücking, Hannes; Kloska, Stephan; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22586

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

On PTV definition for glioblastoma based on fiber tracking of diffusion tensor imaging data - Witulla, Barbara; Goerig, Nicole; Putz, Florian; Frey, Benjamin; Engelhorn, Tobias; Dörfler, Arnd; Uder, Michael; Fietkau, Rainer; Bert, Christoph; Laun, Frederik Bernd (PLoS ONE, 2020)
Radiotherapy (RT) is commonly applied for the treatment of glioblastoma multiforme (GBM). Following the planning target volume (PTV) definition procedure standardized in guidelines, a 20% risk of missing non-local recurrences is present. Purpose of this study was to evaluate whether diffusion tensor imaging (DTI)-based fiber tracking may be beneficial for PTV definition taking into account the prediction of distant recurrences. 56 GBM patients were examined with magnetic resonance imaging (MRI) including DTI performed before RT after resection of the primary tumor. Follow-up MRIs were acquired in three month intervals. For the seven patients with a distant recurrence, fiber tracking was performed with three algorithms and it was evaluated whether connections existed from the primary tumor region to the distant recurrence. It depended strongly on the used tracking algorithm and the used tracking parameters whether a connection was observed. Most of the connections were weak and thus not usable for PTV definition. Only in one of the seven patients with a recurring tumor, a clear connection was present. It seems unlikely that DTI-based fiber tracking can be beneficial for predicting distant recurrences in the planning of PTVs for glioblastoma multiforme.
CRIS-Team Scopus Importer:2020-01-21

Optimized angiographic computed tomography with intravenous contrast injection: An alternative to conventional angiography in the follow-up of clipped aneurysms? Clinical article - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver; Saake, Marc; Lücking, Hannes; Rösch, Julie; Knossalla, Frauke; Dörfler, Arnd (Journal of Neurosurgery, 2012)
Object. The purpose of this study was to evaluate the diagnostic accuracy of an optimized angiographic CT (ACT) program with intravenous contrast agent injection (ivACT) in the assessment of potential aneurysm remnants after neurosurgical clipping compared with conventional digital subtraction angiography (DSA). Methods. The authors report on 14 patients with 19 surgically clipped cerebral aneurysms who were scheduled to undergo angiographic follow-up. For each patient, the authors performed ivACT with dual rotational acquisition and conventional angiography including a 3D rotational run. The ivACT and 3D DSA data were reconstructed with different imaging modes, including a newly implemented subtraction mode with motion correction. Thereafter, the data sets were merged by the dual-volume technique, and freely rotatable 3D images were obtained for further analysis. Observed aneurysm remnants were electronically measured and classified for each modality by 2 experienced neuroradiologists. Results. Digital subtraction angiography and ivACT both provided high-quality images without motion artifacts. Artifact disturbances from the aneurysm clips led to a compromised, but still sufficient, image quality in 1 case. The ivACT assessed all aneurysm remnants as true-positive up to a minimal size of 2.6 x 2.4 mm in accordance with the DSA findings. There was a tendency for ivACT to overestimate the size of the aneurysm remnants. All cases without aneurysm remnants on DSA were scored correctly as true-negative by ivACT. Conclusions. By using an optimized image acquisition protocol as well as enhanced postprocessing algorithms, the noninvasive ivACT seems to achieve results comparable to those of conventional angiography in the follow-up of clipped cerebral aneurysms. The authors have shown that ivACT can provide reliable diagnostic information about potential aneurysm remnants after neurosurgical clipping with high sensitivity and specificity, sufficient for clinical decision making, at least for aneurysms in the anterior circulation located distal to the internal carotid artery. These preliminary results may be a promising step to replace conventional angiography by a noninvasive imaging technique in selected cases after aneurysm clipping.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aneurysm clipping; Angiographic computed tomography; Follow-up imaging; Noninvasive imaging; Vascular disorders

Optimized angiographic CT using intravenous contrast injection: a noninvasive imaging option for the follow-up of coiled aneurysms? - Gölitz, Philipp; Struffert, Tobias; Kaschka, Iris; Roessler, Karl; Knossalla, F.; Dörfler, Arnd (American Journal of Neuroradiology, 2014)
Because recanalization of coiled cerebral aneurysms is reported to occur, follow-up imaging is mandatory, ideally noninvasively. Our study aimed to evaluate the accuracy of an optimized angiographic CT by using intravenous contrast material injection in the assessment of coiled cerebral aneurysms, compared with MR angiography and digital subtraction angiography, the criterion standard.We included 69 patients with 76 coiled cerebral aneurysms. In each patient, we performed an angiographic CT with intravenous contrast material injection with a dual rotational acquisition, a time-of-flight MR angiography, and a DSA. The angiographic CT with intravenous contrast material injection data was postprocessed by using newly implemented reconstructions modes and a dual-volume technique. An aneurysm occlusion rate was assessed in angiographic CT with intravenous contrast material injection and MRA; remnants were measured and correlated with DSA, respectively.Twenty-eight remnants were revealed by DSA with a mean size of 3.1 × 3.1 mm. Angiographic CT with intravenous contrast material injection demonstrated a sensitivity of 93% and a specificity of 96% in remnant detection. MRA showed almost identical accuracy (sensitivity of 93%, specificity of 100%). Assessment of remnant size by angiographic CT with intravenous contrast material injection and by MRA revealed a high significant correlation with DSA, respectively (P < .001).Optimized angiographic CT with intravenous contrast material injection and MRA demonstrated accuracy comparable with that of DSA in the follow-up of coiled aneurysms, respectively. The assessment of remnant size showed a high correlation with DSA for both techniques. Due to the lack of radiation exposure, MRA seems to be the preferred technique. However, angiographic CT with intravenous contrast material injection can be considered a reliable, noninvasive alternative in patients with MR imaging contraindications or in cases of compromising artifacts due to metal implants (ie, clips).
EVALuna2:22327

Optimized Flat-Detector CT in Stroke Imaging: Ready for First-Line Use? - Eckert, Matthias; Gölitz, Philipp; Lücking, Hannes; Struffert, Tobias; Knossalla, Frauke; Dörfler, Arnd (Cerebrovascular Diseases, 2017)
Using flat-detector CT (FD-CT) for stroke imaging has the advantage that both diagnostic imaging and endovascular therapy can be performed directly within the Angio Suite without any patient transfer and time delay. Thus, stroke management could be speeded up significantly, and patient outcome might be improved. But as precondition for using FD-CT as primary imaging modality, a reliable exclusion of intracranial hemorrhage (ICH) has to be possible. This study aimed to investigate whether optimized native FD-CT, using a newly implemented reconstruction algorithm, may reliably detect ICH in stroke patients. Additionally, the potential to identify ischemic changes was evaluated.Cranial FD-CT scans were obtained in 102 patients presenting with acute ischemic stroke (n = 32), ICH (n = 45) or transient ischemic attack (n = 25). All scans were reconstructed with a newly implemented half-scan cone-beam algorithm. Two experienced neuroradiologists, unaware of clinical findings, evaluated independently the FD-CTs screening for hemorrhage or ischemic signs. The findings were correlated to CT, and rater and inter-rater agreement was assessed.FD-CT demonstrated high sensitivity (95-100%) and specificity (100%) in detecting intracerebral and intraventricular hemorrhage (IVH). Overall, interobserver agreement (? = 0.92) was almost perfect and rater agreement to CT highly significant (r = 0.81). One infratentorial ICH and 10 or 11 of 22 subarachnoid hemorrhages (SAHs) were missed of whom 7 were perimesencephalic. The sensitivity for detecting acute ischemic signs was poor in blinded readings (0 or 25%, respectively).Optimized FD-CT, using a newly implemented reconstruction algorithm, turned out as a reliable tool for detecting supratentorial ICH and IVH. However, detection of infratentorial ICH and perimesencephalic SAH is limited. The potential of FD-CT in detecting ischemic changes is poor in blinded readings. Thus, plain FD-CT seems insufficient as a standalone modality in acute stroke, but within a multimodal imaging approach primarily using the FD technology, native FD-CT seems capable to exclude reliably supratentorial hemorrhage. Currently, FD-CT imaging seems not yet ready for wide adoption, replacing regular CT, and should be reserved for selected patients. Furthermore, prospective evaluations are necessary to validate this approach in the clinical setting.
EVALuna2:22513

Optimizing contrast-enhanced magnetic resonance imaging characterization of brain metastases: Relevance to stereotactic radiosurgery - Anzalone, Nicoletta; Essig, Marco; Lee, Seung-Koo; Dörfler, Arnd; Ganslandt, Oliver; Combs, Stephanie E.; Picozzi, Piero (Neurosurgery, 2013)
Intracranial metastases are the most common form of intra-axial brain tumor. Management approaches to brain metastases include surgical resection, whole-brain radiotherapy, and stereotactic radiosurgery (SRS). The management approach that is selected is based typically on algorithms that incorporate the number, size, and location of lesions. SRS is the treatment of choice when metastases detected on imaging are few (maximum, 3-5) and/or of small size (≤30 mm) and offers the advantages of noninvasiveness and the ability to treat inaccessible lesions compared with surgical resection. Contrast-enhanced magnetic resonance imaging (MRI) is the standard imaging technique for determining the number, size, and location of metastatic lesions. In SRS, the capability of MRI to delineate lesion borders precisely in 3 dimensions helps reduce recurrence rates and minimize radiation necrosis in surrounding tissue. Optimization of the MRI protocol, including selection of the appropriate gadolinium-based contrast agent (GBCA), is paramount for accurate lesion imaging. GBCAs differ in their safety, tolerability, and efficacy because of their diverse physicochemical properties. Gadobutrol and gadobenate dimeglumine are high-relaxivity GBCAs that demonstrate superior efficacy for imaging metastatic lesions compared with other GBCAs, whereas gadobutrol additionally provides macrocyclic stability. This article reviews recent comparative trials of GBCAs and discusses their relevance for optimizing MRI protocols in the management of brain metastases, with particular relevance to SRS. ABBREVIATIONS:: CNR, contrast-to-noise ratioCNS, central nervous systemGBCA, gadolinium-based contrast agentNSF, nephrogenic systemic fibrosisSRS, stereotactic radiosurgeryWBRT, whole-brain radiotherapy. © 2013 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain metastases; Gadobutrol; Gadolinium-based contrast media; MRI; Stereotactic radiosurgery

Parametric color coding of digital subtraction angiography in the evaluation of carotid cavernous fistulas - Gölitz, Philipp; Struffert, Tobias; Lücking, Hannes; Roesch, J.; Knossalla, F.; Ganslandt, Oliver; Deuerling-Zheng, Y.; Dörfler, Arnd (Clinical Neuroradiology, 2013)
Purpose: Angiographic assessment of carotid cavernous fistulas (CCFs) can be complex. Our purpose was to examine whether the use of parametric color coding in the postprocessing of DSA series is advantageous in the evaluation of CCFs. Methods: We enrolled 16 patients with angiographically proven CCFs. Endovascular treatment was performed in 14 cases. For postprocessing of digital subtraction angiography (DSA) series, a newly implemented algorithm of parametric color coding was used, turning sequential images of two-dimensional (2D)-DSA series into a single color-coded image. Angiographic data of initial, interventional, and postinterventional 2D-DSA series were compared with color-coded images. Whether parametric color coding could facilitate evaluation of fistula architecture and provide a more precise estimation of fistula venous drainage patterns as well as whether flow analysis could reveal objective changes during and after treatment were investigated. Results: In 56 % of the cases, parametric color coding was observed to facilitate visualization of fistula angioarchitecture. Estimation of fistula drainage flow patterns was considered to be improved in 31 % of the cases. For assessment of hemodynamic changes during and after treatment, parametric color coding was assumed to be helpful in 21 % of the cases, especially because revealing flow changes that were not visible on 2D-DSA series were now visible. Conclusions: Parametric color coding is a fast application tool that might provide additional support in the angiographic evaluation of CCFs. Visualization of complex fistula architecture could be facilitated, and flow analysis might improve assessment of venous drainage patterns, thereby increasing overall diagnostic confidence. During and after treatment, hemodynamic changes that were not visible on 2D-DSA series could now be depicted. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cerebrovascular disease; Digital subtraction angiography; Endovascular treatment; Image postprocessing

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment

Parenchymatous hemorrhage is associated with unfavorable longterm outcome in patients with atraumatic subarachnoid hemorrhage - Gerner, Stefan; Kuramatsu, J.; Reichl, J.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Dörfler, Arnd; Struffert, Tobias; Schwab, Sibylle; Huttner, Hagen (2017)
EVALuna2:34024

Parkinson's disease or multiple system atrophy: potential separation by quantitative susceptibility mapping - Marxreiter, Franz; Lambrecht, Vera; Mennecke, Angelika; Hanspach, Jannis; Jukic, Jelena; Regensburger, Martin; Herrler, Jürgen; German, Alexander; Kassubek, Jan; Groen, Georg; Mueller, Hans-Peter; Laun, Frederik Bernd; et al. (Therapeutic Advances in Neurological Disorders, 2023)
Background:Due to the absence of robust biomarkers, and the low sensitivity and specificity of routine imaging techniques, the differential diagnosis between Parkinson's disease (PD) and multiple system atrophy (MSA) is challenging. High-field magnetic resonance imaging (MRI) opened up new possibilities regarding the analysis of pathological alterations associated with neurodegenerative processes. Recently, we have shown that quantitative susceptibility mapping (QSM) enables visualization and quantification of two major histopathologic hallmarks observed in MSA: reduced myelin density and iron accumulation in the basal ganglia of a transgenic murine model of MSA. It is therefore emerging as a promising imaging modality on the differential diagnosis of Parkinsonian syndromes. Objectives:To assess QSM on high-field MRI for the differential diagnosis of PD and MSA. Methods:We assessed 23 patients (nine PDs and 14 MSAs) and nine controls using QSM on 3T and 7T MRI scanners at two academic centers. Results:We observed increased susceptibility in MSA at 3T in prototypical subcortical and brainstem regions. Susceptibility measures of putamen, pallidum, and substantia nigra reached excellent diagnostic accuracy to separate both synucleinopathies. Increase toward 100% sensitivity and specificity was achieved using 7T MRI in a subset of patients. Magnetic susceptibility correlated with age in all groups, but not with disease duration in MSA. Sensitivity and specificity were particularly high for possible MSA, and reached 100% in the putamen. Conclusion:Putaminal susceptibility measures, in particular on ultra-high-field MRI, may distinguish MSA patients from both, PD and controls, allowing an early and sensitive diagnosis of MSA.
CRIS-Team WoS Importer:2023-03-17

PASSED: Brain atrophy in non-demented individuals in a long-term longitudinal study from two independent cohorts - Haas, Anna-Lena; Olm, Pauline; Utz, Janine; Siegmann, Eva-Maria; Spitzer, Philipp; Florvaag, Anna; Schmidt, Manuel; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Frontiers in Aging Neuroscience, 2023)
Introduction: Alzheimer’s disease (AD) is indicated by a decrease in amyloid beta 42 (Aβ42) level or the Aβ42/Aβ40 ratio, and by increased levels of Tau with phosphorylated threonine at position 181 (pTau181) in cerebrospinal fluid (CSF) years before the onset of clinical symptoms. However, once only pTau181 is increased, cognitive decline in individuals with subjective or mild cognitive impairment is slowed compared to individuals with AD. Instead of a decrease in Aβ42 levels, an increase in Aβ42 was observed in these individuals, leading to the proposal to refer to them as nondemented subjects with increased pTau-levels and Aβ surge with subtle cognitive deterioration (PASSED). In this study, we determined the longitudinal atrophy rates of AD, PASSED, and Biomarker-negative nondemented individuals of two independent cohorts to determine whether these groups can be distinguished by their longitudinal atrophy patterns or rates. Methods: Depending on their CSF-levels of pTau 181 (T), total Tau (tTau, N), Aβ42 or ratio of Aβ42/Aβ40 (A), 185 non-demented subjects from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and 62 non-demented subjects from Erlangen AD cohort were assigned to an ATN group (A–T–N–, A–T+N±, A+T–N±and A+T+N±) and underwent T1-weighted structural magnetic resonance imaging (sMRI). Longitudinal grey matter (GM) atrophy patterns were assessed with voxel-based morphometry (VBM) using the cat12 toolbox on spm12 (statistical parametric mapping) of MRI scans from individuals in the ADNI cohort with a mean follow-up of 2 and 5 years, respectively. The annualized atrophy rate for individuals in the Erlangen cohort was determined using region of interest analysis (ROI) in terms of a confirmatory analysis. Results: In the A–T+N± group, VBM did not identify any brain region that showed greater longitudinal atrophy than the A+T+N±, A+T+N± or biomarker negative control group. In contrast, marked longitudinal atrophy in the temporal lobe was evident in the A+T–N± group compared with A+T–N± and biomarker-negative subjects. The ROI in the angular gyrus identified by VBM analysis of the ADNI cohort did not discriminate better than the hippocampal volume and atrophy rate between AD and PASSED in the confirmatory analysis. Discussion: In this study, nondemented subjects with PASSED did not show a unique longitudinal atrophy pattern in comparison to nondemented subjects with AD. The nonsignificant atrophy rate compared with controls suggests that increased pTau181-levels without concomitant amyloidopathy did not indicate a neurodegenerative disorder.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Alzheimer disease/physiopathology*; amyloid beta-peptides/cerebrospinal fluid*; ATN classification; longitudinal studies; magnetic resonance imaging; medial temporal lobe; SNAP; tau proteins/cerebrospinal fluid*

Patient-individualized boundary conditions for CFD simulations using time-resolved 3D angiography - Bögel, Marco; Gehrisch, Sonja; Redel, Thomas; Rohkohl, Christopher; Dörfler, Arnd; Maier, Andreas; Kowarschik, Markus; Hölter, Philip (International Journal of Computer Assisted Radiology and Surgery, 2016)
Hemodynamic simulations are of increasing interest for the assessment of aneurysmal rupture risk and treatment planning. Achievement of accurate simulation results requires the usage of several patient-individual boundary conditions, such as a geometric model of the vasculature but also individualized inflow conditions.We propose the automatic estimation of various parameters for boundary conditions for computational fluid dynamics (CFD) based on a single 3D rotational angiography scan, also showing contrast agent inflow. First the data are reconstructed, and a patient-specific vessel model can be generated in the usual way. For this work, we optimize the inflow waveform based on two parameters, the mean velocity and pulsatility. We use statistical analysis of the measurable velocity distribution in the vessel segment to estimate the mean velocity. An iterative optimization scheme based on CFD and virtual angiography is utilized to estimate the inflow pulsatility. Furthermore, we present methods to automatically determine the heart rate and synchronize the inflow waveform to the patient's heart beat, based on time-intensity curves extracted from the rotational angiogram. This will result in a patient-individualized inflow velocity curve.The proposed methods were evaluated on two clinical datasets. Based on the vascular geometries, synthetic rotational angiography data was generated to allow a quantitative validation of our approach against ground truth data. We observed an average error of approximately [Formula: see text] for the mean velocity, [Formula: see text] for the pulsatility. The heart rate was estimated very precisely with an average error of about [Formula: see text], which corresponds to about 6 ms error for the duration of one cardiac cycle. Furthermore, a qualitative comparison of measured time-intensity curves from the real data and patient-specific simulated ones shows an excellent match.The presented methods have the potential to accurately estimate patient-specific boundary conditions from a single dedicated rotational scan.
EVALuna2:23010

Peak perihemorrhagic edema correlates with functional outcome in intracerebral hemorrhage - Volbers, Bastian; Giede-Jeppe, Antje; Gerner, Stefan; Sembill, Jochen; Kuramatsu, Joji; Lang, Stefan; Lücking, Hannes; Staykov, Dimitre; Huttner, Hagen (Neurology, 2018)
Objective To evaluate the association of perihemorrhagic edema (PHE) evolution and peak edema extent with day 90 functional outcome in patients with intracerebral hemorrhage (ICH) and identify pathophysiologic factors influencing edema evolution. Methods This retrospective cohort study included patients with spontaneous supratentorial ICH between January 2006 and January 2014. ICH and PHE volumes were studied using a validated semiautomatic volumetric algorithm. Multivariable logistic regression and propensity score matching (PSM) accounting for age, ICH volume, and location were used for assessing measures associated with functional outcome and PHE evolution. Clinical outcome on day 90 was assessed using the modified Rankin Scale (0-3 = favorable, 4-6 = poor). Results A total of 292 patients were included. Median age was 70 years (interquartile range [IQR] 62-78), median ICH volume on admission 17.7 mL (IQR 7.9-40.2). Besides established factors for functional outcome, i.e., ICH volume and location, age, intraventricular hemorrhage, and NIH Stroke Scale score on admission, multivariable logistic regression revealed peak PHE volume (odds ratio [OR] 0.984 [95% confidence interval (CI) 0.973-0.994]) as an independent predictor of day 90 outcome. Peak PHE volume was independently associated with initial PHE increase up to day 3 (OR 1.060 [95% CI 1.018-1.103]) and neutrophil to lymphocyte ratio on day 6 (OR 1.236 [95% CI 1.034-1.477; PSM cohort, n = 124]). Initial PHE increase (PSM cohort, n = 224) was independently related to hematoma expansion (OR 3.647 [95% CI 1.533-8.679]) and fever burden on days 2-3 (OR 1.456 [95% CI 1.103-1.920]). Conclusion Our findings suggest that peak PHE volume represents an independent predictor of functional outcome after ICH. Inflammatory processes and hematoma expansion seem to be involved in PHE evolution and may represent important treatment targets.
EVALuna2:34919

Peak Troponin I Levels Are Associated with Functional Outcome in Intracerebral Hemorrhage - Gerner, Stefan; Auerbeck, Katrin; Sprügel, Maximilian; Sembill, Jochen; Madzar, Dominik; Gölitz, Philipp; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2018)
Background: Troponin I is a widely used and reliable marker of myocardial damage and its levels are routinely measured in acute stroke care. So far, the influence of troponin I elevations during hospital stay on functional outcome in patients with atraumatic intracerebral hemorrhage (ICH) is unknown. Methods: Observational single-center study including conservatively treated ICH patients over a 9-year period. Patients were categorized according to peak troponin I level during hospital stay (<= 0.040, 0.041-0.500, > 0.500 ng/mL) and compared regarding baseline and hematoma characteristics. Multivariable analyses were performed to investigate independent associations of troponin levels during hospital stay with functional outcome -assessed using the modified Rankin Scale (mRS; favorable 0-3/unfavorable 4-6) -and mortality after 3 and 12 months. To account for possible con-founding propensity score (PS)-matching (1: 1; caliper 0.1) was performed accounting for imbalances in baseline characteristics to investigate the impact of troponin I values on outcome. Results: Troponin elevations (> 0.040 ng/mL) during hospital stay were observed in 308 out of 745 (41.3%) patients and associated with poorer status on admission (Glasgow Coma Scale/National Institute of Health Stroke Scale). Multivariable analysis revealed troponin I levels during hospital stay to be independently associated with unfavorable outcome after 12 months (risk ratio [95% CI]: 1.030 [1.009-1.051] per increment of 1.0 ng/mL; p = 0.005), but not with mortality. After PS-matching, patients with troponin I elevation (= 0.040 ng/mL) versus those without had a significant higher rate of -unfavorable outcome after 3 and 12 months (mRS 4-6 at 3 months: < 0.04 ng/mL: 159/265 [60.0%] versus = 0.04 ng/mL: 199/266 [74.8%]; p < 0.001; at 12 months: < 0.04 ng/mL: 141/248 [56.9%] versus <= 0.04 ng/mL: 179/251 [71.3%]; p = 0.001). Conclusions: Troponin I elevations during hospital stay occur frequently in ICH patients and are independently associated with functional outcome after 3 and 12 months but not with mortality. (c) 2018 S. Karger AG, Basel
EVALuna2:34936

Pearls & Oy-sters: Moyamoya Vasculopathy and Its Association With Congenital Heart Disease - Osterloh, Justus; Heim, Christian; Siedler, Gabriela; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Neurology, 2021)
CRIS-Team Scopus Importer:2021-06-25

Pearls & Oy-sters: SARS-CoV-2 Infection of the CNS in a Patient With Meningeosis Carcinomatosa - Steininger, Philipp; Seifert, Frank; Balk, Stefanie; Kuramatsu, Joji; Kremer, Andreas; Coras, Roland; Engelhorn, Tobias; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Enßer, Armin (Neurology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Pedicle screw instrumentation of the cervicothoracic junction in the sitting position using ct-guided navigation: Application and technical aspects - Hore, Nirjhar; Lücking, Hannes; Schmitt, Hubert; Buchfelder, Michael; Brandner, Sebastian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background We evaluate the feasibility and potential advantages of spinal CT navigation in the placement of pedicle screws at the cervicothoracic junction in the sitting position to counteract the anatomy-related limitations of 2D fluoroscopy. Methods We retrospectively analyze the data from 15 patients who underwent CT-based navigation-guided placement of a total of 36 pedicle screws at the cervicothoracic junction in the sitting position. Results CT-based spinal navigation is a useful method in increasing accuracy of pedicle screw instrumentation in the sitting position, successfully counteracting the anatomy-related limitations of 2D fluoroscopy at the cervicothoracic junction. Conclusion CT-based navigation-guided placement of pedicle screws at the cervicothoracic junction in the sitting position proved to be an accurate, safe, and user-friendly method.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cervical spine; Sitting position; Spinal navigation

Perihemorrhagic edema revisiting hematoma volume, location and surface - Sprügel, Maximilian; Kuramatsu, J. B.; Volbers, Bastian; Koelbl, K.; Gerner, Stefan; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Perihemorrhagic edema: Revisiting hematoma volume, location, and surface - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Gerner, Stefan; Sembill, Jochen; Madžar, Dominik; Bobinger, Tobias; Kölbl, Kathrin; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (Neurology, 2019)
OBJECTIVE: To determine the influence of intracerebral hemorrhage (ICH) location and volume and hematoma surface on perihemorrhagic edema evolution. METHODS: Patients with ICH of the prospective Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage (UKER-ICH) cohort study (NCT03183167) between 2010 and 2013 were analyzed. Hematoma and edema volume during hospital stay were volumetrically assessed, and time course of edema evolution and peak edema correlated to hematoma volume, location, and surface to verify the strength of the parameters on edema evolution. RESULTS: Overall, 300 patients with supratentorial ICH were analyzed. Peak edema showed a high correlation with hematoma surface (R2 = 0.864, p < 0.001) rather than with hematoma volumes, regardless of hematoma location. Smaller hematomas with a higher ratio of hematoma surface to volume showed exponentially higher relative edema (R2 = 0.755, p < 0.001). Multivariable logistic regression analysis revealed a cutoff ICH volume of 30 mL, beyond which an increase of total mass lesion volume (combined volume of hematoma and edema) was not associated with worse functional outcome. Specifically, peak edema was associated with worse functional outcome in ICH <30 mL (odds ratio [OR] 2.63, 95% confidence interval [CI] 1.68-4.12, p < 0.001), contrary to ICH ≥30 mL (OR 1.20, 95% CI 0.88-1.63, p = 0.247). There were no significant differences between patients with lobar and those with deep ICH after adjustment for hematoma volumes. CONCLUSIONS: Peak perihemorrhagic edema, although influencing mortality, is not associated with worse functional outcomes in ICH volumes >30 mL. Although hematoma volume correlates with peak edema extent, hematoma surface is the major parameter for edema evolution. The effect of edema on functional outcome is therefore more pronounced in smaller and irregularly shaped hematomas, and these patients may particularly benefit from edema-modifying therapies.
CRIS-Team Scopus Importer:2019-09-27

Physics-Informed Conditional Autoencoder Approach for Robust Metabolic CEST MRI at 7T - Rajput, Junaid R.; Möhle, Tim A.; Fabian, Moritz; Mennecke, Angelika; Sembill, Jochen; Kuramatsu, Joji; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Zaiß, Moritz (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2023)
Chemical exchange saturation transfer (CEST) is an MRI method that provides insights on the metabolic level. Several metabolite effects appear in the CEST spectrum. These effects are isolated by Lorentzian curve fitting. The separation of CEST effects suffers from the inhomogeneity of the saturation field B1. This leads to inhomogeneities in the associated metabolic maps. Current B1 correction methods require at least two sets of CEST-spectra. This at least doubles the acquisition time. In this study, we investigated the use of an unsupervised physics-informed conditional autoencoder (PICAE) to efficiently correct B1 inhomogeneity and isolate metabolic maps while using a single CEST scan. The proposed approach integrates conventional Lorentzian model into the conditional autoencoder and performs voxel-wise B1 correction and Lorentzian line fitting. The method provides clear interpretation of each step and is inherently generative. Thus, CEST-spectra and fitted metabolic maps can be created at arbitrary B1 levels. This is important because the B1 dispersion contains information about the exchange rates and concentration of metabolite protons, paving the way for their quantification. The isolated maps for tumor data showed a robust B1 correction and more than 25% increase in structural similarity index (SSIM) with gadolinium reference image compared to the standard interpolation-based method and subsequent Lorentzian curve fitting. This efficient correction method directly results in at least 50% reduction in scan time.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Acquisition time; Bound loss; CEST; Interpretability; Lorentzian fit; Physics-informed autoencoder

Physiological effects of cigarette smoking in the limbic system revealed by 3 tesla magnetic resonance spectroscopy - Mennecke, Angelika; Gossler, Andrea; Hammen, Thilo; Dörfler, Arnd; Stadlbauer, Andreas; Roesch, Julie; Kornhuber, Johannes; Bleich, Stefan; Dölken, Marc; Thürauf, Norbert (Journal of Neural Transmission, 2014)
Several studies and recent models of effects of nicotine, the main addictive and psychoactive component in tobacco, point to action of the drug on the limbic system during maintenance of addiction, either direct or indirect via projections from the ventral tegmental area. The objective of this study was to demonstrate physiological effects of cigarette smoking on the hippocampus and the grey matter of the dorsal anterior cingulate cortex in the human brain with regard to addiction and withdrawal. This aim was achieved by group comparisons of results of magnetic resonance spectroscopy between non-smokers, smokers and smokers during withdrawal. 12 smokers and 12 non-smokers were measured with single voxel proton magnetic resonance spectroscopy for total N-acetyl aspartate, glutamate and glutamine, choline-containing compounds, myo-inositol and total creatine in the right and the left hippocampus and in the right and the left dorsal anterior cingulate cortex. Smokers were examined twice, first during regular cigarette smoking and second on the third day of nicotine withdrawal. The ratios to total creatine were used for better reliability. In our study, Glx/tCr was significantly increased and tCho/tCr was significantly decreased in the left cingulate cortex in smokers compared to non-smokers (p = 0.01, both). Six out of seven smokers showed normalization of the Glx/tCr in the left cingulate cortex during withdrawal. Although these results are preliminary due to the small sample size, our results confirm the assumption that cigarette smoking interferes directly or indirectly with the glutamate circuit in the dorsal anterior cingulate cortex.
EVALuna2:22826

Physiological MRI Biomarkers in the Differentiation Between Glioblastomas and Solitary Brain Metastases - Heynold, Elisabeth; Zimmermann, Max; Hore, Nirjhar; Buchfelder, Michael; Dörfler, Arnd; Stadlbauer, Andreas; Kremenevski, Natalia (Molecular Imaging and Biology, 2021)
Purpose: Glioblastomas (GB) and solitary brain metastases (BM) are the most common brain tumors in adults. GB and BM may appear similar in conventional magnetic resonance imaging (cMRI). Their management strategies, however, are quite different with significant consequences on clinical outcome. The aim of this study was to evaluate the usefulness of a previously presented physiological MRI approach scoping to obtain quantitative information about microvascular architecture and perfusion, neovascularization activity, and oxygen metabolism to differentiate GB from BM. Procedures: Thirty-three consecutive patients with newly diagnosed, untreated, and histopathologically confirmed GB or BM were preoperatively examined with our physiological MRI approach as part of the cMRI protocol. Results: Physiological MRI biomarker maps revealed several significant differences in the pathophysiology of GB and BM: Central necrosis was more hypoxic in GB than in BM (30 %; P = 0.036), which was associated with higher neovascularization activity (65 %; P = 0.043) and metabolic rate of oxygen (48 %; P = 0.004) in the adjacent contrast-enhancing viable tumor parts of GB. In peritumoral edema, GB infiltration caused neovascularization activity (93 %; P = 0.018) and higher microvascular perfusion (30 %; P = 0.022) associated with higher tissue oxygen tension (33 %; P = 0.020) and lower oxygen extraction from vasculature (32 %; P = 0.040). Conclusion: Our physiological MRI approach, which requires only 7 min of extra data acquisition time, might be helpful to noninvasively distinguish GB and BM based on pathophysiological differences. However, further studies including more patients are required.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Angiogenesis; Brain metastasis; Glioblastoma; Hypoxia; Physiological MRI

Physiological MRI of microvascular architecture, neovascularization activity, and oxygen metabolism facilitate early recurrence detection in patients with IDH-mutant WHO grade 3 glioma - Stadlbauer, Andreas; Heinz, Gertraud; Oberndorfer, Stefan; Zimmermann, Max; Kinfe, Thomas Mehari; Buchfelder, Michael; Dörfler, Arnd; Kremenevski, Natalia; Marhold, Franz (Neuroradiology, 2021)
Purpose: This study aimed to determine the diagnostic performance of physiological MRI biomarkers including microvascular perfusion and architecture, neovascularization activity, tissue oxygen metabolism, and tension for recurrence detection of IDH-mutant WHO grade 3 glioma. Methods: Sixty patients with IDH-mutant WHO grade 3 glioma who received overall 288 follow-up MRI examinations at 3 Tesla after standard treatment were retrospectively evaluated. A conventional MRI protocol was extended with a physiological MRI approach including vascular architecture mapping and quantitative blood-oxygen-level-dependent imaging which required 7 min extra data acquisition time. Custom-made MATLAB software was used for the calculation of MRI biomarker maps of microvascular perfusion and architecture, neovascularization activity, tissue oxygen metabolism, and tension. Statistical procedures included receiver operating characteristic analysis. Results: Overall, 34 patients showed recurrence of the WHO grade 3 glioma; of these, in 15 patients, recurrence was detected one follow-up examination (averaged 160 days) earlier by physiological MRI data than by conventional MRI. During this time period, the tumor volume increased significantly (P = 0.001) on average 7.4-fold from 1.5 to 11.1 cm3. Quantitative analysis of MRI biomarkers demonstrated microvascular but no macrovascular hyperperfusion in early recurrence. Neovascularization activity (AUC = 0.833), microvascular perfusion (0.682), and oxygen metabolism (0.661) showed higher diagnostic performance for early recurrence detection of WHO grade 3 glioma compared to conventional MRI including cerebral blood volume (0.649). Conclusion: This study demonstrated that the targeted assessment of microvascular features and tissue oxygen tension as an early sign of neovascularization activity provided valuable information for recurrence diagnostic of WHO grade 3 glioma.
CRIS-Team Scopus Importer:2021-06-23
Keywords: Glioma; Humans; Magnetic resonance imaging; Neoplasm recurrence; Neovascularization; Oxygen metabolism; Treatment failure

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2019)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
CRIS-Team Scopus Importer:2020-02-21
Keywords: angiogenesis; Glioblastoma; hypoxia; recurrence; treatment failure; tumor microenvironment

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2020)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
EVALuna2:212798

Potential of Sodium MRI as a Biomarker for Neurodegeneration and Neuroinflammation in Multiple Sclerosis - Huhn, Konstantin; Engelhorn, Tobias; Linker, Ralf A.; Nagel, Armin Michael (Frontiers in Neurology, 2019)
In multiple sclerosis (MS), experimental and ex vivo studies indicate that pathologic intra-and extracellular sodium accumulation may play a pivotal role in inflammatory as well as neurodegenerative processes. Yet, in vivo assessment of sodium in the microenvironment is hard to achieve. Here, sodium magnetic resonance imaging ((NaMRI)-Na-23) with its non-invasive properties offers a unique opportunity to further elucidate the effects of sodium disequilibrium in MS pathology in vivo in addition to regular proton based MRI. However, unfavorable physical properties and low in vivo concentrations of sodium ions resulting in low signal-to-noise-ratio (SNR) as well as low spatial resolution resulting in partial volume effects limited the application of (NaMRI)-Na-23. With the recent advent of high-field MRI scanners and more sophisticated sodium MRI acquisition techniques enabling better resolution and higher SNR, (NaMRI)-Na-23 revived. These studies revealed pathologic total sodium concentrations in MS brains now even allowing for the (partial) differentiation of intra-and extracellular sodium accumulation. Within this review we (1) demonstrate the physical basis and imaging techniques of (NaMRI)-Na-23 and (2) analyze the present and future clinical application of (NaMRI)-Na-23 focusing on the field of MS thus highlighting its potential as biomarker for neuroinflammation and -degeneration.
CRIS-Team WoS Importer:2019-02-22

Precision Learning: Reconstruction Filter Kernel Discretization - Syben-Leisner, Christopher; Stimpel, Bernhard; Breininger, Katharina; Würfl, Tobias; Fahrig, Rebecca; Dörfler, Arnd; Maier, Andreas (Proceedings of the 5th International Conference on Image Formation in X-ray Computed Tomography, 2018)
UnivIS-Import:2018-09-11:Pub.2018.tech.IMMD.IMMD5.precis_0

Predicting Glioblastoma Response to Bevacizumab Through MRI Biomarkers of the Tumor Microenvironment - Stadlbauer, Andreas; Roessler, Karl; Zimmermann, Max; Buchfelder, Michael; Kleindienst, Andrea; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Molecular Imaging and Biology, 2019)
Purpose: Glioblastoma (GB) is one of the most vascularized of all solid tumors and, therefore, represents an attractive target for antiangiogenic therapies. Many lesions, however, quickly develop escape mechanisms associated with changes in the tumor microenvironment (TME) resulting in rapid treatment failure. To prevent patients from adverse effects of ineffective therapy, there is a strong need to better predict and monitor antiangiogenic treatment response. Procedures: We utilized a novel physiological magnetic resonance imaging (MRI) method combining the visualization of oxygen metabolism and neovascularization for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and aerobic glycolysis. This approach, termed TME mapping, was used to monitor changes in tumor biology and pathophysiology within the TME in response to bevacizumab treatment in 18 patients with recurrent GB. Results: We detected dramatic changes in the TME by rearrangement of its compartments after the onset of bevacizumab treatment. All patients showed a decrease in active tumor volume and neovascularization as well as an increase in hypoxia and necrosis in the first follow-up after 3 months. We found that recurrent GB with a high percentage of neovascularization and active tumor before bevacizumab onset showed a poor or no treatment response. Conclusions: TME mapping might be useful to develop strategies for patient stratification and response prediction before bevacizumab onset.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Angiogenesis; Antiangiogenic therapy; Bevacizumab; Glioblastoma; Hypoxia; Recurrence; Treatment failure; Treatment monitoring; Tumor microenvironment

Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery

Prediction of Response to Certolizumab-Pegol in Rheumatoid Arthritis By Functional MRI of the Brain - an Interim Analysis of an Ongoing Investigator Initiated Phase III Trial - Schenker, Hannah; Heß, Andreas; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Kleyer, Arnd; Reiser, Michaela; Hueber, Axel; Englbrecht, Matthias; Feist, Eugen; Voll, Reinhard; Bannert, Bettina; et al. (2017)
EVALuna2:33139

Prediction of response to Certolizumab-Pegol in rheumatoid arthritis (PreCePRA) by functional MRI of the brain – Study protocol for a randomized double-blind controlled study - Schenker, Hannah; Tascilar, Koray; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Strobelt, Sandra; Kleyer, Arnd; Simon, David; Mendez, L.; Hagen, Melanie; Schönau, V.; Hueber, A.; et al. (Contemporary Clinical Trials Communications, 2021)
Background: Tumor necrosis factor inhibitors (TNFi) signify a major advance in the treatment of rheumatoid arthritis (RA). However, treatment success initially remains uncertain as approximately half of the patients do not respond adequately to TNFi. Thus, an unmet need exists to better predict therapeutic outcome of biologicals. Objectives: We investigated whether brain activity associated with arthritis measured by functional magnetic resonance imaging (fMRI) of the brain can serve as a predictor of response to TNFi in RA patients. Methods: PreCePRA is a multi-center, randomized, double-blind, placebo-controlled fMRI trial on patients with RA [1] [2]. Active RA patients failing csDMARDs therapy with a DAS28 > 3.2 and at least three tender and/or swollen joints underwent a brain BOLD (blood-oxygen-level dependent) fMRI scan upon joint compression at screening. Patients were then randomized into a 12-week double-blinded treatment phase with 200 mg Certolizumab Pegol (CZP) every two weeks (arm 1: fMRI BOLD signal activated volume > 2000 voxel, i.e. 2 cm3; arm 2: fMRI BOLD signal activated volume <2000 voxel) or placebo (arm 3). DAS28 low disease activity at 12 weeks was assigned as primary endpoint. A 12-week follow-up phase in which patients were switched from the placebo to the treatment arm followed the blinded phase. fMRI was carried out at screening as well as after 12 and 24 weeks of receiving CZP or placebo. Conclusion: We hypothesize that high-level central nervous representation of pain in patients with rheumatoid arthritis predicts response to the TNFi CZP which we further investigate in the PreCePRA trial.
CRIS-Team Scopus Importer:2021-06-04
Keywords: functional MRI; Neuroimaging; Rheumatoid arthritis; TNF inhibition

PREDICTION OF RESPONSE TO CERTOLIZUMAB PEGOL TREATMENT BY FUNCTIONAL MRI OF THE BRAIN: AN INTERNATIONAL, MULTI-CENTER, RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL (PRECEPRA) - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Hagen, Melanie; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Predictors for occlusion of cerebral AVMs following radiation therapy : Radiation dose and prior embolization, but not Spetzler-Martin grade - Knippen, Stefan; Putz, Florian; Semrau, Sabine; Lambrecht, Ulrike; Knippen, Arzu; Buchfelder, Michael; Schlaffer, Sven-Martin; Struffert, Tobias; Fietkau, Rainer (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Intracranial arteriovenous malformations (AVMs) may show a harmful development. AVMs are treated by surgery, embolization, or radiation therapy. OBJECTIVE: This study investigated obliteration rates and side effects in patients with AVMs treated by radiation therapy. METHODS: A total of 40 cases treated between 2005 and 2013 were analyzed. Single-dose stereotactic radiosurgery (SRS) was received by 13 patients and 27 received hypofractionated stereotactic radiation therapy (HSRT). In 20 patients, endovascular embolization had been performed prior to irradiation and 24 patients (60 %) had a history of previous intracranial hemorrhage. RESULTS: Treatment resulted in complete obliteration (CO) in 23/40 cases and partial obliteration in 8/40. CO was achieved in 85 % of patients receiving SRS compared to 44 % of those receiving HSRT. In the HSRT group, a first indication of an influence of AVM volume on obliteration rate was found. Equivalent 2 Gy fraction doses (EQD2) >70 Gy showed an obliteration rate of 50 %. Prior embolization was significantly associated with a higher portion of CO (p = 0.032). Median latency period (24.2 vs. 26 months) until CO was similar in both groups (SRS vs. HSRT). The rate of intracranial hemorrhage in patients with no prior bleeding events was 0 %. CONCLUSION: Excellent obliteration rates were achieved by SRS. Consistent with the literature, this data analysis suggests that the results of HSRT are volume-dependent. Furthermore, regimens with EQD2 doses >70 Gy appear more likely to achieve obliteration than schemes with lower doses. The findings indicate that radiation therapy does not increase the risk of bleeding. Prior embolization may have a good prognostic impact.
EVALuna2:32909

Presence of Concomitant Systemic Cancer is Not Associated with Worse Functional Long-Term Outcome in Patients with Intracerebral Hemorrhage - Spuergel, Maximilian I.; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Hartwich, Julius; Giede-Jeppe, Antje; Madzar, Dominik; Beuscher, Vanessa D.; Lücking, Hannes; Struffert, Tobias; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2017)
Data on clinical characteristics and outcome of patients with intracerebral hemorrhage (ICH) and concomitant systemic cancer disease are very limited.Nine hundred and seventy three consecutive primary ICH patients were analyzed using our prospective institutional registry over a period of 9 years (2006-2014). We compared clinical and radiological parameters as well as outcome - scored using the modified Rankin Scale (mRS) and analyzed in a dichotomized fashion as favorable outcome (mRS = 0-3) and unfavorable outcome (mRS = 4-6) - of ICH patients with and without cancer. Relevant imbalances in baseline clinical and radiological characteristics were adjusted using propensity score (PS) matching.Prevalence of systemic cancer among patients with ICH was 8.5% (83/973). ICH patients with cancer were older (77 [70-82] vs. 72 [63-80] years; p = 0.002), had more often prior renal dysfunction (19/83 [22.9%] vs.107/890 [12.0%]; p = 0.005), and smaller hemorrhage volumes (10.1 [4.8-24.3] vs. 15.3 [5.4-42.9] mL; p = 0.017). After PS-matching there were no significant differences neither in mortality nor in functional outcome both at 3 months (mortality: 33/81 [40.7%] vs. 55/158 [34.8%]; p = 0.368; mRS = 0-3: 28/81 [34.6%] vs. 52/158 [32.9%]; p = 0.797) and 12 months (mortality: 39/78 [50.0%] vs. 70/150 [46.7%]; p = 0.633; mRS = 0-3: 25/78 [32.1%] vs. 53/150 [35.3%]; p = 0.620) among patients with and without concomitant systemic cancer. ICH volume tended to be highest in patients with hematooncologic malignancy and smallest in urothelial cancer.Patients with ICH and concomitant systemic cancer on average are older; however, they show smaller ICH volumes compared to patients without cancer. Yet, mortality and functional outcome is not different in ICH patients with and without cancer. Thus, the clinical history or the de novo diagnosis of concomitant malignancies in ICH patients should not lead to unjustified treatment restrictions.
EVALuna2:22553

PRG3 induces Ras-dependent oncogenic cooperation in gliomas - Fan, Zheng; Bittermann-Rummel, Philipp; Yakubov, Eduard; Chen, Daishi; Broggini, Thomas; Sehm, Tina; Hatipoglu Majernik, Gökce; Hock, Stefan; Schwarz, Marc; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; et al. (Oncotarget, 2016)
Malignant gliomas are one of the most devastating cancers in humans. One characteristic hallmark of malignant gliomas is their cellular heterogeneity with frequent genetic lesions and disturbed gene expression levels conferring selective growth advantage. Here, we report on the neuronal-associated growth promoting gene PRG3 executing oncogenic cooperation in gliomas. We have identified perturbed PRG3 levels in human malignant brain tumors displaying either elevated or down-regulated PRG3 levels compared to non-transformed specimens. Further, imbalanced PRG3 levels in gliomas foster Ras-driven oncogenic amplification with increased proliferation and cell migration although angiogenesis was unaffected. Hence, PRG3 interacts with RasGEF1 (RasGRF1/CDC25), undergoes Ras-induced challenges, whereas deletion of the C-terminal domain of PRG3 (PRG3ΔCT) inhibits Ras. Moreover PRG3 silencing makes gliomas resistant to Ras inhibition. In vivo disequilibrated PRG3 gliomas show aggravated proliferation, invasion, and deteriorate clinical outcome. Thus, our data show that the interference with PRG3 homeostasis amplifies oncogenic properties and foster the malignancy potential in gliomas.
EVALuna2:23011

Principles of T2 *-weighted dynamic susceptibility contrast MRI technique in brain tumor imaging - Shiroishi, Mark S.; Castellazzi, Gloria; Boxerman, Jerrold L.; D'Amore, Francesco; Essig, Marco; Nguyen, Thanh B.; Provenzale, James M.; Enterline, David S.; Anzalone, Nicoletta; Dörfler, Arnd; Rovira, Alex; Wintermark, Max; et al. (Journal of Magnetic Resonance Imaging, 2015)
Dynamic susceptibility contrast magnetic resonance imaging (DSC-MRI) is used to track the first pass of an exogenous, paramagnetic, nondiffusible contrast agent through brain tissue, and has emerged as a powerful tool in the characterization of brain tumor hemodynamics. DSC-MRI parameters can be helpful in many aspects, including tumor grading, prediction of treatment response, likelihood of malignant transformation, discrimination between tumor recurrence and radiation necrosis, and differentiation between true early progression and pseudoprogression. This review aims to provide a conceptual overview of the underlying principles of DSC-MRI of the brain for clinical neuroradiologists, scientists, or students wishing to improve their understanding of the technical aspects, pitfalls, and controversies of DSC perfusion MRI of the brain. Future consensus on image acquisition parameters and postprocessing of DSC-MRI will most likely allow this technique to be evaluated and used in high-quality multicenter studies and ultimately help guide clinical care.
EVALuna2:23001

Prior-based automatic segmentation of the carotid artery lumen in TOF MRA (PASCAL) - Hutter, Jana; Hofmann, Hannes; Grimm, Robert; Greiser, Andreas; Saake, Marc; Hornegger, Joachim; Dörfler, Arnd; Schmitt, Peter (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2012)
In current clinical practice, examinations of the carotid artery bifurcation are commonly carried out with Computed Tomography Angiography (CTA) or contrast-enhanced Magnetic Resonance Angiography (ceMRA). Quantitative information about vessel morphology, extracted from segmentations, is promising for diagnosis of vessel pathologies. However, both above-mentioned techniques require the administration of contrast media. In contrary, non-ce MRA methods such as Time-of-Flight (TOF) provide fully non-invasive imaging without any exogenous contrast agent. The diagnostic value of TOF MRA, however, for assessment of the carotid bifurcation area can be hampered due to its susceptibility to irregular blood flow patterns. Conventional methods for lumen segmentation are very sensitive to such signal voids and produce inaccurate results. In this work, a novel, fully automatic 3D segmentation algorithm is proposed which uses prior knowledge about irregular flow patterns. The presented technique has been successfully tested on eleven volunteer datasets as well as in a patient case, offering the comparison to CTA images. The sensitivity could be increased by 29.2% to 85.6% compared to standard level set methods. The root mean squared error in diameter measurements was reduced from 4.85mm to 1.44 mm.
CRIS-Team Scopus Importer:2022-08-05

Prognostic Accuracy of CTP Summary Maps in Patients with Large Vessel Occlusive Stroke and Poor Revascularization after Mechanical Thrombectomy-Comparison of Three Automated Perfusion Software Applications - Mühlen, Iris; Borutta, Matthias; Siedler, Gabriela; Engelhorn, Tobias; Hock, Stefan; Knott, Michael; Hölter, Philip; Volbers, Bastian; Schwab, Stefan; Dörfler, Arnd (Tomography, 2022)
Background: Innovative automated perfusion software solutions offer support in the management of acute stroke by providing information about the infarct core and penumbra. While the performance of different software solutions has mainly been investigated in patients with successful recanalization, the prognostic accuracy of the hypoperfusion maps in cases of futile recanalization has hardly been validated. Methods: In 39 patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation and poor revascularization (thrombolysis in cerebral infarction (TICI) 0-2a) after mechanical thrombectomy (MT), hypoperfusion analysis was performed using three different automated perfusion software solutions (A: RAPID, B: Brainomix e-CTP, C: Syngo.via). The hypoperfusion volumes (HV) as Tmax > 6 s were compared with the final infarct volumes (FIV) on follow-up CT 36-48 h after futile recanalization. Bland-Altman analysis was applied to display the levels of agreement and to evaluate systematic differences. Based on the median hypoperfusion intensity ratio (HIR, volumetric ratio of tissue with a Tmax > 10 s and Tmax > 6 s) patients were dichotomized into high- and low-HIR groups. Subgroup analysis with favorable (<0.6) and unfavorable (>= 0.6) HIR was performed with respect to the FIV. HIR was correlated to clinical baseline and outcome parameters using Pearson's correlation. Results: Overall, there was good correlation without significant differences between the HVs and the FIVs with package A (r = 0.78, p < 0.001) being slightly superior to B and C. However, levels of agreement were very wide for all software applications in Bland-Altman analysis. In cases of large infarcts exceeding 150 mL the performance of the automated software solutions generally decreased. Subgroup analysis revealed the FIV to be generally underestimated in patients with HIR >= 0.6 (p < 0.05). In the subgroup with favorable HIR, however, there was a trend towards an overestimation of the FIV. Nevertheless, packages A and B showed good correlation between the HVs and FIVs without significant differences (p > 0.2), while only package C significantly overestimated the FIV (-54.6 +/- 56.0 mL, p = 0.001). The rate of modified Rankin Scale (mRS) 0-3 after 3 months was significantly higher in favorable vs. unfavorable HIR (42.1% vs. 13.3%, p = 0.02). Lower HIR was associated with higher Alberta Stroke Program Early CT Score (ASPECTS) at presentation and on follow-up imaging, lower risk of malignant edema, and better outcome (p < 0.05). Conclusion: Overall, the performance of the automated perfusion software solutions to predict the FIV after futile recanalization is good, with decreasing accuracy in large infarcts exceeding 150 mL. However, depending on the HIR, FIV can be significantly over- and underestimated, with Syngo showing the widest range. Our results indicate that the HIR can serve as valuable parameter for outcome predictions and facilitate the decision whether or not to perform MT in delicate cases.
CRIS-Team WoS Importer:2022-07-08

Projection image-to-image translation in hybrid x-ray/MR imaging - Stimpel, Bernhard; Syben-Leisner, Christopher; Würfl, Tobias; Breininger, Katharina; Lommen, Jonathan; Dörfler, Arnd; Maier, Andreas (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2019)
The potential benefit of hybrid X-ray and MR imaging in the interventional environment is large due to the combination of fast imaging with high contrast variety. However, a vast amount of existing image enhancement methods requires the image information of both modalities to be present in the same domain. To unlock this potential, we present a solution to image-to-image translation from MR projections to corresponding x-ray projection images. The approach is based on a state-of-the-art image generator network that is modified to fit the specific application. Furthermore, we propose the inclusion of a gradient map in the loss function to allow the network to emphasize high-frequency details in image generation. Our approach is capable of creating x-ray projection images with natural appearance. Additionally, our extensions show clear improvement compared to the baseline method.
CRIS-Team Scopus Importer:2019-07-12

Projection-to-Projection Translation for Hybrid X-ray and Magnetic Resonance Imaging - Stimpel, Bernhard; Syben-Leisner, Christopher; Würfl, Tobias; Breininger, Katharina; Hölter, Philip; Dörfler, Arnd; Maier, Andreas (Scientific Reports, 2019)
Hybrid X-ray and magnetic resonance (MR) imaging promises large potential in interventional medical imaging applications due to the broad variety of contrast of MRI combined with fast imaging of X-ray-based modalities. To fully utilize the potential of the vast amount of existing image enhancement techniques, the corresponding information from both modalities must be present in the same domain. For image-guided interventional procedures, X-ray fluoroscopy has proven to be the modality of choice. Synthesizing one modality from another in this case is an ill-posed problem due to ambiguous signal and overlapping structures in projective geometry. To take on these challenges, we present a learning-based solution to MR to X-ray projection-to-projection translation. We propose an image generator network that focuses on high representation capacity in higher resolution layers to allow for accurate synthesis of fine details in the projection images. Additionally, a weighting scheme in the loss computation that favors high-frequency structures is proposed to focus on the important details and contours in projection imaging. The proposed extensions prove valuable in generating X-ray projection images with natural appearance. Our approach achieves a deviation from the ground truth of only 6% and structural similarity measure of 0.913 ± 0.005. In particular the high frequency weighting assists in generating projection images with sharp appearance and reduces erroneously synthesized fine details.<br

PROPHYLACTIC AND PROLONGED HYPOTHERMIA IN POOR-GRADESAH REDUCES DEGREE OF VASOSPASM AND RATE OF DELAYED CEREBRAL INFARCTIONS - Kuramatsu, J. B.; Kollmar, Rainer; Staykov, Dimitre; Kloska, Stephan; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Schwab, Stefan; Huttner, Hagen (2016)
EVALuna2:22484

Prophylactic nimodipine treatment and improvement in hearing outcome after vestibular schwannoma surgery: a combined analysis of a randomized, multicenter, Phase III trial and its pilot study - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2017)
OBJECTIVE In clinical routines, neuroprotective strategies in neurosurgical interventions are still missing. A pilot study (n = 30) and an analogously performed Phase III trial (n = 112) pointed to a beneficial effect of prophylactic nimodipine and hydroxyethyl starch (HES) in vestibular schwannoma (VS) surgery. Considering the small sample size, the data from both studies were pooled. METHODS The patients in both investigator-initiated studies were assigned to 2 groups. The treatment group (n = 70) received parenteral nimodipine (1-2 mg/hour) and HES (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 72) was not treated prophylactically. Facial and cochlear nerve functions were documented preoperatively, during the inpatient care, and 1 year after surgery. RESULTS Pooled raw data were analyzed retrospectively. Intent-to-treat analysis revealed a significantly lower risk for hearing loss (Class D) 12 months after surgery in the treatment group compared with the control group (OR 0.46, 95% CI 0.22-0.97; p = 0.04). After exclusion of patients with preoperative Class D hearing, this effect was more pronounced (OR 0.38, 95% CI 0.17-0.83; p = 0.016). Logistic regression analysis adjusted for tumor size showed a 4 times lower risk for hearing loss in the treatment group compared with the control group (OR 0.25, 95% CI 0.09-0.63; p = 0.003). Facial nerve function was not significantly improved with treatment. Apart from dose-dependent hypotension (p < 0.001), the study medication was well tolerated. CONCLUSIONS Prophylactic nimodipine is safe and may be recommended in VS surgery to preserve hearing. Prophylactic neuroprotective treatment in surgeries in which nerves are at risk seems to be a novel and promising concept. Clinical trial registration no.: DRKS 00000328 ( https://drks-neu.uniklinik-freiburg.de/drks_web/ ).
EVALuna2:33133

Prophylactic nimodipine treatment for cochlear and facial nerve preservation after vestibular schwannoma surgery: a randomized multicenter Phase III trial - Scheller, Christian; Wienke, Andreas; Tatagiba, Marcos; Gharabaghi, Alireza; Ramina, Kristofer F.; Ganslandt, Oliver Thomas; Bischoff, Barbara; Zenk, Johannes; Engelhorn, Tobias; Matthies, Cordula; Westermaier, Thomas; Antoniadis, Gregor; et al. (Journal of Neurosurgery, 2016)
OBJECT A pilot study of prophylactic nimodipine and hydroxyethyl starch treatment showed a beneficial effect on facial and cochlear nerve preservation following vestibular schwannoma (VS) surgery. A prospective Phase III trial was undertaken to confirm these results. METHODS An open-label, 2-arm, randomized parallel group and multicenter Phase III trial with blinded expert review was performed and included 112 patients who underwent VS surgery between January 2010 and February 2013 at 7 departments of neurosurgery to investigate the efficacy and safety of the prophylaxis. The surgery was performed after the patients were randomly assigned to one of 2 groups using online randomization. The treatment group (n = 56) received parenteral nimodipine (1-2 mg/hr) and hydroxyethyl starch (hematocrit 30%-35%) from the day before surgery until the 7th postoperative day. The control group (n = 56) was not treated prophylactically. RESULTS Intent-to-treat analysis showed no statistically significant effects of the treatment on either preservation of facial nerve function (35 [67.3%] of 52 [treatment group] compared with 34 [72.3%] of 47 [control group]) (p = 0.745) or hearing preservation (11 [23.4%] of 47 [treatment group] compared with 15 [31.2%] of 48 [control group]) (p = 0.530) 12 months after surgery. Since tumor sizes were significantly larger in the treatment group than in the control group, logistic regression analysis was required. The risk for deterioration of facial nerve function was adjusted nearly the same in both groups (OR 1.07 [95% CI 0.34-3.43], p = 0.91). In contrast, the risk for postoperative hearing loss was adjusted 2 times lower in the treatment group compared with the control group (OR 0.49 [95% CI 0.18-1.30], p = 0.15). Apart from dose-dependent hypotension (p < 0.001), no clinically relevant adverse reactions were observed. CONCLUSIONS There were no statistically significant effects of the treatment. Despite the width of the confidence intervals, the odds ratios may suggest but do not prove a clinically relevant effect of the safe study medication on the preservation of cochlear nerve function after VS surgery. Further study is needed before prophylactic nimodipine can be recommended in VS surgery.
EVALuna2:22832

Propofol-related urine discoloration in a patient with fatal atypical intracerebral hemorrhage treated with hypothermia - Regensburger, Martin; Huttner, Hagen; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (SpringerPlus, 2014)
Introduction: Mild therapeutic hypothermia is an increasingly recognised treatment option to reduce perihemorrhagic edema in severe intracerebral hemorrhage. Case description: We report the case of a 77-year old woman with atypical intracerebral hemorrhage that was treated with mild hypothermia in addition to osmotic therapy. The patient’s urine subsequently showed a green discoloration. Urine discoloration was completely reversible upon discontinuation of propofol. Discussion and evaluation: Propofol-related urine discoloration may have been provoked by hypothermia. Due to the benign nature of this side effect, propofol should be stopped and gastrointestinal function should be supported. Conclusion: More studies are needed to show a causal role of hypothermia and related decreased enzymatic function.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Enterohepatic circulation; Hypothermia; Intracerebral hemorrhage; Liver enzyme function; Urine discoloration

Prospective intraindividual comparison of gadoterate and gadobutrol for cervical and intracranial contrast-enhanced magnetic resonance angiography - Lang, Stefan; Weibart, Marina; Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Essig, Marco; Kloska, Stephan; Dörfler, Arnd; Hölter, Philip (Neuroradiology, 2017)
PURPOSE: Gadobutrol (GB) is reported to provide improved relaxivity and concentration compared to gadoterate (GT). This study was designed to intraindividually compare quantitative and qualitative enhancement characteristics of GB to GT in cervicocranial magnetic resonance angiography (MRA) of patients with cerebrovascular disease (CVD). METHODS: Patients (n = 54) with CVD underwent two identical contrast-enhanced magnetic resonance angiography (CE-MRA) examinations of the cervical and intracranial vasculature in randomized order, using GB and GT in equimolar dose. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were obtained by two independent neuroradiologists, blinded to the applied contrast agents. Qualitative assessment was performed using a three-point scale with a focus on M1/M2 segments. RESULTS: One thousand and twenty-six vessel segments were analyzed. GB revealed a significantly higher SNR (p = 0.032) and CNR (p = 0.031) in all vessel segments. GB featured a significantly higher SNR and CNR in thoracic (p = 0.022; p = 0.016) and cervical vessels (p = 0.03; p = 0.038), as well as in the posterior circulation (p = 0.012; p = 0.005). In blinded qualitative assessment, overall preference was given to GB (p = 0.02), showing a significant better delineation of the M1/M2 segments (p = 0.041). CONCLUSION: Compared to GT, the use of GB results in a significantly higher SNR and CNR in cervical and cerebral CE-MRA, leading to a better delineation of the intracranial vasculature. Present results underline the potential of GB for improved CE-MRA assessment of vasculature in CVD patients.
EVALuna2:33134

Pulsed Arterial Spin Labeling and Segmented Brain Volumetry in the Diagnostic Evaluation of Frontotemporal Dementia, Alzheimer’s Disease and Mild Cognitive Impairment - Marterstock, Dominique; Knott, Michael; Lang, Stefan; Oberstein, Timo; Kornhuber, Johannes; Dörfler, Arnd; Schmidt, Manuel; Hölter, Philip (Tomography, 2022)
Background: Previous studies suggest that brain atrophy can not only be defined by its morphological extent, but also by the cerebral blood flow (CBF) within a certain area of the brain, including white and gray matter. The aim of this study is to investigate known atrophy patterns in different forms of dementia and to compare segmented brain volumetrics and pulsed arterial spin labeling (pASL) data to explore the correlation between brain maps with atrophy and this non-contrast-enhanced brain-perfusion method. Methods: Our study comprised 17 patients with diagnosed cognitive impairment (five Alzheimer’s disease = AD, five frontotemporal dementia = FTD, seven mild cognitive impairment = MCI) and 19 healthy control subjects (CO). All patients and controls underwent 4D-pASL brain-perfusion MR imaging and T1w MPRAGE. The data were assessed regarding relative brain volume on the basis of 286 brain regions, and absolute and relative cerebral blood flow (CBF/rCBF) were derived from pASL data in the corresponding brain regions. Mini-Mental State Examination (MMSE) was performed to assess cognitive functions. Results: FTD patients demonstrated significant brain atrophy in 43 brain regions compared to CO. Patients with MCI showed significant brain atrophy in 18 brain regions compared to CO, whereas AD patients only showed six brain regions with significant brain atrophy compared to CO. There was good correlation of brain atrophy and pASL perfusion data in five brain regions of patients with diagnosed FTD, especially in the superior temporal gyrus (r = 0.900, p = 0.037), the inferior frontal white matter (pars orbitalis; r = 0.968, p = 0.007) and the thalami (r = 0.810, p = 0.015). Patients with MCI demonstrated a correlation in one brain region (left inferior fronto-occipital fasciculus; r = 0.786, p = 0.036), whereas patients with diagnosed AD revealed no correlation. Conclusions: pASL can detect affected brain regions in cognitive impairment and corresponds with brain atrophy, especially for patients suffering from FTD and MCI. However, there was no correlation of perfusion alterations and brain atrophy in AD. pASL perfusion might thus represent a promising tool for noninvasive brain-perfusion evaluation in specific dementia subtypes as a complimentary imaging-based bio marker in addition to brain volumetry.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alzheimer’s disease; Brain volumetry; Dementia; Frontotemporal dementia; Mild cognitive impairment; Pulsed arterial spin labeling

Pulseq-CEST: Towards multi-site multi-vendor compatibility and reproducibility of CEST experiments using an open-source sequence standard - Herz, Kai; Mueller, Sebastian; Perlman, Or; Zaitsev, Maxim; Knutsson, Linda; Sun, Phillip Zhe; Zhou, Jinyuan; Van Zijl, Peter; Heinecke, Kerstin; Schuenke, Patrick; Farrar, Christian T.; Schmidt, Manuel; et al. (Magnetic Resonance in Medicine, 2021)
Purpose As the field of CEST grows, various novel preparation periods using different parameters are being introduced. At the same time, large, multisite clinical studies require clearly defined protocols, especially across different vendors. Here, we propose a CEST definition standard using the open Pulseq format for a shareable, simple, and exact definition of CEST protocols.
CRIS-Team WoS Importer:2021-05-28

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction - Kossel, Clara-Sophie; Kobus, Franca; Borutta, Matthias; Kärtner, Maximilian; Kuramatsu, Joji; Engelhorn, Tobias; Schwab, Stefan; Köhn, Julia (Journal of Neurology, 2023)
Background: Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients undergoing EVT. Methods: From 10/2018 to 10/2021, neurocritical-care-unit patients were retrospectively enrolled after EVT of anterior circulation LVO. We monitored parameters of pupillary reactivity [light-reflex-latency (Lat), constriction- and redilation-velocities (CV, DV), percentage-change-of-apertures (per-change); NeurOptics-pupilometer®] up to every hour on day 1–3 of ICU stay. BE was defined as midline shift ≥ 5 mm on follow-up imaging 3–5 days after EVT. We calculated mean values of intra-individual differences between successive pairs of parameters (mean-deltas), determined best discriminative cut-off values for BE development (ROC-analyses), and evaluated prognostic performance of pupillometry for BE development (sensitivity/specificity/positive-/negative-predictive-values). Results: 3241 pupillary assessments of 122 patients [67 women, 73 years (61.0–85.0)] were included. 13/122 patients developed BE. Patients with BE had significantly lower CVs, DVs, and smaller per-changes than patients without BE. On day 1 after EVT mean-deltas of CV, DV, and per-changes were significantly lower in patients with than without BE. Positive-predictive-values of calculated thresholds to discriminate both groups were considerably low, yet, we found high negative-predictive-values for CV, DV, per-changes, and mean-deltas (max.: 98.4%). Conclusion: Our data suggest associations between noninvasively detected changes in pupillary reactivity and BE early after LVO-EVT. Pupillometry may identify patients who are unlikely to develop BE and may not need repetitive follow-up-imaging or rescue-therapy.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Automated pupillometry; Endovascular treatment; Ischemic stroke; Large vessel occlusion; Pupillary reactivity

Quality assurance guidelines for interstitial hyperthermia - Trefna, H. Dobsicek; Schmidt, Manuel; Van Rhoon, G. C.; Kok, H. P.; Gordeyev, S. S.; Lamprecht, U.; Marder, D.; Nadobny, J.; Ghadjar, P.; Abdel-Rahman, S.; Kukielka, A. M.; Strnad, Vratislav; et al. (International Journal of Hyperthermia, 2019)
Quality assurance (QA) guidelines are essential to provide uniform execution of clinical hyperthermia treatments and trials. This document outlines the clinical and technical consequences of the specific properties of interstitial heat delivery and specifies recommendations for hyperthermia administration with interstitial techniques. Interstitial hyperthermia aims at tumor temperatures in the 40-44 degrees C range as an adjunct to radiation or chemotherapy. The clinical part of this document imparts specific clinical experience of interstitial heat delivery to various tumor sites as well as recommended interstitial hyperthermia workflow and procedures. The second part describes technical requirements for quality assurance of current interstitial heating equipment including electromagnetic (radiative and capacitive) and ultrasound heating techniques. Detailed instructions are provided on characterization and documentation of the performance of interstitial hyperthermia applicators to achieve reproducible hyperthermia treatments of uniform high quality. Output power and consequent temperature rise are the key parameters for characterization of applicator performance in these QA guidelines. These characteristics determine the specific maximum tumor size and depth that can be heated adequately. The guidelines were developed by the ESHO Technical Committee with participation of senior STM members and members of the Atzelsberg Circle.
CRIS-Team WoS Importer:2019-04-09

Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32-channel phased-array head coil: Application to patients with secondary progressive multiple sclerosis - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael; Schmidt, Manuel (NMR in Biomedicine, 2022)
Apparent tissue sodium concentrations (aTSCs) determined by 23Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal-to-noise ratio of 23Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual-tuned 23Na/1H birdcage coil with a receive-only 32-channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired-samples Wilcoxon rank-sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS (p = 0.42). The proposed quantification workflow for 23Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group (p = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients (p = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23Na brain MRI as a biomarker in diseases such as MS.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 7 T; brain MRI; multiple sclerosis

Quantitative and qualitative comparison of 4D-DSA with 3D-DSA using computational fluid dynamics simulations in cerebral aneurysms - Lang, Sabine; Birkhold, A. I.; Schmidt, Manuel; Endres, J.; Strother, C.; Dörfler, Arnd; Lücking, Hannes; Hölter, Philip (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: 4D-DSA allows time-resolved 3D imaging of the cerebral vasculature. The aim of our study was to evaluate this method in comparison with the current criterion standard 3D-DSA by qualitative and quantitative means using computational fluid dynamics. MATERIALS AND METHODS: 3D- and 4D-DSA datasets were acquired in patients with cerebral aneurysms. Computational fluid dynamics analysis was performed for all datasets. Using computational fluid dynamics, we compared 4D-DSA with 3D-DSA in terms of both aneurysmal geometry (quantitative: Maximum diameter, ostium size [OZ1/2], volume) and hemodynamic parameters (qualitative: Flow stability, flow complexity, inflow concentration; quantitative: Average/maximum wall shear stress, impingement zone, low-stress zone, intra-aneurysmal pressure, and flow velocity). Qualitative parameters were descriptively analyzed. Correlation coefficients (r, P value) were calculated for quantitative parameters. RESULTS: 3D- and 4D-DSA datasets of 10 cerebral aneurysms in 10 patients were postprocessed. Evaluation of aneurysmal geometry with 4D-DSA (rmaximum diameter = 0.98, Pmaximum diameter <.001; rOZ1/OZ2 = 0.98/0.86, POZ1/OZ2 =.001/.002; rvolume = 0.98, Pvolume <.001) correlated highly with 3D-DSA. Evaluation of qualitative hemodynamic parameters (flow stability, flow complexity, inflow concentration) did show complete accordance, and evaluation of quantitative hemodynamic parameters (raverage/maximum wall shear stress diastole=0.92/0.88, Paverage/maximum wall shear stress diastole <.001/.001; raverage/maximum wall shear stress systole = 0.94/0.93, Paverage/maximum wall shear stress systole < .001/.001; rimpingement zone=0.96, Pimpingement zone <.001; rlow-stress zone=1.00, Plow-stress zone <.01; rpressure diastole=0.84,Ppressure diastole< .002; rpressure systole=0.9, Ppressure systole <.001; rflow velocity diastole=0.95, Pflow velocity diastole <.001; rflow velocity systole=0.93,Pflow velocity systole <.001) did show nearly complete accordance between 4D- and 3D-DSA. CONCLUSIONS: Despite a different injection protocol, 4D-DSA is a reliable basis for computational fluid dynamics analysis of the intracranial vasculature and provides equivalent visualization of aneurysm geometry compared with 3D-DSA.
CRIS-Team Scopus Importer:2019-09-17

Quantitative Corticospinal Tract Assessment in Acute Intracerebral Hemorrhage - Volbers, Bastian; Mennecke, Angelika; Kästle, Nicola; Huttner, Hagen; Schwab, Stefan; Schmidt, Manuel; Engelhorn, Tobias Martin; Dörfler, Arnd (Translational Stroke Research, 2020)
Intracerebral hemorrhage (ICH) prognostication during the acute phase is often subjective among physicians and often affects treatment decisions. The present study explores objective imaging parameters using quantitative corticospinal tract (CST) fiber reconstruction during the acute phase of ICH and correlates these parameters with functional outcome and patient recovery. We prospectively enrolled nonsurgical spontaneous supratentorial ICH patients and obtained an MRI scan on day 5 ± 1. Q-space diffeomorphic reconstruction was performed using DSI Studio, and quantitative anisotropy (QA) was calculated. The CST was reconstructed based on QA. The dichotomized modified Rankin Scale score on day 90 (favorable outcome = 0–2) and Barthel Index (favorable recovery = 100 on day 90 or improvement between discharge and day 90 > 60%) were assessed. Thirty-three patients, median age 72 years (interquartile range (IQR) 64–83), 21 female (64%), 21 (64%) with lobar hemorrhage, median ICH volume on admission 15.0 (IQR 7.0–27.4) mL, were included. Sixteen patients (48%) had a favorable outcome and 24 (73%) had a favorable recovery. The mean number of ipsilesional reconstructed CST fiber pathways was higher in patients with favorable outcomes (153 (standard deviation (SD) 103) vs. 60 (SD 39), p = 0.003) and predicted outcome after adjustment (Exp(B) = 1.016 (95% CI = 1.002–1.030)). QA in the ipsilesional posterior limb of the internal capsule showed a trend towards an association with favorable outcome (Exp(B) = 1.194 (95% CI = 0.991–1.439 (adjusted))). The total (ipsilesional + contralesional) number of reconstructed fiber pathways was associated with favorable recovery (Exp(B) = 1.025 (95% CI = 1.003–1.047 (adjusted))). Quantitative tractography parameters assessed in the acute phase of ICH may represent a promising predictor of long-term outcome and recovery. This might facilitate prognostic evaluation and organization of rehabilitation.
CRIS-Team Scopus Importer:2020-10-02
Keywords: All rehabilitation; DWI; Intracerebral hemorrhage; MRI; Outcome research

QUANTITATIVE MAGNETIC RESONANCE IMAGING CORRELATES WITH EARLY S100B PROFILE AND FUNCTIONAL OUTCOME AFTER ACUTE BRAIN INJURY - Roeckelein, Verena; Kloska, Stephan; Uder, Michael; Buchfelder, Michael; Kleindienst, Andrea (2016)
EVALuna2:14588

Quantitative susceptibility mapping depicts severe myelin deficit and iron deposition in a transgenic model of multiple system atrophy - Lambrecht, Vera; Hanspach, Jannis; Hoffmann, Alana; Seyler, Lisa; Mennecke, Angelika; Straub, Sina; Marxreiter, Franz; Bäuerle, Tobias; Winkler, Jürgen; Laun, Frederik Bernd (Experimental Neurology, 2020)
Despite internationally established diagnostic criteria, multiple system atrophy (MSA) is frequently misdiagnosed, particularly at disease onset. While neuropathological changes such as demyelination and iron deposition are typically detected in MSA, these structural hallmarks were so far only demonstrated post-mortem. Here, we examine whether myelin deficit observed in a transgenic murine model of MSA can be visualized and quantified in vivo using specific magnetic resonance imaging (MRI) approaches. Reduced myelin content was measured histologically in prototypical white matter as well as mixed grey-white matter regions i.e. corpus callosum, anterior commissure, and striatum of transgenic mice overexpressing human α-synuclein under the control of the myelin basic protein promotor (MBP29-hα-syn mice). Correspondingly, in vivo quantitative susceptibility mapping (QSM) showed a strongly reduced susceptibility contrast in white matter regions and T2-weighted MR imaging revealed a significantly reduced grey-white matter contrast in MBP29-hα-syn mice. In addition, morphological analysis suggested a pronounced, white matter-specific deposition of iron in MBP29-hα-syn mice. Importantly, in vivo MRI results were matched by comprehensive structural characterization of myelin, iron, and axonal directionality. Taken together, our results provide strong evidence that QSM is a very sensitive tool measuring changes in myelin density in conjunction with iron deposition in MBP29-hα-syn mice. This multimodal neuroimaging approach may pave the way towards a novel non-invasive technique to detect crucial neuropathological changes specifically associated with MSA.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Iron; Multiple system atrophy; Myelin imaging; Quantitative susceptibility mapping; White matter

Quiet diffusion-weighted head scanning: Initial clinical evaluation in ischemic stroke patients at 1.5T - Rösch, Julie; Ott, Martin; Heismann, Bjoern; Dörfler, Arnd; Engelhorn, Tobias; Sembritzki, Klaus; Grodzki, David M. (Journal of Magnetic Resonance Imaging, 2016)
PURPOSE: To compare the quality and diagnostic value of routine single-shot, echo-planar imaging, diffusion-weighted imaging (ss-EPI-DWI) to those of quiet readout segmented EPI-DWI (q-DWI) in magnetic resonance imaging (MRI) of acute stroke. MATERIALS AND METHODS: Twenty-six patients with acute stroke underwent a 1.5T MRI including diffusion-weighted ss-EPI and q-DWI. The two sequences were protocolled to have identical spatial resolution and spatial coverage. q-DWI was tested with (regular q-DWI) and without (fast q-DWI) averaging in 13 patients each. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content were performed. RESULTS: SNR and CNR values of the q-DWI scans were considerably higher than those of ss-EPI DWI (P ≤ 0.0078). No statistical difference was found for lesion conspicuity (P ≥ 0.125). Statistical differences were found for level of artifacts (P ≥ 0.0078) and overall image quality (P ≥ 0.002). Both were evaluated better in the ss-EPI DWI than in the regular and fast q-DWI. Apart from one fast q-DWI patient, radiologists voted the images to have the same diagnostic content, with upper 90% confidence limits of 0.238 for regular q-DWI and 0.429 for fast q-DWI. CONCLUSION: If the acoustic burden is critical to the patient, q-DWI is an equivalent quiet alternative to ss-EPI DWI for use in stroke patients. J. Magn. Reson. Imaging 2016;44:1238-1243.
EVALuna2:33143

Quiet FLAIR at 7T MRI - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Dörfler, Arnd; Grodzki, David M. (Investigative Radiology, 2020)
OBJECTIVE: The aim of this study was to investigate acoustic noise reduction and image quality of cranial magnetic resonance imaging (MRI) at 7T MRI with and without sequence-based acoustic noise reduction. MATERIALS AND METHODS: Fifteen patients and 5 healthy volunteers underwent 7T MRI scanning. A fluid-attenuated inversion recovery (FLAIR) sequence was acquired with and without sequence-based acoustic noise reduction. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio, contrast-to-noise ratio, lesion conspicuity, level of artifacts, and overall image quality were performed. Furthermore, detection rates of white matter lesions were evaluated by 2 observers for both sequences. RESULTS: Acoustic noise was significantly reduced from initially 92.7 dB(A) to 78.9 dB(A), corresponding to an 80% reduction in sound pressure. The visual assessment revealed no significant difference in the level of artifacts. Although rated very high by both readers, lesion conspicuity and image quality averaged better for the regular FLAIR sequence. Signal-to-noise ratio and contrast-to-noise ratio slightly decreased when applying the sequence-based acoustic noise reduction. No significant difference was found between the detection rates of white matter lesions for both observers. CONCLUSIONS: Reducing sound pressure by 80% in FLAIR imaging at 7T ultra-high-field MRI is feasible while maintaining high diagnostic image quality.
CRIS-Team Scopus Importer:2020-10-23

Radiation dose in cerebral angiography and flat detector CT applications in neuroradiology - Struffert, Tobias; Lang, Sabine; Scholz, R.; Hauer, M.; Dörfler, Arnd (Radiologe, 2015)
Flat detectors (FD) have completely replaced image intensifiers in angiography. Due to this development not only the image quality of 2D digital subtraction angiography series (2-D-DSA) could be improved but also the acquisition of computed tomography (CT)-like cross-sectional images (FD-CT) within the angio suite became feasible. These techniques are now being used in daily clinical routine. Only little information about effective doses of these applications to patients has been published in the literature. We describe the effective patient dose of current applications in the field of angiography and demonstrate strategies to minimize the dose to the patient. In addition, we compare FD-CT applications to standard multislice CT applications.
EVALuna2:22998

Radiologische Diagnostik zerebraler Metastasen - Engelhorn, Tobias; et al. (Onkologe, 2014)
Background. Imaging plays a key role in the diagnosis of central nervous system (CNS) metastases. Objective. In this review the role of magnetic resonance imaging (MRI) and computed tomography (CT) in the work-up of cerebral metastases is presented. In addition to characteristic imaging findings technical aspects for improved detection of CNS metastases and differential diagnoses are shown. Material and methods. This review is based on own experience and relevant recent publications. Results. In the diagnosis of CNS metastases contrast-enhanced MRI is the radiological method of choice. The sensitivity can be further increased by increasing contrast medium dose as well as the use of various magnetization transfer techniques. Functional MRI techniques, such as magnetic resonance spectroscopy, perfusion and diffusion-weighted imaging, diffusion tensor imaging and dynamic contrast-enhanced imaging can further improve the differential diagnosis and detection of recurrent disease. If CT is used for diagnostics of cerebral metastases it should be performed with increased contrast combined with a scan delay. Conclusions. Contrast-enhanced MRI ideally using a multimodal protocol is the most sensitive method for the detection of CNS metastases and should therefore be preferred to CT. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Computed tomography; Contrast medium; Magnetic resonance imaging; Metastasis

Radiopacity of intracerebral hemorrhage correlates with perihemorrhagic edema - Wagner, Irina; Volbers, Bastian; Hilz, Max-Josef; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background: Experimental evidence indicates that iron plays a key role in edema formation after intracerebral hemorrhage (ICH). We investigated the relationship between ICH radiopacity on CT as a marker of hematoma iron content and perihemorrhagic edema (PHE) after ICH. Methods: We retrospectively investigated patients with spontaneous lobar and ganglionic supratentorial ICH who received follow-up CT scans during the first 7days after symptom onset (d1, d2-4, d5-7). Measurements of ICH and edema volumes were taken using a semiautomatic threshold-based volumetric algorithm. Radiopacity of the blood clot was determined using the mean Hounsfield unit (HU) count of the ICH. Results: A total of 117 patients aged 71.92±11.55years with spontaneous ICH (34.63±32.44ml) were included in the analysis. Mean ICH radiopacity was 59.7±3.4HU. We found significantly larger relative PHE at d2-4 (1.7±0.9 vs. 1.3±0.8; P=0.032) and d5-7 (2.0±1.3 vs. 1.3±0.9; P=0.007) and larger peak relative PHE (2.3±1.6 vs. 1.6±1.1; P=0.006) in patients with ICH radiopacity >60HU (n=59), as compared to patients with ICH radiopacity <60HU (n=58). Conclusions: Higher ICH radiopacity, reflecting higher in vivo hematoma iron content, is associated with more PHE after ICH. © 2011 The Author(s). European Journal of Neurology © 2011 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Intracerebral hemorrhage; Perihemorrhagic edema; Radiopacity

Radiostereometric migration measurement of an uncemented Cerafit® femoral stem: 26 patients followed for 10 years - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Tschunko, Franz (Biomedizinische Technik, 2017)
Radiostereometric analysis (RSA) is the gold standard for evaluating micromotions of orthopaedic implants. The method is applied for identifying novel design weaknesses in endoprostheses. Current research frequently assesses relatively short time periods. Short-term RSA studies have been widely used for predicting the long-term stability of many hip prosthetic designs, but only a few studies have focused on uncemented hip implants, especially for extended periods. The purpose of this study was to analyse the migration pattern of the Cerafit® femoral stem within 10 years and to verify the predictive value of short-term RSA after 2 years for this uncemented femoral hip stem. Twenty-six patients were followed for 10 years. Ten years after implantation, a mean subsidence of 0.22 mm±0.56 mm, a mean internal rotation of 0.59°±1.67° and a mean maximum total point motion (MTPM) of 1.28 mm±0.54 mm were detected. The main migration took place in the first 6 weeks after surgery (subsidence of 0.36 mm±0.73 mm; internal rotation of 0.62°±1.49°, MTPM of 1.05 mm±0.68 mm). All the migration values measured were small. No late-onset migration was observed. This study suggests that the Cerafit® implants are stable after 10 years. Thus, RSA could be the best tool to assess long-term implant behaviour.
EVALuna2:33711

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Real-Time, In Vivo Monitoring, and Quantitative Assessment of Intra-Arterial Vasospasm Therapy - Gölitz, Philipp; Kaschka, Iris; Lang, Stefan; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd (Neurocritical Care, 2016)
Our study aimed to evaluate whether the effect of an intra-arterial vasospasm therapy can be assessed quantitatively by in vivo blood flow analysis using the postprocessing algorithm parametric color coding (PCC).We evaluated 17 patients presenting with acute clinical deterioration due to vasospasm following subarachnoidal hemorrhage treated with intra-arterial nimodipine application. Pre- and post-interventional DSA series were post-processed by PCC. The relative time to maximum opacification (rTmax) was calculated in 14 arterially and venously located points of interest. From that data, the pre- and post-interventional cerebral circulation time (CirT) was calculated. Additionally, the arterial vessel diameters were measured. Pre- and post-interventional values were compared and tested for significance, respectively.Flow analysis revealed in all arterial vessel segments a non-statistically significant prolongation of rTmax after treatment. The mean CirT was 5.62 s (±1.19 s) pre-interventionally and 5.16 s (±0.81 s) post-interventionally, and the difference turned out as statistically significant (p = 0.039). A significantly increased diameter was measurable in all arterial segments post-interventionally.PCC is a fast applicable imaging technique that allows via real-time and in vivo blood flow analysis a quantitative assessment of the effect of intra-arterial vasospasm therapy. Our results seem to validate in vivo that an intra-arterial nimodipine application induces not only vasodilatation of the larger vessels, but also improves the microcirculatory flow, leading to a shortened cerebral CirT that reaches normal range post-interventionally. Procedural monitoring via PCC offers the option to compare quantitatively different therapy regimes, which allows optimization of existing approaches and implementation of individualized treatment strategies.
EVALuna2:22520

Real world application of ocrelizumab in multiple sclerosis: Single-center experience of 128 patients - Prockl, Victoria; Nickel, Franziska; Utz, Kathrin S.; Fröhlich, Kilian; Engelhorn, Tobias; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf; Huhn, Konstantin (Journal of the Neurological Sciences, 2020)
Background: Pivotal trials showed good clinical efficiency of the monoclonal antibody ocrelizumab while being well tolerated and manageable in multiple sclerosis (MS). However, data on adverse events in everyday practice are scarce. Hence, our study aims at investigating short-term tolerability of ocrelizumab in a “real-world” setting. Methods: In this retrospective cohort study, data of 128 (86 relapsing-remitting, 42 progressive) MS patients at initiation of ocrelizumab were analyzed at the MS center of the University of Erlangen, Germany. Additionally, follow-up data of 68 patients at 6-months retreatment were analyzed. Structured phone interviews were applied after ocrelizumab initiation to report undocumented side effects. Results: Patients predominantly switched from monoclonal antibodies (46%), orals (20%), injectables (10%), steroids or immunosuppressants (each 8%), with a mean interval of 9.0 months after the last application of the previous immunotherapy. Applying a combined premedication with steroids, antihistamines and antipyretics for >90% of patients, ocrelizumab treatment was well tolerated and mainly comprised mild (n = 59/128 at initiation, n = 5/68 at 6 months retreatment) and rarely moderate (n = 7/128 at initiation, n = 2/68 at 6 months) side effects. Predominantly mild infusion related reactions (IRR) were reported with a declining percentage over the follow-up applications. Infections occurred rarely. No severe side effects were observed. Secondary, treatment appeared efficient when looking at clinical surrogates of stable disease. Discussion: Our study delineates good short-term tolerability of ocrelizumab in a miscellaneous “real-world” MS cohort. Additional studies are warranted to confirm these beneficial findings and to reveal safety concerns in the longer-term follow-up.
CRIS-Team Scopus Importer:2020-06-26
Keywords: B-cell depletion; CD 20; Immunomodulatory treatment; Monoclonal antibody; Multiple sclerosis; Ocrelizumab; Side effects

Recurrence of glioblastoma is associated with elevated microvascular transit time heterogeneity and increased hypoxia - Stadlbauer, Andreas; Mouridsen, Kim; Dörfler, Arnd; Hansen, Mikkel Bo; Oberndorfer, Stefan; Zimmermann, Max; Buchfelder, Michael; Heinz, Gertraud; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2018)
Dynamic susceptibility contrast (DSC) perfusion MRI provide information about differences in macro- and microvasculature when executed with gradient-echo (GE; sensitive to macrovasculature) and spin-echo (SE; sensitive to microvasculature) contrast. This study investigated whether there are differences between macro- and microvascular transit time heterogeneity (MVTH and µVTH) and tissue oxygen tension (PO2mit) in newly-diagnosed and recurrent glioblastoma. Fifty-seven patients with glioblastoma (25 newly-diagnosed/32 recurrent) were examined with GE- and SE-DSC perfusion sequences, and a quantitative blood-oxygen-level-dependent (qBOLD) approach. Maps of MVTH, µVTH and coefficient of variation (MCOV and µCOV) were calculated from GE- and SE-DSC data, respectively, using an extended flow-diffusion equation. PO2mit maps were calculated from qBOLD data. Newly-diagnosed and recurrent glioblastoma showed significantly lower ( P ≤ 0.001) µCOV values compared to both normal brain and macrovasculature (MCOV) of the lesions. Recurrent glioblastoma had significantly higher µVTH ( P = 0.014) and µCOV ( P = 0.039) as well as significantly lower PO2mit values ( P = 0.008) compared to newly-diagnosed glioblastoma. The macrovasculature, however, showed no significant differences. Our findings provide evidence of microvascular adaption in the disorganized tumor vasculature for retaining the metabolic demands in stress response of therapeutically-uncontrolled glioblastomas. Thus, µVTH and PO2mit mapping gives insight into the tumor microenvironment (vascular and hypoxic niches) responsible for therapy resistance.
EVALuna2:212789

Reduction of cerebral infarct size by dronedarone - Engelhorn, Tobias; Schwarz, Marc A.; Heusch, Gerd; Dörfler, Arnd; Schulz, Rainer (Cardiovascular Drugs and Therapy, 2011)
In the ATHENA trial, dronedarone reduced the incidence of stroke in patients with atrial fibrillation. Since smaller cerebral infarcts are sometimes asymptomatic, the reduced incidence of stroke might reflect reduction of infarct size (IS) by dronedarone. However, no data on this effect of dronedarone are available.In 60 rats, the middle cerebral artery was occluded (MCAO) for 1 h followed by reperfusion. IS was assessed at day 7. Animals were examined using a neurological 5 points score. Twelve animals served as controls (group A), 12 animals received 30 mg/kg (group B) and 100 mg/kg (group C) dronedarone daily starting 3 days before MCAO; 12 animals received 30 mg/kg (group D) starting 2 h after MCAO. In all groups treatment was maintained until day 7. In 12 additional animals (6 controls, 6 pretreated animals) fractional anisotropy (FA) was assessed using magnetic resonance imaging (MRI).IS in group A was 151 ± 45 mm(3) versus 94 ± 42 mm(3) in group B, 79 ± 29 mm(3) in group C, and 127 ± 51 mm(3) in group D, respectively (B,C,D P < 0.05 vs. A). Neuroscores and weight loss (expressed as percent of initial weight) were less in treatment groups: 1.8 ± 0.6 and 91% in group B, 1.4 ± 0.5 and 93% in group C, and 2.1 ± 0.6 and 89% in group D compared to 2.4 ± 0.5 and 83% in controls (B,C,D P < 0.05 vs. A). FA in the ischemic penumbra was significantly higher in treated than in control animals (0.44 ± 0.2 vs. 0.35 ± 0.17; P < 0.05).Dronedarone administered before and after MCAO reduces IS and improves FA and neurological outcome in transient cerebral ischemia.
EVALuna2:22954

Refined Functional Magnetic Resonance Imaging and Magnetoencephalography Mapping Reveals Reorganization in Language-Relevant Areas of Lesioned Brains - Zimmermann, Max; Rössler, Karl; Kaltenhäuser, Martin; Grummich, Peter; Yang, Bing; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (World Neurosurgery, 2019)
BACKGROUND: Neurosurgical decisions regarding interventions close to brain areas with language-related functions remain highly challenging because of the risk of postoperative dysfunction. To minimize these risks, improvements in the preoperative mapping of language-related regions are required, especially as space-occupying lesions often lead to altered cortical topography and language area reorganization. METHODS: The degree of deviation and language area reorganization were investigated in 26 functional magnetic resonance imaging- and magnetoencephalography-dissociable cortical sub-areas displaying language-related activations in each of 18 patients with brain lesions and 3 healthy volunteers (during visual language tasks). RESULTS: Both modalities showed good congruency of the language areas. The mean spatial distance of the centroids and maxima was 9.06 mm and 10.58 mm, respectively, allowing us to define more specific anatomical positions. Postoperatively, language abilities increased in 11% (2 of 18) of the patients, remained unchanged in 83% (15 of 18) of the patients, and decreased in 6% (1 of 18) of the patients, respectively. Signs of language function reorganization detected on both functional magnetic resonance imaging and magnetoencephalography were present in 29% (5 of 17) of the patients. Attenuation of neurovascular coupling was found postoperatively in 17% (3 of 18) of the patients. Monohemispheric language processing cannot be assumed always in patients with brain lesions. CONCLUSIONS: The more detailed subdivision of language-relevant brain areas shown in this study can help to achieve more radical tumor resection without postoperative language deficits.
EVALuna2:212793

Refined Functional Magnetic Resonance Imaging and Magnetoencephalography Mapping Reveals Reorganization in Language-Relevant Areas of Lesioned Brains - Zimmermann, Max; Rössler, Karl; Kaltenhäuser, Martin; Grummich, Peter; Yang, Bing; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (World Neurosurgery, 2020)
Background: Neurosurgical decisions regarding interventions close to brain areas with language-related functions remain highly challenging because of the risk of postoperative dysfunction. To minimize these risks, improvements in the preoperative mapping of language-related regions are required, especially as space-occupying lesions often lead to altered cortical topography and language area reorganization. Methods: The degree of deviation and language area reorganization were investigated in 26 functional magnetic resonance imaging- and magnetoencephalography-dissociable cortical sub-areas displaying language-related activations in each of 18 patients with brain lesions and 3 healthy volunteers (during visual language tasks). Results: Both modalities showed good congruency of the language areas. The mean spatial distance of the centroids and maxima was 9.06 mm and 10.58 mm, respectively, allowing us to define more specific anatomical positions. Postoperatively, language abilities increased in 11% (2 of 18) of the patients, remained unchanged in 83% (15 of 18) of the patients, and decreased in 6% (1 of 18) of the patients, respectively. Signs of language function reorganization detected on both functional magnetic resonance imaging and magnetoencephalography were present in 29% (5 of 17) of the patients. Attenuation of neurovascular coupling was found postoperatively in 17% (3 of 18) of the patients. Monohemispheric language processing cannot be assumed always in patients with brain lesions. Conclusions: The more detailed subdivision of language-relevant brain areas shown in this study can help to achieve more radical tumor resection without postoperative language deficits.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Brain tumor; Broca; fMRI; Language; MEG; Reorganization; Wernicke

Reirradiation of recurent glioblastomas: High prognostic significance of contrast-enhancing tumor volume - Mansoorian, Sina; Coras, Roland; Weissmann, Thomas; Lettmaier, Sebastian; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Schmidt, M.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Respiratory Motion Compensation for C-arm CT Liver Imaging - Sindel, Aline; Bögel, Marco; Maier, Andreas; Fahrig, Rebecca; Hornegger, Joachim; Dörfler, Arnd (Bildverarbeitung für die Medizin 2015, 2015)
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD5.respir

Retinal microangiopathy in arterial hypertension as an early marker of a cerebral macroangiopathy - Michelson, Georg; Engelhorn, Tobias; Dörfler, Arnd (Deutsche Medizinische Wochenschrift, 2011)
A 54-year-old man reported having had nonspecific attacks of dizziness. His BMI was 27.7. Since 11 years he had been treated for arterial hypertension and had received oral medication for type 2 diabetes for one year. The latest blood pressure value was 134/109 mm Hg during treatment with a combination of atenolol, chlortalidone und hydralazine-HCl; furthermore hr received simvastatin, metformin, glimepirid und ramipril. A standardized telemedical imaging of the retina ("talkingeyes (®) ") was undertaken, revealing focal and generalized arteriolar narrowing of the retinal vessels and a retinal microinfarction (cotton wool spot) in the right eye. The arterial/venous ratio was decreased to 0.74 in the right and 0.77 in the left eye.Optical coherence tomographie (OCT) revealed an ischemic microinfarction of the retina with marked axonal swelling. The digital subtraction angiography of the cerebral vessels revealed a 40 % stenosis of the right internal carotid artery and a proximal, highgrade stenosis of the basilary artery.Angioplasty with stent insertion of the basilary artery was performed. Long-term observation showed no restenosis and a reduction in the size of the the retinal microinfarct.Retinal microinfarctions denote localized retinal areas of hypoxia and underperfusion. They may act as markers of a generalized micro- and macroangiopathy. Patients with severe retinal microangiopathic changes should be examined thoroughly to detect early macroangiopathic changes. These can be treated by interventional procedures thus avoiding irreversible end-organ damages.
EVALuna2:21059

Rheumatoid vasculitis of the central nervous system - Lee, D. H.; Blinzler, C.; Stöckl, Thomas; Engelhorn, Tobias; Buslei, R.; Schwab, Sibylle; Linker, Ralf (Der Nervenarzt, 2015)
EVALuna2:7259

Robust blood flow velocity estimation from 3D rotational angiography - Bögel, Marco; Gehrisch, S.; Redel, T.; Rohkohl, C.; Birkhold, A.; Hölter, Philip; Maier, Andreas; Kowarschik, M.; Dörfler, Arnd (Proceedings - International Conference on Image Processing, ICIP, 2018)
Blood flow velocity estimation techniques from 2D fluoroscopy and more recently rotational angiography images represent a topic of wide interest in various clinical research areas. In particular, they can be an important step towards patient-specific flow simulations. Additionally, it can be of diagnostic interest to evaluate volumetric blood flow in stenotic vessel segments; e.g. in a patient's brain. In this work, we present a robust optimization-based approach to estimate mean blood flow velocities from rotational digital subtraction angiography (DSA) images. Our method was extensively evaluated on 70 simulated datasets and 6 clinical datasets with MR phase contrast ground truth data. Our evaluation explores the limitations of image-based velocity estimation; i.e., measurements over short or small vessel segments. Overall, we were able to estimate the mean velocity with average errors as little as 4% for simulation studies, if the vessel segment is sufficiently long, and achieved results within the confines of the MR phase contrast ground truth data for our clinical data, with an average relative error to the centerline measurement of 9.5%±10.5%. The achieved accuracy enables patient-specific hemodynamic simulations and may also be of immediate diagnostic interest.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Angiography; Contrast medium; Flow quantification; Velocity estimation

Safety and Efficacy of a 3-Dimensional Stent Retriever With Aspiration-Based Thrombectomy vs Aspiration-Based Thrombectomy Alone in Acute Ischemic Stroke Intervention: A Randomized Clinical Trial - Nogueira, Raul G.; Frei, Donald; Kirmani, Jawad F.; Zaidat, Osama; Lopes, Demetrius; Turk, Aquilla S.; Heck, Donald; Mason, Brian; Haussen, Diogo C.; Levy, Elad I.; Mehta, Siddhart; Lazzaro, Marc; et al. (JAMA Neurology, 2018)
Importance: The treatment effects of individual mechanical thrombectomy devices in large-vessel acute ischemic stroke (AIS) remain unclear. Objective: To determine whether the novel 3-dimensional (3-D) stent retriever used in conjunction with an aspiration-based mechanical thrombectomy device (Penumbra System; Penumbra) is noninferior to aspiration-based thrombectomy alone in AIS. Design, Setting, and Participants: This randomized, noninferiority clinical trial enrolled patients at 25 North American centers from May 19, 2012, through November 19, 2015, with follow-up for 90 days. Adjudicators of the primary end points were masked to treatment allocation. Patients with large-vessel intracranial occlusion AIS presenting with a National Institutes of Health Stroke Scale (NIHSS) score of at least 8 within 8 hours of onset underwent 1:1 randomization to 3-D stent retriever with aspiration or aspiration alone. The primary analyses were conducted in the intention-to-treat population. Interventions: Mechanical thrombectomy using intracranial aspiration with or without the 3-D stent retriever. Main Outcomes and Measures: The primary effectiveness end point was the rate of a modified Thrombolysis in Cerebral Infarction (mTICI) grade of 2 to 3 with a 15% noninferiority margin. Device- and procedure-related serious adverse events at 24 hours were the primary safety end points. Results: Of 8082 patients screened, 198 patients were enrolled (111 women [56.1%] and 87 men [43.9%]; mean [SD] age, 66.9 [13.0] years) and randomized, including 98 in the 3-D stent retriever with aspiration group and 100 in the aspiration alone group; an additional 238 patients were eligible but not enrolled. The median baseline NIHSS score was 18.0 (interquartile range, 14.0-23.0). Eighty-two of 94 patients in the 3-D stent retriever and aspiration group (87.2%) had an mTICI grade of 2 to 3 compared with 79 of 96 in the aspiration alone group (82.3%; difference, 4.9%; 90% CI, -3.6% to 13.5%). None of the other measures were significantly different between the 2 groups. Device-related serious adverse events were reported by 4 of 98 patients in the 3-D stent retriever with aspiration group (4.1%) vs 5 of 100 patients in the aspiration only group (5.0%); procedure-related serious adverse events, 10 of 98 (10.2%) vs 14 of 100 (14.0%). A 90-day modified Rankin Scale score of 0 to 2 was reported by 39 of 86 patients in the 3-D stent retriever with aspiration group (45.3%) vs 44 of 96 patients in the aspiration only group (45.8%). Conclusions and Relevance: The present study provides class 1 evidence for the noninferiority of the 3-D stent retriever with aspiration vs aspiration alone in AIS. Future trials should evaluate whether these results can be generalized to other stent retrievers. Trial Registration: clinicaltrials.gov Identifier: NCT01584609.
EVALuna2:34023

Segmentation of Cerebral Vasculature - Alicioglu, Yesim; Spiegel, Martin; Wimmer, Andreas; Struffert, Tobias; Hornegger, Joachim; Dörfler, Arnd (Proceedings of the 5th Russian-Bavarian Conference on Biomedical Engineering, 2009)

Seizures among long-term survivors of conservatively treated ICH patients: incidence, risk factors, and impact on functional outcome - Madzar, Dominik; Kuramatsu, Joji; Gollwitzer, Stephanie; Lücking, Hannes; Kloska, Stephan; Hamer, Hajo; Köhrmann, Martin; Huttner, Hagen (Neurocritical Care, 2014)
Seizures are a common complication after intracerebral hemorrhage (ICH) but there is a substantial lack of information on the long-term incidence in ICH survivors and whether post-ICH seizures affect functional long-term outcome.Over a five-year period 464 consecutive patients with spontaneous ICH were analyzed. Focussing on 1-year ICH survivors, clinical, and radiological parameters were retrieved from institutional prospective databases. The occurrence of seizures was categorized as early (<=7 days) or late (>7 days). Functional outcome was assessed by mailed questionnaires and telephone interviews, and was categorized into good vs. poor (mRS: 0-2 vs. 3-5) and favorable vs. unfavorable (mRS: 0-3 vs. 4-5). Multivariate regression models were calculated to investigate risk factors associated with post-ICH seizures including an a priori defined subgroup analysis of lobar ICH patients.Among 203 long-term ICH survivors, 19.7 % developed seizures of which 55 % occurred late. Factors associated with seizures were lobar location (OR 8.10; 95 % CI 3.04-21.59; p < 0.001), sepsis (OR 4.59; 95 % CI 1.20-17.53; p = 0.026), and history of alcohol abuse (OR 3.36; 95 % CI 1.25-9.06; p = 0.017). Subgroup analysis of lobar ICH patients revealed history of alcohol abuse as the only independent predictor of post-ICH seizures (OR 5.22; 95 % CI 1.25-21.78; p = 0.024). Functional long-term outcome among survivors was slightly worse in patients with post-ICH seizures (p = 0.059). In multivariate regression modeling for prediction of poor outcome, the parameter "post-ICH seizures" again reached a statistical trend (p = 0.065), and established parameters such as age, GCS, and hemorrhage volume were independently related to poor outcome.Post-ICH seizures among long-term ICH survivors are common and may contribute to unfavorable functional outcome. Especially lobar ICH patients with a history of alcohol abuse are at risk to develop post-ICH seizures. Therefore, this subgroup may represent a target population for a prophylactic anticonvulsive treatment approach, preferably investigated in a prospective randomized trial.
EVALuna2:22307

Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics - Seuß, Hannes; Dankerl, Peter; Ihle, Matthias; Grandjean, Andrea; Hammon, Rebecca; Kaestle, Nicola; Fasching, Peter; Maier, Christian; Christoph, Jan; Sedlmayr, Martin; Uder, Michael; Hammon, Matthias; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Projects involving collaborations between different institutions require data security via selective de-identification of words or phrases. A semi-automated de-identification tool was developed and evaluated on different types of medical reports natively and after adapting the algorithm to the text structure. Materials and Methods A semi-automated de-identification tool was developed and evaluated for its sensitivity and specificity in detecting sensitive content in written reports. Data from 4671 pathology reports (4105 + 566 in two different formats), 2804 medical reports, 1008 operation reports, and 6223 radiology reports of 1167 patients suffering from breast cancer were de-identified. The content was itemized into four categories: direct identifiers (name, address), indirect identifiers (date of birth/operation, medical ID, etc.), medical terms, and filler words. The software was tested natively (without training) in order to establish a baseline. The reports were manually edited and the model re-trained for the next test set. After manually editing 25, 50, 100, 250, 500 and if applicable 1000 reports of each type re-training was applied. Results In the native test, 61.3 % of direct and 80.8 % of the indirect identifiers were detected. The performance (P) increased to 91.4 % (P25), 96.7 % (P50), 99.5 % (P100), 99.6 % (P250), 99.7 % (P500) and 100 % (P1000) for direct identifiers and to 93.2 % (P25), 97.9 % (P50), 97.2 % (P100), 98.9 % (P250), 99.0 % (P500) and 99.3 % (P1000) for indirect identifiers. Without training, 5.3 % of medical terms were falsely flagged as critical data. The performance increased, after training, to 4.0 % (P25), 3.6 % (P50), 4.0 % (P100), 3.7 % (P250), 4.3 % (P500), and 3.1 % (P1000). Roughly 0.1 % of filler words were falsely flagged. Conclusion Training of the developed de-identification tool continuously improved its performance. Training with roughly 100 edited reports enables reliable detection and labeling of sensitive data in different types of medical reports. Key Points: · Collaborations between different institutions require de-identification of patients' data. · Software-based de-identification of content-sensitive reports grows in importance as a result of 'Big data'. · A de-identification software was developed and tested natively and after training. · The proposed de-identification software worked quite reliably, following training with roughly 100 edited reports. · A final check of the texts by an authorized person remains necessary. Citation Format · Seuss H, Dankerl P, Ihle M et al. Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics. Fortschr Röntgenstr 2017; 189: 661 - 671.
EVALuna2:14623

Severity assessment in maximally treated ICH patients: The max-ICH score - Sembill, Jochen; Gerner, Stefan; Volbers, Bastian; Bobinger, Tobias; Lücking, Hannes; Kloska, Stephan; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, 2017)
As common prognostication models in intracerebral hemorrhage (ICH) are developed variably including patients with early (<24 hours) care limitations (ECL), we investigated its interaction with prognostication in maximally treated patients and sought to provide a new unbiased severity assessment tool.This observational cohort study analyzed consecutive ICH patients (n = 583) from a prospective registry over 5 years. We characterized the influence of ECL on overall outcome by propensity score matching and on conventional prognostication using receiver operating characteristic analyses. We established the max-ICH score based on independent predictors of 12-month functional outcome in maximally treated patients and compared it to existing models.Prevalence of ECL was 19.2% (n = 112/583) and all of these patients died. Yet propensity score matching displayed that 50.7% (n = 35/69) theoretically could have survived, with 18.8% (n = 13/69) possibly reaching favorable outcome (modified Rankin Scale score 0-3). Conventional prognostication seemed to be confounded by ECL, documented by a decreased predictive validity (area under the curve [AUC] 0.67, confidence interval [CI] 0.61-0.73 vs AUC 0.80, CI 0.76-0.83; p < 0.01), overestimating poor outcome (mortality by 44.8%, unfavorable outcome by 10.1%) in maximally treated patients. In these patients, the novel max-ICH score (0-10) integrates strength-adjusted predictors, i.e., NIH Stroke Scale score, age, intraventricular hemorrhage, anticoagulation, and ICH volume (lobar and nonlobar), demonstrating improved predictive accuracy for functional outcome (12 months: AUC 0.81, CI 0.77-0.85; p < 0.01). The max-ICH score may more accurately delineate potentials of aggressive care, showing favorable outcome in 45.4% (n = 214/471) and a long-term mortality rate of only 30.1% (n = 142/471).Care limitations significantly influenced the validity of common prognostication models resulting in overestimation of poor outcome. The max-ICH score demonstrated increased predictive validity with minimized confounding by care limitations, making it a useful tool for severity assessment in ICH patients.
EVALuna2:22564

Sex differences in perihemorrhagic edema evolution after spontaneous intracerebral hemorrhage - Wagner, Irina; Volbers, Bastian; Kloska, Stephan; Schwab, Stefan; Staykov, Dimitre; Dörfler, Arnd (European Journal of Neurology, 2012)
Background and purpose: Clinical data on sex differences in perihemorrhagic edema (PHE) after intracerebral hemorrhage (ICH) are lacking. Methods: Patients with spontaneous supratentorial ICH who had received standard conservative treatment were identified retrospectively. PHE development was assessed over a 14-day period on follow-up CT scans (days 1, 2-4, 5-7, 8-11, and 12-14). ICH and PHE volumes were assessed semiautomatically and compared between men and women. Results: A total of 387 patients (233 men) were included. Starting at days 2-4, women showed lower PHE values (P<0.05;/ days 2-4, 8-11) or a trend toward significance (P≤0.1; days 5-7, 12-14). Conclusions: Female sex may predict lower PHE volumes. © 2012 The Author(s) European Journal of Neurology © 2012 EFNS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Gender; Intracerebral hemorrhage; Perihemorrhagic edema

Sidebands in CEST MR—How to recognize and avoid them - Schüre, Jan-Rüdiger; Weinmüller, Simon; Kamm, Lukas; Herz, Kai; Zaiß, Moritz (Magnetic Resonance in Medicine, 2024)
Purpose: Clinical scanners require pulsed CEST sequences to maintain amplifier and specific absorption rate limits. During off-resonant RF irradiation and interpulse delay, the magnetization can accumulate specific relative phases within the pulse train. In this work, we show that these phases are important to consider, as they can lead to unexpected artifacts when no interpulse gradient spoiling is performed during the saturation train. Methods: We investigated sideband artifacts using a CEST-3D snapshot gradient-echo sequence at 3 T. Initially, Bloch-McConnell simulations were carried out with Pulseq-CEST, while measurements were performed in vitro and in vivo. Results: Sidebands can be hidden in Z-spectra, and their structure becomes clearly visible only at high sampling. Sidebands are further influenced by B0 inhomogeneities and the RF phase cycling within the pulse train. In vivo, sidebands are mostly visible in liquid compartments such as CSF. Multi-pulse sidebands can be suppressed by interpulse gradient spoiling. Conclusion: We provide new insights into sidebands occurring in pulsed CEST experiments and show that, similar as in imaging sequences, gradient and RF spoiling play an important role. Gradient spoiling avoids misinterpretations of sidebands as CEST effects especially in liquid environments including pathological tissue or for CEST resonances close to water. It is recommended to simulate pulsed CEST sequences in advance to avoid artifacts.
CRIS-Team Scopus Importer:2024-02-16
Keywords: artifacts; CEST; gradient spoiling; phase-cycling; pulsed CEST imaging; pulseq-CEST; sidebands

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy - Sembill, Jochen; Knott, Michael; Xu, Mingming; Röder, Sebastian; Hagen, Manuel; Sprügel, Maximilian; Mrochen, Anne; Borutta, Matthias; Hölter, Philip; Engelhorn, Tobias Martin; Rothhammer, Veit; Macha, Kosmas; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: In patients with lobar intracerebral hemorrhage (ICH), etiologic characterization represents a tradeoff between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy (CAA). METHODS: This external validation analyzed 210 consecutive patients with lobar ICH and available CT and MRI studies from a prospective single-center observational cohort study (2006-2015, Longitudinal Cohort Study on ICH Care [UKER-ICH,] NCT03183167). We investigated the interrater variability and diagnostic accuracy of the simplified Edinburgh CT-based criteria for identification of ICH associated with probable CAA according to MRI-based modified Boston criteria as a reference standard. We evaluated the utility of the simplified Edinburgh criteria by decision curve analysis, comparing the theoretical clinical net benefit (weighted benefit-harm at varying threshold probabilities) of the high-risk category (finger-like projections and subarachnoid hemorrhage) for ruling in and the low-risk category (neither finger-like projections nor subarachnoid hemorrhage) for ruling out with the assumptions of no or all patients having CAA (default strategies). RESULTS: Of 210 patients, 70 (33.3%) had high risk, 67 (31.9%) had medium risk, and 73 (34.8%) had low risk for CAA-associated ICH according to simplified Edinburgh CT criteria, showing moderate interrater variability. Discrimination was good (area under the receiver operating characteristics curve 0.74, 95% CI 0.67-0.81) without evidence of poor calibration (Hosmer-Lemeshow, p = 0.54) for validation of MRI-based diagnosis of probable CAA (n = 94 of 210, 44.8%). The rule-in criteria (high risk), had 87.1% (79.3%-92.3%) specificity, and the rule-out criteria (low risk), had 80.9% (71.1%-88.0%) sensitivity. Decision curve analysis suggested a theoretical clinical net benefit for ruling in but not for ruling out probable CAA compared to default strategies. DISCUSSION: Applying the simplified Edinburgh CT criteria during diagnostic workup seems clinically useful and may accurately identify CAA in patients with lobar ICH. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT03183167. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with lobar hemorrhages, the simplified Edinburgh criteria accurately identify those at high risk of CAA.
CRIS-Team Scopus Importer:2022-06-03

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian; Röder, Sebastian; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin Michael; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; et al. (Stroke, 2019)
Background and Purpose- Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods- ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results- Siponimod significantly reduced PHE measured by magnetic resonance imaging (P=0.021) as well as wet-dry method (P=0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group (P=0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score (P=0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod (P=0.037). Mice treated with siponimod showed a reduced weight loss after ICH (P=0.036). Conclusions- Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients.
EVALuna2:204480

Siponimod reduces perihemorrhagic edema and improves neurological outcome in experimental intracerebral hemorrhage - Bobinger, Tobias; Manaenko, A.; Baeurele, T.; Seyler, L.; Nagel, Armin Michael; Engelhorn, Tobias; Dörfler, Arnd; Kuramatsu, J. B.; Schwab, Stefan; Huttner, Hagen (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Site and size of multiple sclerosis lesions predict enhanced or decreased female orgasmic function - Winder, Klemens; Seifert, Frank; Koehn, Julia; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (Journal of Neurology, 2015)
Neuroimaging identified brain areas involved in female orgasm. In women with multiple sclerosis (MS), associations between orgasmic function and the site and size of MS-related magnetic resonance imaging (MRI) changes are undetermined. This study intended to correlate MS-associated cerebral lesion load and location with clinical scores of female orgasmic function. In 50 women with MS (mean age 37.0 ± 9.9 years), we assessed Female Sexual Function Index (FSFI) scores for orgasmic frequency, difficulty and satisfaction. We determined disease duration, Expanded Disability Status Scale (EDSS) scores, and cerebral MS-lesion load and location using T2-weighed 1.5 T MRIs. We correlated FSFI scores for orgasm with patient age, disease duration, EDSS scores, and cerebral MS-lesion load (Spearman rank correlation; significance: p < 0.05). FSFI scores for orgasm correlated inversely with MS-lesion load in the left temporal periventricular white matter and right middle-inferior occipital area, but directly with MS-lesion load in the right frontal primary motor cortex, left prefrontal/inferior frontal cortex, right amygdala, left temporal middle-inferior and fusiform areas, and midbrain. FSFI scores for orgasm did not correlate with patient age, disease duration and EDSS scores (p > 0.05). In conclusion, our results indicate that MS-lesions in left temporal periventricular and right visual association areas deteriorate orgasmic function. In contrast, direct correlations between frontotemporal or midbrain lesions and higher FSFI scores, indicating enhanced or disinhibited orgasmic function, suggest that these brain regions normally buffer orgasmic responses. Moreover, our results indicate that orgasmic dysfunction in women with MS evolves independently of disease duration and physical disability.
EVALuna2:22361

Skin sodium is increased in male patients with multiple sclerosis and related animal models - Huhn, Konstantin; Linz, Peter; Pemsel, Franziska; Michalke, Bernhard; Seyferth, Stefan; Kopp, Christoph; Chaudri, Mohammad Anwar; Rothhammer, Veit; Dörfler, Arnd; Uder, Michael; Nagel, Armin M.; Müller, Dominik N.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Novel MRI techniques allow a noninvasive quantification of tissue sodium and reveal the skin as a prominent compartment of sodium storage in health and disease. Since multiple sclerosis (MS) immunopathology is initiated in the periphery and increased sodium concentrations induce proinflammatory immune cells, the skin represents a promising compartment linking high sodium concentrations and MS immunopathology. We used a 7-T sodium MRI (23Na-MRI) and inductively coupled plasma mass spectrometry to investigate the skin sodium content in two mouse models of MS. We additionally performed 3-T 23Na-MRI of calf skin and muscles in 29 male relapsing-remitting MS (RRMS) patients and 29 matched healthy controls. Demographic and clinical information was collected from interviews, and disease activity was assessed by expanded disability status scale scoring. 23Na-MRI and chemical analysis demonstrated a significantly increased sodium content in the skin during experimental autoimmune encephalomyelitis independent of active immunization. In male patients with RRMS, 23Na-MRI demonstrated a higher sodium signal in the area of the skin compared to age- and biological sex-matched healthy controls with higher sodium, predicting future disease activity in cranial MRI. In both studies, the sodium enrichment was specific to the skin, as we found no alterations of sodium signals in the muscle or other tissues. Our data add to the recently identified importance of the skin as a storage compartment of sodium and may further represent an important organ for future investigations on salt as a proinflammatory agent driving autoimmune neuroinflammation such as that in MS.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Experimental autoimmune encephalomyelitis; Multiple sclerosis; Skin; Sodium magnetic resonance imaging

Snack food as a modulator of human resting-state functional connectivity. - Mendez Torrijos, Andrea; Kreitz, Silke; Ivan, Claudiu-Ionut; Konerth, Laura; Rösch, Julie; Pischetsrieder, Monika; Moll, Gunther; Kratz, Oliver; Dörfler, Arnd; Horndasch, Stefanie; Hess, Andreas (Cns Spectrums, 2018)
OBJECTIVE To elucidate the mechanisms of how snack foods may induce non-homeostatic food intake, we used resting state functional magnetic resonance imaging (fMRI), as resting state networks can individually adapt to experience after short time exposures. In addition, we used graph theoretical analysis together with machine learning techniques (support vector machine) to identifying biomarkers that can categorize between high-caloric (potato chips) vs. low-caloric (zucchini) food stimulation. METHODS Seventeen healthy human subjects with body mass index (BMI) 19 to 27 underwent 2 different fMRI sessions where an initial resting state scan was acquired, followed by visual presentation of different images of potato chips and zucchini. There was then a 5-minute pause to ingest food (day 1=potato chips, day 3=zucchini), followed by a second resting state scan. fMRI data were further analyzed using graph theory analysis and support vector machine techniques. RESULTS Potato chips vs. zucchini stimulation led to significant connectivity changes. The support vector machine was able to accurately categorize the 2 types of food stimuli with 100% accuracy. Visual, auditory, and somatosensory structures, as well as thalamus, insula, and basal ganglia were found to be important for food classification. After potato chips consumption, the BMI was associated with the path length and degree in nucleus accumbens, middle temporal gyrus, and thalamus. CONCLUSION The results suggest that high vs. low caloric food stimulation in healthy individuals can induce significant changes in resting state networks. These changes can be detected using graph theory measures in conjunction with support vector machine. Additionally, we found that the BMI affects the response of the nucleus accumbens when high caloric food is consume
Keywords: Food intake; graph theory; resting state networks; RS-fMRi; snack food; support vector machine

Snapshot CEST++: Advancing rapid whole-brain APTw-CEST MRI at 3 T - Sedykh, Maria; Liebig, Patrick; Herz, Kai; Fabian, Moritz; Mennecke, Angelika; Weinmüller, Simon; Schmidt, Manuel; Dörfler, Arnd; Zaiß, Moritz (NMR in Biomedicine, 2023)
APTw CEST MRI suffers from long preparation times and consequently long acquisition times ( 5 min). Recently, a consensus on the preparation module for clinical APTw CEST at 3 T was found in the community, and we present a fast whole-brain APTw CEST MRI sequence following this consensus preparation of pulsed RF irradiation of 2 s duration at 90% RF duty-cycle and a B1,rms of 2 μT. After optimization of the snapshot CEST approach for APTw imaging regarding flip angle, voxel size and frequency offset sampling, we extend it by undersampled GRE acquisition and compressed sensing reconstruction. This allows 2 mm isotropic whole-brain APTw imaging for clinical research at 3 T below 2 min. With this sequence, a fast snapshot APTw imaging method is now available for larger clinical studies of brain tumors.
CRIS-Team Scopus Importer:2023-08-04
Keywords: 3T CEST; APTw; brain tumor; compressed sensing; snapshot CEST

Specific cerebral multiple sclerosis lesions are associated with sympathetic cardiovascular activation - Winder, K.; Linker, R. A.; Seifert, F.; Wang, R.; Lee, D-H.; Engelhorn, Tobias; Dörfler, Arnd; Fröhlich, Katharina; Hilz, M. J. (EUROPEAN JOURNAL OF NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-07-30

Specific Lobar Affection Reveals a Rostrocaudal Gradient in Functional Outcome in Spontaneous Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Möller, Sebastian; Huber, Angelika; Lücking, Hannes; Kloska, Stephan; Madzar, Dominik; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (Stroke, 2017)
Several studies have reported a better functional outcome in lobar intracerebral hemorrhage (ICH) compared with deep location. However, among lobar ICH, a correlation of hemorrhage site-involving the specific lobes-with functional outcome has not been established.Conservatively treated patients with supratentorial ICH, admitted to our hospital over a 5-year period (2008-2012), were retrospectively analyzed. Lobar patients were classified as isolated or overlapping ICH according to affected lobes. Demographic, clinical, and radiological characteristics were recorded and compared among lobar ICH patients using above subclassification. Functional outcome-dichotomized into favorable (modified Rankin Scale, 0-3) and unfavorable (modified Rankin Scale, 4-6)-was assessed after 3 and 12 months. Multivariate regression analysis was performed to identify predictors for favorable outcome.Of overall 553 patients, 260 had lobar ICH. In isolated lobar ICH, median hematoma-volume decreased from rostral (frontal, 22.4 mL [7.3-55.5 mL]) to caudal (occipital, 7.1 mL [5.2-16.4 mL]; P=0.045), whereas the proportion of patients with favorable outcome increased (frontal: 23/63 [36.5%] versus occipital: 10/12 [83.3%]; P=0.003). Patients with overlapping lobar ICH had larger ICH volumes than isolated lobar ICH (overlapping, 48.9 mL [22.6-78.5 mL] versus 15.3 mL [5.0-44.6 mL]; P<0.001) and poorer clinical status on admission (Glasgow Coma Scale and National Institutes of Health Stroke Scale). Correlations with anatomic aspects provided evidence of a rostrocaudal gradient with increasing gray/white-matter ratio and decreasing hematoma-volume and rate of hematoma enlargement from frontal to occipital ICH location. Multivariate analysis revealed affection of occipital lobe (odds ratio, 3.75 [1.38-10.22]) and affection of frontal lobe (odds ratio, 0.52 [0.28-0.94]) to be independent predictors for favorable outcome and unfavorable outcome, respectively.Among patients with lobar ICH radiological and outcome characteristics differed according to location. Especially affection of the frontal lobe was frequent and associated with unfavorable outcome after 3 months.
EVALuna2:22482

Standardized acquisition and post-processing of dynamic susceptibility contrast perfusion in patients with brain tumors, cerebrovascular disease and dementia: comparability of post-processing software - Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Larsson, Elna Marie; Nguyen, Than; Essig, Marco; Dörfler, Arnd; Hölter, Philip (British Journal of Radiology, 2020)
OBJECTIVE: MR-perfusion post-processing still lacks standardization. This study evaluates the results of perfusion analysis with two established software solutions in a large series of patients with different diseases when a highly standardized processing workflow is ensured. METHODS: Multicenter data of 260 patients (80 with brain tumors, 124 with cerebrovascular disease and 56 with dementia examined with the same MR protocol) were analyzed. Raw data sets were processed with two software suites: Olea sphere and NordicICE. Group differences were analyzed with paired t-tests and one-way ANOVA. RESULTS: Perfusion metrics were significantly different for all examined diseases in the unaffected brain for both software suites [ratio cortex/white matter left hemisphere: mean transit time (MTT) 0.991 vs 0.847, p < 0.05; relative cerebral bloodflow (rBF) 3.23 vs 4.418, p < 0.001; relative cerebral bloodvolume (rBVc) 2.813 vs 3.884, p < 0.001; right hemisphere: MTT 1.079 vs 0.854, p < 0.05; rBF 3.262 vs 4.378, p < 0.001; rBVc 2.762 vs 3.935, p < 0.001)]. Perfusion results were also significantly different in patients with stroke (ratio cortex/white matter affected hemisphere: MTT 1.058 vs 0.784; p < 0.001), dementia (ratio cortex/white matter left hemisphere: rBVc 1.152 vs 1.795, p < 0.001; right hemisphere: rBVc 1.396 vs 1.662, p < 0.05) and brain tumors (ratio cortex/whole tumor rBVc: 0.778 vs 0.919, p < 0.001 and ratio cortex/tumor hotspot rBVc: 0.529 vs 0.512, p < 0.05). CONCLUSION: Despite a highly standardized workflow, parametric perfusion maps are depended on the chosen software. Radiologists should consider software related variances when using dynamic susceptibility contrast perfusion for clinical imaging and research. ADVANCES IN KNOWLEDGE: This multicenter study compared perfusion parameters calculated by two commercial dynamic susceptibility contrast perfusion post-processing software solutions in different central nervous system disorders with a large sample size and a highly standardized processing workflow. Despite, parametric perfusion maps are depended on the chosen software which impacts clinical imaging and research.
CRIS-Team Scopus Importer:2019-12-24

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Stent-Assisted Coiling Using Leo+ Baby Stent: Immediate and Mid-Term Results - Lücking, Hannes; Struffert, Tobias; Gölitz, Philipp; Engelhorn, Tobias; Brandner, Sebastian; Kuramatsu, Joji; Lang, Stefan; Schmidt, Manuel; Dörfler, Arnd (Clinical Neuroradiology, 2020)
Background: Stent-assisted coiling is well-established for treatment of cerebral aneurysms. The technique enables treatment of wide-neck, bifurcation and recurrent aneurysms with high packing rates. While described in extenso for laser cut stents, the results of patients treated with the Leo+ Baby (Balt, Montmorency, France) braided microstent are presented. Material and Methods: Patients were included if treated with a Leo+ Baby and with digital subtraction angiography (DSA) follow-up available of at least 6 months. Data were evaluated for successful deployment, aneurysm occlusion according to the modified Raymond-Roy classification (MRRC), stent patency and procedure-related morbidity and mortality. Results: A total of 81 patients were included and Leo+ Baby deployment was successful in all cases. Coils were used in 80 cases. In 1 case 2 stents were used stent-in-stent without additional coiling. Initial aneurysm occlusion rates were MRRCi1 51.9%, MRRCi2 11.1%, MRRCi3a 24.7% and MRRCi3b 12.3%. Occlusion rates after 6 months were MRRC6m1 78.9%, MRRC6m2 3.9%, MRRC6m3a 6.6% and MRRC6m3b 10.5%. Procedure-related morbidity was 1 case of acute stent thrombosis successfully treated with tirofiban and 1 case with transient hemiparesis due to stent thrombosis after 4 months. There was 1 case of coil-associated subarachnoid hemorrhage (SAH) which caused prolonged hospitalization. No procedure-related mortality was observed. Conclusion: The results confirm that stent-assisted coiling with the Leo+ Baby stent is safe and efficient for treatment of wide neck or recurrent cerebral aneurysms. Spontaneous progressive aneurysm occlusion over 6 months supports the theory of considerable flow-modulating effects of Leo+ Baby.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Bifurcation aneurysm; Braided stent; Cerebral aneurysm; Coiling; Low profile stent

Structural brain imaging - Kälviäinen, Reetta; Dörfler, Arnd (Elsevier B.V., 2012)
CRIS-Team Scopus Importer:2022-08-05

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Successful Surgery of Exophytic Brainstem Glioma Mimicking Cerebellar-Pontine Angle Tumor: Case Report and Review of Literature - Roessler, Karl; Heynold, Elisabeth; Coras, Roland; Lücking, Hannes; Buchfelder, Michael (World Neurosurgery, 2019)
Background: Nontectal plate exophytic brainstem gliomas with pilocytic histology are rare and occur mainly in children. Because of their eloquent location, therapy usually consists of bioptic histologic verification and radiotherapy in case of progression. Case Description: We report on a 43-year-old patient who presented with intermittent tinnitus and reduced hearing in his left ear, as well as a slight left-sided ataxia. Magnetic resonance imaging revealed a left-sided solid cystic cerebellar-pontine angle (CPA) tumor completely obliterating the CPA. Radiologically, a solid cystic vestibular schwannoma was diagnosed. Intraoperatively, a glossy-grayish, intensively bleeding tumor without any capsule or delineation to the brainstem or cranial nerves was resected using electrophysiologic monitoring. Postoperative histology revealed a pilocytic astrocytoma. Three months postoperatively, hearing was preserved (pure tone average—35 dB) and ataxia was equal to what it was preoperatively, gradually becoming better. Postoperative magnetic resonance scans demonstrated a complete resection of the tumor with completely restored brainstem contours. Conclusions: Exophytic brainstem gliomas may occur in the CPA and mimic vestibular schwannoma. Complete resection even with preserved hearing without neurologic deterioration may be feasible.
EVALuna2:204027
Keywords: Cerebellar-pontine angle; Complete resection; Pilocytic astrocytoma; Vestibular schwannoma hearing preservation

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema. - Sehm, Tina; Fan, Zheng; Ghoochani, Ali; Rauh, Manfred; Engelhorn, Tobias; Minakaki, Georgia; Dörfler, Arnd; Klucken, Jochen; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai (Oncotarget, 2016)
The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 µM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induces ferroptotic cell death in glioma cells. There is no evidence for impact on autophagic flux following SAS application. However, SAS can potentiate the efficacy of the standard chemotherapeutic and autophagy-inducing agent temozolomide (Temcat, Temodal or Temodar®). We also investigated SAS in non-transformed cellular constituents of the brain. Neurons and brain tissue are almost non-responding to SAS whereas isolated astrocytes are less sensitive towards SAS toxicity compared to gliomas. In vivo SAS treatment does not affect experimental tumor growth and treated animals revealed comparable tumor volume as untreated controls. However, SAS treatment resulted in reduced glioma-derived edema and, hence, total tumor volume burden as revealed by T2-weighted magnetic resonance imaging. Altogether, we show that SAS can be utilized for targeting the glutamate antiporter xCT activity as a tumor microenvironment-normalizing drug, while crucial cytotoxic effects in brain tumors are minor.

Supratentorial lesions contribute to trigeminal neuralgia in multiple sclerosis - Fröhlich, Katharina; Winder, Klemens; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank (Cephalalgia, 2018)
Background It has been proposed that multiple sclerosis lesions afflicting the pontine trigeminal afferents contribute to trigeminal neuralgia in multiple sclerosis. So far, there are no imaging studies that have evaluated interactions between supratentorial lesions and trigeminal neuralgia in multiple sclerosis patients. Methods We conducted a retrospective study and sought multiple sclerosis patients with trigeminal neuralgia and controls in a local database. Multiple sclerosis lesions were manually outlined and transformed into stereotaxic space. We determined the lesion overlap and performed a voxel-wise subtraction analysis. Secondly, we conducted a voxel-wise non-parametric analysis using the Liebermeister test. Results From 12,210 multiple sclerosis patient records screened, we identified 41 patients with trigeminal neuralgia. The voxel-wise subtraction analysis yielded associations between trigeminal neuralgia and multiple sclerosis lesions in the pontine trigeminal afferents, as well as larger supratentorial lesion clusters in the contralateral insula and hippocampus. The non-parametric statistical analysis using the Liebermeister test yielded similar areas to be associated with multiple sclerosis-related trigeminal neuralgia. Conclusions Our study confirms previous data on associations between multiple sclerosis-related trigeminal neuralgia and pontine lesions, and showed for the first time an association with lesions in the insular region, a region involved in pain processing and endogenous pain modulation.
EVALuna2:34503

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

Symmetric tract-based spatial statistics of patients with left versus right mesial temporal lobe epilepsy with hippocampal sclerosis - Mennecke, Angelika; Rösch, Julie; Kasper, Burkhard; Schmidt, Manuel; Roessler, Karl; Coras, Roland; Hamer, Hajo; Dörfler, Arnd; Laun, Frederik Bernd (NeuroReport, 2018)
This study aims to investigate the diffusion metrics of left versus right temporal lobe epilepsy in a well-defined subgroup of patients with mesial temporal lobe epilepsy (mTLE) because of unilateral hippocampal sclerosis while taking into account interhemispheric differences. Eighteen patients with TLE [nine left temporal lobe epilepsy (LTLE) and nine right temporal lobe epilepsy (RTLE)] and a norm group of 36 nonepileptic individuals were scanned with a multiband accelerated diffusion tensor imaging protocol at 3T. The scalar diffusion tensor parameters fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) and, after projection on a symmetric skeleton, their hemispheric difference (dFA, dMD, and dRD) were analyzed using tract-based spatial statistics. In the cluster with significantly (P<0.008) different dFA, dMD, and dRD between right TLE and left TLE, the hemispheric difference in the mean scalar indices (dmFA, dmMD, and dmRD) was assessed and tested for differences using a one-way analysis of variance and for correlation with patient age, seizure onset, or duration of epilepsy using Pearson's correlation. Patients with LTLE showed lower dFA, higher dMD, and higher dRD (P<0.008) compared with patients with RTLE in a cluster including parts of the uncinated and inferior longitudinal fasciculus and the inferior fronto-occipital fasciculus. dmFA, dmMD, and dmRD differed significantly between groups (P<10, corrected) and showed no correlation with patient age, seizure onset, or duration of epilepsy. The exclusion of bilateral interindividual variance through the calculation of the hemispheric difference of the diffusion metrics by the symmetric variant of tract-based spatial statistics allows for a sensitive differentiation of LTLE and RTLE with unilateral hippocampal sclerosis.
EVALuna2:34910

Systemic inflammatory response syndrome and long-term outcome after intracerebral hemorrhage - Hagen, Manuel; Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Lücking, Hannes; Hölter, Philip; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, Neuroimmunology and Neuroinflammation, 2019)
ObjectiveTo investigate whether the systemic inflammatory response syndrome (SIRS) without infection as surrogate of a systemic immune response is associated with poor long-term functional outcome in patients with spontaneous intracerebral hemorrhage (ICH).MethodsWe analyzed consecutive patients with spontaneous ICH from our prospective cohort study (2018-2015). SIRS was defined according to standard criteria: i.e., 2 or more of the following parameters during hospitalization: body temperature <36°C or >38°C, respiratory rate >20 per minute, heart rate >90 per minute, or white blood cell count <4,000/L or >12,000/L in the absence of infection. The primary outcome consisted of the modified Rankin Scale (mRS) at 3 and 12 months investigated by adjusted ordinal shift analyses. Bias and confounding were addressed by propensity score matching and multivariable regression models.ResultsOf 780 patients with ICH, 21.8% (n = 170) developed SIRS during hospitalization. Patients with SIRS showed more severe ICH compared with those without; i.e., larger ICH volumes (18.3 cm3, interquartile range [IQR 4.6-47.2 cm3] vs 7.4 cm3, IQR [2.4-18.6 cm3]; p < 0.01), increased intraventricular hemorrhage (57.6%, n = 98/170 vs 24.8%, n = 79/319; p < 0.01), and poorer neurologic admission status (NIH Stroke Scale score 16, IQR [7-30] vs 6, IQR [3-12]; p < 0.01). ICH severity-adjusted analyses revealed an independent association of SIRS with poorer functional outcome after 3 (OR 1.80, 95% CI [1.08-3.00]; p = 0.025) and 12 months (OR 1.76, 95% CI [1.04-2.96]; p = 0.034). Increased ICH volumes on follow-up imaging (OR 1.38, 95% CI [1.01-1.89]; p = 0.05) and previous liver dysfunction (OR 3.01, 95% CI [1.03-10.19]; p = 0.04) were associated with SIRS.ConclusionsIn patients with ICH, we identified SIRS to be predictive of poorer long-term functional outcome over the entire range of mRS estimates. Clinically relevant associations with SIRS were documented for previous liver dysfunction and hematoma enlargement.
CRIS-Team Scopus Importer:2019-10-29

T2-sequence with contrast inversion: diagnostic value in the investigation of gray matter heterotopias - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Hamer, Hajo; Dörfler, Arnd; Engelhorn, Tobias Martin (NeuroReport, 2020)
To compare the diagnostic value of T1-inversion recovery sequence (T1 IR) to that of a T2-sequence with contrast inversion (T2 CI) in the investigation of heterotopias. In this study, we processed a contrast-inverted copy of our coronal T2-sequence of 21 patients with subependymal and subcortical heterotopias on an online picture archiving and communication system workstation. The diagnostic performance of these images was compared with the T1 IR of the same patients by quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), lesion-to-white matter contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content. SNR values of the T2 CI were significantly higher than those of the T1 IR. CNR values of both sequences were similar. No relevant difference was found for lesion conspicuity and level of artifacts. Overall image quality of the T2 CI was rated slightly better by one reader. Both readers voted the images to have the same diagnostic content. Beside the exact depiction of the hippocampus in the high resoluted T2-sequence, its contrast-inverted copy (T2 CI) is also useful in the detection of heterotopias. In conjunction with the MPRAGE or MP2RAGE as a three-dimensional sequence, it could offer an equivalent and time-saving alternative to the T1 IR in the investigation of this type of malformation of cortical development.
CRIS-Team Scopus Importer:2020-05-29

Teaching NeuroImages: Stroke and bilateral visual loss in a young adult: More than coincidence - Volbers, Bastian; Kaldefoss, K.; Bergua, A.; Kloska, Stephan; Schwab, Sibylle; Köhrmann, Martin (Neurology, 2012)
EVALuna2:21072

Technical feasibility of 2D-3D coregistration for visualization of self-expandable microstents to facilitate coil embolization of broad-based intracranial aneurysms: An in vitro study - Richter, Gregor; Pfister, Marcus; Struffert, Tobias; Engelhorn, Tobias; Dölken, Marc; Spiegel, Martin; Hornegger, Joachim; Dörfler, Arnd (Neuroradiology, 2009)
Introduction: The use of self-expandable microstents for treatment of broad-based intracranial aneurysms is widely spread. However, poor fluoroscopic visibility of the stents remains disadvantageous during the coiling procedure. Flat detector angiographic computed tomography (ACT) provides high resolution imaging of microstents even though integration of this imaging modality in the neurointerventional workflow has not been widely reported. Methods: An acrylic glass model was used to simulate the situation of a broad-based sidewall aneurysm. After insertion of a self-expandable microstent, ACT was performed. The resulting 3D dataset of the Microstent was subsequently projected into a conventional 2D fluoroscopic roadmap. This 3D visualization of the stent supported the coil embolization procedure of the in vitro aneurysm. Results: In vitro 2D-3D coregistration with integration of 3D ACT data of a self-expandable microstent in a conventional 2D roadmap is feasible. Conclusions: Unsatisfying stent visibility constrains clinical cases with complex parent vessel anatomy and challenging aneurysm geometry; hence, this technique potentially may be useful in such cases. In our opinion, the clinical feasibility and utility of this new technique should be verified in a clinical aneurysm embolization study series using 2D-3D coregistration. © 2009 Springer-Verlag.

Temporal and Volumetric Denoising via Quantile Sparse Image Prior - Schirrmacher, Franziska; Köhler, Thomas; Endres, Jürgen; Lindenberger, Tobias; Husvogt, Lennart; Fujimoto, James G.; Hornegger, Joachim; Dörfler, Arnd; Maier, Andreas; Hölter, Philip (Medical Image Analysis, 2018)
This paper introduces an universal and structure-preserving regularization term, called quantile sparse image (QuaSI) prior. The prior is suitable for denoising images from various medical imaging modalities. We demonstrate its effectiveness on volumetric optical coherence tomography (OCT) and computed tomography (CT) data, which show different noise and image characteristics. OCT offers high-resolution scans of the human retina but is inherently impaired by speckle noise. CT on the other hand has a lower resolution and shows high-frequency noise. For the purpose of denoising, we propose a variational framework based on the QuaSI prior and a Huber data fidelity model that can handle 3-D and 3-D+t data. Efficient optimization is facilitated through the use of an alternating direction method of multipliers (ADMM) scheme and the linearization of the quantile filter. Experiments on multiple datasets emphasize the excellent performance of the proposed method.<br
UnivIS-Import:2018-09-11:Pub.2018.tech.IMMD.IMMD5.tempor
Keywords: Spatio-temporal denoising; Variational approach; QuaSI prior; ADMM

Tetrahedral and polyhedral mesh evaluation for cerebral hemodynamic simulation–a comparison - Spiegel, Martin; Redel, Thomas; Zhang, Yao; Struffert, Tobias; Hornegger, Joachim; Grossman, Robert G.; Dörfler, Arnd; Karmonik, Christof (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2009)
Computational fluid dynamic (CFD) based on patient-specific medical imaging data has found widespread use for visualizing and quantifying hemodynamics in cerebrovascular disease such as cerebral aneurysms or stenotic vessels. This paper focuses on optimizing mesh parameters for CFD simulation of cerebral aneurysms. Valid blood flow simulations strongly depend on the mesh quality. Meshes with a coarse spatial resolution may lead to an inaccurate flow pattern. Meshes with a large number of elements will result in unnecessarily high computation time which is undesirable should CFD be used for planning in the interventional setting. Most CFD simulations reported for these vascular pathologies have used tetrahedral meshes. We illustrate the use of polyhedral volume elements in comparison to tetrahedral meshing on two different geometries, a sidewall aneurysm of the internal carotid artery and a basilar bifurcation aneurysm. The spatial mesh resolution ranges between 5,119 and 228,118 volume elements. The evaluation of the different meshes was based on the wall shear stress previously identified as a one possible parameter for assessing aneurysm growth. Polyhedral meshes showed better accuracy, lower memory demand, shorter computational speed and faster convergence behavior (on average 369 iterations less).
UnivIS-Import:2017-01-09:Pub.2009.tech.IMMD.IMMD5.tetrah_3

Tetrahedral vs. polyhedral mesh size evaluation on flow velocity and wall shear stress for cerebral hemodynamic simulation - Spiegel, Martin; Redel, Thomas; Zhang, Y. Jonathan; Struffert, Tobias; Hornegger, Joachim; Grossman, Robert G.; Dörfler, Arnd; Karmonik, Christof (Computer Methods in Biomechanics and Biomedical Engineering, 2011)
Haemodynamic factors, in particular wall shear stresses (WSSs) may have significant impact on growth and rupture of cerebral aneurysms. Without a means to measure WSS reliably in vivo, computational fluid dynamic (CFD) simulations are frequently employed to visualise and quantify blood flow from patient-specific computational models. With increasing interest in integrating these CFD simulations into pretreatment planning, a better understanding of the validity of the calculations in respect to computation parameters such as volume element type, mesh size and mesh composition is needed. In this study, CFD results for the two most common aneurysm types (saccular and terminal) are compared for polyhedral- vs. tetrahedral-based meshes and discussed regarding future clinical applications. For this purpose, a set of models were constructed for each aneurysm with spatially varying surface and volume mesh configurations (mesh size range: 5119-258, 481 volume elements). WSS distribution on the model wall and point-based velocity measurements were compared for each configuration model. Our results indicate a benefit of polyhedral meshes in respect to convergence speed and more homogeneous WSS patterns. Computational variations of WSS values and blood velocities are between 0.84 and 6.3% from the most simple mesh (tetrahedral elements only) and the most advanced mesh design investigated (polyhedral mesh with boundary layer). © 2011 Taylor & Francis.

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The annual meeting of the German society of neuroradiology cologne, October 10th to 12th, 2013 - Dörfler, Arnd (Clinical Neuroradiology, 2013)
CRIS-Team Scopus Importer:2022-08-05

The diagnosis, treatment and follow-up of extracranial carotid stenosis: A multidisciplinary German-Austrian guideline based on evidence and consensus Diagnostik, Therapie und Nachsorge der extrakraniellen Carotisstenose: Multidisziplinäre, evidenz- und konsensbasierte deutsch-österreichische Leitlinie - Eckstein, Hans-Henning; Kuehnl, Andreas; Dörfler, Arnd; Kopp, Ina B.; Lawall, Holger; Ringleb, Peter A. (Deutsches Ärzteblatt international, 2013)
Background: Extracranial atherosclerotic lesions of the carotid bifurcation cause 10% to 20% of all cases of cerebral ischemia. Until now, there have been no comprehensive evidence- and consensus-based recommendations for the management of patients with extracranial carotid stenosis in Germany and Austria. Methods: The literature was systematically searched for pertinent publications (1990-2011). On the basis of 182 randomized clinical trials (RCTs) and 308 systematic reviews, 30 key questions were answered and evidence-based recommendations were issued.
CRIS-Team Scopus Importer:2022-08-05

The Effects of a Normal Rate versus a Slow Intervalled Rate of Oral Nutrient Intake and Intravenous Low Rate Macronutrient Application on Psychophysical Function - Two Pilot Studies - Denzer-Lippmann, Melanie; Bachlechner, Stephan; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes; Thürauf, Norbert (Frontiers in Psychology, 2017)
Stomach distension and energy per time are factors influencing satiety. Moreover, different rates of nutrient intake induce different stomach distension. The goal of our studies was to elucidate the influence of different oral rates of nutrient intake (normal rate versus slow intervalled rate; study I) and intravenous low rate macronutrient application (protein, carbohydrate, fat) or placebo (study II) on psychophysical function. The pilot studies investigated the effects of 1) study I: a mixed nutrient solution (1/3 protein, 1/3 fat, 1/3 carbohydrates) 2) study II: intravenous macronutrient infusions (protein, carbohydrate, fat) or placebo on psychophysical function (mood, hunger, food craving, alertness, smell intensity ratings and hedonic ratings) in human subjects. In study I 10 male subjects (age range: 21-30 years) completed the study protocol participating in both test conditions and in study II 20 male subjects (age range: 19-41 years) completed the study protocol participating in all test conditions. Additionally, metabolic function was analyzed and cognitive and olfactory tests were conducted twice starting 100 min before the beginning of the intervention and 240 min after. Psychophysical (mood, hunger, fat-, protein-, carbohydrate-, sweets- and vegetable-craving), alertness and metabolic function tests were performed seven times on each examination day. Greater effects on hunger and food cravings were observed for normal rate of intake compared to slow intervalled rate of intake and intravenous low rate macronutrient application. Our findings potentially confirm that volume of the food ingested and a higher rate of energy per time contribute to satiety during normal rate of food intake, while slow intervalled rate of food intake and intravenous low rate macronutrient application showed no effects on satiation. Our results motivate the view that a certain amount of volume of the food ingested and a certain energy per time ratio are necessary to reduce hunger and food craving.
EVALuna2:33741
Keywords: food ingestion; food intake; rate of food intake; psychophysical function; food craving; parenteral food administration; parenteral food intake

The Effects of Different Isocaloric Oral Nutrient Solutions on Psychophysical, Metabolic, Cognitive, and Olfactory Function in Young Male Subjects - Bachlechner, Stephan; Denzer-Lippmann, Melanie Y.; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes; Thürauf, Norbert (Frontiers in Psychology, 2017)
Food intake influences human cognition, olfaction, hunger, and food craving. However, little research has been done in this field to elucidate the effects of different nutrients. Thus, the goal of our study was to investigate the effects of oral ingestion of different nutrient solutions on olfactory, cognitive, metabolic and psychophysical function. Twenty healthy men participated in our study employing a double-blind, cross-over, repeated measurement design. Participants were tested on four different study days. Each day participants received, in randomized order, one of three isocaloric (protein, carbohydrate or fat 600 kcal, 1,500mL) solutions or a placebo. Olfactory and cognitive tests (monitoring only) were conducted three times, i.e., 60min before the beginning of nutrient intake, following oral ingestion of the solution and 60, and 240min after. Psychophysical and metabolic function tests (active grehlin, desacyl ghrelin, insulin, glucagon, glucose, triglyceride, urea) were performed 7 times on each examination day (observation period: -60min, 0 = solution intake, +60, +120, +180, +240, and +300min). Ratings of hunger and food craving significantly differed over the observation period with lowest ratings following application of the protein solution. Highest ratings of craving were found following placebo intake. We further observed a significant positive correlation of active grehlin with hunger and fat, protein and sweets craving for each nutrient solution. Active grehlin significantly correlated with carbohydrate craving for carbohydrate and fat solution and with vegetable craving for fat solution only. Hunger hormone levels, hunger and food craving ratings demonstrated that the hierarchical order that appears in satiating efficiencies of isovolumetric-isocaloric ingested macronutrients is protein > fat > carbohydrate. Our study reveals that the type of nutrient exerts a significant influence on metabolic parameters, hunger and food craving.
Keywords: food ingestion; food intake; oral intake; olfaction; psychophysical function

The effects of RF coils and SAR supervision strategies for clinically applicable nonselective parallel-transmit pulses at 7 T - Herrler, Jürgen; Williams, Sydney N.; Liebig, Patrick; Ding, Belinda; McElhinney, Paul; Allwood-Spiers, Sarah; Meixner, Christian R.; Gunamony, Shajan; Nagel, Armin Michael; Dörfler, Arnd; Gumbrecht, Rene; Porter, David A.; et al. (Magnetic Resonance in Medicine, 2023)
Purpose: To investigate the effects of using different parallel-transmit (pTx) head coils and specific absorption rate (SAR) supervision strategies on pTx pulse design for ultrahigh-field MRI using a 3D-MPRAGE sequence. Methods: The PTx universal pulses (UPs) and fast online-customized (FOCUS) pulses were designed with pre-acquired data sets (B0, B1+ maps, specific absorption rate [SAR] supervision data) from two different 8 transmit/32 receive head coils on two 7T whole-body MR systems. For one coil, the SAR supervision model consisted of per-channel RF power limits. In the other coil, SAR estimations were done with both per-channel RF power limits as well as virtual observation points (VOPs) derived from electromagnetic field (EMF) simulations using three virtual human body models at three different positions. All pulses were made for nonselective excitation and inversion and evaluated on 132 B0, B1+, and SAR supervision datasets obtained with one coil and 12 from the other. At both sites, 3 subjects were examined using MPRAGE sequences that used UP/FOCUS pulses generated for both coils. Results: For some subjects, the UPs underperformed when simulated on a different coil from which they were derived, whereas FOCUS pulses still showed acceptable performance in that case. FOCUS inversion pulses outperformed adiabatic pulses when scaled to the same local SAR level. For the self-built coil, the use of VOPs showed reliable overestimation compared with the ground-truth EMF simulations, predicting about 52% lower local SAR for inversion pulses compared with per-channel power limits. Conclusion: FOCUS inversion pulses offer a low-SAR alternative to adiabatic pulses and benefit from using EMF-based VOPs for SAR estimation.
CRIS-Team Scopus Importer:2023-01-20
Keywords: fast online customized (FOCUS) pulses; parallel transmission (pTx); radiofrequency (RF) coils; UHF MRI; universal pulses (UPs); virtual observation points (VOPs)

The FRED for Cerebral Aneurysms of the Posterior Circulation: A Subgroup Analysis of the EuFRED Registry - Griessenauer, C. J.; Möhlenbruch, M. A.; Hendrix, P.; Ulfert, C.; Islak, C.; Sonnberger, M.; Engelhorn, Tobias; Müller-Thies-Broussalis, E.; Finkenzeller, T.; Holtmannspötter, M.; Buhk, J. H.; Reith, W.; et al. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Flow diversion for the posterior circulation remains a promising treatment option for selected posterior circulation aneurysms. The Flow-Redirection Intraluminal Device (FRED) system has not been previously assessed in a large cohort of patients with posterior circulation aneurysms. The purpose of the present study was to assess safety and efficacy of FRED in this location. MATERIALS AND METHODS: Consecutive patients with posterior circulation aneurysms treated at 8 centers participating in the European FRED study (EuFRED) between April 2012 and January 2019 were retrospectively reviewed. Complication and radiographic and functional outcomes were evaluated. RESULTS: Eighty-four patients (median age, 54 years) with 84 posterior circulation aneurysms were treated with the FRED. A total of 25 aneurysms (29.8%) had previously ruptured, even though most aneurysms were diagnosed incidentally (45.2%). The intradural vertebral artery was the most common location (50%), and saccular, the most common morphology (40.5%). The median size was 7 mm. There were 8 (9.5%) symptomatic thromboembolic and no hemorrhagic complications. Thromboembolic complications occurred mostly (90.9%) in nonsaccular aneurysms. On last follow-up at a median of 24 months, 78.2% of aneurysms were completely occluded. Functional outcome at a median of 27 months was favorable in 94% of patients. All mortalities occurred in patients with acute subarachnoid hemorrhage and its sequelae. CONCLUSIONS: The largest cohort of posterior circulation aneurysms treated with the FRED to date demonstrated favorable safety and efficacy profiles of the device for this indication. Treatment in the setting of acute subarachnoid hemorrhage was strongly related to mortality, regardless of whether procedural complications occurred.
CRIS-Team Scopus Importer:2020-04-28

The FRESH Study: Treatment of Intracranial Aneurysms with the New FRED X Flow Diverter with Antithrombotic Surface Treatment Technology-First Multicenter Experience in 161 Patients - Vollherbst, D. F.; Lücking, Hannes; Duplessis, J.; Sonnberger, M.; Maurer, C.; Kocer, N.; Killer-Oberpfalzer, M.; Rautio, R.; Valvassori, L.; Berlis, A.; Gasser, S.; Gatt, S.; et al. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Flow diverters with antithrombotic coatings are increasingly used to improve the safety of flow diverter treatments of intracranial aneurysms. This study aimed to investigate the safety and short-term efficacy of the new FRED X flow diverter. MATERIALS AND METHODS: Medical charts and procedural and imaging data of a consecutive series of patients with intracranial aneurysms who were treated with the FRED X at 9 international neurovascular centers were retrospectively analyzed. RESULTS: One hundred sixty-one patients (77.6% women; mean age, 55 years) with 184 aneurysms (11.2% acutely ruptured) were included in this study. Most aneurysms were located in the anterior circulation (77.0%), most frequently at the ICA (72.7%). The FRED X was successfully implanted in all procedures. Additional coiling was performed in 29.8%. In-stent balloon angioplasty was necessary in 2.5%. The rate of major adverse events was 3.1%. Thrombotic events occurred in 7 patients (4.3%) with 4 intra- and 4 postprocedural in-stent thromboses, respectively (1 patient had both peri- and postprocedural thrombosis). Of these thrombotic events, only 2 (1.2%) led to major adverse events (ischemic strokes). Postinterventional neurologic morbidity and mortality were observed in 1.9% and 1.2%, respectively. The rate of complete aneurysm occlusion after a mean follow-up of 7.0 months was 66.0%. CONCLUSIONS: The new FRED X is a safe and feasible device for aneurysm treatment. In this retrospective multicenter study, the rate of thrombotic complications was low, and the short-term occlusion rates are satisfactory.
CRIS-Team Scopus Importer:2023-04-21

The hyperintense acute reperfusion marker on fluid-attenuated inversion recovery magnetic resonance imaging is caused by gadolinium in the cerebrospinal fluid - Köhrmann, Martin; Struffert, Tobias; Frenzel, Thomas; Schwab, Stefan; Dörfler, Arnd (Stroke, 2012)
Background and PurposeS-: The hyperintense acute reperfusion marker (HARM) on fluid-attenuated inversion recovery MRI is believed to be caused by gadolinium-based contrast agents crossing a disrupted blood-brain barrier. However, this hypothesis has never been directly verified in humans. Methods-: In this study, we analyzed cerebrospinal fluid samples of patients with HARM on imaging regarding the presence and concentration of gadolinium-based contrast agents. Results-: Gadobutrol was found in concentrations of approximately 50 μmol/L. Using phantom MRI experiments, we demonstrate that the detected concentrations are consistent with the observed HARM imaging pattern. Conclusions-: Our study yields first direct evidence in humans that the imaging phenomenon HARM is indeed caused by leakage of gadolinium-based contrast agents into the cerebrospinal fluid. © 2011 American Heart Association. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: FLAIR; hyperintensive acute reperfusion marker; MRI

The Impact of Burst Motor Cortex Stimulation on Cardiovascular Autonomic Modulation in Chronic Pain: A Feasibility Study for a New Approach to Objectively Monitor Therapeutic Effects - Borutta, Matthias; Köhn, Julia; Souza de Oliveira, Daniela; Del Vecchio, Alessandro; Engelhorn, Tobias; Schwab, Stefan; Buchfelder, Michael; Kinfe, Thomas Mehari (Pain and Therapy, 2023)
Introduction: Chronic refractory pain of various origin occurs in 30–45% of pain patients, and a considerable proportion remains resistant to pharmacological and behavioral therapies, requiring adjunctive neurostimulation therapies. Chronic pain is known to stimulate sympathetic outflow, yet the impact of burst motor cortex stimulation (burstMCS) on objectifiable autonomic cardiovascular parameters in chronic pain remains largely unknown. Methods: In three patients with chronic pain (2 facial pain/1 post-stroke pain), we compared pain intensity using a visual analog scale (VAS 1–10) and parameters of autonomic cardiovascular modulation at supine rest, during parasympathetic challenge with six cycles per minute of metronomic deep breathing, and during sympathetic challenge (active standing) at baseline and after 4 months of burstMCS compared to age-/gender-matched healthy controls. Results: While two out of three patients were responsive after 4 months of adjunctive burstMCS (defined as pain reduction of > 30%), no differences were found in any of the three patients regarding the R-R intervals of adjacent QRS complexes (RRI, 642 vs. 676 ms) and blood pressure (BP, 139/88 vs. 141/90 mmHg). Under resting conditions, parameters of parasympathetic tone [normalized units of high-frequency oscillations of RRI (RRI-HFnu power) 0.24 vs. 0.38, root-mean-square differences of successive RRI (RRI-RMSSD) 7.7 vs. 14.7 ms], total autonomic cardiac modulation [RRI total power 129.3 vs. 406.2 ms2, standard deviation of RRI (RRI-SD) 11.6 vs. 18.5 ms, coefficient of variation of RRI (RRI-CV) 1.9 vs. 3.7%], and baroreceptor reflex sensitivity (BRS, 1.9 vs. 2.3 ms/mmHg) increased, and parameters of sympathetic tone [normalized units of low-frequency oscillations of RRI (RRI-LFnu power) 0.76 vs. 0.62] and sympatho-vagal balance [ratio of RR-LF to RRI-HF power (RRI-LF/HF ratio) 3.4 vs. 1.9] decreased after 4 months of burstMCS. Low-frequency oscillations of systolic blood pressure (SBP-LF power), a parameter of sympathetic cardiovascular modulation, increased slightly (17.6 vs. 20.4 mmHg2). During parasympathetic stimulation, the expiratory–inspiratory ratio (E/I ratio) increased slightly, while upon sympathetic stimulation, the ratio between the shortest RRI around the 15th heartbeat and the longest RRI around the 30th heartbeat after standing up (RRI 30/15 ratio) remained unchanged. Conclusion: Four months of adjunctive burstMCS was associated with an increase in parameters reflecting both total and parasympathetic autonomic modulation and baroreceptor reflex sensitivity. In contrast, sympathetic tone declined in our three patients, suggesting stimulation-associated improvement not only in subjectively perceived VAS pain scores, but also in objectifiable parameters of autonomic cardiovascular modulation.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Autonomic cardiovascular modulation; Burst motor cortex stimulation; Chronic post stroke pain; Objective outcome measures

The impact of dietary isoflavonoids on malignant brain tumors - Sehm, Tina; Fan, Zheng; Weiss, Ruth; Schwarz, Marc; Engelhorn, Tobias; Hore, Nirjhar; Dörfler, Arnd; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nic E. (Cancer Medicine, 2014)
Poor prognosis and limited therapeutic options render malignant brain tumors one of the most devastating diseases in clinical medicine. Current treatment strategies attempt to expand the therapeutic repertoire through the use of multimodal treatment regimens. It is here that dietary fibers have been recently recognized as a supportive natural therapy in augmenting the body's response to tumor growth. Here, we investigated the impact of isoflavonoids on primary brain tumor cells. First, we treated glioma cell lines and primary astrocytes with various isoflavonoids and phytoestrogens. Cell viability in a dose-dependent manner was measured for biochanin A (BCA), genistein (GST), and secoisolariciresinol diglucoside (SDG). Dose-response action for the different isoflavonoids showed that BCA is highly effective on glioma cells and nontoxic for normal differentiated brain tissues. We further investigated BCA in ex vivo and in vivo experimentations. Organotypic brain slice cultures were performed and treated with BCA. For in vivo experiments, BCA was intraperitoneal injected in tumor-implanted Fisher rats. Tumor size and edema were measured and quantified by magnetic resonance imaging (MRI) scans. In vascular organotypic glioma brain slice cultures (VOGIM) we found that BCA operates antiangiogenic and neuroprotective. In vivo MRI scans demonstrated that administered BCA as a monotherapy was effective in reducing significantly tumor-induced brain edema and showed a trend for prolonged survival. Our results revealed that dietary isoflavonoids, in particular BCA, execute toxicity toward glioma cells, antiangiogenic, and coevally neuroprotective properties, and therefore augment the range of state-of-the-art multimodal treatment approach.
EVALuna2:22829

The POST trial: initial post-market experience of the Penumbra system: revascularization of large vessel occlusion in acute ischemic stroke in the United States and Europe - Tarr, Robert; Hsu, Dan; Kulcsar, Zsolt; Bonvin, Christophe; Rufenacht, Daniel; Alfke, Karsten; Stingele, Robert; Jansen, Olav; Frei, Donald; Bellon, Richard; Madison, Michael; Struffert, Tobias; et al. (Journal of Neurointerventional Surgery, 2018)
BACKGROUND AND PURPOSE: The purpose of this study was to assess the initial post-market experience of the device and how it is compared with the Penumbra Pivotal trial used to support the 510k application. METHODS: A retrospective case review of 157 consecutive patients treated with the Penumbra system at seven international centers was performed. Primary endpoints were revascularization of the target vessel (TIMI score of 2 or 3), good functional outcome as defined by a modified Rankin scale (mRS) score of ≤2 and incidence of procedural serious adverse events. Results were compared with those of the Penumbra pivotal trial. RESULTS: A total of 157 vessels were treated. Mean baseline values at enrollment were: age 65 years, NIHSS score 16. After use of the Penumbra system, 87% of the treated vessels were revascularized to TIMI 2 (54%) or 3 (33%) as compared with 82% reported in the Pivotal trial. Nine procedural serious adverse events were reported in 157 patients (5.7%). All-cause mortality was 20% (32/157), and 41% had a mRS of ≤2 at 90-day follow-up as compared with only 25% in the Pivotal trial. Patients who were successfully revascularized by the Penumbra system had significantly better outcomes than those who were not. CONCLUSION: Initial post-market experience of the Penumbra system revealed that the revascularization rate and safety profile of the device are comparable to those reported in the Pivotal trial. However, the proportion of patients who had good functional outcome was higher than expected.
EVALuna2:34914

The Value of syngo DynaPBV Neuro During Neuro-Interventional Hypotensive Balloon Occlusion Test - Yang, M.; Wu, J.; Ma, L.; Pan, L.; Li, J.; Chen, G.; Struffert, Tobias; Sun, Q.; Beilner, J.; Deuerling-Zheng, Y. (Clinical Neuroradiology, 2015)
This study explored the value of flat detector computed tomography based brain perfusion imaging in assessing patient's tolerance prior to the permanent internal carotid artery occlusion.Ten patients diagnosed with neurovascular diseases through digital subtracted angiography (DSA) were enrolled into this study. Temporary balloon occlusion test (BOT) was performed for each patient with hypotensive challenge. During the test, parametric color-coded quantitative DSA (CCQ-DSA) was generated to evaluate the venous filling symmetry on both hemispheres. In addition, cerebral blood volume (CBV) maps were acquired before and during the test. Regions of interests were defined to quantitatively extract CBV value from affected and unaffected hemispheres and calculate relative CBV (rCBV), indicating perfusion symmetry.All the patients showed good perfusion symmetry before the test with rCBV close to 1.00. During the test, good perfusion symmetry was detected in 7 patients with averaged rCBV 1.03 ± 0.06. Only short venous delay and no ischemic complications were recognized. One patient had neither neurologic deficits nor long venous delay detected, however, showed hyper-perfusion in specific regions in the CBV maps. Two patients failed to pass the test, which showed significantly low CBV value from the affected hemisphere with maximum rCBV reduction close to 45 %.CBV map had in general good consistency with clinical manifestations as well as venous filling in the BOT. Besides, it may provide further evidence of hemodynamic variations and delayed ischemic complications, and thus, had a potential to reduce risks and increase treatment safety.
EVALuna2:23009

Thrombocytopenia and Clinical Outcomes in Intracerebral Hemorrhage: A Retrospective Multicenter Cohort Study - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2021)
BACKGROUND AND PURPOSE: The impact of platelets on hematoma enlargement (HE) of intracerebral hemorrhage (ICH) is not yet sufficiently elucidated. Especially the role of reduced platelet counts on HE and clinical outcomes is still poorly understood. This study investigated the influence of thrombocytopenia on HE, functional outcome, and mortality in patients with ICH with or without prior antiplatelet therapy (APT). METHODS: Individual participant data of multicenter cohort studies (multicenter RETRACE program [German-Wide Multicenter Analysis of Oral Anticoagulation-Associated Intracerebral Hemorrhage] and single-center UKER-ICH registry [Universitätsklinikum Erlangen Cohort of Patients With Spontaneous ICH]) were grouped into APT and non-APT ICH patients according to the platelet count, that is, with or without thrombocytopenia (cells <150×109/L). Of all patients, 51.5% (1124 of 2183) were on vitamin K antagonist. Imbalances in baseline characteristics including proportions of vitamin K antagonist patients were addressed using propensity score matching. Outcome analyses included HE (>33%), as well as mortality and functional outcome, after 3 months using the modified Rankin Scale, dichotomized into favorable (modified Rankin Scale score, 0-3) and unfavorable (modified Rankin Scale score, 4-6). RESULTS: Of overall 2252 ICH patients, 11.4% (52 of 458) under APT and 14.0% (242 of 1725) without APT presented with thrombocytopenia on admission. The proportion of patients with HE was not significantly different between patients with or without thrombocytopenia among APT and non-APT ICH patients after propensity score matching (HE: APT patients: 9 of 40 [22.5%] thrombocytopenia versus 27 of 115 [23.5%] nonthrombocytopenia, P=0.89; non-APT patients: 54 of 174 [31.0%] thrombocytopenia versus 106 of 356 [29.8%] nonthrombocytopenia, P=0.77). In both (APT and non-APT) propensity score matching cohorts, there were no significant differences regarding functional outcome. Mortality after 3 months did not differ among non-APT patients, whereas the mortality rate was significantly higher for APT patients with thrombocytopenia versus APT patients with normal platelet count (APT: 29 of 46 [63.0%] thrombocytopenia versus 58 of 140 [41.4%] nonthrombocytopenia, P=0.01; non-APT: 95 of 227 [41.9%] thrombocytopenia versus 178 of 455 [39.1%] nonthrombocytopenia, P=0.49). CONCLUSIONS: Our study implies that thrombocytopenia does not affect rates of HE and functional outcome among ICH patients, neither in patients with nor without APT. In light of increased mortality, the significance of platelet transfusions for ICH patients with thrombocytopenia and previous APT should be explored in future studies.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cohort studies; hematoma enlargement; intracerebral hemorrhage; platelet count; thrombocytopenia

Time-dependent risk factors for epileptic seizures in glioblastoma patients: A retrospective analysis of 520 cases - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Brandner, Sebastian; Welte, Tamara; Balk, Stefanie; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; Adler, Werner; Schwab, Stefan; Putz, Florian; et al. (Epilepsia, 2023)
Objective: Epilepsy is a common comorbidity of glioblastoma. Seizures may occur in various phases of the disease. We aimed to assess potential risk factors for seizures in accordance with the point in time at which they occurred. Methods: We retrospectively analyzed medical files of adult patients with de novo glioblastoma treated at our institution between January 2006 and January 2020. We categorized seizures as preoperative seizures (POS), early postoperative seizures (EPS; before initiation of radio[chemo]therapy [RCT]), seizures during radiotherapy (SDR; during or <30 days after RCT), and posttherapeutic seizures (PTS; ≥30 days after completion of RCT). We addressed associations between patients' characteristics and their seizures. Results: In the final cohort (N = 520), 292 patients experienced seizures. POS, EPS, SDR, and/or PTS occurred in 29.6% (154/520), 6.0% (31/520), 13.8% (70/509), and 36.1% (152/421) of patients, respectively. POS occurred more frequently in patients with higher Karnofsky Performance Scale scores (odds ratio [OR] = 3.27, p =.001) and tumor location in the temporal lobe (OR = 1.51, p =.034). None of the parameters we analyzed was related to the occurrence of EPS. SDR were independently associated with tumor location (parietal lobe, OR = 1.86, p =.027) and POS, but not EPS, and were independent of RCT. PTS were independently associated with tumor progression (OR = 2.32, p <.001) and with occurrence of SDR (OR = 3.36, p <.001), and negatively correlated with temporal lobe location (OR =.58, p <.014). In patients with tumors exclusively located in the temporal lobe, complete tumor resection was associated with a decreased risk of postoperative seizures. Significance: Seizures in glioblastoma patients have various, time-dependent risk factors. Temporal lobe localization was a risk factor for preoperative seizures; surgery may have had a protective effect in these patients. RCT did not have dose-dependent pro- or anticonvulsive effects. PTS were associated with tumor progression.
CRIS-Team Scopus Importer:2023-07-07
Keywords: glioblastoma; radiochemotherapy; seizures; surgery

Time-Resolved C-Arm Computed Tomographic Angiography Derived From Computed Tomographic Perfusion Acquisition: New Capability for One-Stop-Shop Acute Ischemic Stroke Treatment in the Angiosuite - Yang, Pengfei; Niu, Kai; Wu, Yijing; Struffert, Tobias; Dörfler, Arnd; Schafer, Sebastian; Royalty, Kevin; Strother, Charles; Chen, Guang-Hong (Stroke, 2015)
Multimodal imaging using cone beam C-arm computed tomography (CT) may shorten the delay from ictus to revascularization for acute ischemic stroke patients with a large vessel occlusion. Largely because of limited temporal resolution, reconstruction of time-resolved CT angiography (CTA) from these systems has not yielded satisfactory results. We evaluated the image quality and diagnostic value of time-resolved C-arm CTA reconstructed using novel image processing algorithms.Studies were done under an Institutional Review Board approved protocol. Postprocessing of data from 21 C-arm CT dynamic perfusion acquisitions from 17 patients with acute ischemic stroke were done to derive time-resolved C-arm CTA images. Two observers independently evaluated image quality and diagnostic content for each case. ICC and receiver-operating characteristic analysis were performed to evaluate interobserver agreement and diagnostic value of this novel imaging modality.Time-resolved C-arm CTA images were successfully generated from 20 data sets (95.2%, 20/21). Two observers agreed well that the image quality for large cerebral arteries was good but was more limited for small cerebral arteries (distal to M1, A1, and P1). receiver-operating characteristic curves demonstrated excellent diagnostic value for detecting large vessel occlusions (area under the curve=0.987-1).Time-resolved CTAs derived from C-arm CT perfusion acquisitions provide high quality images that allowed accurate diagnosis of large vessel occlusions. Although image quality of smaller arteries in this study was not optimal ongoing modifications of the postprocessing algorithm will likely remove this limitation. Adding time-resolved C-arm CTAs to the capabilities of the angiography suite further enhances its suitability as a one-stop shop for care for patients with acute ischemic stroke.
EVALuna2:23004

Towards Real-time Guidewire Detection and Tracking in the Field of Neuroradiology - Spiegel, Martin; Pfister, Markus; Hahn, Dieter; Daum, Volker; Hornegger, Joachim; Struffert, Tobias; Dörfler, Arnd (Medical Imaging 2009: Biomedical Applications in Molecular, Structural, and Functional Imaging, 2009)
Two-dimensional roadmapping is considered state-of-the-art in guidewire navigation during endovascular interventions. This paper presents a methodology for extracting the guidewire from a sequence of 2-D roadmap images in almost real time. The detected guidewire can be used to improve its visibility on noisy fluoroscopic images or to do a back projection of the guidewire into a registered 3-D vessel tree. A lineness filter based on the Hessian matrix is used to detect only those line structures in the image that lie within the vessel tree. Loose wire fragments are properly linked by a novel connection method fulfilling clinical processing requirements. We show that Dijkstra's algorithm can be applied to efficiently compute the optimal connection path. The entire guidewire is finally approximated by a B-spline curve in a least-squares manner. The proposed method is both integrated into a commercial clinical prototype and evaluated on five different patient data sets containing up to 249 frames per image series. © 2009 SPIE.

Toxic retrobulbar neuritis due to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-based chronic sinusitis in the left sphenoid sinus: a case report - Schapher, Mirco; Brügel, Jacob; Güner, Fabian; Volbers, Bastian; Eichhorn, Philip; Agaimy, Abbas; Berger, Magdalena; Mardin, Christian; Dörfler, Arnd; Hock, Stefan (Journal of Medical Case Reports, 2023)
BACKGROUND: Abrupt visual impairment constitutes a medical urgency, necessitating an interdisciplinary diagnostic and therapeutic approach owing to the broad spectrum of potential etiologies, thereby engaging numerous medical specialties. CASE PRESENTATION: A 21-year-old Mixed White and Asian female patient, with medical history of nonsteroidal antiinflammatory drug-exacerbated respiratory disease necessitating previous sinus surgery, reported sudden monocular vision loss. Unremarkable ophthalmological examination of the fellow eye and hematological parameters, save for a slight elevation in lymphocytes and eosinophils, were observed. Imaging studies indicated recurrence of bilateral chronic rhinosinusitis with nasal polyps and a mucocele in the left sphenoid sinus, accompanied by bony structural deficits. Emergency revision sinus surgery, guided by navigation, was promptly performed. The patient received treatment with methylprednisolone, ceftriaxone, cyanocobalamin, pyridoxine, thiamine, and acetylsalicylic acid. During the hospital stay, she developed steroid-induced glaucoma, which was subsequently managed successfully. Negative microbiological swabs, along with pathohistological evidence of increased tissue eosinophilia and the patient's clinical history, led to the diagnosis of toxic retrobulbar neuritis secondary to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-associated chronic rhinosinusitis of the left sphenoid sinus. CONCLUSIONS: In cases of acute unilateral vision loss, optic neuritis is a highly probable differential diagnosis and may be induced by pathologies of the paranasal sinuses. Nonsteroidal antiinflammatory drug-exacerbated respiratory disease, a subtype of chronic rhinosinusitis, is associated with type 2 inflammation, which is increasingly recognized for its role in the pathogenesis of bronchial asthma, eosinophilic esophagitis, and atopic eczema. Clinicians should consider chronic rhinosinusitis as a potential differential diagnosis in unilateral visual loss and be cognizant of the rising significance of type 2 inflammations, which are relevant to a variety of diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blindness; Case report; Inflammation mediators; Neuritis; Optic; Sinusitis

Transient Enlargement in Meningiomas Treated with Stereotactic Radiotherapy - Maksoud, Ziad; Schmidt, Manuel; Huang, Yixing; Rutzner, Sandra; Mansoorian, Sina; Weissmann, Thomas; Bert, Christoph; Distel, Luitpold; Semrau, Sabine; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; et al. (Cancers, 2022)
To investigate the occurrence of pseudoprogression/transient enlargement in meningiomas after stereotactic radiotherapy (RT) and to evaluate recently proposed volumetric RANO meningioma criteria for response assessment in the context of RT. Sixty-nine meningiomas (benign: 90%, atypical: 10%) received stereotactic RT from January 2005–May 2018. A total of 468 MRI studies were segmented longitudinally during a median follow-up of 42.3 months. Best response and local control were evaluated according to recently proposed volumetric RANO criteria. Transient enlargement was defined as volumetric increase ≥20% followed by a subsequent regression ≥20%. The mean best volumetric response was −23% change from baseline (range, −86% to +19%). According to RANO, the best volumetric response was SD in 81% (56/69), MR in 13% (9/69) and PR in 6% (4/69). Transient enlargement occurred in only 6% (4/69) post RT but would have represented 60% (3/5) of cases with progressive disease if not accounted for. Transient enlargement was characterized by a mean maximum volumetric increase of +181% (range, +24% to +389 %) with all cases occurring in the first year post-RT (range, 4.1–10.3 months). Transient enlargement was significantly more frequent with SRS or hypofractionation than with conventional fractionation (25% vs. 2%, p = 0.015). Five-year volumetric control was 97.8% if transient enlargement was recognized but 92.9% if not accounted for. Transient enlargement/pseudoprogression in the first year following SRS and hypofractionated RT represents an important differential diagnosis, especially because of the high volumetric control achieved with stereotactic RT. Meningioma enlargement during subsequent post-RT follow-up and after conventional fractionation should raise suspicion for tumor progression. <
Keywords: meningioma; volumetric analysis; segmentation; transient enlargement; pseudoprogression; stereotactic radiotherapy; radiosurgery; response assessment

Transient naming deficits associated with insular lesions in a patient with encephalitis - Marxreiter, Franz; Utz, Kathrin; Schlachetzki, Johannes; Seifert, Frank; Schmidt, Manuel; Dörfler, Arnd; Schwab, Stefan; Schenk, Thomas (Neurocase, 2019)
We describe a patient with acute herpes simplex encephalitis with left-hemispheric hippocampal, parahippocampal and insular lesions. Although prototypic language areas were unaffected, the patient suffered from an inability to name objects or animals displayed on pictures. This deficit was transient and gradually disappeared 8 weeks after the initial diagnosis. Our findings are in line with a previous report showing similar deficits in a patient with a comparable lesion pattern and support the hypothesis that left insular lesions can produce severe naming deficits. Using FDG-PET we ruled out that functional deactivation in classical language areas account for the observed naming deficits.
EVALuna2:204482

Truncation correction for VOI C-arm CT using scattered radiation - Bier, Bastian; Maier, Andreas; Hofmann, Hannes; Schwemmer, Chris; Xia, Yan; Struffert, Tobias; Hornegger, Joachim (Medical Imaging 2013: Physics of Medical Imaging, 2013)
In C-arm computed tomography, patient dose reduction by volume-of-interest (VOI) imaging is of increasing interest for many clinical applications. A remaining limitation of VOI imaging is the truncation artifact when reconstructing a 3D volume. It can either be cupping towards the boundaries of the field-of-view (FOV) or an incorrect offset in the Hounsfield values of the reconstructed voxels. In this paper, we present a new method for correction of truncation artifacts in a collimated scan. When axial or lateral collimation are applied, scattered radiation still reaches the detector and is recorded outside of the FOV. If the full area of the detector is read out we can use this scattered signal to estimate the truncated part of the object. We apply three processing steps: detection of the collimator edge, adjustment of the area outside the FOV, and interpolation of the collimator edge. Compared to heuristic truncation correction methods we were able to reconstruct high contrast structures like bones outside of the FOV. Inside the FOV we achieved similar reconstruction results as with water cylinder truncation correction. These preliminary results indicate that scattered radiation outside the FOV can be used to improve image quality and further research in this direction seems beneficial. © 2013 SPIE.

Twice-refocused stimulated echo diffusion imaging: Measuring diffusion time dependence at constant T-1 weighting - Martin, Jan; Endt, Sebastian; Wetscherek, Andreas; Kuder, Tristan Anselm; Dörfler, Arnd; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2019)
Purpose Diffusion times longer than 50 ms are typically probed with stimulated-echo sequences. Varying the diffusion time in stimulated-echo sequences affects the T-1 weighting of subcompartments, complicating the analysis of diffusion time dependence. Although inversion recovery preparation could be used to change the T-1 weighting, it cannot ensure equal T-1 weighting at arbitrary mixing times. In this article, a sequence that ensures constant T-1 weighting over a wide range of diffusion times is presented. Methods The proposed sequence features 2 independent longitudinal storage periods: TM1 and TM2. Diffusion encoding is performed during TM1, effectively coupling the diffusion time and TM1. Equal T-1 weighting at arbitrary diffusion times is realized by keeping the total mixing time TM1 + TM2 constant. The sequence was compared with conventional stimulated-echo measurements of diffusion in a 2-compartment phantom consisting of distilled water and paraffinum perliquidum. Additionally, in vivo DTI of the brain was carried out for 8 healthy volunteers with diffusion times ranging from 50 to 500 ms. Results Diffusion time dependence of the axial and radial diffusivity was detected in the brain. Both sequences resulted in almost identical diffusivities in white matter. In regions containing partial volumes of gray and white matter, a dependency on T-1 weighting was observed. Conclusion In accordance with previous studies, little variance of T-1 values appeared to be present in healthy white matter. However, this is likely different in diseased tissue. Here, the proposed sequence can be effective in differentiating between diffusion time dependence and T-1 weighting effects.
CRIS-Team WoS Importer:2019-11-12

Two- to five-year follow-up of 78 patients after treatment with the Flow Redirection Endoluminal Device - Lücking, Hannes; Dörfler, Arnd; Gölitz, Philipp; Engelhorn, Tobias; Lang, Stefan; Hölter, Philip (Interventional Neuroradiology, 2019)
Background and purpose Flow-diverter stents are well-established for the treatment of cerebral aneurysms. Flow Redirection Endoluminal Device differs from other flow-diverter stents by its dual-layer design and has proved equality to other devices in numerous short-term surveys. However, follow-up data covering substantially more than one year are still limited for this device. We present our long-term experience with Flow Redirection Endoluminal Device.
CRIS-Team WoS Importer:2019-10-22

Two- to five-year follow-up of 78 patients after treatment with the Flow Redirection Endoluminal Device - Lücking, Hannes; Dörfler, Arnd; Gölitz, Philipp; Hölter, Philip; Engelhorn, Tobias; Lang, Stefan (Interventional Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Flow-diverter stents are well-established for the treatment of cerebral aneurysms. Flow Redirection Endoluminal Device differs from other flow-diverter stents by its dual-layer design and has proved equality to other devices in numerous short-term surveys. However, follow-up data covering substantially more than one year are still limited for this device. We present our long-term experience with Flow Redirection Endoluminal Device. MATERIALS AND METHODS: Seventy-eight patients harboring distal internal carotid artery (91%) or vertebrobasilar (9%) cerebral aneurysms treated with Flow Redirection Endoluminal Device with or without adjunctive coiling met the inclusion criteria. All cases were evaluated for aneurysm occlusion (according to Modified Raymond Roy Classification, MRRC), for flow-diverter stents patency and configuration and for procedure- and device-related morbidity and mortality. RESULTS: Mean follow-up interval was 36.9 ± 9.5 months (<30 months: n = 18; 31-42 months: n = 31; >42 months: n = 24). Total and subtotal aneurysm occlusion after six months was assessed in 92.0% (MRRC1 = 77.3%, MRRC2 = 14.7%, MRRC3a =2.7%, MRRC3b = 4.1%) and increased to 95.9% (MRRC1 = 90.5%, MRRC2 = 5.4%, MRRC3a = 2.7%). There was one case of aneurysm growth requiring early re-treatment. Procedure-related morbidity was observed in three cases (3.8%; one transient hemiparesis, one suspected foreign-body reaction, and one micro-wire perforation). There was no procedure- or device-related mortality. In-stent stenosis due to intimal hyperplasia was observed in two cases and fish-mouthing in three cases. CONCLUSIONS: Our long-term data covering two to five years after flow diversion confirm that Flow Redirection Endoluminal Device is a safe and effective device for the treatment of cerebral aneurysms with progressive high aneurysm occlusion rates; recurrence rates were very low. Overall device-related morbidity was low and was not observed later than six months after intervention.
EVALuna2:212795

Ultraearly assessed reperfusion status after middle cerebral artery recanalization predicting clinical outcome - Gölitz, Philipp; Mühlen, Iris; Gerner, Stefan; Knossalla, F.; Dörfler, Arnd (Acta Neurologica Scandinavica, 2018)
Objectives: Mechanical thrombectomy has high evidence in stroke therapy; however, successful recanalization guarantees not a favorable clinical outcome. We aimed to quantitatively assess the reperfusion status ultraearly after successful middle cerebral artery (MCA) recanalization to identify flow parameters that potentially allow predicting clinical outcome. Materials and Methods: Sixty-seven stroke patients with acute MCA occlusion, undergoing recanalization, were enrolled. Using parametric color coding, a post-processing algorithm, pre-, and post-interventional digital subtraction angiography series were evaluated concerning the following parameters: pre- and post-procedural cortical relative time to peak (rTTP) of MCA territory, reperfusion time, and index. Functional long-term outcome was assessed by the 90-day modified Rankin Scale score (mRS; favorable: 0-2). Results: Cortical rTTP was significantly shorter before (3.33 +/- 1.36seconds; P = .03) and after intervention (2.05 +/- 0.70seconds; P=.003) in patients with favorable clinical outcome. Additionally, age (P=.005) and initial National Institutes of Health Stroke Scale score (P = .02) were significantly different between the patients, whereas reperfusion index and time as well as initially estimated infarct size were not. In multivariate analysis, only post-procedural rTTP (P=.005) was independently associated with favorable clinical outcome. 2.29seconds for post-procedural rTTP might be a threshold to predict favorable clinical outcome. Conclusions: Ultraearly quantitative assessment of reperfusion status after successful MCA recanalization reveals post-procedural cortical rTTP as possible independent prognostic value in predicting favorable clinical outcome, even determining a threshold value might be possible. In consequence, focusing stroke therapy on microcirculatory patency could be valuable to improve outcome.
EVALuna2:34935

Ultra-early Detection of Microcirculatory Injury as Predictor of Developing Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Gölitz, Philipp; Rösch, Julie; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Clinical Neuroradiology, 2018)
Purpose Delayed cerebral ischemia (DCI) still remains amajor complication after subarachnoid hemorrhage (SAH). The aim of our study was to evaluate whether flow analysis of admission digital subtraction angiography (DSA) using parametric color coding (PCC), apostprocessing algorithm, allows ultra-early identification of SAH patients at risk for developing subsequent symptomatic vasospasm. Methods In this study 52patients who suffered SAH from aneurysm rupture, were retrospectively enrolled. Of the patients 26 developed DCI and angiographically proven cerebral vasospasm and 26age, gender-and clinical status-matched SAH patients without DCI served as controls. Using PCC, the following flow parameters were calculated: cerebral circulation time (CirT), cortical relative time to peak (rTTP) and microvascular transit time (TT). Results Mean cerebral CirT and cortical rTTP were longer in the DCI group (6.42s +/- 1.54 and 3.16s +/- 0.86, respectively) than in the non-DCI group (5.77s +/- 1.86 and 3.11s +/- 1.41, respectively), but without statistical significance. The mean microvascular TT was statistically significantly (p = 0.04) longer in the DCI group (3.19s +/- 0.78) than in the non-DCI group (2.67s +/- 0.73). Conclusion Angiographic flow analysis might be suitable for ultra-early detection and quantitative assessment of microcirculatory injury in SAH patients, predictive of developing subsequent DCI. Prolonged microvascular TT seems to be asignificant independent factor positively associated with DCI development. Identifying SAH patients at risk for DCI ultra-early after ictus might contribute to initiate prophylactic therapies before clinical deterioration.
EVALuna2:34933

Ultra-high field MRI of human hippocampi: Morphological and multiparametric differentiation of hippocampal sclerosis subtypes - Gillmann, Clarissa; Coras, Roland; Roessler, Karl; Dörfler, Arnd; Uder, Michael; Blümcke, Ingmar; Bäuerle, Tobias (PLoS ONE, 2018)
The aim of the present study is to differentiate subtypes of hippocampal sclerosis (HS) using ex vivo ultra-high field magnetic resonance imaging (MRI). Included were 14 surgically resected hippocampi of patients with medically intractable temporal lobe epilepsy. The resected hippocampi were histologically categorized into subtypes of hippocampal sclerosis (HS type 1 (n = 10), HS type 2 (n = 2) and no-HS (n = 2)) and subsequently scanned on a preclinical 7T MRI acquiring T2-weighted morphology, relaxometry and diffusion tensor imaging. On the morphological images, the pyramidal cell layer (PCL) of the hippocampus was segmented and the following parameters were derived: T2 signal intensity, T1-, T2- and T2*-relaxation times, apparent diffusion coefficient (ADC), fractional anisotropy (FA) and mean diffusivity (MD). Furthermore, the area of the PCL was determined, as well as the parameter product which refers to the widths of the PCL parallel and perpendicular to the stratum moleculare. Spearman correlation coefficient was used to demonstrate relationships between MR-parameters and type of sclerosis. In comparison to no-HS specimens, the PCL was significantly narrower in HS type 1 and HS type 2 hippocampi. This narrowing affected the entire cornu ammonis sector (CA) 1 in HS type 1, while it was limited to the upper half of CA1 in direction to CA2 in HS type 2. The parameter product median increased from 0.43 to 1.67 and 2.91 mm2 for HS type 1, HS type 2 and no-HS, respectively. Correlation coefficients were significant for the PCL parameters product (0.73), area (0.71), T2*-time (-0.67), FA (0.65) and ADC (0.55). Our initial results suggest that HS type 1, HS type 2 and no-HS subtypes can be distinguished from each other using ex vivo UHF MRI based on T2-weighted morphologic images and the assessment of the parameter product. Upon clinical translation, UHF-MRI may provide a promising technique for the preoperative differentiation of HS subtypes in patients.
EVALuna2:34592

Ultra high-field SWI of the substantia nigra at 7T: reliability and consistency of the swallow-tail sign - Schmidt, Manuel; Engelhorn, Tobias; Marxreiter, Franz; Winkler, Jürgen; Lang, Stefan; Kloska, Stephan; Gölitz, Philipp; Dörfler, Arnd (BMC Neurology, 2017)
BACKGROUND: The loss of the swallow-tail sign of the substantia nigra has been proposed for diagnosis of Parkinson's disease. Aim was to evaluate, if the sign occurs consistently in healthy subjects and if it can be reliably detected with high-resolution 7T susceptibility weighted imaging (SWI). METHODS: Thirteen healthy adults received SWI at 7T. 3 neuroradiologists, who were blinded to patients' diagnosis, independently classified subjects regarding the swallow-tail sign to be present or absent. Accuracy, positive and negative predictive values (PPV and NPV) as well as inter- and intra-rater reliability and internal consistency were analyzed. RESULTS: The sign could be detected in 81% of the cases in consensus reading. Accuracy to detect the sign compared to the consensus was 100, 77 and 96% for the three readers with PPV reader 1/2/3 = 1/0.45/0.83 and NPV = 1/1/1. Inter-rater reliability was excellent (inter-class correlation coefficient = 0.844, alpha = 0.871). Intra-rater reliability was good to excellent (reader 1 R/L = 0.625/0.786; reader 2 = 0.7/0.64; reader 3 = 0.9/1). CONCLUSION: The swallow-tail sign can be reliably detected. However, our data suggest its occurrence is not consistent in healthy subjects. It may be possible that one reason is an individually variable molecular organization of nigrosome 1 so that it does not return a uniform signal in SWI.
EVALuna2:33135

Unruptured Intracranial Aneurysms- Pathogenesis and Individualized Management - Etminan, Nima; Dörfler, Arnd; Steinmetz, Helmuth (Deutsches Ärzteblatt international, 2020)
BACKGROUND: About 2 million adults in Germany harbor an unruptured intracranial aneurysm (IA). Rupture can lead to a life-threatening subarachnoid hemorrhage. If an IA is detected incidentally in cranial imaging, it must be decided how to proceed. METHODS: This review includes key publications that were identified by a selective search in the PubMed database using the search term "unruptured intracranial aneurysms," which was performed in July 2019, and based on information obtained from the German Federal Statistical Office on the frequency of the hospital discharge diagnosis "cerebral aneurysm," excluding the diagnosis "subarachnoid hemorrhage," in Germany from 2005 to 2017. RESULTS: The number of patients in Germany who were admitted or treated for an unruptured IA increased by a factor of 2.3 from 2005 to 2017. The average 5-year rupture risk of approximately 3% must be weighed against the approximately 4% risk associated with an endovascular or microneurosurgical treatment. This emphasizes the need for more precise data on the risk of rupture and for algorithms enabling individualized decision-making for patients with unruptured IA. Risk factors such as IA morphology, arterial hypertension, active smoking, and alcohol consumption (>150 g/week) can markedly increase the risk of rupture, which is generally relatively low. Growing aneurysms are 12 times more likely to rupture than stable ones. Follow-up imaging is thus essential whenever observation rather than intervention is chosen as the initial management. CONCLUSION: Patients with unruptured IA should be massessed and managed individually. It is also important that risk factors should be treated, if present. Eligible patients are currently being recruited for a phase III clinical trial on the efficacy of blood pressure reduction combined with acetylsalicylic acid intake to counteract inflammatory processes in the arterial wall.
CRIS-Team Scopus Importer:2020-06-05

Validation of automatic MRI hippocampal subfield segmentation by histopathological evaluation in patients with temporal lobe epilepsy - Menzler, Katja; Hamer, Hajo; Mross, Peter; Rosenow, Felix; Deichmann, Ralf; Wagner, Marlies; Gracien, René Maxime; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Belke, Marcus; Knake, Susanne (Seizure-European Journal of Epilepsy, 2021)
Objective: The present study validates the results of automated hippocampal subfield segmentation with histopathology in epilepsy patients undergoing epilepsy surgery. Methods: We performed an automated hippocampal subfield segmentation on presurgical three-dimensional, T1-weighted magnetization Prepared Rapid Acquisition of Gradient Echoes Magnetic Resonance Imaging (MRI) data of 25 patients with unilateral mesial temporal lobe epilepsy due to hippocampal sclerosis (HS), using Freesurfer Version 6.0. The resulting volumes of cornu ammonis (CA) subfields CA1, CA2/3, CA4 and the dentate gyrus (DG) were compared to the histopathological cell count. Results: We found a significant correlation between histopathology in subregion CA2 and automated segmentation of subregion CA1 (p = 0.0062), CA2/3 (p = 0.004), CA4 (p = 0.0062) and the DG (p = 0.0054), between histopathology in CA3 and automated segmentation of CA1 (p = 0.0132), CA2/3 (p = 0.0004), CA4 (p = 0.0032) and the DG (p = 0.0037), as well as between histopathology in the DG and automated segmentation of CA1 (p = 0.0115), CA2/3 (p < 0.0001), CA4 (p < 0.0001) and the DG (p = 0.0001). The histopathological finding of HS type 1 could correctly be classified in all cases on MRI. Significance: The present study shows significant correlations between histopathological evaluation and results of the automated segmentation of the hippocampus, thereby validating the automated segmentation method. As the differential involvement of different hippocampal subfields may be associated with clinical parameters and the outcome after epilepsy surgery, the automated segmentation is also promising for prognostic purposes.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Automated segmentation; Hippocampal subfields; Mesiotemporal sclerosis; Mri

Value of Flat-detector Computed Tomography Angiography with Intravenous Contrast Media Injection in the Evaluation and Treatment of Acutely Ruptured Aneurysms of the AcomA complex: A Single Center Experience in 15 Cases - Rösch, Julie; Lang, Stefan; Gölitz, Philipp; Kallmünzer, Bernd; Roessler, Karl; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2018)
Objective To illustrate the added value of flat-detector computed tomography angiography with intravenous contrast media injection (intravenous FDCTA) in the evaluation of complex A1/A2/AcomA aneurysms. Patients and Methods We retrospectively reviewed 15patients with ruptured aneurysms. In each patient, an intravenous FDCTA was performed and its diagnostic value investigated. Results In all patients, FDCTA contributed relevant additional information concerning the anatomy of the A1/A2/AcomA complex and the relationship of the aneurysm neck to these vascular structures, which could not be gained by 2D- and 3D-DSA, and changed the management in 33% of the patients (5 out of 15). In an additional 5cases, knowledge of the detailed anatomy was helpful to plan the exact stent position. Conclusion In case of complex A1/A2/AcomA aneurysms, intravenous FDCTA is an effective option to visualize the exact location of the aneurysm neck and the relationship between the aneurysm and the adjacent vessels. Thus, it is of significant added value in the precise planning of atherapeutic strategy.
EVALuna2:34934

Variable White Matter Atrophy and Intellectual Development in a Family With X-linked Creatine Transporter Deficiency Despite Genotypic Homogeneity - Heussinger, Nicole; Saake, Marc; Mennecke, Angelika; Dörr, Helmuth-Günther; Trollmann, Regina (Pediatric Neurology, 2017)
The X-linked creatine transporter deficiency (CRTD) caused by an SLC6A8 mutation represents the second most common cause of X-linked intellectual disability. The clinical phenotype ranges from mild to severe intellectual disability, epilepsy, short stature, poor language skills, and autism spectrum disorders. The objective of this study was to investigate phenotypic variability in the context of genotype, cerebral creatine concentration, and volumetric analysis in a family with CRTD.The clinical phenotype and manifestations of epilepsy were assessed in a Caucasian family with CRTD. DNA sequencing and creatine metabolism analysis confirmed the diagnosis. Cerebral magnetic resonance imaging (cMRI) with voxel-based morphometry and magnetic resonance spectroscopy was performed in all family members.An SLC6A8 missense mutation (c.1169C>T; p.Pro390Leu, exon 8) was detected in four of five individuals. Both male siblings were hemizygous, the mother and the affected sister heterozygous for the mutation. Structural cMRI was normal, whereas voxel-based morphometry analysis showed reduced white matter volume below the first percentile of the reference population of 290 subjects in the more severely affected boy compared with family members and controls. Normalized creatine concentration differed significantly between the individuals (P < 0.005).There is a broad phenotypic variability in CRTD even in family members with the same mutation. Differences in mental development could be related to atrophy of the subcortical white matter.
EVALuna2:14646

Variation of membrane particle–bound CD133 in cerebrospinal fluid of patients with subarachnoid and intracerebral hemorrhage - Bobinger, Tobias; Röder, Sebastian; Sprügel, Maximilian; Fröhlich, Kilian; Beuscher, Vanessa; Hölter, Philip; Lücking, Hannes; Corbeil, Denis; Huttner, Hagen (Journal of Neurosurgery, 2021)
OBJECTIVE Previous studies have demonstrated that human CSF contains membrane particles carrying the stem cell antigenic marker CD133 (prominin-1). Here, the authors analyzed the variation of the amount of these CD133-positive particles in the CSF of patients with subarachnoid hemorrhage (SAH) and intracerebral hemorrhage (ICH). METHODS Consecutive CSF samples from 47 patients with SAH or ICH were compared to 14 healthy control patients. After differential ultracentrifugation of CSF, the membrane particle fraction was separated on gel electrophoresis and its CD133 content was probed by immunoblotting using the mouse monoclonal antibody 80B258 directed against human CD133. The antigen-antibody complexes were detected by chemiluminescence reagents and quantified using human Caco-2 cell extract as positive control with a standardized curve. RESULTS As compared to healthy controls (6.3 ± 0.5 ng of bound CD133 antibody; n = 14), the amount of membrane particle–associated CD133 immunoreactivities was significantly elevated in patients with SAH and ICH (38.2 ± 6.6 ng and 61.3 ± 11.0 ng [p < 0.001] for SAH [n = 18] and ICH [n = 29], respectively). In both groups the CD133 level dropped during the first 7 days (i.e., day 5–7: SAH group, 24.6 ± 10.1 ng [p = 0.06]; ICH group, 25.0 ± 4.8 ng [p = 0.002]). Whereas changes in the amount of CD133-positive membrane particles between admission and day 5–7 were not associated with clinical outcomes in patients with ICH (modified Rankin Scale [mRS] scores 0–3, −30.9 ± 12.8 ng vs mRS scores 4–6, −21.8 ± 10.7 ng; p = 0.239), persistent elevation of CD133 in patients with SAH was related to impaired functional outcome 3 months after ictus (mRS scores 0–2, −29.9 ± 8.1 ng vs mRS scores 3–6, 7.6 ± 20.3 ng; p = 0.027). These data are expressed as the mean ± standard error of the mean (SEM). CONCLUSIONS Levels of membrane particle–associated CD133 in the CSF of patients with SAH and ICH are significantly increased in comparison to healthy patients, and they decline during the hospital stay. Specifically, the persistent elevation of CD133-positive membrane particles within the first week may represent a possible surrogate measure for impaired functional outcome in patients with SAH.
CRIS-Team Scopus Importer:2021-04-09
Keywords: CD133; Intracerebral hemorrhage; Membrane particles; Prominin-1; Stem cells; Subarachnoid hemorrhage; Vascular disorders

Vascular architecture mapping for early detection of glioblastoma recurrence - Stadlbauer, Andreas; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Zimmermann, Max; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Neurosurgical Focus, 2019)
OBJECTIVE: Treatment failure and inevitable tumor recurrence are the main reasons for the poor prognosis of glioblastoma (GB). Gross-total resection at repeat craniotomy for GB recurrence improves patient overall survival but requires early and reliable detection. It is known, however, that even advanced MRI approaches have limited diagnostic performance for distinguishing tumor progression from pseudoprogression. The novel MRI technique of vascular architectural mapping (VAM) provides deeper insight into tumor microvascularity and neovascularization. In this study the authors evaluated the usefulness of VAM for the monitoring of GB patients and quantitatively analyzed the features of neovascularization of early- and progressed-stage GB recurrence. METHODS: In total, a group of 115 GB patients who received overall 374 follow-up MRI examinations after standard treatment were retrospectively evaluated in this study. The clinical routine MRI (cMRI) protocol at 3 Tesla was extended with the authors' experimental VAM approach, requiring 2 minutes of extra time for data acquisition. Custom-made MATLAB software was used for calculation of imaging biomarker maps of macrovascular perfusion from perfusion cMRI as well as of microvascular perfusion and architecture from VAM data. Additionally, cMRI data were analyzed by two board-certified radiologists in consensus. Statistical procedures included receiver operating characteristic (ROC) analysis to determine diagnostic performances for GB recurrence detection. RESULTS: Overall, cMRI showed GB recurrence in 89 patients, and in 28 of these patients recurrence was detected earlier with VAM data, by 1 (20 patients) or 2 (8 patients) follow-up examinations, than with cMRI data. The mean time difference between recurrence detection with VAM and cMRI data was 147 days. During this time period the mean tumor volume increased significantly (p < 0.001) from 9.7 to 26.8 cm3. Quantitative analysis of imaging biomarkers demonstrated microvascular but no macrovascular hyperperfusion in early GB recurrence. Therefore, ROC analysis revealed superior diagnostic performance for VAM compared with cMRI. CONCLUSIONS: This study demonstrated that the targeted assessment of microvascular features using the VAM technique provided valuable information about early neovascularization activity in recurrent GB that is complementary to perfusion cMRI and may be helpful for earlier and more precise monitoring of patients suffering from GB. This VAM approach is compatible with existing cMRI protocols. Prospective clinical trials are necessary to investigate the clinical usefulness and potential benefit of increased overall survival with the use of VAM in patients with recurrent GB.
CRIS-Team Scopus Importer:2019-12-13
Keywords: AUC = area under the ROC curve; CA = contrast agent; CBV = cerebral blood volume; CE = contrast enhanced; cMRI = clinical routine MRI; cNAWM = contralateral normal appearing white brain matter; DSC = dynamic susceptibility contrast; EPI = echo-planar imaging; FN = false negative; FP = false positive; GB = glioblastoma; GE = gradient echo; glioblastoma; MRI; MTI = microvessel type indicator; MVD = microvessel density; neovascularization; OS = overall survival; RANO = Response Assessment in Neuro-Oncology; recurrence; ROC = receiver operating characteristic; ROI = region of interest; SE = spin echo; T1W = T1 weighted; TN = true negative; TP = true positive; VAM = vascular architectural mapping; vascular architecture; VHL = vascular hysteresis loop; VSI = vessel size index; µCBV = microvascular CBV

Vascular Hysteresis Loops and Vascular Architecture Mapping in Patients with Glioblastoma treated with Antiangiogenic Therapy - Stadlbauer, Andreas; Zimmermann, Max; Oberndorfer, Stefan; Dörfler, Arnd; Buchfelder, Michael; Heinz, Gertraud; Roessler, Karl (Scientific Reports, 2017)
In this study, we investigated the variability of vascular hysteresis loop (VHL) shapes and the spatial heterogeneity of neovascularization and microvascular alterations using vascular architecture mapping (VAM) in patients with recurrent glioblastoma during bevacizumab mono-therapy. VAM data were acquired in 13 patients suffering from recurrent glioblastoma prior to and 3 months after bevacizumab treatment onset using a dual contrast agent injections approach as part of routine MRI. Two patients were additionally examined after the first cycle of bevacizumab to check for early treatment response. VHLs were evaluated as biomarker maps of neovascularization activity: microvessel type indicator (MTI) and curvature (Curv) of the VHL-long-axis. Early response to bevacizumab was dominated by reduction of smaller microvasculature (around 10 µm). In the 3-month follow-up, responding tumors additionally showed a reduction in larger microvasculature (>20 µm). VAM biomarker images revealed spatially heterogeneous microvascular alterations during bevacizumab treatment. Responding, non-responding, progressive, and remote-progressive tumor areas were observed. MTI may be useful to predict responding and non-responding tumor regions, and Curv to assess severity of vasogenic edema. Analysis of VHLs in combination with VAM biomarkers may lead to a new perspective on investigating the spatial heterogeneity of neovascularization and microvascular alterations in glioblastoma during antiangiogenic therapy.
EVALuna2:33144

Vasospasm in intracerebral hemorrhage with ventricular involvement: a prospective pilot transcranial Doppler sonography study - Kiphuth, Ines C.; Huttner, Hagen; Breuer, Lorenz; Engelhorn, Tobias; Schwab, Stefan; Köhrmann, Martin (Cerebrovascular Diseases, 2011)
Cerebral vasospasm (VSP) is a common complication after subarachnoid hemorrhage (SAH), but has rarely been reported after intracerebral hemorrhage (ICH) without subarachnoidal bleeding. The underlying pathophysiological mechanism is mainly mediated by circulating heme products within the cerebrospinal fluid, and thus patients with ICH and ventricular involvement (IVH) may also be in danger of developing VSP. The incidence and role of VSP in IVH, however, have not been systematically studied.We prospectively enrolled 115 patients with ICH with or without IVH into the study between April 2009 and April 2010. All patients received serial extracranial and transcranial Doppler sonography (TCD) at baseline, on days 3-5 and 7-9 to detect and monitor VSP. In addition, CT scans taken on admission, after 24 h and before discharge were evaluated for the occurrence of delayed cerebral ischemia.Three out of 53 patients (5.7%) with IVH showed a significant elevation of flow velocities over the examined timeframe. One of these patients developed severe VSP resulting in secondary ischemic infarction. None of the ICH patients without IVH showed significantly elevated flow velocities or secondary infarction.Cerebral VSP with secondary infarction may occur in patients with spontaneous IVH, though far less frequently than in SAH; thus, systematic screening of all patients with IVH may not be warranted. However, serial TCD should be considered in patients with secondary clinical worsening or extensive IVH.
EVALuna2:21961

Verbesserung der Deep Learning basierten Autodetektion von Hirnmetastasen durch Integration von MRT-Voraufnahmen - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2022)
Keywords: Deep learning; brain metastasis

"Virtual stent" - clinical evaluation and user experience of on-the-fly stent simulation in treatment of cerebral aneurysms - Lücking, Hannes; Birkhold, Annette; Hölter, Philip; Lang, Stefan; Gölitz, Philipp; Schmidt, Manuel; Mrochen, Anne; Brandner, Sebastian; Dörfler, Arnd (Interventional Neuroradiology, 2021)
Background Predicting final stent position can be challenging when treating cerebral aneurysms. Third-Party software proved helpful in selecting proper stents in treatment planning. Recent angiographic systems provide basic stent simulation capabilities integrated in the post-processing software to simulate stent position. Goal of this analysis was to evaluate the simulation process and correlation with definite stent position. Materials and Methods Thirty-three datasets with fusiform (n = 10) and saccular (n = 23) aneurysms, treated with stent or flow-diverter, were processed. A "virtual stent" of the same (nominal) size was simulated and its position was compared to the treatment result. Simulated length was rated in five grades (too short, shorter, equal, longer, too long), with regard to side-branches, anchoring zone etc. Simulation quality (centerline recognition/adherence to vessel margins) was rated in three grades (no, minor or major corrections required). Results Simulation was successful in 32/33 cases (97%), with one abortive attempt (3%). In 27/33 simulations (82%), there was no need for centerline refinement. Minor corrections were necessary in four and major corrections in two cases. Simulated nominal length was rated "equal" in 14/33 (42%) cases and "shorter" or "longer" - but within acceptable range - in each 9/33 (27%) cases. Conclusion Basic stent simulation tools available with genuine angiographic workplace software can provide good simulation capabilities without need for third-party equipment. They can facilitate treatment planning and help to avoid shortage of devices. Yet, lack of calculation of foreshortening in large vessel diameters leaves the user to rely on their experience to account for device-specific properties.
CRIS-Team WoS Importer:2021-11-12

Visualisation of tumour regression after local chemotherapy with magnetic nanoparticles - A pilot study - Lyer, Stefan; Tietze, Rainer; Jurgons, Roland; Struffert, Tobias; Engelhorn, Tobias; Schreiber, Eveline; Dörfler, Arnd; Alexiou, Christoph (Anticancer Research, 2010)
Magnetic drug targeting (MDT) is a new locoregional chemotherapy method that increases the drug dose in the tumour region, while simultaneously reducing the overall dose through the application of chemotherapeuticbound superparamagnetic nanoparticles, which are focused by an external magnetic field to the desired body compartment. An important factor in this kind of therapy is the vascularisation of the targeted tumour. In this pilot study, the visualisation of the tumour-vascularisation before and after MDT was investigated. Materials and Methods: In a rabbit VX-2 tumour model, mitoxantrone bound to Fe3O4-nanoparticles was applied through the femoral artery close to the tumour. The visualisation of vascularisation and tumour size before and after MDT was performed using a biplane angiographic system (Siemens Axiom Artis dBA) to obtain conventional angiographic series with a standard iodine contrast agent. In addition, cross-sectional images were obtained with the new technique of flat panel detector computed tomography (FD-CT) called DYNA-CT. Results: The tumours and the supplying vessels were clearly displayed by FD-CT before and after MDT. The tumours of the study group showed considerable size reductions and the angiography showed a drastic reduction of the tumour supporting vessels following MDT. Conclusion: MDT leads to significant tumour size reductions within several weeks after a single administration of chemotherapy. In this pilot study, FD-CT offered an excellent possibility to monitor the vascularisation and the size of the tumours before and after MDT.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Angiography; Computed tomography; Flat-panel CT; Local chemotherapy; Magnetic drug targeting; Tumour vascularisation

Visualization of CSF Flow with Time-resolved 3D MR Velocity Mapping in Aqueductal Stenosis Before and After Endoscopic Third Ventriculostomy : A Feasibility Study - Brandner, Sebastian; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Dörfler, Arnd; Stadlbauer, Andreas (Clinical Neuroradiology, 2018)
PURPOSE: The aim of this study was to evaluate timed-resolved three-dimensional (3D) magnetic resonance (MR) velocity mapping as a method for investigation of cerebrospinal fluid (CSF) flow changes in patients with aqueductal stenosis (AS) treated by endoscopic third ventriculostomy (ETV). METHODS: The MR velocity mapping was performed in 12 AS patients before and after ETV and in 10 healthy volunteers by using a 3-Tesla MR system. Time-resolved 3D MR velocity mapping data were acquired with a standard 3D phase contrast (PC) sequence with cardiac triggering. Values of mean (vmean) and maximum (vpeak) velocity were measured at several ventricular structures using dedicated software. RESULTS: Of the patients 11 showed a satisfactory clinical improvement after ETV, whereas one patient needed subsequent shunt implantation. All AS patients showed significant hypomotile CSF flow dynamics in the third ventricle when compared to healthy subjects before surgery (p < 0.05). In contrast, CSF flow velocity was increased within the Foramen of Monro in AS patients. After ETV, all AS patients showed a decrease of CSF flow dynamics within the third ventricle. Mean and peak CSF flow velocities through the ventriculostomy were 1.72 ± 0.59 cm/s (vmean) and 3.53 ± 0.79 cm/s (vpeak), respectively after ETV. The patient who needed shunt implantation after ETV had the lowest flow velocities through the ventriculostomy. CONCLUSION: This study demonstrates that timed-resolved 3D MR velocity mapping is a useful imaging investigation for diagnostics and follow-up in patients with AS. This new technique provides an insight into the physiological CSF flow changes related with AS and its treatment.
EVALuna2:212790

Visualization of large vessel occlusion, clot extent, and collateral supply using volume perfusion flat detector computed tomography in acute stroke patients - Gölitz, Philipp; Lang, Stefan; Lücking, Hannes; Kalmuenzer, Bernd; Struffert, Tobias; Dörfler, Arnd; Hölter, Philip (Acta Radiologica, 2019)
Background: Flat detector computed tomography angiography (FDCTA) can be reconstructed from volume perfusion flat detector computed tomography (VP-FDCT). Thus, CTA equivalent stroke imaging might be feasible within the angio suite. Purpose: To evaluate the diagnostic accuracy of FDCTA in detecting large vessel occlusion (LVO) and collateral supply in acute stroke patients. Material and Methods: Sixteen patients with LVO of the anterior circulation were analyzed retrospectively. Each patient underwent a multimodal CT stroke protocol, subsequent VP-FDCT, and digital subtraction angiography (DSA) for endovascular stroke therapy. Angiographic images reconstructed secondarily from VP-FDCT were evaluated with regard to visualization of LVO, Collateral Score (CS), Clot Burden Score (CBS), and image quality. Results: Image quality of FDCTA was sufficient for diagnosis with a strong correlation between CTA and FDCTA (median score: CTA = 4 ± 0.447; FDCTA = 4 ± 0.5). Detection of LVO could be achieved with high sensitivity and specificity for FDCTA and CTA (97.9%, 95% confidence interval [CI] = 96.0–99.9; 92.6%, 95% CI = 84.3–100.0 vs. 96.8%, 95% CI = 93.2–100.0; 86.3%, 95% CI = 88.2–95.2). CBS and CS assessment showed no significant difference between FDCTA and CTA for both readers (reader1 CBS : P = 0.751, reader1 CS : P = 0.718; reader2 CBS : P = 0.164; reader2 CS : P = 0.582) and an excellent interrater agreement (CTA CBS ICC = 0.984, FDCTA CBS ICC = 0.951; CTA CS ICC = 0.754, FDCTA CS ICC = 0.789). Conclusion: FDCTA, reconstructed from VP-FDCT data, allows reliable detection of ICA or MCA M1 segment occlusion comparable to CTA and may provide information concerning the clot extent with sufficient image quality.
CRIS-Team Scopus Importer:2019-10-11
Keywords: Central nervous system; flat detector computed tomography; interventional; stroke

Volumetric Regression in Brain Metastases After Stereotactic Radiotherapy: Time Course, Predictors, and Significance - Oft, Dominik; Schmidt, Manuel; Weissmann, Thomas; Roesch, Johannes; Mengling, Veit; Masitho, Siti; Bert, Christoph; Lettmaier, Sebastian; Frey, Benjamin; Distel, Luitpold; Fietkau, Rainer; Putz, Florian (Frontiers in Oncology, 2021)
Background: There is insufficient understanding of the natural course of volumetric regression in brain metastases after stereotactic radiotherapy (SRT) and optimal volumetric criteria for the assessment of response and progression in radiotherapy clinical trials for brain metastases are currently unknown. Methods: Volumetric analysis via whole-tumor segmentation in contrast-enhanced 1 mm³-isotropic T1-Mprage sequences before SRT and during follow-up. A total of 3,145 MRI studies of 419 brain metastases from 189 patients were segmented. Progression was defined using a volumetric extension of the RANO-BM criteria. A subset of 205 metastases without progression/radionecrosis during their entire follow-up of at least 3 months was used to study the natural course of volumetric regression after SRT. Predictors for volumetric regression were investigated. A second subset of 179 metastases was used to investigate the prognostic significance of volumetric response at 3 months (defined as ≥20% and ≥65% volume reduction, respectively) for subsequent local control. Results: Median relative metastasis volume post-SRT was 66.9% at 6 weeks, 38.6% at 3 months, 17.7% at 6 months, 2.7% at 12 months and 0.0% at 24 months. Radioresistant histology and FSRT vs. SRS were associated with reduced tumor regression for all time points. In multivariate linear regression, radiosensitive histology (p=0.006) was the only significant predictor for metastasis regression at 3 months. Volumetric regression ≥20% at 3 months post-SRT was the only significant prognostic factor for subsequent control in multivariate analysis (HR 0.63, p=0.023), whereas regression ≥65% was no significant predictor. Conclusions: Volumetric regression post-SRT does not occur at a constant rate but is most pronounced in the first 6 weeks to 3 months. Despite decreasing over time, volumetric regression continues beyond 6 months post-radiotherapy and may lead to complete resolution of controlled lesions by 24 months. Radioresistant histology is associated with slower regression. We found that a cutoff of ≥20% regression for the volumetric definition of response at 3 months post-SRT was predictive for subsequent control whereas the currently proposed definition of ≥65% was not. These results have implications for standardized volumetric criteria in future radiotherapy trials for brain metastases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: brain metastases; longitudinal analysis; MRI; stereotactic radiosurgery; stereotactic radiotherapy; volumetric analysis; volumetric regression

Volumetry and Surgical Grading Systems for Vestibular Schwannoma Size Assessment and their Relationship to Postoperative Facial Nerve Function - Strauß, Catharina; Rampp, Stefan; Scheller, Christian; Prell, Julian; Strauss, Christian; Dörfler, Arnd; Engelhorn, Tobias (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Treatment modalities in vestibular schwannoma (VS) are difficult to compare since different techniques for size measurements are used. The purpose of this study was to evaluate the relation between different tumor size grading systems regarding their compatibility as well as the relationship to facial nerve outcome facilitating comparisons of different studies.
CRIS-Team WoS Importer:2021-06-18

Voxel-wise lesion mapping of restless legs syndrome in multiple sclerosis - Fröhlich, Kilian; Knott, Michael; Hock, Stefan; Dörfler, Arnd; Seifert, Frank; Winder, Klemens (Neurological Sciences, 2022)
Objective Restless legs syndrome (RLS) is known to be associated with multiple sclerosis (MS) and may be caused by MS lesions in specific cerebral brain regions. Applying a voxel-wise lesion analysis, we tried to identify the contribution of cerebral MS lesions to RLS. Methods In this retrospective study, we established a cohort of people with MS with documented RLS and controls of people with MS without RLS matched disease severity. Diagnosis of MS and RLS was based on the current guidelines. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3 T). After manual delineation, lesion maps were converted into stereotaxic space. We generated a lesion overlap and performed a Liebermeister test with 4000 permutations to compare the absence or presence of RLS voxel-wise between patients with and without lesions in a given voxel. Results Forty of the patients with RLS and MS fulfilled the inclusion criteria. The voxel-wise analysis yielded associations between RLS and MS in the subcortex of the left gyrus precentralis. Conclusion Our voxel-wise analysis shows associations in the subcortex of the left gyrus precentralis. Thus, our data suggests that a dysfunction of the efferent motor system due to cerebral lesions may contribute to the pathophysiology of RLS in MS.
CRIS-Team WoS Importer:2022-05-20

Voxel-wise lesion mapping of self-reported urinary incontinence in multiple sclerosis - Fröhlich, Katharina; Wang, Ruihao; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Nickel, Franziska; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf A.; Seifert, Frank; Winder, Klemens (Neurourology and Urodynamics, 2019)
Aims Besides spinal lesions, urinary incontinence may be attributed to particular cerebral lesion sites in multiple sclerosis (MS) patients. We intended to determine the contribution of suprapontine lesions to urinary incontinence in MS using a voxel-wise lesion analysis. Methods In this retrospective study, we sought MS patients with documented urinary incontinence in a local database. We established a control group of MS-patients without documented urinary incontinence matched for gender, age, and disease severity. Patients with urinary incontinence due to local diseases of the urinary tract were excluded. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3T). After manual delineation and transformation into stereotaxic space, we determined the lesion overlap and compared the presence or absence of urinary incontinence voxel-wise between patients with and without lesions in a given voxel performing the Liebermeister test with 4000 permutations. Results A total of 56 patients with urinary incontinence and MS fulfilled the criteria and were included. The analysis yielded associations between urinary incontinence and MS in the frontal white matter, temporo-occipital, and parahippocampal regions. Conclusions Our voxel-wise analysis indicated associations between self-reported urinary incontinence and lesions in the left frontal white matter and right parahippocampal region. Thus, our data suggest that dysfunction of supraspinal bladder control due to cerebral lesions may contribute to the pathophysiology of urinary incontinence in MS.
CRIS-Team WoS Importer:2019-11-12

What is the hemodynamic effect of the Woven EndoBridge? An in vivo quantification using time-density curve analysis - Gölitz, Philipp; Lücking, Hannes; Hölter, Philip; Knossalla, Frauke; Dörfler, Arnd (Neuroradiology, 2020)
Purpose: Using the Woven EndoBridge (WEB) for aneurysm treatment has emerged as endovascular approach aiming for flow disruption in aneurysm sac. Since quantifiable data confirming the hemodynamic effect are lacking, we investigated in vivo aneurysmal flow alterations using time-density curve (TDC) analysis. Additionally, we evaluated whether flow parameters could be identified as independent factor to predict aneurysm occlusion. Methods: Forty cerebral aneurysm patients treated with WEB were enrolled. Pre- and postinterventional digital subtraction angiography series were postprocessed and TDCs generated. TDCs were quantified calculating the parameters aneurysmal inflow velocity, outflow velocity, mean flow velocity, and relative time-to-peak (rTTP) of aneurysm filling. Pre- and postinterventional values were compared and related to occlusion rate. Results: WEB implanting induced highly significant rTTP prolongation by 52% (p = 0.001) and highly significant decrease of aneurysmal inflow, outflow, and mean flow velocity (p < 0.001). While outflow velocity was reduced by 49%, inflow velocity was reduced by 33% only. No statistically significant difference between the occluded and the non-occluded group was observed. No flow parameter reached significance level concerning predicting aneurysm occlusion. Conclusion: Flow quantification confirms a significant flow-disrupting effect of WEB reducing more the outflow than the inflow velocity. In our small cohort, no flow parameter reached statistical significance to show predictive value regarding complete aneurysm occlusion. The hemodynamic effect of WEB is on comparable level to flow-diverting stents meaning that aneurysm closure can be delayed. In case of only slight inflow changes and high aneurysmal hemodynamic stress, some aneurysms might not be adequately protected in the short term.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Aneurysm; Digital subtraction angiography; Hemodynamics; Image postprocessing; Intrasaccular flow diverter; Time-density curve

Whole-brain quantitative CEST MRI at 7T using parallel transmission methods and B1+ correction - Liebert, Andrzej; Tkotz, Katharina; Herrler, Jürgen; Linz, Peter; Mennecke, Angelika; German, Alex; Liebig, Patrick; Gumbrecht, Rene; Schmidt, Manuel; Dörfler, Arnd; Uder, Michael; Zaiß, Moritz; et al. (Magnetic Resonance in Medicine, 2021)
Purpose: To enable whole-brain quantitative CEST MRI at ultra-high magnetic field strengths (B0 ≥ 7T) within short acquisition times. Methods: Multiple interleaved mode saturation (MIMOSA) was combined with fast online-customized (FOCUS) parallel transmission (pTx) excitation pulses and (Formula presented.) correction to achieve homogenous whole-brain coverage. Examinations of 13 volunteers were performed on a 7T MRI system with 3 different types of pulse sequences: (1) saturation in circular polarized (CP) mode and CP mode readout, (2) MIMOSA and CP readout, and (3) MIMOSA and FOCUS readout. For comparison, the inverse magnetic transfer ratio metric for relayed nuclear Overhauser effect and amide proton transfer were calculated. To investigate the number of required acquisitions for a good (Formula presented.) correction, 4 volunteers were measured with 6 different B1 amplitudes. Finally, time point repeatability was investigated for 6 volunteers. Results: MIMOSA FOCUS sequence using (Formula presented.) correction, with both single and multiple points, reduced inhomogeneity of the CEST contrasts around the occipital lobe and cerebellum. Results indicate that the most stable inter-subject coefficient of variation was achieved using the MIMOSA FOCUS sequence. Time point repeatability of MIMOSA FOCUS with single-point (Formula presented.) correction showed a maximum coefficient of variation below 8% for 3 measurements in a single volunteer. Conclusion: A combination of MIMOSA FOCUS with a single-point (Formula presented.) correction can be used to achieve quantitative CEST measurements at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced as additional scans required for (Formula presented.) correction can be omitted.
CRIS-Team Scopus Importer:2021-03-12
Keywords: 7T; chemical exchange saturation transfer; fast-online customized pulses; multiple interleaved mode saturation; parallel transmission; spiral non-selective trajectory

Why Does It Shine?-A Prognostic Analysis about Predisposing Factors for Blood-Brain Barrier Damage after Revascularisation of Cerebral Large-Vessel Occlusion. - Knott, Michael; Hock, Stefan; Soder, Liam; Mühlen, Iris; Kremer, Svenja; Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Schwab, Stefan; Engelhorn, Tobias; Dörfler, Arnd (Journal of Cardiovascular Development and Disease, 2023)
BACKGROUND: Hyperdense lesions in CT after EVT of LVO are common. These lesions are predictors for haemorrhages and an equivalent of the final infarct. The aim of this study based on FDCT was the evaluation of predisposing factors for these lesions. METHODS: Using a local database, 474 patients with mTICI ≥ 2B after EVT were recruited retrospectively. A postinterventional FDCT after recanalisation was analysed regarding such hyperdense lesions. This was correlated with a variety of items (demographics, past medical history, stroke assessment/treatment and short-/long-term follow-up). RESULTS: Significant differences were present in NHISS at admission, regarding time window, ASPECTS in initial NECT, location of the LVO, CT-perfusion (penumbra, mismatch ratio), haemostatic parameters (INR, aPTT), duration of EVT, number of EVT attempts, TICI, affected brain region, volume of demarcation and FDCT-ASPECTS. The ICH-rate, the volume of demarcation in follow-up NECT and the mRS at 90 days differed in association with these hyperdensities. INR, the location of demarcation, the volume of demarcation and the FDCT-ASPECTS could be demonstrated as independent factors for the development of such lesions. CONCLUSION: Our results support the prognostic value of hyperdense lesions after EVT. We identified the volume of the lesion, the affection of grey matter and the plasmatic coagulation system as independent factors for the development of such lesions.
EVALuna2:536989

Woman with sudden-onset speech difficulties. - To, Vi Tuong Daniel; Marterstock, Dominique; Madžar, Dominik (Journal of the American College of Emergency Physicians Open, 2023)
EVALuna2:540367

Work and Training Conditions of German Residents in Radiology - Results from a Nationwide Survey Conducted by the Young Radiology Forum in the German Roentgen Society - Oechtering, Thekla H.; Panagiotopoulos, Nikolaos; Völker, Martin; Lohwasser, Stefan; Ellmann, Stephan; Molwitz, Isabel; Storz, Corinna; Winther, Hinrich; Eisenblaetter, Michel; Antoch, Gerald; Schönberg, Stefan O.; Barkhausen, Jörg; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose Good training is the basis for high job satisfaction and high-quality patient care in radiology. The aim of this survey was to record the current state of working conditions for residents in radiology training in Germany and to focus on the aspects of training and psychosocial workload. The description of the actual state should help to identify possible problem areas and to develop improvement approaches. Materials and Methods At the beginning of 2018, we sent an electronic questionnaire to the German Roentgen Society (DRG), the German Association of Chairmen in Academic Radiology (KLR), the Chief Physician Forum of the DRG (CAFRAD) and the Forum of Registered Radiologists (FUNRAD) with the request to forward it to radiology residents. With 63 questions, the questionnaire covered seven essential areas of medical working and training conditions. In order to ensure interdisciplinary comparability, most questions were identical to previous surveys among residents of other disciplines. Results 643 residents started the survey. 501 (78 %) questionnaires were fully processed and included in the final analysis. 65 % of respondents were satisfied with their current job situation. At the same time, shortcomings, especially with regard to the reconciliation of family and work as well as scientific and clinical work, became clear. Only 36 % of participants with children were satisfied with the compatibility of family and work at their workplace. Only 31 % of the researchers were satisfied with their research conditions. In addition, residents experienced a high psychosocial workload. Conclusion Job satisfaction is high among radiology residents in direct comparison to other disciplines. However, based on this survey, adjustments to working conditions and training in radiology seem necessary to maintain the health of the physicians concerned, to encourage motivation for scientific work and to enhance development opportunities, especially for women, through a better compatibility of work and family life. The present survey identifies strategies and leadership tools that can help to achieve this. Key Points: Residents in radiology training.. have a relatively high job satisfaction. experience a high psychosocial workload. evaluate the compatibility of family and work as in need of improvement. are interested in research, but evaluate research conditions as insufficient Citation Format Oechtering TH, Panagiotopoulos N, Völker M et al. Work and Training Conditions of German Residents in Radiology - Results from a Nationwide Survey Conducted by the Young Radiology Forum in the German Roentgen Society. Fortschr Röntgenstr 2020; 192: 458 - 469
CRIS-Team Scopus Importer:2020-05-22
Keywords: continuing education; ER-ratio; psychosocial workload; radiology; resident; working conditions